2FHL: The SECOND CATALOG of HARD FERMI-LAT SOURCES - Ackermann, M.; Ajello, Marco; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal Supplement Series, 2016)
We present a catalog of sources detected above 50 GeV by the Fermi-Large Area Telescope (LAT) in 80 months of data. The newly delivered Pass 8 event-level analysis allows the detection and characterization of sources in the 50 GeV-2 TeV energy range. In this energy band, Fermi-LAT has detected 360 sources, which constitute the second catalog of hard Fermi-LAT sources (2FHL). The improved angular resolution enables the precise localization of point sources (∼1.′7 radius at 68% C. L.) and the detection and characterization of spatially extended sources. We find that 86% of the sources can be associated with counterparts at other wavelengths, of which the majority (75%) are active galactic nuclei and the rest (11%) are Galactic sources. Only 25% of the 2FHL sources have been previously detected by Cherenkov telescopes, implying that the 2FHL provides a reservoir of candidates to be followed up at very high energies. This work closes the energy gap between the observations performed at GeV energies by Fermi-LAT on orbit and the observations performed at higher energies by Cherenkov telescopes from the ground.
Keywords: catalogs; gamma-rays: general

3.9 day orbital modulation in the TeV γ-ray flux and spectrum from the X-ray binary LS 5039 - van Eldik, Christopher; Funk, Stefan; et al. (Astronomy & Astrophysics, 2006)
Aims. LS 5039 is a High Mass X-ray Binary (HMXRB) comprising a compact object in an eccentric 3.9 day orbit around a massive O6.SV star. Observations at energies above 0.1 TeV (10 eV) by the High Energy Stereoscopic System (HESS) in 2004 revealed that LS 5039 is a source of Very High Energy (VHE) γ-rays and hence, is able to accelerate particles to multi-TeV energies. Deeper observations by HESS were carried out in 2005 in an effort to probe further the high energy astrophysics taking place. In particular, we have searched for orbital modulation of the VHE γ-ray flux, which if detected, would yield new information about the complex variation in γ-ray absorption and production within X-ray binary systems. Methods. Observations at energies above 0.1 TeV (10 eV), were carried out with the High Energy Stereoscopic System (HESS) of Cherenkov Telescopes in 2005. A timing analysis was performed on the dataset employing the Lomb-Scargle and Normalised Rayleigh statistics, and orbital phase-resolved energy spectra were obtained. Results. The timing analysis reveals a highly significant (post-trial chance probability <10 ) peak in the TeV emission periodogram at a frequency matching that of the 3.9 day orbital motion of the compact object around the massive stellar companion. This is the first time in γ-ray astronomy that orbital modulation has been observed, and periodicity clearly established using ground-based γ-ray detectors. The γ-ray emission is largely confined to half of the orbit, peaking around the inferior conjunction epoch of the compact object. Around this epoch, there is also a hardening of the energy spectrum in the energy range between 0.2 TeV and a few TeV. Conclusions. The γ-ray flux vs. orbital phase profile suggests the presence of γ-ray absorption via pair production, which would imply that a large fraction of the γ-ray production region is situated within ∼1 AU of the compact object. This source size constraint can be compared to the collimated outflows or jets observed in LS 5039 resolved down to scales of a few AU. The spectral hardening is however not explained exclusively by the absorption effect, indicating that other effects are present, perhaps related to the γ-ray production mechanism(s). If the γ-ray emission arises from accelerated electrons, the hardening may arise from variations with phase in the maximum electron energies, the dominant radiative mechanism, and/or the angular dependence in the inverse-Compton scattering cross-section. Overall, these results provide new insights into the competing γ-ray absorption and production processes in X-ray binaries. © ESO 2006.
Keywords: Acceleration of particles; Block hole physics; Gamma rays: observations; Stars: binaries: close

3FHL: The Third Catalog of Hard Fermi-LAT Sources - Ajello, Marco; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bregeon, J.; et al. (Astrophysical Journal Supplement Series, 2017)
We present a catalog of sources detected above 10 GeV by the Fermi Large Area Telescope (LAT) in the first 7 years of data using the Pass 8 event-level analysis. This is the Third Catalog of Hard Fermi-LAT Sources (3FHL), containing 1556 objects characterized in the 10 GeV-2 TeV energy range. The sensitivity and angular resolution are improved by factors of 3 and 2 relative to the previous LAT catalog at the same energies (1FHL). The vast majority of detected sources (79%) are associated with extragalactic counterparts at other wavelengths, including 16 sources located at very high redshift (z > 2). Of the sources, 8% have Galactic counterparts and 13% are unassociated (or associated with a source of unknown nature). The high-latitude sky and the Galactic plane are observed with a flux sensitivity of 4.4 to 9.5 x 10(-11) ph cm(-2) s(-1), respectively (this is approximately 0.5% and 1% of the Crab Nebula flux above 10 GeV). The catalog includes 214 new gamma-ray sources. The substantial increase in the number of photons (more than 4 times relative to 1FHL and 10 times to 2FHL) also allows us to measure significant spectral curvature for 32 sources and find flux variability for 163 of them. Furthermore, we estimate that for the same flux limit of 10(-12) erg cm(-2) s(-1), the energy range above 10 GeV has twice as many sources as the range above 50 GeV, highlighting the importance, for future Cherenkov telescopes, of lowering the energy threshold as much as possible.
CRIS-Team WoS Importer:2020-01-15

A BROADBAND STUDY OF THE EMISSION FROM THE COMPOSITE SUPERNOVA REMNANT MSH 11-62 - Slane, Patrick; Hughes, John P.; Temim, Tea; Rousseau, Romain; Castro, Daniel; Foight, Dillon; Gaensler, B. M.; Funk, Stefan; Lemoine-Goumard, Marianne; Gelfand, Joseph D.; Moffett, David A.; Dodson, Richard G.; et al. (Astrophysical Journal, 2012)
MSH 11-62 (G291.0-0.1) is a composite supernova remnant for which radio and X-ray observations have identified the remnant shell as well as its central pulsar wind nebula. The observations suggest a relatively young system expanding into a low-density region. Here, we present a study of MSH 11-62 using observations with the Chandra, XMM-Newton, and Fermi observatories, along with radio observations from the Australia Telescope Compact Array. We identify a compact X-ray source that appears to be the putative pulsar that powers the nebula, and show that the X-ray spectrum of the nebula bears the signature of synchrotron losses as particles diffuse into the outer nebula. Using data from the Fermi Large Area Telescope, we identify gamma-ray emission originating from MSH 11-62. With density constraints from the new X-ray measurements of the remnant, we model the evolution of the composite system in order to constrain the properties of the underlying pulsar and the origin of the gamma-ray emission.
CRIS-Team WoS Importer:2020-01-15

A Decade of Gamma-Ray Bursts Observed by Fermi-LAT: The Second GRB Catalog - Ajello, M.; Arimoto, M.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bhat, P. N.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bonnell, J.; et al. (Astrophysical Journal, 2019)
The Large Area Telescope (LAT) aboard the Fermi spacecraft routinely observes high-energy emission from gamma-ray bursts (GRBs). Here we present the second catalog of LAT-detected GRBs, covering the first 10 yr of operations, from 2008 to 2018 August 4. A total of 186 GRBs are found; of these, 91 show emission in the range 30-100 MeV (17 of which are seen only in this band) and 169 are detected above 100 MeV. Most of these sources were discovered by other instruments (Fermi/GBM, Swift/BAT, AGILE, INTEGRAL) or reported by the Interplanetary Network (IPN); the LAT has independently triggered on four GRBs. This catalog presents the results for all 186 GRBs. We study onset, duration, and temporal properties of each GRB, as well as spectral characteristics in the 100 MeV-100 GeV energy range. Particular attention is given to the photons with the highest energy. Compared with the first LAT GRB catalog, our rate of detection is significantly improved. The results generally confirm the main findings of the first catalog: the LAT primarily detects the brightest GBM bursts, and the high-energy emission shows delayed onset as well as longer duration. However, in this work we find delays exceeding 1 ks and several GRBs with durations over 10 ks. Furthermore, the larger number of LAT detections shows that these GRBs not only cover the high-fluence range of GBM-detected GRBs but also sample lower fluences. In addition, the greater number of detected GRBs with redshift estimates allows us to study their properties in both the observer and rest frames. Comparison of the observational results with theoretical predictions reveals that no model is currently able to explain all results, highlighting the role of LAT observations in driving theoretical models.
CRIS-Team WoS Importer:2019-06-28

Adsorption dynamics of CO2 on copper-precovered ZnO(0001)-Zn: A molecular-beam scattering and thermal-desorption spectroscopy study - Funk, Stefan; et al. (Journal of Chemical Physics, 2005)
Initial, S-0, as well as coverage-dependent adsorption probability measurements, S(Theta), have been conducted at normal impact angle and as a function of the impact energy of CO2, E-i, adsorption temperature, T-s, and copper precoverage, Theta(Cu) (at 300 K). S-0, which decreased from similar to 0.4 exponentially to similar to 0.05 with E-i was independent of Theta(Cu). Astonishingly, S-0 for Cu on ZnO(0001)-Zn is smaller than for the clean support which indicates a chemical modification of the support by the Cu deposits. S(Theta) curves consist of two regimes, a Kisliuk-type and Langmuirian-type section. The first is consistent with capture zone models; the second may indicate direct adsorption of CO2 on the Cu cluster. The thermal-desorption (TDS) curves for Cu on ZnO(0001)-Zn consist of two structures with binding energies of 26 and similar to 40 kJ/mol (nu=1x10(13) l/s). The TDS results indicate that CO2 populates predominantly the Cu deposits and the rim along the Cu nanoparticles. No indications for CO2 dissociation could be obtained with Auger electron spectroscopy. (c) 2005 American Institute of Physics.
CRIS-Team WoS Importer:2020-01-15

A fast alignment method for grating-based X-ray phase-contrast imaging systems - Schuster, Max; Ludwig, Veronika; Akstaller, Bernhard; Seifert, Maria; Wolf, Andreas; Michel, Thilo; Neumayer, P.; Funk, Stefan; Anton, Gisela (Journal of Instrumentation, 2019)
The alignment of a grating-based X-ray phase-contrast interferometer is an iterative process that requires numerous steps of changing the distances and angles between the gratings. For each alignment step an image is acquired to evaluate the detected intensity signature in order to optimize the observed moir'e pattern. Thus, a large number of images has to be taken for the alignment procedure. This is not feasible within reasonable time at X-ray sources like X-ray backlighters where the time between two X-ray shots is on the scale of hours. Here, we report on the development of a stable and transportable setup ready-to-use for grating-based X-ray phase-contrast imaging. A comprehensive set of reference images taken at a continuous beam serves as a look-up table which enables the grating alignment within very few alignment steps. Since this method features a fast, reliable and predictable alignment, it is also beneficial for grating-based X-ray phase-contrast imaging systems at common X-ray sources.
CRIS-Team Scopus Importer:2019-10-08
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

A future very-high-energy view of our Galaxy - Funk, Stefan; Hinton, J. A.; Hermann, G.; Digel, S. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

A gamma-ray determination of the Universe's star formation history - Abdollahi, S.; Ackermann, M.; Ajello, M.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; et al. (Science, 2018)
The light emitted by all galaxies over the history of the Universe produces the extragalactic background light (EBL) at ultraviolet, optical, and infrared wavelengths. The EBL is a source of opacity for gamma rays via photon-photon interactions, leaving an imprint in the spectra of distant gamma-ray sources. We measured this attenuation using 739 active galaxies and one gamma-ray burst detected by the Fermi Large Area Telescope. This allowed us to reconstruct the evolution of the EBL and determine the star formation history of the Universe over 90% of cosmic time. Our star formation history is consistent with independent measurements from galaxy surveys, peaking at redshift z similar to 2. Upper limits of the EBL at the epoch of reionization suggest a turnover in the abundance of faint galaxies at z similar to 6.
CRIS-Team WoS Importer:2020-01-15

A gamma-ray pulsar timing array constrains the nanohertz gravitational wave background - Ajello, M.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bhattacharyya, B.; Bissaldi, E.; Blandford, R. D.; Bloom, E.; et al. (Science, 2022)
After large galaxies merge, their central supermassive black holes are expected to form binary systems. Their orbital motion should generate a gravitational wave background (GWB) at nanohertz frequencies. Searches for this background use pulsar timing arrays, which perform long-term monitoring of millisecond pulsars at radio wavelengths. We used 12.5 years of Fermi Large Area Telescope data to form a gamma-ray pulsar timing array. Results from 35 bright gamma-ray pulsars place a 95% credible limit on the GWB characteristic strain of 1.0 x 10(-14) at a frequency of 1 year(-1). The sensitivity is expected to scale with t(obs), the observing time span, as t(obs)(-13/6). This direct measurement provides an independent probe of the GWB while offering a check on radio noise models.
CRIS-Team WoS Importer:2022-05-20

A MeerKAT, e-MERLIN, HESS, and Swift search for persistent and transient emission associated with three localized FRBs - Chibueze, J. O.; Caleb, M.; Spitler, L.; Ashkar, H.; Schussler, F.; Stappers, B. W.; Venter, C.; Heywood,; Richards, A. M. S.; Williams, D. R. A.; Kramer, M.; Beswick, R.; et al. (Monthly Notices of the Royal Astronomical Society, 2022)
We report on a search for persistent radio emission from the one-off fast radio burst (11(B) 20190714A, as well as from two repeating FRBs, 20190711A and 20171019A, using the MeerKAT radio telescope. For FRB 20171019A, we also conducted simultaneous observations with the High-Energy Stereoscopic System (H.E.S.S.) in very high-energy gamma rays and searched for signals in the ultraviolet, optical, and X-ray bands. For this FRB, we obtain a UV flux upper limit of 1.39 x 10(-16) erg cm(-2) s(-1) angstrom(-1), X-ray limit of similar to 6.6 x 10(-14) erg cm(-2) s(-1) and a limit on the very high energy gamma-ray flux Phi(E > 120 GeV) < 1.7 x 10(-12) erg cm(-2) S-1. We obtain a radio upper limit of similar to 15 mu Jy beam(-1) for persistent emission at the locations of both FRBs 20190711A and 20171019A with MeerKAT. However, we detected an almost unresolved (ratio of integrated flux to peak flux is similar to 1.7 beam) radio emission, where the synthesized beam size was similar to 8 arcsec size with a peak brightness of similar to 53 mu Jy beam(-1) at MeerKAT and similar to 86 mu Jy beam(-1) at e-MERLIN, possibly associated with FRB 20190714A at z = 0.2365. This represents the first detection of persistent continuum radio emission potentially associated with a (as-yet) non- repeating FRB. If the association is confirmed, one of the strongest remaining distinction between repeaters and non-repeaters would no longer be applicable. A parallel search for repeat bursts from these FRBs revealed no new detections down to a fluence of 0.08 Jy ms for a 1 ms duration burst.
CRIS-Team WoS Importer:2022-08-05

AMULTI-WAVELENGTH INVESTIGATION OF THE UNIDENTIFIED GAMMA-RAY SOURCE HESS J1708-410 - Van Etten, Adam; Funk, Stefan; Hinton, Jim (Astrophysical Journal, 2009)
We report on recent XMM-Newton observations, archival radio continuum and CO data, and spectral energy distribution (SED) modeling of the unidentified Galactic plane source HESS J1708-410. No significant extended X-ray emission is observed, and we place an upper limit of 3.2 x 10(-13) erg cm(-2) s(-1) in the 2-4 keV range for the region of TeV emission. Molonglo Galactic Plane Survey data are used to place an upper limit of 0.27 Jy at 843 MHz for the source, with a 2.4 GHz limit of 0.4 Jy from the Parkes survey of the southern Galactic plane. (CO)-C-12 (J 1 -> 0) data of this region indicates a plausible distance of 3 kpc for HESS J1708-410. SED modeling of both the HESS detection and flux upper limits offer useful constraints on the emission mechanisms, magnetic field, injection spectrum, and ambient medium surrounding this source.
CRIS-Team WoS Importer:2020-01-15

A new population of very high energy gamma-ray sources in the Milky Way - Funk, Stefan; et al. (Science, 2005)
Very high energy gamma-rays probe the long-standing mystery of the origin of cosmic rays. Produced in the interactions of accelerated particles in astrophysical objects, they can be used to image cosmic particle accelerators. A first-sensitive survey of the inner part of the Milky Way with the High Energy Stereoscopic System (HESS) reveals a population of eight previously unknown firmly detected sources of very high energy gamma-rays. At least two have no known radio or x-ray counterpart and may be representative of a new class of "dark" nucleonic cosmic ray sources.
CRIS-Team WoS Importer:2020-01-15

An exceptional very high energy gamma-ray flare of PKS 2155-304 - van Eldik, Christopher; Funk, Stefan; et al. (Astrophysical Journal, 2007)
The high-frequency peaked BL Lac PKS 2155-304 at redshift z = 0.116 is a well-known VHE (>100 GeV) γ-ray emitter. Since 2002 its VHE flux has been monitored using the H.E.S.S. stereoscopic array of imaging atmospheric Cerenkov telescopes in Namibia. During the 2006 July dark period, the average VHE flux was measured to be more than 10 times typical values observed from the object. This article focuses solely on an extreme γ-ray outburst detected in the early hours of 2006 July 28 (MJD 53,944). The average flux observed during this outburst is I(>200 GeV) = (1.72 ± 0.05 ±0.34) × 10 cm s , corresponding to ∼7 times the flux, I(>200 GeV), observed from the Crab Nebula. Peak fluxes are measured with 1 minute timescale resolution at more than twice this average value. Variability is seen up to ∼600 s in the Fourier power spectrum, and well-resolved bursts varying on timescales of ∼200 s are observed. There are no strong indications for spectral variability within the data. Assuming the emission region has a size comparable to the Schwarzschild radius of a ∼10 M black hole, Doppler factors greater than 100 are required to accommodate the observed variability timescales. © 2007. The American Astronomical Society. All rights reserved.
Keywords: BL lacertae objects: individual (PKS 2155-304); Galaxies: active; Gamma rays: observations

An extremely bright gamma-ray pulsar in the Large Magellanic Cloud - Ackermann, Markus; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Barbieri, C.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Science, 2015)
Pulsars are rapidly spinning, highly magnetized neutron stars, created in the gravitational collapse of massive stars. We report the detection of pulsed giga-electron volt gamma rays from the young pulsar PSR J0540-6919 in the Large Magellanic Cloud, a satellite galaxy of the Milky Way. This is the first gamma-ray pulsar detected in another galaxy. It has the most luminous pulsed gamma-ray emission yet observed, exceeding the Crab pulsar's by a factor of 20. PSR J0540-6919 presents an extreme test case for understanding the structure and evolution of neutron star magnetospheres.
CRIS-Team WoS Importer:2020-01-15

A polarized fast radio burst at low Galactic latitude - Petroff, E.; Burke-Spolaor, S.; Keane, E. F.; Mclaughlin, M. A.; Miller, R.; Andreoni, I.; Bailes, Matthew; Barr, E. D.; Bernard, S. R.; Bhandari, S.; Bhat, N. D. R.; Burgay, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2017)
We report on the discovery of a new fast radio burst (FRB), FRB 150215, with the Parkes radio telescope on 2015 February 15. The burst was detected in real time with a dispersion measure (DM) of 1105.6 +/- 0.8 pc cm(-3), a pulse duration of 2.8(-0.5)(+1.2) ms, and a measured peak flux density assuming that the burst was at beam centre of 0.7(-0.1)(+0.2) Jy. The FRB originated at a Galactic longitude and latitude of 24.66 degrees, 5.28 degrees and 25 degrees away from the Galactic Center. The burst was found to be 43 +/- 5 per cent linearly polarized with a rotation measure (RM) in the range -9 < RM < 12 rad m(-2) (95 per cent confidence level), consistent with zero. The burst was followed up with 11 telescopes to search for radio, optical, X-ray, gamma-ray and neutrino emission. Neither transient nor variable emission was found to be associated with the burst and no repeat pulses have been observed in 17.25 h of observing. The sightline to the burst is close to the Galactic plane and the observed physical properties of FRB 150215 demonstrate the existence of sight lines of anomalously low RM for a given electron column density. The Galactic RM foreground may approach a null value due to magnetic field reversals along the line of sight, a decreased total electron column density from the Milky Way, or some combination of these effects. A lower Galactic DM contribution might explain why this burst was detectable whereas previous searches at low latitude have had lower detection rates than those out of the plane.
Keywords: polarization; methods: data analysis; surveys; ISM: structure

A possible association of the new VHE gamma-ray source HESS J1825-137 with the pulsar wind nebula G18.0-0.7 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We report on a possible association of the recently discovered very high-energy gamma-ray source HESSJ1825-137 wit the pulsar wind nebula (commonly referred to as G 18.0-0.7) of the 2.1 x 10(4) year old Vela-like pulsar PSRB1823-13.HESSJ1825-137 was detected with a significance of 8.1 sigma in the Galactic Plane survey conducted wit the HESS instrument in 2004. The centroid position of HESSJ1825-137 is offset by 11' south of the pulsar position. XMM-Newton observations have revealed X-ray synchrotron emission of an asymmetric pulsar wind nebula extending to the south of the pulsar. We argue that the observed morphology and TeV spectral index suggest that HESSJ1825-137 and G18.0-0.7 may be associated: the lifetime of TeV emitting electrons is expected to be longer compared to the XMM-Newton X-ray emitting electrons, resulting in electrons from earlier epochs (when the spin-down power was larger) contributing to the present TeV flux. These electrons are expected to be synchrotron cooled, which explains the observed photon index of similar to 2.4, and the longer lifetime of TeV emitting electrons naturally explains why the TeV nebula is larger that the X-ray size. Finally, supernova remnant expansion into an inhomogeneous medium is expected to create reverse shocks interacting at different times wit the pulsar wind nebula, resulting in the offset X-ray and TeV gamma-ray morphology.
CRIS-Team WoS Importer:2020-01-15

Application of deep learning methods to analysis of imaging atmospheric Cherenkov telescopes data - Shilon, Idan; Kraus, Michael; Büchele, Matthias; Egberts, K.; Fischer, T.; Holch, T. L.; Lohse, T.; Schwanke, U.; Steppa, C.; Funk, Stefan (Astroparticle Physics, 2019)
Ground based gamma-ray observations with Imaging Atmospheric Cherenkov Telescopes (IACTs) play a significant role in the discovery of very high energy (E > 100 GeV) gamma-ray emitters. The analysis of IACT data demands a highly efficient background rejection technique, as well as methods to accurately determine the position of its source in the sky and the energy of the recorded gamma-ray. We present results for background rejection and signal direction reconstruction from first studies of a novel data analysis scheme for IACT measurements. The new analysis is based on a set of Convolutional Neural Networks (CNNs) applied to images from the four H.E.S.S. phase-I telescopes. As the H.E.S.S. cameras pixels are arranged in a hexagonal array, we demonstrate two ways to use such image data to train CNNs: by resampling the images to a square grid and by applying modified convolution kernels that conserve the hexagonal grid properties.The networks were trained on sets of Monte-Carlo simulated events and tested on both simulations and measured data from the H.E.S.S. array. A comparison between the CNN analysis to current state-of-the-art algorithms reveals a clear improvement in background rejection performance. When applied to H.E.S.S. observation data, the CNN direction reconstruction performs at a similar level as traditional methods. These results serve as a proof-of-concept for the application of CNNs to the analysis of events recorded by IACTs. (C) 2018 Published by Elsevier B.V.
Keywords: Gamma-ray astronomy; IACT; Analysis technique; Deep learning; Convolutional neural networks; Recurrent neural networks

Application of deep learning methods to analysis of imaging atmospheric Cherenkov telescopes data - Shilon, Idan; Kraus, Michael; Büchele, Matthias; Egberts, K.; Fischer, T.; Holch, T. L.; Lohse, T.; Schwanke, U.; Steppa, C.; Funk, Stefan (Astroparticle Physics, 2019)
Ground based gamma-ray observations with Imaging Atmospheric Cherenkov Telescopes (IACTs) play a significant role in the discovery of very high energy (E > 100 GeV) gamma-ray emitters. The analysis of IACT data demands a highly efficient background rejection technique, as well as methods to accurately determine the position of its source in the sky and the energy of the recorded gamma-ray. We present results for background rejection and signal direction reconstruction from first studies of a novel data analysis scheme for IACT measurements. The new analysis is based on a set of Convolutional Neural Networks (CNNs) applied to images from the four H.E.S.S. phase-I telescopes. As the H.E.S.S. cameras pixels are arranged in a hexagonal array, we demonstrate two ways to use such image data to train CNNs: by resampling the images to a square grid and by applying modified convolution kernels that conserve the hexagonal grid properties.
CRIS-Team WoS Importer:2019-02-21

Application of graph networks to background rejection in Imaging Air Cherenkov Telescopes - Glombitza, Jonas; Joshi, Vikas; Bruno, Benedetta; Funk, Stefan (Journal of Cosmology and Astroparticle Physics, 2023)
Imaging Air Cherenkov Telescopes (IACTs) are essential to ground-based observations of gamma rays in the GeV to TeV regime. One particular challenge of ground-based gamma-ray astronomy is an effective rejection of the hadronic background. We propose a new deep-learning-based algorithm for classifying images measured using single or multiple Imaging Air Cherenkov Telescopes. We interpret the detected images as a collection of triggered sensors that can be represented by graphs and analyzed by graph convolutional networks. For images cleaned of the light from the night sky, this allows for an efficient algorithm design that bypasses the challenge of sparse images in deep learning approaches based on computer vision techniques such as convolutional neural networks. We investigate different graph network architectures and find a promising performance with improvements to previous machine-learning and deep-learning-based methods.
CRIS-Team Scopus Importer:2023-12-01
Keywords: cosmic rays detectors; gamma ray detectors; Machine learning

A Search for Cosmic-Ray Proton Anisotropy with the Fermi Large Area Telescope - Ajello, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bottacini, E.; Brandt, T. J.; Bruel, P.; et al. (Astrophysical Journal, 2019)
The Fermi Large Area Telescope (LAT) has amassed a large data set of primary cosmic-ray protons throughout its mission. In fact, it is the largest set of identified cosmic-ray protons ever collected at this energy. The LAT' s wide field of view and full-sky survey capabilities make it an excellent instrument for studying cosmic-ray anisotropy. As a space-based survey instrument, the LAT is sensitive to anisotropy in both R.A. and decl., while ground-based observations only measure the anisotropy in R.A. We present the results of the first-ever proton anisotropy search using Fermi LAT. The data set was collected over eight years and consists of approximately 179 million protons above 78 GeV, enabling it to probe dipole anisotropy below an amplitude of 10(-3), resulting in the most stringent limits on the decl. dependence of the dipole to date. We measure a dipole amplitude delta = 3.9 +/- 1.5 x 10(-4) with a p-value of 0.01 (pretrials) for protons with energy greater than 78 GeV. We discuss various systematic effects that could give rise to a dipole excess and calculate upper limits on the dipole amplitude as a function of minimum energy. The 95% confidence level upper limit on the dipole amplitude is delta(UL) = 1.3 x 10(-3) for protons with energy greater than 78 GeV and delta(UL )= 1.2 x 10(-3) for protons with energy greater than 251 GeV.
CRIS-Team WoS Importer:2019-10-11

A search for new sources below 100 MeV in the Fermi-LAT data - Principe, Giacomo; Malyshev, Dmitry; Ballet, J.; Funk, Stefan (REND LINCEI-SCI FIS, 2019)
The Fermi Large Area Telescope (LAT) has discovered more than 3000 sources between 100 MeV and 300 GeV (3FGL), including over 200 γ-ray pulsars. The majority of these pulsars have their spectral energy peaks (in νFν) above 1 GeV. There exists another population of very energetic, young rotation-powered pulsars having non-thermal hard X-ray emission with spectral energy distributions (SEDs) peaking around 1 MeV, but having no detected emission by Fermi LAT above 100 MeV. Previous analyses of point sources in the gamma ray range were done only below 30 MeV (COMPTEL) or above 100 MeV (Fermi-LAT). Below 30 MeV, the imaging Compton telescope (COMPTEL) detected 26 steady sources in the energy range from 0.75 to 30 MeV. Since the Fermi LAT detects gamma rays down to 20 MeV, we create a list of sources detected in the energy range between 30 MeV and 100 MeV, using PGWave, a background-independent tool that makes use of a wavelet transform. This closes a gap of point source analysis between the COMPTEL catalog and the Fermi-LAT catalog and provides information and constraint for this missing MeV pulsar population.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Gamma rays: general-catalog; Pulsars

A search for new supernova remnant shells in the Galactic plane with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
A search for new supernova remnants (SNRs) has been conducted using TeV gamma-ray data from the H.E.S.S. Galactic plane survey. As an identification criterion, shell morphologies that are characteristic for known resolved TeV SNRs have been used. Three new SNR candidates were identified in the H.E.S.S. data set with this method. Extensive multiwavelength searches for counterparts were conducted. A radio SNR candidate has been identified to be a counterpart to HESS J1534-571. The TeV source is therefore classified as a SNR. For the other two sources, HESS J1614-518 and HESS J1912 + 101, no identifying counterparts have been found, thus they remain SNR candidates for the time being. TeV-emitting SNRs are key objects in the context of identifying the accelerators of Galactic cosmic rays. The TeV emission of the relativistic particles in the new sources is examined in view of possible leptonic and hadronic emission scenarios, taking the current multiwavelength knowledge into account.
CRIS-Team WoS Importer:2020-01-15

A search for very high energy gamma-ray emission from the starburst galaxy NGC253 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We present the result of 28 h of observations of the nearby starburst galaxy NGC 253 with the HESS detector in 2003. We find no evidence for very high energy gamma-ray emission from this object. Gamma-ray emission above 400 GeV from NGC 253 had been reported by the CANGAROO collaboration in 2002. From the HESS data we derive upper limits on the flux above 300 GeV of 1.9 x 10(-12) photons cm(-2) s(-1) for a point-like source and 6.3 x 10(-12) photons cm(-2) s(-1) for a source of radius 0.5 degrees as reported by CANGAROO, both at a confidence level of 99%. These upper limits are inconsistent with the spectrum reported by CANGAROO. The expected very high energy gamma-ray emission from this object is discussed in the framework of a galactic wind propagation model.
CRIS-Team WoS Importer:2020-01-15

A set of tools for determining the LAT performance in specific applications - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

ASSOCIATING LONG-TERM gamma-RAY VARIABILITY WITH THE SUPERORBITAL PERIOD OF LS I+61 degrees 303 - Ackermann, M.; Ajello, M.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bonamente, E.; Brandt, T. J.; Bregeon, J.; Brigida, M.; Bruel, P.; Buehler, R.; et al. (Astrophysical Journal Letters, 2013)
Gamma-ray binaries are stellar systems for which the spectral energy distribution (discounting the thermal stellar emission) peaks at high energies. Detected from radio to TeV gamma rays, the gamma-ray binary LS I + 61 degrees 303 is highly variable across all frequencies. One aspect of this system's variability is the modulation of its emission with the timescale set by the similar to 26.4960 day orbital period. Here we show that, during the time of our observations, the gamma-ray emission of LS I + 61 degrees 303 also presents a sinusoidal variability consistent with the previously known superorbital period of 1667 days. This modulation is more prominently seen at orbital phases around apastron, whereas it does not introduce a visible change close to periastron. It is also found in the appearance and disappearance of variability at the orbital period in the power spectrum of the data. This behavior could be explained by a quasi-cyclical evolution of the equatorial outflow of the Be companion star, whose features influence the conditions for generating gamma rays. These findings open the possibility to use gamma-ray observations to study the outflows of massive stars in eccentric binary systems.
Keywords: gamma rays: general; gamma rays: stars; stars: emission-line; Be

A STATISTICAL APPROACH TO RECOGNIZING SOURCE CLASSES FOR UNASSOCIATED SOURCES IN THE FIRST FERMI-LAT CATALOG - Ackermann, Markus; Ajello, Marco; Allafort, A.; Antolini, E.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2012)
The Fermi Large Area Telescope (LAT) First Source Catalog (1FGL) provided spatial, spectral, and temporal properties for a large number of gamma-ray sources using a uniform analysis method. After correlating with the most-complete catalogs of source types known to emit gamma rays, 630 of these sources are "unassociated" (i.e., have no obvious counterparts at other wavelengths). Here, we employ two statistical analyses of the primary gamma-ray characteristics for these unassociated sources in an effort to correlate their gamma-ray properties with the active galactic nucleus (AGN) and pulsar populations in 1FGL. Based on the correlation results, we classify 221 AGN-like and 134 pulsar-like sources in the 1FGL unassociated sources. The results of these source "classifications" appear to match the expected source distributions, especially at high Galactic latitudes. While useful for planning future multiwavelength follow-up observations, these analyses use limited inputs, and their predictions should not be considered equivalent to "probable source classes" for these sources. We discuss multiwavelength results and catalog cross-correlations to date, and provide new source associations for 229 Fermi-LAT sources that had no association listed in the 1FGL catalog. By validating the source classifications against these new associations, we find that the new association matches the predicted source class in similar to 80% of the sources.
CRIS-Team WoS Importer:2020-01-15

A very-high-energy component deep in the γ-ray burst afterglow - Abdalla, H.; Adam, R.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Barnard, M.; et al. (Nature, 2019)
Gamma-ray bursts (GRBs) are brief flashes of γ-rays and are considered to be the most energetic explosive phenomena in the Universe1. The emission from GRBs comprises a short (typically tens of seconds) and bright prompt emission, followed by a much longer afterglow phase. During the afterglow phase, the shocked outflow—produced by the interaction between the ejected matter and the circumburst medium—slows down, and a gradual decrease in brightness is observed2. GRBs typically emit most of their energy via γ-rays with energies in the kiloelectronvolt-to-megaelectronvolt range, but a few photons with energies of tens of gigaelectronvolts have been detected by space-based instruments3. However, the origins of such high-energy (above one gigaelectronvolt) photons and the presence of very-high-energy (more than 100 gigaelectronvolts) emission have remained elusive4. Here we report observations of very-high-energy emission in the bright GRB 180720B deep in the GRB afterglow—ten hours after the end of the prompt emission phase, when the X-ray flux had already decayed by four orders of magnitude. Two possible explanations exist for the observed radiation: inverse Compton emission and synchrotron emission of ultrarelativistic electrons. Our observations show that the energy fluxes in the X-ray and γ-ray range and their photon indices remain comparable to each other throughout the afterglow. This discovery places distinct constraints on the GRB environment for both emission mechanisms, with the inverse Compton explanation alleviating the particle energy requirements for the emission observed at late times. The late timing of this detection has consequences for the future observations of GRBs at the highest energies.
CRIS-Team Scopus Importer:2019-12-03

Background modelling in very-high-energy gamma-ray astronomy - Funk, Stefan; et al. (Astronomy & Astrophysics, 2007)
Ground based Cherenkov telescope systems measure astrophysical gamma-ray emission against a background of cosmic-ray induced air showers. The subtraction of this background is a major challenge for the extraction of spectra and morphology of gamma-ray sources.
CRIS-Team WoS Importer:2020-01-15

Binaries with the eyes of CTA - Paredes, J. M.; Bednarek, Wlodek; Bordas, Pol; Bosch-Ramon, Valenti; De Cea Del Pozo, E.; Dubus, Guillaume; Funk, Stefan; Hadasch, Daniela; Khangulyan, Dmitry; Markoff, S.; Moldon, Javier; Munar-Adrover, Pere; et al. (Astroparticle Physics, 2013)
The binary systems that have been detected in gamma rays have proven very useful to study high-energy processes, in particular particle acceleration, emission and radiation reprocessing, and the dynamics of the underlying magnetized flows. Binary systems; either detected or potential gamma-ray emitters, can be grouped in different subclasses depending on the nature of the binary components or the origin of the particle acceleration: the interaction of the winds of either a pulsar and a massive star or two massive stars: accretion onto a compact object and jet formation; and interaction of a relativistic outflow with the external medium. We evaluate the potentialities of an instrument like the Cherenkov telescope array (CIA) to study the non-thermal physics of gamma-ray binaries, which requires the observation of high-energy phenomena at different time and spatial scales. We analyze the capability of cm, under different configurations, to probe the spectral, temporal and spatial behavior of gamma-ray binaries in the context of the known or expected physics of these sources. CIA will be able to probe with high spectral, temporal and spatial resolution the physical processes behind the gamma-ray emission in binaries, significantly increasing as well the number of known sources. This will allow the derivation of information on the particle acceleration and emission sites qualitatively better than what is currently available. (C) 2012 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

BLAZAR SPECTRAL PROPERTIES AT 74 MHz - Massaro, Francesco; Giroletti, Marcello; Paggi, Alessandro; D'Abrusco, Raffaele; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
Blazars are the most extreme class of active galactic nuclei. Despite a previous investigation at 102 MHz for a small sample of BL Lac objects and our recent analysis of blazars detected in the Westerbork Northern Sky Survey, a systematic study of the blazar spectral properties at frequencies below 100 MHz has been never carried out. In this paper, we present the first analysis of the radio spectral behavior of blazars based on the recent Very Large Array Low-frequency Sky Survey (VLSS) at 74 MHz. We search for blazar counterparts in the VLSS catalog, confirming that they are detected at 74 MHz. We then show that blazars present radio-flat spectra (i.e., radio spectral indices of similar to 0.5) when evaluated, which also about an order of magnitude in frequency lower than previous analyses. Finally, we discuss the implications of our findings in the context of the blazars-radio galaxies connection since the low-frequency radio data provide a new diagnostic tool to verify the expectations of the unification scenario for radio-loud active galaxies.
CRIS-Team WoS Importer:2020-01-15

BL LAC CANDIDATES FOR TeV OBSERVATIONS - Massaro, Francesco; Paggi, Alessandro; Errando, Manel; D'Abrusco, Raffaele; Masetti, Nicola; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
BL Lac objects are the most numerous class of extragalactic TeV-detected sources. One of the biggest difficulties in investigating their TeV emission is due to their limited number, since only 47 BL Lac objects are known to be TeV emitters. In this paper, we propose new criteria to select TeV BL Lac candidates based on infrared and X-ray observations. We apply our selection criteria to the BL Lac objects listed in the ROMA-BZCAT catalog, thereby identifying 41 potential TeV emitters. We then perform a search over a more extended sample combining the ROSAT bright source catalog and the WISE all-sky survey, revealing 54 additional candidates for TeV observations. Our investigation also led to a tentative classification of 16 unidentified X-ray sources as BL Lac candidates. This analysis provides new interesting BL Lac targets for future observations with ground-based Cherenkov telescopes.
CRIS-Team WoS Importer:2020-01-15

BRIGHT ACTIVE GALACTIC NUCLEI SOURCE LIST FROM THE FIRST THREE MONTHS OF THE FERMI LARGE AREA TELESCOPE ALL-SKY SURVEY - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
The first three months of sky-survey operation with the Large Area Telescope (LAT) onboard the Fermi Gamma-Ray Space Telescope reveal 132 bright sources at |b| > 10 degrees with test statistic greater than 100 ( corresponding to about 10 sigma). Two methods, based on the CGRaBS, CRATES, and BZCat catalogs, indicate high-confidence associations of 106 of these sources with known active galactic nuclei (AGNs). This sample is referred to as the LAT Bright AGN Sample (LBAS). It contains two radio galaxies, namely, Centaurus A and NGC 1275, and 104 blazars consisting of 58 flat spectrum radio quasars (FSRQs), 42 BL Lac objects, and 4 blazars with unknown classification. Four new blazars were discovered on the basis of the LAT detections. Remarkably, the LBAS includes 10 high-energy-peaked BL Lacs (HBLs), sources which were previously difficult to detect in the GeV range. Another 10 lower-confidence associations are found. Only 33 of the sources, plus two at |b| < 10 degrees, were previously detected with Energetic Gamma-Ray Experiment Telescope( EGRET), probably due to variability. The analysis of the gamma-ray properties of the LBAS sources reveals that the average GeV spectra of BL Lac objects are significantly harder than the spectra of FSRQs. No significant correlation between radio and peak gamma-ray fluxes is observed. Blazar log N-log S distributions and luminosity functions are constructed to investigate the evolution of the different blazar classes, with positive evolution indicated for FSRQs but none for BL Lacs. The contribution of LAT blazars to the total extragalactic gamma-ray intensity is estimated.
CRIS-Team WoS Importer:2020-01-15

Calibration of cameras of the HESS detector - Funk, Stefan; et al. (Astroparticle Physics, 2004)
H.E.S.S.-the high energy stereoscopic system-is a new system of large atmospheric Cherenkov telescopes for GeV/ TeV astronomy. Each of the four telescopes of 107 m(2) mirror area is equipped with a 960-pixel photomultiplier-tube camera. This paper describes the methods used to convert the photomultiplier signals into the quantities needed for Cherenkov image analysis. Two independent calibration techniques have been applied in parallel to provide an estimation of uncertainties. Results on the long-term stability of the H.E.S.S. cameras are also presented. (C) 2004 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Catalog of Long-term Transient Sources in the First 10 yr of Fermi-LAT Data - Baldini, Luca; Ballet, J.; Bastieri, Denis; Becerra Gonzalez, J.; Bellazzini, R.; Berretta, A.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; Bruel, P.; et al. (Astrophysical Journal Supplement Series, 2021)
We present the first Fermi Large Area Telescope (LAT) catalog of long-term gamma-ray transient sources (1FLT). This comprises sources that were detected on monthly time intervals during the first decade of Fermi-LAT operations. The monthly timescale allows us to identify transient and variable sources that were not yet reported in other Fermi-LAT catalogs. The monthly data sets were analyzed using a wavelet-based source detection algorithm that provided the candidate new transient sources. The search was limited to the extragalactic regions of the sky to avoid the dominance of the Galactic diffuse emission at low Galactic latitudes. The transient candidates were then analyzed using the standard Fermi-LAT maximum likelihood analysis method. All sources detected with a statistical significance above 4 sigma in at least one monthly bin were listed in the final catalog. The 1FLT catalog contains 142 transient gamma-ray sources that are not included in the 4FGL-DR2 catalog. Many of these sources (102) have been confidently associated with active galactic nuclei (AGNs): 24 are associated with flat-spectrum radio quasars, 1 with a BL Lac object, 70 with blazars of uncertain type, 3 with radio galaxies, 1 with a compact steep-spectrum radio source, 1 with a steep-spectrum radio quasar, and 2 with AGNs of other types. The remaining 40 sources have no candidate counterparts at other wavelengths. The median gamma-ray spectral index of the 1FLT-AGN sources is softer than that reported in the latest Fermi-LAT AGN general catalog. This result is consistent with the hypothesis that detection of the softest gamma-ray emitters is less efficient when the data are integrated over year-long intervals.
CRIS-Team WoS Importer:2021-09-24

Chandra and HESS observations of the supernova remnant CTB 37B - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel; et al. (Astronomy & Astrophysics, 2008)
We discovered the > 100 GeV γ-ray source, HESS J1713-381, apparently associated with the shell-type supernova remnant (SNR) CTB 37B, using HESS in 2006. In 2007 we performed X-ray follow-up observations with Chandra with the aim of identifying a synchrotron counterpart to the TeV source and/or thermal emission from the SNR shell. These new Chandra data, together with additional TeV data, allow us to investigate the nature of this object in much greater detail than was previously possible. The new X-ray data reveal thermal emission from a ∼4′ region in close proximity to the radio shell of CTB 37B. The temperature of this emission implies an age for the remnant of ∼5000 years and an ambient gas density of ∼0.5 cm. Both these estimates are considerably uncertain due to the asymmetry of the SNR and possible modifications of the kinematics due to efficient cosmic ray (CR) acceleration. A bright (≈7 × 10 erg cm s) and unresolved (<1″) source (CXOUJ17.1405.7-381031), with a soft (Γ ≈ 3.3) non-thermal spectrum is also detected in coincidence with the radio shell. Absorption indicates a column density consistent with the thermal emission from the shell, suggesting a genuine association rather than a chance alignment. The observed TeV morphology is consistent with an origin in the complete shell of CTB 37B. The lack of diffuse non-thermal X-ray emission suggests an origin of the γ-ray emission via the decay of neutral pions produced in interactions of protons and nuclei, rather than inverse Compton (IC) emission from relativistic electrons. © ESO 2008.
Keywords: Gamma rays: observations; ISM: supernova remnants; X-rays: individuals: G348.7+0.3

CHANDRA, KECK, AND VLA OBSERVATIONS OF THE CRAB NEBULA DURING THE 2011-APRIL GAMMA-RAY FLARE - Weisskopf, Martin C.; Tennant, Allyn F.; Arons, Jonathan; Blandford, Roger; Buehler, Rolf; Caraveo, Patrizia; Cheung, Chi C.; Costa, Enrico; De Luca, Andrea; Ferrigno, Carlo; Fu, Hai; Funk, Stefan; et al. (Astrophysical Journal, 2013)
We present results from our analysis of Chandra X-Ray Observatory, W. M. Keck Observatory, and Karl G. Jansky Very Large Array (VLA) images of the Crab Nebula that were contemporaneous with the gamma-ray flare of 2011 April. Despite hints in the X-ray data, we find no evidence for statistically significant variations that pinpoint the specific location of the flares within the Nebula. The Keck observations extend this conclusion to the "inner knot," i.e., the feature within an arcsecond of the pulsar. The VLA observations support this conclusion. We also discuss theoretical implications of the gamma-ray flares and suggest that the most dramatic gamma-ray flares are due to radiation-reaction-limited synchrotron emission associated with sudden, dissipative changes in the current system sustained by the central pulsar.
CRIS-Team WoS Importer:2020-01-15

Chandra observations of the HII complex G5.89-0.39 and TeV source HESSJ1800-240B - Hampton, E.; Rowell, Gavin; Horns, D.; Uchiyama, Y.; Funk, Stefan; Wagner, S. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2012)
CRIS-Team WoS Importer:2020-01-15

Characterisation and testing of CHEC-M-A camera prototype for the small-sized telescopes of the Cherenkov telescope array - Zorn, J.; White, Richard; Watson, J. J.; Armstrong, T. P.; Balzer, A.; Barcelo, M.; Berge, D.; Bose, R.; Brown, A. M.; Bryan, M.; Chadwick, P. M.; Clark, Paul; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2018)
The Compact High Energy Camera (CHEC) is a camera design for the Small-Sized Telescopes (SSTs; 4 m diameter mirror) of the Cherenkov Telescope Array (CTA). The SSTs are focused on very-high-energy gamma-ray detection via atmospheric Cherenkov light detection over a very large area. This implies many individual units and hence cost-effective implementation, as well as shower detection at large impact distance, and hence large field of view (FoV), and efficient image capture in the presence of large time gradients in the shower image detected by the camera. CHEC relies on dual-mirror optics to reduce the plate-scale and make use of 6 x 6 mm(2) pixels, leading to a low-cost (similar to 150 k(sic)), compact (0.5 m x 0.5 m), and light (similar to 45 kg) camera with 2048 pixels providing a camera FoV of similar to 9 degrees. The CHEC electronics are based on custom TARGET (TeV array readout with GSa/s sampling and event trigger) application-specific integrated circuits (ASICs) and field programmable gate arrays (FPGAs) sampling incoming signals at a gigasample per second, with flexible camera-level triggering within a single backplane FPGA. CHEC is designed to observe in the gamma-ray energy range of 1-300 TeV, and at impact distances up to similar to 500 m. To accommodate this and provide full flexibility for later data analysis, full waveforms with 96 samples for all 2048 pixels can be read out at rates up to similar to 900 Hz. The first prototype, CHEC-M, based on mull-anode photomultipliers (MAPMs) as photosensors, was commissioned and characterised in the laboratory and during two measurement campaigns on a telescope structure at the Paris Observatory in Meudon. In this paper, the results and conclusions from the laboratory and on-site testing of CHEC-M are presented. They have provided essential input on the system design and on operational and data analysis procedures for a camera of this type. A second full-camera prototype based on Silicon photomultipliers (SiPMs), addressing the drawbacks of CHEC-M identified during the first prototype phase, has already been built and is currently being commissioned and tested in the laboratory.
CRIS-Team WoS Importer:2020-01-15
Keywords: Full-waveform readout; Cherenkov telescope array; Imaging atmospheric Cherenkov telescopes; Gamma-rays

Characterising the VHE diffuse emission in the central 200 parsecs of our Galaxy with H.E.S.S. - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
The diffuse very high-energy (VHE; > 100 GeV) gamma-ray emission observed in the central 200 pc of the Milky Way by H.E.S.S. was found to follow dense matter distribution in the central molecular zone (CMZ) up to a longitudinal distance of about 130 pc to the Galactic centre (GC), where the flux rapidly decreases. This was initially interpreted as the result of a burst-like injection of energetic particles 104 yr ago, but a recent more sensitive H.E.S.S. analysis revealed that the cosmic-ray (CR) density profile drops with the distance to the centre, making data compatible with a steady cosmic PeVatron at the GC. In this paper, we extend this analysis to obtain, for the first time, a detailed characterisation of the correlation with matter and to search for additional features and individual gamma-ray sources in the inner 200 pc. Taking advantage of 250 h of H.E.S.S. data and improved analysis techniques, we perform a detailed morphology study of the diffuse VHE emission observed from the GC ridge and reconstruct its total spectrum. To test the various contributions to the total gamma-ray emission, we used an iterative 2D maximum-likelihood approach that allows us to build a phenomenological model of the emission by summing a number of different spatial components. We show that the emission correlated with dense matter covers the full CMZ and that its flux is about half the total diffuse emission flux. We also detect some emission at higher latitude that is likely produced by hadronic collisions of CRs in less dense regions of the GC interstellar medium. We detect an additional emission component centred on the GC and extending over about 15 pc that is consistent with the existence of a strong CR density gradient and confirms the presence of a CR accelerator at the very centre of our Galaxy. We show that the spectrum of full ridge diffuse emission is compatible with that previously derived from the central regions, suggesting that a single population of particles fills the entire CMZ. Finally, we report the discovery of a VHE gamma-ray source near the GC radio arc and argue that it is produced by the pulsar wind nebula candidate G0.13-0.11.
Keywords: gamma rays: general; gamma rays: ISM; Galaxy: center; cosmic rays

Characterization of a prototype imaging calorimeter for the Advanced Particle-astrophysics Telescope from an Antarctic balloon flight and CERN beam test - Hughes, Zachary; Alnussirat, S.; Altomare, C.; Bose, R. G.; Braun, D.; Buckley, J. H.; Buhler, J. D.; Burns, E.; Chamberlain, R. D.; Chen, W.; Cherry, M. L.; Di Venere, L.; et al. (Proceedings of Science, 2022)
We report the results and analysis methods from field-testing the imaging calorimeter prototype for the Advanced Particle-astrophysics Telescope (APT) through an antarctic balloon flight (in the 2019 austral Antarctic balloon season) and through a CERN heavy-ion beam test in 2018. The Advanced Particle-astrophysics Telescope is a proposed space-based gamma- and cosmic-ray instrument that utilizes a novel distributed imaging calorimeter for both particle tracking and energy reconstruction. The imaging CsI calorimeter (ICC) consists of a CsI:Na scintillator read out by (WLS) fibers in both the x- and y-planes. To function both as a gamma-ray and cosmic-ray instrument APT must operate over a large dynamic range, from the single photon-election regime for low energy gamma-ray events to high-Z cosmic-ray events. Analysis of data from a 150 mm x 150 mm prototype instrument (APTlite) on a piggy-back flight on the 2019 SuperTIGER-2.3 balloon instrument provided cosmic ray data that were used to demonstrate the key detector and electronics elements of the ICC. Significantly, analysis of flight data demonstrated the large dynamic range of the instrument, showing the possibility to reconstruct the nuclear charge through analysis of the scintillation tail of saturating high-Z cosmic-ray events by utilizing the deep memory depth available to the TARGET waveform digitizer electronics. Spatial reconstruction of events was performed using a two-sided Voigt profile demonstrating position localization within the imaging calorimeter plane to less 3 WLS fiber widths. Charge resolution was evaluated on a 50 mm x 50 mm prototype placed in the 150 GeV/nuc, A/Z = 2.2 CERN SPS beam line. Nuclei were tagged using HNX/TIGERISS silicon-strip detectors and silicon pad detectors, which allowed for fragmentation cuts in the data. The vastly saturating signals were reconstructed from the CsI:Na scintillation tail and show an APT charge resolution up to Z = 11 (with experimental limitations preventing full evaluation for Z larger 11) and demonstrated no significant non-linearity in the Z2 measurement derived from the CsI:Na optical signal response up to Z = 82.
CRIS-Team Scopus Importer:2022-12-23

CHARACTERIZATION OF THE INNER KNOT OF THE CRAB: THE SITE OF THE GAMMA-RAY FLARES? - Rudy, Alexander; Horns, Dieter; Deluca, Andrea; Kolodziejczak, Jeffery; Tennant, Allyn; Yuan, Yajie; Buehler, Rolf; Arons, Jonathon; Blandford, Roger; Caraveo, Patrizia; Costa, Enrico; Funk, Stephan; et al. (Astrophysical Journal, 2015)
A particularly intriguing recent result from gamma-ray astronomy missions is the detection of powerful flares from the Crab Nebula, which challenges the current understanding of pulsar wind nebulae and acceleration mechanisms. To search for the production site(s) of these flares, we conducted a multi-wavelength observing campaign using Keck, the Hubble Space Telescope (HST), and the Chandra X-ray Observatory. As the short timescales of the gamma-ray flares (less than or similar to 1 day) suggest a small emitting region, the Crab's inner knot (about 0.6 arcsec from the pulsar) is a candidate site for such flaring. This paper describes observations of the inner knot, seeking to understand its nature and possible relationship with gamma-ray flares. Using singular-value decomposition, analysis of the HST images yielded results consistent with traditional methods while substantially reducing some uncertainties. These analyses show that the knot's intrinsic properties (especially size and brightness) are correlated with its (projected) separation from the pulsar. This characterization of the inner knot helps in constraining standard shock model parameters, under the assumption that the knot lies near the shocked surface. While the standard shock model gives good agreement in several respects, two puzzles persist: (a) the observed angular size of the knot relative to the pulsar-knot separation is much smaller than expected; and (b) the variable high degree of polarization (reported by others) is difficult to reconcile with a highly relativistic downstream flow. However, the IR-optical flux of the inner knot is marginally consistent with the shock accelerating most of the Nebula's optical-emitting particles.
CRIS-Team WoS Importer:2020-01-15

Characterizing the γ-ray long-term variability of PKS 2155 - 304 with H.E.S.S. and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Studying the temporal variability of BL Lac objects at the highest energies provides unique insights into the extreme physical processes occurring in relativistic jets and in the vicinity of super-massive black holes. To this end, the long-term variability of the BL Lac object PKS 2155 304 is analyzed in the high (HE, 100MeV < E < 300 GeV) and very high energy (VHE, E > 200 GeV) gamma-ray domain. Over the course of similar to 9 yr of H. E. S. S. observations the VHE light curve in the quiescent state is consistent with a log-normal behavior. The VHE variability in this state is well described by flicker noise (power-spectral-density index beta(VHE) = 1 .10(+ 0 : 10) (0 : 13)) on timescales larger than one day. An analysis of similar to 5.5 yr of HE Fermi-LAT data gives consistent results (beta(HE) = 1 : 20(+ 0 : 21) (0 : 23), on timescales larger than 10 days) compatible with the VHE findings. The HE and VHE power spectral densities show a scale invariance across the probed time ranges. A direct linear correlation between the VHE and HE fluxes could neither be excluded nor firmly established. These long-term-variability properties are discussed and compared to the red noise behavior (beta similar to 2) seen on shorter timescales during VHE-flaring states. The difference in power spectral noise behavior at VHE energies during quiescent and flaring states provides evidence that these states are influenced by different physical processes, while the compatibility of the HE and VHE long-term results is suggestive of a common physical link as it might be introduced by an underlying jet-disk connection.
Keywords: BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Galaxies: jets; Galaxies: nuclei; Gamma rays: galaxies; Radiation mechanisms: non-thermal

Comparing different approaches for stellar intensity interferometry - Karl, Sebastian; Zmija, Andreas; Richter, Stefan; Vogel, Naomi; Malyshev, Dmitry; Zink, Adrian; Michel, Thilo; Anton, Gisela; von Zanthier, Joachim; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Stellar intensity interferometers correlate photons within their coherence time and could overcome the baseline limitations of existing amplitude interferometers. Intensity interferometers do not rely on phase coherence of the optical elements and thus function without high-grade optics and light combining delay lines. However, the coherence time of starlight observed with realistic optical filter bandwidths (> 0.1 nm) is usually much smaller than the time resolution of the detection system (> 10 ps), resulting in a greatly reduced correlation signal. Reaching high signal-to-noise ratio in a reasonably short measurement time can be achieved in different ways: either by increasing the time resolution, which increases the correlation signal height, or by increasing the photon rate, which decreases statistical uncertainties of the measurement. We present laboratory measurements employing both approaches and directly compare them in terms of signal-to-noise ratio. A high-time-resolution interferometry setup designed for small-to-intermediate-sized optical telescopes and thus lower photon rates (diameters < some metres) is compared to a setup capable of measuring high photon rates, which is planned to be installed at Cherenkov telescopes with dish diameters of > 10 m. We use a xenon lamp as a common light source simulating starlight. Both setups measure the expected correlation signal and work at the expected shot-noise limit of statistical uncertainties for measurement times between 10 min and 23 h. We discuss the quantitative differences in the measurement results and give an overview of suitable operation regimes for each of the interferometer concepts.
CRIS-Team WoS Importer:2022-04-08
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; telescopes; stars: imaging

Comparison of Fermi-LAT and CTA in the region between 10-100 GeV - Funk, Stefan; Hinton, J. A. (Astroparticle Physics, 2013)
The past decade has seen a dramatic improvement in the quality of data available at both high (HE: 100 MeV to 100 GeV) and very high (VHE: 100 GeV to 100 TeV) gamma-ray energies. With three years of data from the Fermi Large Area Telescope (LAT) and deep pointed observations with arrays of Cherenkov telescope, continuous spectral coverage from 100 MeV to similar to 10 TeV exists for the first time for the brightest gamma-ray sources. The Fermi-LAT is likely to continue for several years, resulting in significant improvements in high energy sensitivity. On the same timescale, the Cherenkov Telescope Array (CTA) will be constructed providing unprecedented VHE capabilities. The optimisation of CTA must take into account competition and complementarity with Fermi, in particularly in the overlapping energy range 10-100 GeV. Here we compare the performance of Fermi-LAT and the current baseline CTA design for steady and transient, point-like and extended sources. (C) 2012 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Complementarity of dark matter searches in the phenomenological MSSM - Cahill-Rowley, M.; Cotta, R.; Drlica-Wagner, A.; Funk, Stefan; Hewett, J. L.; Ismail, A.; Rizzo, T. G.; Wood, M. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2015)
As is well known, the search for and eventual identification of dark matter in supersymmetry requires a simultaneous, multipronged approach with important roles played by the LHC as well as both direct and indirect dark matter detection experiments. We examine the capabilities of these approaches in the 19-parameter phenomenological MSSM which provides a general framework for complementarity studies of neutralino dark matter. We summarize the sensitivity of dark matter searches at the 7 and 8 (and eventually 14) TeV LHC, combined with those by Fermi, CTA, IceCube/DeepCore, COUPP, LZ and XENON. The strengths and weaknesses of each of these techniques are examined and contrasted and their interdependent roles in covering the model parameter space are discussed in detail. We find that these approaches explore orthogonal territory and that advances in each are necessary to cover the supersymmetric weakly interacting massive particle parameter space. We also find that different experiments have widely varying sensitivities to the various dark matter annihilation mechanisms, some of which would be completely excluded by null results from these experiments.

Constraining Dark Matter Models from a Combined Analysis of Milky Way Satellites with the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Physical Review Letters, 2011)
Satellite galaxies of the Milky Way are among the most promising targets for dark matter searches in gamma rays. We present a search for dark matter consisting of weakly interacting massive particles, applying a joint likelihood analysis to 10 satellite galaxies with 24 months of data of the Fermi Large Area Telescope. No dark matter signal is detected. Including the uncertainty in the dark matter distribution, robust upper limits are placed on dark matter annihilation cross sections. The 95% confidence level upper limits range from about 10(-26) cm(3) s(-1) at 5 GeV to about 5 x 10(-23) cm(3) s(-1) at 1 TeV, depending on the dark matter annihilation final state. For the first time, using gamma rays, we are able to rule out models with the most generic cross section (similar to 3 x 10(-26) cm(3) s(-1) for a purely s-wave cross section), without assuming additional boost factors.
CRIS-Team WoS Importer:2020-01-15

CONSTRAINTS ON THE COSMIC-RAY DENSITY GRADIENT BEYOND THE SOLAR CIRCLE FROM FERMI gamma-RAY OBSERVATIONS OF THE THIRD GALACTIC QUADRANT - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2011)
We report an analysis of the interstellar gamma-ray emission in the third Galactic quadrant measured by the Fermi Large Area Telescope. The window encompassing the Galactic plane from longitude 210 degrees to 250 degrees has kinematically well-defined segments of the Local and the Perseus arms, suitable to study the cosmic-ray (CR) densities across the outer Galaxy. We measure no large gradient with Galactocentric distance of the gamma-ray emissivities per interstellar H atom over the regions sampled in this study. The gradient depends, however, on the optical depth correction applied to derive the H I column densities. No significant variations are found in the interstellar spectra in the outer Galaxy, indicating similar shapes of the CR spectrum up to the Perseus arm for particles with GeV to tens of GeV energies. The emissivity as a function of Galactocentric radius does not show a large enhancement in the spiral arms with respect to the interarm region. The measured emissivity gradient is flatter than expectations based on a CR propagation model using the radial distribution of supernova remnants and uniform diffusion properties. In this context, observations require a larger halo size and/or a flatter CR source distribution than usually assumed. The molecular mass calibrating ratio, X-CO = N(H-2)/W-CO, is found to be (2.08 +/- 0.11) x 10(20) cm(-2)(K km s(-1))(-1) in the Local arm clouds and is not significantly sensitive to the choice of Hi spin temperature. No significant variations are found for clouds in the interarm region.
CRIS-Team WoS Importer:2020-01-15

CONSTRAINTS ON THE COSMIC-RAY DENSITY GRADIENT BEYOND THE SOLAR CIRCLE FROM FERMI gamma-RAY OBSERVATIONS OF THE THIRD GALACTIC QUADRANT (vol 726, pg 81, 2011) - Ackermann, M.; Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Berenji, B.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2013)

Constraints on the emission region of 3C 279 during strong flares in 2014 and 2015 through VHE γ -ray observations with H.E.S.S. - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2019)
The flat spectrum radio quasar 3C 279 is known to exhibit pronounced variability in the high-energy (100MeV < E < 100 GeV) gamma-ray band, which is continuously monitored with Fermi-LAT. During two periods of high activity in April 2014 and June 2015 target-of-opportunity observations were undertaken with the High Energy Stereoscopic System (H.E.S.S.) in the very-high-energy (VHE, E > 100 GeV) gamma-ray domain. While the observation in 2014 provides an upper limit, the observation in 2015 results in a signal with 8 : 7 sigma significance above an energy threshold of 66 GeV. No VHE variability was detected during the 2015 observations. The VHE photon spectrum is soft and described by a power-law index of 4.2 +/- 0.3. The H.E.S.S. data along with a detailed and contemporaneous multiwavelength data set provide constraints on the physical parameters of the emission region. The minimum distance of the emission region from the central black hole was estimated using two plausible geometries of the broad-line region and three potential intrinsic spectra. The emission region is confidently placed at r greater than or similar to 1 : 7 X 1017 cm from the black hole, that is beyond the assumed distance of the broad-line region. Time-dependent leptonic and lepto-hadronic one-zone models were used to describe the evolution of the 2015 flare. Neither model can fully reproduce the observations, despite testing various parameter sets. Furthermore, the H.E.S.S. data were used to derive constraints on Lorentz invariance violation given the large redshift of 3C 279.
CRIS-Team WoS Importer:2019-07-30
Keywords: Galaxies: active; Quasars: individual: 3C 279; Radiation mechanisms: non-thermal; Relativistic processes

CONSTRAINTS ON THE GALACTIC HALO DARK MATTER FROM FERMI-LAT DIFFUSE MEASUREMENTS - Ackermann, Markus; Ajello, Marco; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2012)
We have performed an analysis of the diffuse gamma-ray emission with the Fermi Large Area Telescope (LAT) in the Milky Way halo region, searching for a signal from dark matter annihilation or decay. In the absence of a robust dark matter signal, constraints are presented. We consider both gamma rays produced directly in the dark matter annihilation/decay and produced by inverse Compton scattering of the e(+)/e(-) produced in the annihilation/decay. Conservative limits are derived requiring that the dark matter signal does not exceed the observed diffuse gamma-ray emission. A second set of more stringent limits is derived based on modeling the foreground astrophysical diffuse emission using the GALPROP code. Uncertainties in the height of the diffusive cosmic-ray halo, the distribution of the cosmic-ray sources in the Galaxy, the index of the injection cosmic-ray electron spectrum, and the column density of the interstellar gas are taken into account using a profile likelihood formalism, while the parameters governing the cosmic-ray propagation have been derived from fits to local cosmic-ray data. The resulting limits impact the range of particle masses over which dark matter thermal production in the early universe is possible, and challenge the interpretation of the PAMELA/Fermi-LAT cosmic ray anomalies as the annihilation of dark matter.
CRIS-Team WoS Importer:2020-01-15

CONSTRAINTS ON THE GALACTIC POPULATION OF TeV PULSAR WIND NEBULAE USING FERMI LARGE AREA TELESCOPE OBSERVATIONS - Acero, F.; Ackermann, M.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2013)
Pulsar wind nebulae (PWNe) have been established as the most populous class of TeV gamma-ray emitters. Since launch, the Fermi Large Area Telescope (LAT) has identified five high-energy (100 MeV < E < 100 GeV) gamma-ray sources as PWNe and detected a large number of PWN candidates, all powered by young and energetic pulsars. The wealth of multi-wavelength data available and the new results provided by Fermi-LAT give us an opportunity to find new PWNe and to explore the radiative processes taking place in known ones. The TeV gamma-ray unidentified (UNID) sources are the best candidates for finding new PWNe. Using 45 months of Fermi-LAT data for energies above 10 GeV, an analysis was performed near the position of 58 TeV PWNe and UNIDs within 5. of the Galactic plane to establish new constraints on PWN properties and find new clues on the nature of UNIDs. Of the 58 sources, 30 were detected, and this work provides their gamma-ray fluxes for energies above 10 GeV. The spectral energy distributions and upper limits, in the multi-wavelength context, also provide new information on the source nature and can help distinguish between emission scenarios, i.e., between classification as a pulsar candidate or as a PWN candidate. Six new GeV PWN candidates are described in detail and compared with existing models. A population study of GeV PWN candidates as a function of the pulsar/PWN system characteristics is presented.
Keywords: gamma rays: general

Constraints on the Intergalactic Magnetic Field Using Fermi-LAT and H.E.S.S. Blazar Observations - Aharonian, F.; Aschersleben, J.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bi, B.; Bouyahiaoui, M.; Breuhaus, M.; Brose, R.; Brun, F.; et al. (Astrophysical Journal Letters, 2023)

Cosmic-ray electron-positron spectrum from 7 GeV to 2 TeV with the Fermi Large Area Telescope - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bloom, E. D.; Bonino, Raffaella; Brandt, T. J.; Bregeon, J.; et al. (Physical Review D, 2017)
We present a measurement of the cosmic-ray electron + positron spectrum between 7 GeV and 2 TeV performed with almost seven years of data collected with the Fermi Large Area Telescope. We find that the spectrum is well fit by a broken power law with a break energy at about 50 GeV. Above 50 GeV, the spectrum is well described by a single power law with a spectral index of 3.07 +/- 0.02 (stat +/- syst) +/- 0.04 (energy measurement). An exponential cutoff lower than 1.8 TeV is excluded at 95% CL.
CRIS-Team WoS Importer:2020-01-15

Dark matter annihilation and decay in dwarf spheroidal galaxies: the classical and ultrafaint dSphs - Bonnivard, V.; Combet, C.; Daniel, Michael K; Funk, Stefan; Geringer-Sameth, Alex; Hinton, J. A.; Maurin, D.; Read, J. I.; Sarkar, Subir; Walker, M. G.; Wilkinson, M. I. (Monthly Notices of the Royal Astronomical Society, 2015)
Dwarf spheroidal (dSph) galaxies are prime targets for present and future gamma-ray telescopes hunting for indirect signals of particle darkmatter. The interpretation of the data requires careful assessment of their dark matter content in order to derive robust constraints on candidate relic particles. Here, we use an optimized spherical Jeans analysis to reconstruct the 'astrophysical factor' for both annihilating and decaying dark matter in 21 known dSphs. Improvements with respect to previous works are: (i) the use of more flexible luminosity and anisotropy profiles to minimize biases, (ii) the use of weak priors tailored on extensive sets of contamination-free mock data to improve the confidence intervals, (iii) systematic cross-checks of binned and unbinned analyses on mock and real data, and (iv) the use of mock data including stellar contamination to test the impact on reconstructed signals. Our analysis provides updated values for the dark matter content of 8 'classical' and 13 'ultrafaint' dSphs, with the quoted uncertainties directly linked to the sample size; themore flexible parametrizationwe use results in changes compared to previous calculations. This translates into our ranking of potentially-brightest and most robust targets - namely Ursa Minor, Draco, Sculptor - and of the more promising, but uncertain targets -namely Ursa Major 2, Coma - for annihilating dark matter. Our analysis of Segue 1 is extremely sensitive to whether we include or exclude a few marginal member stars, making this target one of the most uncertain. Our analysis illustrates challenges that will need to be addressed when inferring the dark matter content of new 'ultrafaint' satellites that are beginning to be discovered in southern sky surveys.
CRIS-Team WoS Importer:2020-01-15

Dark matter constraints from observations of 25 Milky Way satellite galaxies with the Fermi Large Area Telescope - Ackermann, M.; Albert, A.; Anderson, B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonamente, E.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2014)
The dwarf spheroidal satellite galaxies of the Milky Way are some of the most dark-matter-dominated objects known. Due to their proximity, high dark matter content, and lack of astrophysical backgrounds, dwarf spheroidal galaxies are widely considered to be among the most promising targets for the indirect detection of dark matter via gamma rays. Here we report on.-ray observations of 25 Milky Way dwarf spheroidal satellite galaxies based on 4 years of Fermi Large Area Telescope (LAT) data. None of the dwarf galaxies are significantly detected in. rays, and we present.-ray flux upper limits between 500 MeV and 500 GeV. We determine the dark matter content of 18 dwarf spheroidal galaxies from stellar kinematic data and combine LAT observations of 15 dwarf galaxies to constrain the dark matter annihilation cross section. We set some of the tightest constraints to date on the annihilation of dark matter particles with masses between 2 GeV and 10 TeV into prototypical standard model channels. We find these results to be robust against systematic uncertainties in the LAT instrument performance, diffuse.-ray background modeling, and assumed dark matter density profile.

Dark matter in the coming decade: Complementary paths to discovery and beyond - Bauer, Daniel; Buckley, James; Cahill-Rowley, Matthew; Cotta, Randel; Drlica-Wagner, Alex; Feng, Jonathan L.; Funk, Stefan; Hewett, Joanne; Hooper, Dan; Ismail, Ahmed; Kaplinghat, Manoj; Kusenko, Alexander; et al. (Physics of the Dark Universe, 2015)
In this report we summarize the many dark matter searches currently being pursued through four complementary approaches: direct detection, indirect detection, collider experiments, and astrophysical probes. The essential features of broad classes of experiments are described, each with their own strengths and weaknesses. The complementarity of the different dark matter searches is discussed qualitatively and illustrated quantitatively in two simple theoretical frameworks. Our primary conclusion is that the diversity of possible dark matter candidates requires a balanced program drawing from all four approaches. (C) 2015 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Dark matter profiles and annihilation in dwarf spheroidal galaxies: prospectives for present and future gamma-ray observatories - I. The classical dwarf spheroidal galaxies - Charbonnier, A.; Combet, C.; Daniel, Michael K; Funk, Stefan; Hinton, J. A.; Maurin, D.; Power, Chris B; Read, J. I.; Sarkar, Subir; Walker, M. G.; Wilkinson, M. I. (Monthly Notices of the Royal Astronomical Society, 2011)
Due to their large dynamical mass-to-light ratios, dwarf spheroidal galaxies (dSphs) are promising targets for the indirect detection of dark matter (DM) in ?-rays. We examine their detectability by present and future ?-ray observatories. The key innovative features of our analysis are as follows: (i) we take into account the angular size of the dSphs; while nearby objects have higher ?-ray flux, their larger angular extent can make them less attractive targets for background-dominated instruments; (ii) we derive DM profiles and the astrophysical J-factor (which parametrizes the expected ?-ray flux, independently of the choice of DM particle model) for the classical dSphs directly from photometric and kinematic data. We assume very little about the DM profile, modelling this as a smooth split-power-law distribution, with and without subclumps; (iii) we use a Markov chain Monte Carlo technique to marginalize over unknown parameters and determine the sensitivity of our derived J-factors to both model and measurement uncertainties; and (iv) we use simulated DM profiles to demonstrate that our J-factor determinations recover the correct solution within our quoted uncertainties.
CRIS-Team WoS Importer:2020-01-15

Deeper HESS observations of Vela Junior (RX J0852.0-4622): Morphology studies and resolved spectroscopy - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; et al. (Astronomy & Astrophysics, 2018)
Aims. We study gamma-ray emission from the shell-type supernova remnant (SNR) RXJ0852.0-4622 to better characterize its spectral properties and its distribution over the SNR.Methods. The analysis of an extended High Energy Spectroscopic System (H.E.S.S.) data set at very high energies (E > 100 GeV) permits detailed studies, as well as spatially resolved spectroscopy, of the morphology and spectrum of the whole RXJ0852.0-4622 region. The H.E.S.S. data are combined with archival data from other wavebands and interpreted in the framework of leptonic and hadronic models. The joint Fermi-LAT-H.E.S.S. spectrum allows the direct determination of the spectral characteristics of the parent particle population in leptonic and hadronic scenarios using only GeV-TeV data.Results. An updated analysis of the H.E.S.S. data shows that the spectrum of the entire SNR connects smoothly to the high-energy spectrum measured by Fermi-LAT. The increased data set makes it possible to demonstrate that the H.E.S.S. spectrum deviates significantly from a power law and is well described by both a curved power law and a power law with an exponential cutoff at an energy of E-cut = (6.7 +/- 1.2(stat) +/- 1.2(syst)) TeV. The joint Fermi-LAT-H.E.S.S. spectrum allows the unambiguous identification of the spectral shape as a power law with an exponential cutoff. No significant evidence is found for a variation of the spectral parameters across the SNR, suggesting similar conditions of particle acceleration across the remnant. A simple modeling using one particle population to model the SNR emission demonstrates that both leptonic and hadronic emission scenarios remain plausible. It is also shown that at least a part of the shell emission is likely due to the presence of a pulsar wind nebula around PSR J0855-4644.
Keywords: astroparticle physics; gamma rays: general; acceleration of particles; cosmic rays; ISM: supernova remnants

Demystifying an unidentified EGRET source by VHE gamma-ray observations - Funk, Stefan; et al. (Astrophysics and Space Science, 2007)
In a novel approach in observational high-energy gamma-ray astronomy, observations carried out by imaging atmospheric Cherenkov telescopes provide necessary templates to pinpoint the nature of intriguing, yet unidentified EGRET gamma-ray sources. Using GeV-photons detected by EGRET and taking advantage of high spatial resolution images from H.E.S.S. observations, we were able to shed new light on the EGRET observed gamma-ray emission in the Kookaburra complex, whose previous coverage in the literature is somewhat contradictory. 3EG J 14206038 very likely accounts for two GeV gamma-ray sources (E > 1 GeV), both in positional coincidence with the recently reported pulsar wind nebulae (PWN) by HESS in the Kookaburra/Rabbit complex. PWN associations at VHE energies, supported by accumulating evidence from observations in the radio and X-ray band, are indicative for the PSR/plerionic origin of spatially coincident, but still unidentified Galactic gamma-ray sources from EGRET. This not only supports the already suggested connection between variable, but unidentified low-latitude gamma-ray sources with pulsar wind nebulae (3EG J1420-6038 has been suggested as PWN candidate previously), it also documents the ability of resolving apparently confused EGRET sources by connecting the GeV emission as measured from a large-aperture space-based gamma-ray instrument with narrow field-of-view but superior spatial resolution observations by ground-based atmospheric Cherenkov telescopes, a very promising identification technique for achieving convincing individual source identifications in the era of GLAST-LAT.
CRIS-Team WoS Importer:2020-01-15

Detailed VHE studies of the pulsar wind nebula HESS J1825-137 - Mitchel, A. M. W.; Mariaud, C.; Eger, P.; Funk, Stefan; Hahn, J.; Hinton, J.; Parsons, R. D.; Marandon, V. (6th International Symposium on High Energy Gamma-Ray Astronomy, 2017)

Detection of 16 Gamma-Ray Pulsars Through Blind Frequency Searches Using the Fermi LAT - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Anderson, Brandon; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; et al. (Science, 2009)
Pulsars are rapidly rotating, highly magnetized neutron stars emitting radiation across the electromagnetic spectrum. Although there are more than 1800 known radio pulsars, until recently only seven were observed to pulse in gamma rays, and these were all discovered at other wavelengths. The Fermi Large Area Telescope (LAT) makes it possible to pinpoint neutron stars through their gamma-ray pulsations. We report the detection of 16 gamma-ray pulsars in blind frequency searches using the LAT. Most of these pulsars are coincident with previously unidentified gamma-ray sources, and many are associated with supernova remnants. Direct detection of gamma-ray pulsars enables studies of emission mechanisms, population statistics, and the energetics of pulsar wind nebulae and supernova remnants.
CRIS-Team WoS Importer:2020-01-15

DETECTION OF A SPECTRAL BREAK IN THE EXTRA HARD COMPONENT OF GRB 090926A - Ackermann, Markus; Ajello, Marco; Asano, K.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2011)
We report on the observation of the bright, long gamma-ray burst, GRB 090926A, by the Gamma-ray Burst Monitor and Large Area Telescope (LAT) instruments on board the Fermi Gamma-ray Space Telescope. GRB 090926A shares several features with other bright LAT bursts. In particular, it clearly shows a short spike in the light curve that is present in all detectors that see the burst, and this in turn suggests that there is a common region of emission across the entire Fermi energy range. In addition, while a separate high-energy power-law component has already been observed in other gamma-ray bursts, here we report for the first time the detection with good significance of a high-energy spectral break (or cutoff) in this power-law component around 1.4 GeV in the time-integrated spectrum. If the spectral break is caused by opacity to electron-positron pair production within the source, then this observation allows us to compute the bulk Lorentz factor for the outflow, rather than a lower limit.
CRIS-Team WoS Importer:2020-01-15

Detection of extended γ -ray emission around the Geminga pulsar with H.E.S.S. - Aharonian, F.; Ait Benkhali, F.; Aschersleben, J.; Ashkar, H.; Backes, M.; Barbosa Martins, V.; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Bi, B.; Böttcher, M.; et al. (Astronomy & Astrophysics, 2023)
Geminga is an enigmatic radio-quiet γ-ray pulsar located at a mere 250 pc distance from Earth. Extended very-high-energy γ-ray emission around the pulsar was discovered by Milagro and later confirmed by HAWC, which are both water Cherenkov detector-based experiments. However, evidence for the Geminga pulsar wind nebula in gamma rays has long evaded detection by imaging atmospheric Cherenkov telescopes (IACTs) despite targeted observations. The detection of γ-ray emission on angular scales ≳2° poses a considerable challenge for the background estimation in IACT data analysis. With recent developments in understanding the complementary background estimation techniques of water Cherenkov and atmospheric Cherenkov instruments, the H.E.S.S. IACT array can now confirm the detection of highly extended γ-ray emission around the Geminga pulsar with a radius of at least 3° in the energy range 0.5-40 TeV. We find no indications for statistically significant asymmetries or energy-dependent morphology. A flux normalisation of (2.8 ± 0.7)×10-12 cm-2 s-1 TeV-1 at 1 TeV is obtained within a 1° radius region around the pulsar. To investigate the particle transport within the halo of energetic leptons around the pulsar, we fitted an electron diffusion model to the data. The normalisation of the diffusion coefficient obtained of D0 = 7.6-1.2+1.5×1027 cm2 s-1, at an electron energy of 100 TeV, is compatible with values previously reported for the pulsar halo around Geminga, which is considerably below the Galactic average.
CRIS-Team Scopus Importer:2023-06-16
Keywords: Acceleration of particles; Diffusion; Gamma rays: general; Pulsars: general

DETECTION OF GAMMA-RAY EMISSION FROM THE STARBURST GALAXIES M82 AND NGC 253 WITH THE LARGE AREA TELESCOPE ON FERMI - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Astrophysical Journal Letters, 2010)
We report the detection of high-energy gamma-ray emission from two starburst galaxies using data obtained with the Large Area Telescope on board the Fermi Gamma-ray Space Telescope. Steady point-like emission above 200 MeV has been detected at significance levels of 6.8 sigma and 4.8 sigma, respectively, from sources positionally coincident with locations of the starburst galaxies M82 and NGC 253. The total fluxes of the sources are consistent with gamma-ray emission originating from the interaction of cosmic rays with local interstellar gas and radiation fields and constitute evidence for a link between massive star formation and gamma-ray emission in star-forming galaxies.
CRIS-Team WoS Importer:2020-01-15

Detection of TeV gamma-ray emission from the shell-type supernova remnant RX J0852.0-4622 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We report the detection of TeV gamma-rays from the shell-type supernova remnant RXJ0852.0-4622 with data of 3.2 h of live time recorded with HESS in February 2004. An excess of ( 700 +/- 60) events from the whole remnant with a significance of 12 sigma was found. The observed emission region is clearly extended with a radius of the order of 1 degrees and the spatial distribution of the signal correlates with X-ray observations. The spectrum in the energy range between 500 GeV and 15 TeV is well described by a power law with a photon index of Gamma = 2.1 +/- 0. 1(stat) +/- 0.2(syst) and a differential flux at 1 TeV of (phi 1TeV) = (2.1 +/- 0.2(stat) +/- 0.6(syst)) x 10(-11) cm(-2) s(-1) TeV-1. The integral flux above 1 TeV was measured to be Phi(E > 1TeV) = (1.9 +/- 0.3(stat) +/- 0.6(syst)) x 10(-11) cm(-2) s(-1), which is at the level of the flux of the Crab nebula at these energies. More data are needed to draw firm, conclusions on the magnetic field in the remnant and the type of the particle population creating the TeV gamma-rays.
CRIS-Team WoS Importer:2020-01-15

Detection of the Characteristic Pion-Decay Signature in Supernova Remnants - Ackermann, Markus; Ajello, Marco; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; et al. (Science, 2013)
Cosmic rays are particles (mostly protons) accelerated to relativistic speeds. Despite wide agreement that supernova remnants (SNRs) are the sources of galactic cosmic rays, unequivocal evidence for the acceleration of protons in these objects is still lacking. When accelerated protons encounter interstellar material, they produce neutral pions, which in turn decay into gamma rays. This offers a compelling way to detect the acceleration sites of protons. The identification of pion-decay gamma rays has been difficult because high-energy electrons also produce gamma rays via bremsstrahlung and inverse Compton scattering. We detected the characteristic pion-decay feature in the gamma-ray spectra of two SNRs, IC 443 and W44, with the Fermi Large Area Telescope. This detection provides direct evidence that cosmic-ray protons are accelerated in SNRs.
CRIS-Team WoS Importer:2020-01-15

Detection of the Crab Nebula with the 9.7 m prototype Schwarzschild-Couder telescope - Adams, C. B.; Alfaro, R.; Ambrosi, G.; Ambrosio, M.; Aramo, C.; Arlen, T.; Batista, P. I.; Benbow, W.; Bertucci, B.; Bissaldi, E.; Biteau, J.; Bitossi, M.; et al. (Astroparticle Physics, 2021)
The Schwarzschild-Couder Telescope (SCT) is a telescope concept proposed for the Cherenkov Telescope Array. It employs a dual-mirror optical design to remove comatic aberrations over an 8∘ field of view, and a high-density silicon photomultiplier camera (with a pixel resolution of 4 arcmin) to record Cherenkov emission from cosmic ray and gamma-ray initiated particle cascades in the atmosphere. The prototype SCT (pSCT), comprising a 9.7 m diameter primary mirror and a partially instrumented camera with 1536 pixels, has been constructed at the Fred Lawrence Whipple Observatory. The telescope was inaugurated in January 2019, with commissioning continuing throughout 2019. We describe the first campaign of observations with the pSCT, conducted in January and February of 2020, and demonstrate the detection of gamma-ray emission from the Crab Nebula with a statistical significance of 8.6σ.
CRIS-Team Scopus Importer:2021-02-12

DETECTION OF THE ENERGETIC PULSAR PSR B1509-58 AND ITS PULSAR WIND NEBULA IN MSH 15-52 USING THE FERMI-LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Asano, K.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2010)
We report the detection of high-energy gamma-ray emission from the young and energetic pulsar PSR B1509-58 and its pulsar wind nebula (PWN) in the composite supernova remnant G320.4-1.2 (aka MSH 15-52). Using 1 yr of survey data with the Fermi-Large Area Telescope (LAT), we detected pulsations from PSR B1509-58 up to 1 GeV and extended gamma-ray emission above 1 GeV spatially coincident with the PWN. The pulsar light curve presents two peaks offset from the radio peak by phases 0.96 +/- 0.01 and 0.33 +/- 0.02. New constraining upper limits on the pulsar emission are derived below 1 GeV and confirm a severe spectral break at a few tens of MeV. The nebular spectrum in the 1-100 GeV energy range is well described by a power law with a spectral index of (1.57 +/- 0.17 +/- 0.13) and a flux above 1 GeV of (2.91 +/- 0.79 +/- 1.35) x 10(-9) cm(-2) s(-1). The first errors represent the statistical errors on the fit parameters, while the second ones are the systematic uncertainties. The LAT spectrum of the nebula connects nicely with Cherenkov observations, and indicates a spectral break between GeV and TeV energies.
CRIS-Team WoS Importer:2020-01-15

DETECTION OF THE PULSAR WIND NEBULA HESS J1825-137 WITH THE FERMI LARGE AREA TELESCOPE - Grondin, M. -H.; Funk, Stefan; Lemoine-Goumard, M.; Van Etten, A.; Hinton, J. A.; Camilo, F.; Cognard, I.; Espinoza, C. M.; Freire, P. C. C.; Grove, J. E.; Guillemot, L.; Johnston, Simon; et al. (Astrophysical Journal, 2011)
We announce the discovery of 1-100 GeV gamma-ray emission from the archetypal TeV pulsar wind nebula (PWN) HESS J1825-137 using 20 months of survey data from the Fermi-Large Area Telescope (LAT). The gamma-ray emission detected by the LAT is significantly spatially extended, with a best-fit rms extension of sigma = 0 degrees.56 +/- 0 degrees.07 for an assumed Gaussian model. The 1-100 GeV LAT spectrum of this source is well described by a power law with a spectral index of 1.38 +/- 0.12 +/- 0.16 and an integral flux above 1 GeV of (6.50 +/- 0.21 +/- 3.90) x 10(-9) cm(-2) s(-1). The first errors represent the statistical errors on the fit parameters, while the second ones are the systematic uncertainties. Detailed morphological and spectral analyses bring new constraints on the energetics and magnetic field of the PWN system. The spatial extent and hard spectrum of the GeV emission are consistent with the picture of an inverse Compton origin of the GeV-TeV emission in a cooling-limited nebula powered by the pulsar PSR J1826-1334.
CRIS-Team WoS Importer:2020-01-15

Detection of the Small Magellanic Cloud in gamma-rays with Fermi/LAT - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, B.; Blandford, D.; Bloom, E. D.; et al. (Astronomy & Astrophysics, 2010)
Context. The flux of gamma rays with energies greater than 100 MeV is dominated by diffuse emission coming from cosmic-rays (CRs) illuminating the interstellar medium (ISM) of our Galaxy through the processes of Bremsstrahlung, pion production and decay, and inverse-Compton scattering. The study of this diffuse emission provides insight into the origin and transport of cosmic rays.
CRIS-Team WoS Importer:2020-01-15

Detection of variable VHE gamma-ray emission from the extra-galactic gamma-ray binary LMC P3 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Context. Recently, the high-energy (HE, 0.1-100 GeV) gamma-ray emission from the object LMC P3 in the Large Magellanic Cloud (LMC) has been discovered to be modulated with a 10.3-day period, making it the first extra-galactic gamma-ray binary.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Binaries: general; Stars: massive

DETERMINATION OF THE POINT-SPREAD FUNCTION FOR THE FERMI LARGE AREA TELESCOPE FROM ON-ORBIT DATA AND LIMITS ON PAIR HALOS OF ACTIVE GALACTIC NUCLEI - Ackermann, Markus; Ajello, Marco; Allafort, A.; Asano, K.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Bloom, E. D.; et al. (Astrophysical Journal, 2013)
The Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope is a pair-conversion telescope designed to detect photons with energies from approximate to 20 MeV to > 300 GeV. The pre-launch response functions of the LAT were determined through extensive Monte Carlo simulations and beam tests. The point-spread function (PSF) characterizing the angular distribution of reconstructed photons as a function of energy and geometry in the detector is determined here from two years of on-orbit data by examining the distributions of gamma rays from pulsars and active galactic nuclei (AGNs). Above 3 GeV, the PSF is found to be broader than the pre-launch PSF. We checked for dependence of the PSF on the class of gamma-ray source and observation epoch and found none. We also investigated several possible spatial models for pair-halo emission around BL Lac AGNs. We found no evidence for a component with spatial extension larger than the PSF and set upper limits on the amplitude of halo emission in stacked images of low-and high-redshift BL Lac AGNs and the TeV blazars 1ES0229 + 200 and 1ES0347-121.
CRIS-Team WoS Importer:2020-01-15

DEVELOPMENT of the MODEL of GALACTIC INTERSTELLAR EMISSION for STANDARD POINT-SOURCE ANALYSIS of FERMI LARGE AREA TELESCOPE DATA - Acero, F.; Ackermann, M.; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2016)
Most of the celestial γ rays detected by the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope originate from the interstellar medium when energetic cosmic rays interact with interstellar nucleons and photons. Conventional point-source and extended-source studies rely on the modeling of this diffuse emission for accurate characterization. Here, we describe the development of the Galactic Interstellar Emission Model (GIEM), which is the standard adopted by the LAT Collaboration and is publicly available. This model is based on a linear combination of maps for interstellar gas column density in Galactocentric annuli and for the inverse-Compton emission produced in the Galaxy. In the GIEM, we also include large-scale structures like Loop I and the Fermi bubbles. The measured gas emissivity spectra confirm that the cosmic-ray proton density decreases with Galactocentric distance beyond 5 kpc from the Galactic Center. The measurements also suggest a softening of the proton spectrum with Galactocentric distance. We observe that the Fermi bubbles have boundaries with a shape similar to a catenary at latitudes below 20°and we observe an enhanced emission toward their base extending in the north and south Galactic directions and located within ∼4°of the Galactic Center.
Keywords: gamma rays: diffuse background; gamma rays: general; gamma rays: ISM

DISCOVERY OF A GeV BLAZAR SHINING THROUGH THE GALACTIC PLANE - Vandenbroucke, J.; Buehler, Rolf; Ajello, M.; Bechtol, K.; Bellini, Andrea; Bolte, M.; Cheung, C. C.; Civano, F.; Donato, D.; Fuhrmann, L.; Funk, Stefan; Healey, S. E.; et al. (Astrophysical Journal Letters, 2010)
The Fermi Large Area Telescope (LAT) discovered a new gamma-ray source near the Galactic plane, Fermi J0109+6134, when it flared brightly in 2010 February. The low Galactic latitude (b = -1 degrees.2) indicated that the source could be located within the Galaxy, which motivated rapid multi-wavelength follow-up including radio, optical, and X-ray observations. We report the results of analyzing all 19 months of LAT data for the source, and of X-ray observations with both Swift and the Chandra X-ray Observatory. We determined the source redshift, z = 0.783, using a Keck Low-Resolution Imaging Spectrometer observation. Finally, we compiled a broadband spectral energy distribution (SED) from both historical and new observations contemporaneous with the 2010 February flare. The redshift, SED, optical line width, X-ray absorption, and multi-band variability indicate that this new GeV source is a blazar seen through the Galactic plane. Because several of the optical emission lines have equivalent width > 5 angstrom, this blazar belongs in the flat-spectrum radio quasar category.
CRIS-Team WoS Importer:2020-01-15

Discovery of an X-ray nebula around PSR J1718-3825 and implications for the nature of the gamma-ray source HESS J1718-385 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2007)
Combined X-ray synchrotron and inverse-Compton gamma-ray observations of pulsar wind nebulae (PWN) may help to elucidate the processes of acceleration and energy loss in these systems. In particular, such observations provide constraints on the particle injection history and the magnetic field strength in these objects. The newly discovered TeV gamma-ray source HESS J1718-385 has been proposed as the likely PWN of the high spin-down luminosity pulsar PSR J1718-3825. The absence of previous, sensitive X-ray measurements of this pulsar, and the unusual energy spectrum of the TeV source, motivated observations of this region with XMM-Newton. The data obtained reveal a hard-spectrum X-ray source at the position of PSR 1718-3825 and evidence of diffuse emission in the vicinity of the pulsar. We derive limits on the keV emission from the centroid of HESS J1718-385 and discuss the implications of these findings for the PWN nature of this object.
CRIS-Team WoS Importer:2020-01-15

Discovery of a point-like very-high-energy γ-ray source in Monoceros - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2007)
Aims. The complex Monoceros Loop SNR/Rosette Nebula region contains several potential sources of very-high-energy (VHE) y-ray emission and two as yet unidentified high-energy EGRET sources. Sensitive VHE observations are required to probe acceleration processes in this region. Methods. The HESS telescope array has been used to search for very high-energy y-ray sources in this region. CO data from the NANTEN telescope were used to map the molecular clouds in the region, which could act as target material for γ-ray production via hadronic interactions. Results. We announce the discovery of a new y-ray source, HESS J0632+057, located close to the rim of the Monoceros SNR. This source is unresolved by HESS and has no clear counterpart at other wavelengths but is possibly associated with the weak X-ray source 1RXS J063258.3+054857, the Be-star MWC 148 and/or the lower energy γ-ray source 3EGJ0634+0521. No evidence for an associated molecular cloud was found in the CO data. © ESO 2007.
Keywords: Gamma rays: observations

Discovery of a VHE gamma-ray source coincident with the supernova remnant CTB 37A - van Eldik, Christopher; Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, W.; Bernloehr, K.; Boisson, C.; Borrel, V.; Braun, Isabel; et al. (Astronomy & Astrophysics, 2008)
Aims. The supernova remnant (SNR) complex CTB 37 is an interesting candidate for observations with very high energy (VHE) γ-ray telescopes such as HESS. In this region, three SNRs are seen. One of them is potentially associated with several molecular clouds, a circumstance that can be used to probe the acceleration of hadronic cosmic rays. Methods. This region was observed with the HESS Cherenkov telescopes and the data were analyzed with standard HESS procedures. Recent X-ray observations with Chandra and XMM-Newton were used to search for X-ray counterparts. Results. The discovery of a new VHE γ-ray source HESS J1714-385 coincident with the remnant CTB 37A is reported. The energy spectrum is well described by a power-law with a photon index of Γ = 2.30 ± 0.13 and a differential flux at 1 TeV of Φ = (8.7 ± 1.0 ± 1.8) × 10 cm s TeV. The integrated flux above 1 TeV is equivalent to 3% of the flux of the Crab nebula above the same energy. This VHE γ-ray source is a counterpart candidate for the unidentified EGRET source 3EG J1714-3857. The observed VHE emission is consistent with the molecular gas distribution around CTB 37A; a close match is expected in a hadronic scenario for γ-ray production. The X-ray observations reveal the presence of thermal X-rays from the NE part of the SNR. In the NW part of the remnant, an extended non-thermal X-ray source, CXOU J171419.8-383023, is discovered as well. Possible connections of the X-ray emission to the newly found VHE source are discussed. © ESO 2008.
Keywords: Gamma rays: observations; ISM: supernova remnants; X-rays: individuals: G348.5+0.1

Discovery of extended VHE gamma-ray emission from the asymmetric pulsar wind nebula in MSH 15-52 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The Supernova Remnant MSH 15-52 has been observed in very high energy (VHE) gamma-rays using the HESS 4-telescope array located in Namibia. A gamma-ray signal is detected at the 25 sigma level during an exposure of 22.1 h live time. The image reveals an elliptically shaped emission region around the pulsar PSRB1509 - 58, with semi-major axis similar to 6' in the NW-SE direction and semi-minor axis similar to 2'. This morphology coincides with the diffuse pulsar wind nebula as observed at X-ray energies by ROSAT. The overall energy spectrum from 280 GeV up to 40 TeV can be fitted by a power law with photon index Gamma = 2.27 +/- 0.03(stat) +/- 0.20(syst). The detected emission can be plausibly explained by inverse Compton scattering of accelerated relativistic electrons with soft photons.
CRIS-Team WoS Importer:2020-01-15

DISCOVERY OF HIGH-ENERGY GAMMA-RAY EMISSION FROM THE BINARY SYSTEM PSR B1259-63/LS 2883 AROUND PERIASTRON WITH FERMI - Abdo, A. A.; Ackermann, M.; Ajello, M.; Allafort, A.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Berenji, B.; Blandford, R. D.; Bonamente, E.; et al. (Astrophysical Journal Letters, 2011)
We report on the discovery of >= 100 MeV gamma-rays from the binary system PSR B1259-63/LS 2883 using the Large Area Telescope (LAT) on board Fermi. The system comprises a radio pulsar in orbit around a Be star. We report on LAT observations from near apastron to similar to 128 days after the time of periastron, t(p), on 2010 December 15. No gamma-ray emission was detected from this source when it was far from periastron. Faint gamma-ray emission appeared as the pulsar approached periastron. At similar to t(p) + 30 days, the >= 100 MeV gamma-ray flux increased over a period of a few days to a peak flux 20-30 times that seen during the pre-periastron period, but with a softer spectrum. For the following month, it was seen to be variable on daily timescales, but remained at similar to(1-4) x 10(-6) cm(-2) s(-1) before starting to fade at similar to t(p) + 57 days. The total gamma-ray luminosity observed during this period is comparable to the spin-down power of the pulsar. Simultaneous radio and X-ray observations of the source showed no corresponding dramatic changes in radio and X-ray flux between the pre-periastron and post-periastron flares. We discuss possible explanations for the observed gamma-ray-only flaring of the source.
CRIS-Team WoS Importer:2020-01-15

DISCOVERY OF PULSED gamma-RAYS FROM PSR J0034-0534 WITH THE FERMI LARGE AREA TELESCOPE: A CASE FOR CO-LOCATED RADIO AND gamma-RAY EMISSION REGIONS - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
Millisecond pulsars (MSPs) have been firmly established as a class of gamma-ray emitters via the detection of pulsations above 0.1 GeV from eight MSPs by the Fermi Large Area Telescope (LAT). Using 13 months of LAT data, significant gamma-ray pulsations at the radio period have been detected from the MSP PSR J0034-0534, making it the ninth clear MSP detection by the LAT. The gamma-ray light curve shows two peaks separated by 0.274 +/- 0.015 in phase which are very nearly aligned with the radio peaks, a phenomenon seen only in the Crab pulsar until now. The >= 0.1 GeV spectrum of this pulsar is well fit by an exponentially cutoff power law with a cutoff energy of 1.8 +/- 0.6 +/- 0.1 GeV and a photon index of 1.5 +/- 0.2 +/- 0.1, first errors are statistical and second are systematic. The near-alignment of the radio and gamma-ray peaks strongly suggests that the radio and gamma-ray emission regions are co-located and both are the result of caustic formation.
CRIS-Team WoS Importer:2020-01-15

DISCOVERY OF PULSED gamma-RAYS FROM THE YOUNG RADIO PULSAR PSR J1028-5819 WITH THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Astrophysical Journal Letters, 2009)
Radio pulsar PSR J1028-5819 was recently discovered in a high-frequency search (at 3.1 GHz) in the error circle of the Energetic Gamma-Ray Experiment Telescope (EGRET) source 3EG J1027-5817. The spin-down power of this young pulsar is great enough to make it very likely the counterpart for the EGRET source. We report here the discovery of gamma-ray pulsations from PSR J1028-5819 in early observations by the Large Area Telescope (LAT) on the Fermi Gamma-Ray Space Telescope. The gamma-ray light curve shows two sharp peaks having phase separation of 0.460 +/- 0.004, trailing the very narrow radio pulse by 0.200 +/- 0.003 in phase, very similar to that of other known gamma-ray pulsars. The measured gamma-ray flux gives an efficiency for the pulsar of similar to 10-20% (for outer magnetosphere beam models). No evidence of a surrounding pulsar wind nebula is seen in the current Fermi data but limits on associated emission are weak because the source lies in a crowded region with high background emission. However, the improved angular resolution afforded by the LAT enables the disentanglement of the previous COS-B and EGRET source detections into at least two distinct sources, one of which is now identified as PSR J1028-5819.
CRIS-Team WoS Importer:2020-01-15

Discovery of the binary pulsar PSRB1259-63 in very-high-energy gamma rays around periastron with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
We report the discovery of very-high-energy (VHE) gamma-ray emission of the binary system PSRB1259-63/SS2883 of a radio pulsar orbiting a massive, luminous Be star in a highly eccentric orbit. The observations around the 2004 periastron passage of the pulsar were performed with the four 13 m Cherenkov telescopes of the HESS experiment, recently installed in Namibia and in full operation since December 2003. Between February and June 2004, a gamma-ray signal from the binary system was detected with a total significance above 13 sigma. The flux was found to vary significantly on timescales of days which makes PSRB1259- 63 the first variable galactic source of VHE gamma-rays observed so far. Strong emission signals were observed in pre- and post-periastron phases with a flux minimum around periastron, followed by a gradual flux decrease in the months after. The measured time-averaged energy spectrum above a mean threshold energy of 380 GeV can be fitted by a simple power law F-0(E/1TeV)(-Gamma) with a photon index Gamma = 2.7 +/- 0.2(stat) +/- 0.2(sys) and flux normalisation F-0 = ( 1.3 +/- 0.1stat +/- 0.3(sys)) x 10(-12) TeV-1 cm(-2) s(-1). This detection of VHE gamma-rays provides unambiguous evidence for particle acceleration to multi-TeV energies in the binary system. In combination with coeval observations of the X-ray synchrotron emission by the RXTE and INTEGRAL instruments, and assuming the VHE gamma-ray emission to be produced by the inverse Compton mechanism, the magnetic field strength can be directly estimated to be of the order of 1G.
CRIS-Team WoS Importer:2020-01-15

Discovery of the two "wings" of the Kookaburra complex in VHE γ-rays with HESS - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
Aims. Search for Very High Energy γ-ray emission in the Kookaburra complex through observations with the HESS array. Methods. Stereoscopic imaging of Cherenkov light emission of the γ-ray showers in the atmosphere is used for the reconstruction and selection of the events to search for γ-ray signals. Their spectrum is derived by a forward-folding maximum likelihood fit. Results. Two extended γ-ray sources with an angular (68%) radius of 3.3-3.4′ are discovered at high (>13σ) statistical significance: HESS J1420-607 and HESS J1418-609. They exhibit a flux above 1 TeV of (2.97 ±0.188 ±0.60) × 10 and (2.17 ±0.17 ±0.43) × 10 cm s, respectively, and similar hard photon indices ∼2.2. Multi-wavelength comparisons show spatial coincidence with the wings of the Kookaburra. Two pulsar wind nebulae candidates, K3/PSR J1420-6048 and the Rabbit, lie on the edge of the HESS sources. Conclusions. The two new sources confirm the non-thermal nature of at least parts of the two radio wings which overlap with the γ-ray emission and establish their connection with the two X-ray pulsar wind nebulae candidates. Given the large point spread function of EGRET, the unidentified source(s) 3EG J1420-6038/GeV J1417-6100 could possibly be related to either or both HESS sources. The most likely explanation for the Very High Energy γ-rays discovered by HESS is inverse Compton emission of accelerated electrons on the Cosmic Microwave Background near the two candidate pulsar wind nebulæ, K3/PSR J1420-6048 and the Rabbit. Two scenarios which could lead to the observed large (∼10 pc) offset-nebula type morphologies are briefly discussed. © ESO 2006.
Keywords: Gamma rays: observations; ISM: general; Radiation mechanisms: non-thermal

Discovery of very high energy gamma rays associated with an X-ray binary - Funk, Stefan; et al. (Science, 2005)
X-ray binaries are composed of a normal star in orbit around a neutron star or stellar-mass black hole. Radio and x-ray observations have led to the presumption that some x-ray binaries called microquasars behave as scaled-down active galactic nuclei. Microquasars have resolved radio emission that is thought to arise from a relativistic outflow akin to active galactic nuclei jets, in which particles can be accelerated to large energies. Very high energy gamma-rays produced by the interactions of these particles have been observed from several active galactic nuclei. Using the High Energy Stereoscopic System, we find evidence for gamma-ray emission of >100 gigaelectron volts from a candidate microquasar, LS 5039, showing that particles are also accelerated to very high energies in these systems.
CRIS-Team WoS Importer:2020-01-15

Discovery of VHE gamma rays from PKS 2005-489 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The high-frequency peaked BL Lac PKS 2005 2005-489 (z = 0.071) was observed in 2003 and 2004 with the HESS stereoscopic array of imaging atmospheric-Cherenkov telescopes in Namibia. A signal was detected at the 6.7 sigma level in the 2004 observations (24.2 h live time), but not in the 2003 data set (27.3 h live time). PKS 2005 2005-489 is the first blazar independently discovered by HESS to be an emitter of VHE photons, a independently and only the second such blazar in and the Southern Hemisphere. The integral flux above 200GeV observed in 2004 is (6.9 +/- 1.0(stat) +/- 1.4(syst)) x 10(-12) cm(-2) s(-1), corresponding to similar to 2.5% of the flux observed from the Crab Nebula. The 99% upper limit on the flux in 2003, I(> 200 GeV) < 5.2 x 10(-12) cm cm(-2) s(-1), is smaller than, the flux measured in 2004, suggesting an increased level of activity in 2004. However, the data show no evidence for significant variability on any time scale less than a year. An energy spectrum is measured and is characterized by a very soft power law (photon index of G = 4.0 +/- 0.4).
CRIS-Team WoS Importer:2020-01-15

EARLY FERMI GAMMA-RAY SPACE TELESCOPE OBSERVATIONS OF THE QUASAR 3C 454.3 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Battelino, M.; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2009)
This is the first report of Fermi Gamma-Ray Space Telescope observations of the quasar 3C 454.3, which has been undergoing pronounced long-term outbursts since 2000. The data from the Large Area Telescope, covering 2008 July 7-October 6, indicate strong, highly variable.-ray emission with an average flux of similar to 3 x 10 (6) photons cm(-2) s(-1), for energies > 100 MeV. The gamma-ray flux is variable, with strong, distinct, symmetrically shaped flares for which the flux increases by a factor of several on a timescale of about 3 days. This variability indicates a compact emission region, and the requirement that the source is optically thin to pair production implies relativistic beaming with Doppler factor delta > 8, consistent with the values inferred from Very Long Baseline Interferometry observations of superluminal expansion (delta similar to 25). The observed gamma-ray spectrum is not consistent with a simple power law, but instead steepens strongly above similar to 2 GeV, and is well described by a broken power law with photon indices of similar to 2.3 and similar to 3.5 below and above the break, respectively. This is the first direct observation of a break in the spectrum of a high-luminosity blazar above 100 MeV, and it is likely direct evidence for an intrinsic break in the energy distribution of the radiating particles. Alternatively, the spectral softening above 2 GeV could be due to gamma-ray absorption via photon-photon pair production on the soft X-ray photon field of the host active galactic nucleus, but such an interpretation would require the dissipation region to be located very close (less than or similar to 100 gravitational radii) to the black hole, which would be inconsistent with the X-ray spectrum of the source.
CRIS-Team WoS Importer:2020-01-15

Einstein@Home discovers a radio-quiet gamma-ray millisecond pulsar - Clark, Colin J.; Pletsch, Holger J.; Wu, Jason; Guillemot, Lucas; Kerr, Matthew; Johnson, Tyrel J.; Camilo, Fernando; Salvetti, David; Allen, Bruce; Anderson, David; Aulbert, Carsten; Beer, Christian; et al. (Science Advances, 2018)
Millisecond pulsars (MSPs) are old neutron stars that spin hundreds of times per second and appear to pulsate as their emission beams cross our line of sight. To date, radio pulsations have been detected from all rotation-powered MSPs. In an attempt to discover radio-quiet gamma-ray MSPs, we used the aggregated power from the computers of tens of thousands of volunteers participating in the Einstein@Home distributed computing project to search for pulsations from unidentified gamma-ray sources in Fermi Large Area Telescope data. This survey discovered two isolated MSPs, one of which is the only known rotation-powered MSP to remain undetected in radio observations. These gamma-ray MSPs were discovered in completely blind searches without prior constraints from other observations, raising hopes for detecting MSPs from a predicted Galactic bulge population.
CRIS-Team WoS Importer:2020-01-15

Electromagnetic pulse protective shielding for digital x-ray detectors - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Fröjdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
Laser-driven x-ray backlighting can be used to image fast dynamic processes like the propagation of laser-driven shock waves in matter. We demonstrate and evaluate the feasibility of operating the JUNGFRAU detector designed by PSI, a direct detecting x-ray detector, in environments with extreme electromagnetic pulses. The electromagnetic pulse-protective housing is specifically designed for this detector and optimized for pump-probe experiments at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) facility at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. The beryllium x-ray entrance window of the protective housing has a high x-ray transmission of 94% at 8 keV. Measurements have shown that the housing simultaneously provides a relative damping of the electromagnetic field on average higher than 1000 in the frequency range of 100 MHz to 5 GHz. The results demonstrate the feasibility of operating digital detectors in experiments where strong electromagnetic pulses are present.
CRIS-Team Scopus Importer:2023-08-11

Electron acceleration in laboratory-produced turbulent collisionless shocks - Fiuza, F.; Swadling, G. F.; Grassi, A.; Rinderknecht, H. G.; Higginson, D. P.; Ryutov, D. D.; Bruulsema, C.; Drake, R. P.; Funk, Stefan; Glenzer, S.; Gregori, G.; Li, C. K.; et al. (Nature Physics, 2020)
Astrophysical collisionless shocks are among the most powerful particle accelerators in the Universe. Generated by violent interactions of supersonic plasma flows with the interstellar medium, supernova remnant shocks are observed to amplify magnetic fields(1) and accelerate electrons and protons to highly relativistic speeds(2-4). In the well-established model of diffusive shock acceleration(5), relativistic particles are accelerated by repeated shock crossings. However, this requires a separate mechanism that pre-accelerates particles to enable shock crossing. This is known as the 'injection problem', which is particularly relevant for electrons, and remains one of the most important puzzles in shock acceleration(6). In most astrophysical shocks, the details of the shock structure cannot be directly resolved, making it challenging to identify the injection mechanism. Here we report results from laser-driven plasma flow experiments, and related simulations, that probe the formation of turbulent collisionless shocks in conditions relevant to young supernova remnants. We show that electrons can be effectively accelerated in a first-order Fermi process by small-scale turbulence produced within the shock transition to relativistic non-thermal energies, helping overcome the injection problem. Our observations provide new insight into electron injection at shocks and open the way for controlled laboratory studies of the physics underlying cosmic accelerators.
CRIS-Team WoS Importer:2020-06-26

Energy dependent morphology of the pulsar wind nebula HESSJ1825-137 with Fermi-LAT - Principe, G.; Mitchell, Alison M. W.; Caroff, S.; Hinton, J. A.; Parsons, R. D.; Funk, Stefan (Astronomy & Astrophysics, 2020)
Aims. Taking advantage of more than 11 years of Fermi-LAT data, we perform a new and deep analysis of the pulsar wind nebula (PWN) HESS J1825-137. Combining this analysis with recent H.E.S.S. results we investigate and constrain the particle transport mechanisms at work inside the source as well as the system evolution. Methods. The PWN is studied using 11.6 years of Fermi-LAT data between 1 GeV and 1 TeV. In particular, we present the results of the spectral analysis and the first energy-resolved morphological study of the PWN HESS J1825-137 at GeV energies, which provide new insights into the-ray characteristics of the nebula. Results. An optimised analysis of the source returns an extended emission region larger than 2, corresponding to an intrinsic size of about 150 pc, making HESS J1825-137 the most extended-ray PWN currently known. The nebula presents a strong energy dependent morphology within the GeV range, moving from a radius of 1:4 below 10 GeV to a radius of 0.8 above 100 GeV, with a shift in the centroid location. Conclusions. Thanks to the large extension and peculiar energy-dependent morphology, it is possible to constrain the particle transport mechanisms inside the PWN HESS J1825-137. Using the variation of the source extension and position, as well as the constraints on the particle transport mechanisms, we present a scheme for the possible evolution of the system. Finally, we provide an estimate of the electron energy density and we discuss its nature in the PWN and TeV halo-like scenario.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Acceleration of particles; Astroparticle physics; Gamma rays: stars; Pulsars: individual: HESS J1825-137; Pulsars: individual: PSR B1823-13

Energy dependent γ-ray morphology in the pulsar wind nebula HESS J1825-137 - Funk, Stefan; van Eldik, Christopher; et al. (Astronomy & Astrophysics, 2006)
Aims. We present results from deep γ-ray observations of the Galactic pulsar wind nebula HESS J1825-137 performed with the HESS array. Methods. Detailed morphological and spatially resolved spectral studies reveal the very high-energy (VHE) γ-ray aspects of this object with unprecedented precision. Results. We confirm previous results obtained in a survey of the Galactic Plane in 2004. The γ-ray emission extends asymmetrically to the south and south-west of the energetic pulsar PSR J1826-1334, that is thought to power the pulsar wind nebula. The differential γ-ray spectrum of the whole emission region is measured over more than two orders of magnitude, from 270 GeV to 35 TeV, and shows indications for a deviation from a pure power law. Spectra have also been determined for spatially separated regions of HESS J1825-137. The photon indices from a power-law fit in the different regions show a softening of the spectrum with increasing distance from the pulsar and therefore an energy dependent morphology. Conclusions. This is the first time that an energy dependent morphology has been detected in the VHE γ-ray regime. The VHE γ-ray emission of HESS J1825-137 is phenomenologically discussed in the scenario where the γ-rays are produced by VHE electrons via Inverse Compton scattering. The high γ-ray luminosity of the source cannot be explained on the basis of constant spin-down power of the pulsar and requires higher injection power in past. © ESO 2006.
Keywords: Gamma rays: observations; ISM: individual objects: G 18.0-0.7; ISM: individual objects: HESS J1825; ISM: individual objects: PSR B1823-13; ISM: supernova remnants; Pulsars: general

Erratum: First fermi-LAT solar flare catalog (Astrophysical Journal, Supplement Series (2021) 252 (13) DOI: 10.3847/1538-4365/abd32e) - Ajello, Marco; Baldini, Luca; Bastieri, Denis; Bellazzini, R.; Berretta, A.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, Raffaella; Bruel, P.; Buson, S.; Cameron, R. A.; Caputo, R.; et al. (Astrophysical Journal Supplement Series, 2021)
In the published article, several references were accidentally left out of the text. The papers that we would like to cite are the following: 1. In the Introduction section, on page 2 the first sentence of the seventh paragraph should be: In this Fermi-LAT Solar Flare (FLSF) catalog we present the observations of 45 flares with >30?MeV emission in the period 2010–2018 January (covering most of the 24th solar cycle), extending on the work done by Share et al. (2018). 2. In the Results section, page 20 at the end of the first paragraph: All CME information was obtained from the CME online catalog of Gopalswamy et al. (2009, 2010). 3. In the Results section, page 23 at the end of the first paragraph: Winter et al. (2018) also reported that nearly all fast CMEs are associated with long-duration gamma-ray solar flares. 4. In subsection 4.2, Flare Series, on page 23 at the end of the paragraph: Similar results on the connection of long-lasting gamma-ray emission with SEPs were also reported by Gopalswamy et al. (2019). 5. In the Summary and Discussion section, end of list item 7: as first suggested by Gopalswamy et al. (2019). 6. In the Summary and Discussion section, after the second sentence on page 30: Fermi-LAT gamma-ray duration has been found to be correlated with the type II burst duration indicating the shock origin of the underlying electrons and ions (Gopalswamy et al. 2018). 7. In the Summary and Discussion section, at the end of the first paragraph on page 30: Further support for the CME-shock scenario has been reported by Gopalswamy et al. (2018, 2019, 2020, 2021), Kouloumvakos et al. (2020), Plotnikov et al. (2017), and Share et al. (2018). 8. In the Summary and Discussion section, at the end of the second sentence of the second paragraph on page 30, Ryan (2000) should be cited. 9. In the Summary and Discussion section, at the end of the second paragraph on page 30: Intriguing support for this scenario has been reported by Gary et al. (2018) and Grechnev et al. (2018).
CRIS-Team Scopus Importer:2021-10-29

Erratum: Publisher's Note: "Electromagnetic pulse protective shielding for digital x-ray detectors" [Rev. Sci. Instrum. 94, 075106 (2023) (The Review of scientific instruments (2023) 94 7 PII: 089902) - Schreiner, Stephan; Rauch, Constantin; Akstaller, Bernhard; Bleuel, Paulina; Frojdh, Eric; Martynenko, Artem S.; Mozzanica, Aldo; Neumayer, Paul; Wegert, Leonard; Zielbauer, Bernhard; Zink, Adrian; Anton, Gisela; et al. (Review of Scientific Instruments, 2023)
CRIS-Team Scopus Importer:2023-12-22

ESCAPE FROM VELA X - Hinton, J. A.; Funk, Stefan; Parsons, R. D.; Ohm, S. (Astrophysical Journal Letters, 2011)
While the Vela pulsar and its associated nebula are often considered as the archetype of a system powered by a similar to 10(4) year old isolated neutron star, many features of the spectral energy distribution of this pulsar wind nebula (PWN) are both puzzling and unusual. Here we develop a model that for the first time relates the main structures in the system, the extended radio nebula (ERN) and the X-ray cocoon through continuous injection of particles with a fixed spectral shape. We argue that diffusive escape of particles from the ERN can explain the steep Fermi-LAT spectrum. In this scenario Vela X should produce a distinct feature in the locally measured cosmic ray (CR) electron spectrum at very high energies. This prediction can be tested in the future using the Cherenkov Telescope Array. If particles are indeed released early in the evolution of PWNe and can avoid severe adiabatic losses, PWN provides a natural explanation for the rising positron fraction in the local CR spectrum.
CRIS-Team WoS Importer:2020-01-15

Evaluation of the Weighted Mean X-ray Energy for an Imaging System Via Propagation-Based Phase-Contrast Imaging - Seifert, Maria; Weule, Mareike; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Michel, Thilo; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Anton, Gisela; Funk, Stefan; et al. (Journal of Imaging, 2020)
For imaging events of extremely short duration, like shock waves or explosions, it is necessary to be able to image the object with a single-shot exposure. A suitable setup is given by a laser-induced X-ray source such as the one that can be found at GSI (Helmholtzzentrum fur Schwerionenforschung GmbH) in Darmstadt (Society for Heavy Ion Research), Germany. There, it is possible to direct a pulse from the high-energy laser Petawatt High Energy Laser for Heavy Ion eXperiments (PHELIX) on a tungsten wire to generate a picosecond polychromatic X-ray pulse, called backlighter. For grating-based single-shot phase-contrast imaging of shock waves or exploding wires, it is important to know the weighted mean energy of the X-ray spectrum for choosing a suitable setup. In propagation-based phase-contrast imaging the knowledge of the weighted mean energy is necessary to be able to reconstruct quantitative phase images of unknown objects. Hence, we developed a method to evaluate the weighted mean energy of the X-ray backlighter spectrum using propagation-based phase-contrast images. In a first step wave-field simulations are performed to verify the results. Furthermore, our evaluation is cross-checked with monochromatic synchrotron measurements with known energy at Diamond Light Source (DLS, Didcot, UK) for proof of concepts.
CRIS-Team WoS Importer:2020-08-28

Evidence for γ-ray emission from the remnant of Kepleras supernova based on deep H.E.S.S. observations - Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlöhr, K.; Böttcher, M.; Boisson, C.; et al. (Astronomy & Astrophysics, 2022)
Observations with imaging atmospheric Cherenkov telescopes (IACTs) have enhanced our knowledge of nearby supernova (SN) remnants with ages younger than 500 yr by establishing Cassiopeia A and the remnant of Tychoas SN as very-high-energy (VHE) ?-ray sources. The remnant of Kepleras SN, which is the product of the most recent naked-eye SN in our Galaxy, is comparable in age to the other two, but is significantly more distant. If the ?-ray luminosities of the remnants of Tychoas and Kepleras SNe are similar, then the latter is expected to be one of the faintest ?-ray sources within reach of the current generation IACT arrays. Here we report evidence at a statistical level of 4.6? for a VHE signal from the remnant of Kepleras SN based on deep observations by the High Energy Stereoscopic System (H.E.S.S.) with an exposure of 152 h. The measured integral flux above an energy of 226 GeV is ?0.3% of the flux of the Crab Nebula. The spectral energy distribution (SED) reveals a ?-ray emitting component connecting the VHE emission observed with H.E.S.S.To the emission observed at GeV energies with Fermi-LAT. The overall SED is similar to that of the remnant of Tychoas SN, possibly indicating the same nonthermal emission processes acting in both these young remnants of thermonuclear SNe.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Gamma rays: General; Ism: Supernova remnants; Radiation mechanisms: Non-Thermal; Supernovae: Individual: Kepler

Exploring a SNR/molecular cloud association within HESS J1745-303 - Aharonian, F.; Akhperjanian, A. G.; De Almeida, U. Barres; Bazer-Bachi, A. R.; Behera, B.; Beilicke, M.; Benbow, Wystan; Bernloehr, K.; Boisson, C.; Bolz, O.; Borrel, V.; Braun, Isabel V; et al. (Astronomy & Astrophysics, 2008)
Aims. HESS J1745-303 is an extended, unidentified VHE (very high energy) gamma-ray source discovered using HESS in the Galactic Plane Survey. Since no obvious counterpart has previously been found in longer-wavelength data, the processes that power the VHE emission are not well understood.Methods. Combining the latest VHE data with recent XMM-Newton observations and a variety of source catalogs and lower-energy survey data, we attempt to match (from an energetic and positional standpoint) the various parts of the emission of HESS J1745-303 with possible candidates.Results. Though no single counterpart is found to fully explain the VHE emission, we postulate that at least a fraction of the VHE source may be explained by a supernova-remnant/molecular-cloud association and/or a high-spin-down-flux pulsar. © 2008 ESO.
Keywords: Galaxy: general; Gamma rays: observations; ISM: clouds; ISM: cosmic rays; X-rays: general

Extended Gamma-Ray Emission from the G25.0+0.0 Region: A Star-forming Region Powered by the Newly Found OB Association? - Katsuta, J.; Uchiyama, Y.; Funk, Stefan (Astrophysical Journal, 2017)
We report a study of extended gamma-ray emission with the Large Area Telescope (LAT) on board the Fermi Gammaray Space Telescope, which is likely to be the second case of gamma-ray detection from a star-forming region (SFR) in our Galaxy. The LAT source is located in the G25 region, 1 degrees.7. x. 2 degrees.1 around (l, b) = (25 degrees.0, 0 degrees.0). The gamma-ray emission is found to be composed of two extended sources and one pointlike source. The extended sources have similar sizes of about 1 degrees.4. x. 0 degrees.1. An similar to 0 degrees.4 diameter subregion of one has a photon index of Gamma = 1.53 +/- 0.15, and is spatially coincident with HESS J1837-069, likely a pulsar wind nebula. The other parts of the extended sources have a photon index of Gamma = 2.1 +/- 0.2 without significant spectral curvature. Given their spatial and spectral properties, they have no clear associations with sources at other wavelengths. Their gamma-ray properties are similar to those of the Cygnus cocoon SFR, the only firmly established gamma-ray detection of an SFR in the Galaxy. Indeed, we find bubble-like structures of atomic and molecular gas in G25, which may be created by a putative OB association/cluster. The gamma-ray emitting regions appear confined in the bubble-like structure; similar properties are also found in the Cygnus cocoon. In addition, using observations with the XMM-Newton, we find a candidate young massive OB association/cluster G25.18+0.26 in the G25 region. We propose that the extended gamma-ray emission in G25 is associated with an SFR driven by G25.18+0.26. Based on this scenario, we discuss possible acceleration processes in the SFR and compare them with the Cygnus cocoon.
CRIS-Team WoS Importer:2020-01-15

Extended VHE gamma-ray emission towards SGR1806-20, LBV 1806-20, and stellar cluster Cl*1806-20 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Using the High Energy Spectroscopic System (H.E.S.S.) telescopes we have discovered a steady and extended very high-energy (VHE) gamma-ray source towards the luminous blue variable candidate LBV 1806-20, massive stellar cluster Cl* 1806-20, and magnetar SGR 1806-20. The new VHE source, HESS J1808-204, was detected at a statistical significance of >6 sigma (post-trial) with a photon flux normalisation (2.9 +/- 0.4(stat) +/- 0.5(sys)) x 10(-13) ph cm(-2) s(-1) TeV-1 at 1 TeV and a power-law photon index of 2.3 +/- 0.2(stat) +/- 0.3(sys). The luminosity of this source (0.2 to 10 TeV; scaled to distance d = 8 : 7 kpc) is L-VHE similar to 1.6 x 10(34)(d = 8.7 kpc)(2) erg s(-1). The VHE gamma-ray emission is extended and is well fit by a single Gaussian with statistical standard deviation of 0.095 degrees +/- 0.015 degrees. This extension is similar to that of the synchrotron radio nebula G10.0-0.3, which is thought to be powered by LBV 1806-20. The VHE gamma-ray luminosity could be provided by the stellar wind luminosity of LBV 1806-20 by itself and/or the massive star members of Cl* 1806-20. Alternatively, magnetic dissipation (e.g. via reconnection) from SGR 1806-20 can potentially account for the VHE luminosity. The origin and hadronic and/or leptonic nature of the accelerated particles responsible for HESS J1808-204 is not yet clear. If associated with SGR 1806 20, the potentially young age of the magnetar (650 yr) can be used to infer the transport limits of these particles to match the VHE source size. This discovery provides new interest in the potential for high-energy particle acceleration from magnetars, massive stars, and/or stellar clusters.
Keywords: gamma rays: general; stars: magnetars; stars: massive

Fermi and Swift Observations of GRB 190114C: Tracing the Evolution of High-energy Emission from Prompt to Afterglow - Ajello, M.; Arimoto, M.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bottacini, E.; et al. (Astrophysical Journal, 2020)
We report on the observations of gamma-ray burst (GRB) 190114C by the Fermi Gamma-ray Space Telescope and the Neil Gehrels Swift Observatory. The prompt gamma-ray emission was detected by the Fermi GRB Monitor (GBM), the Fermi Large Area Telescope (LAT), and the Swift Burst Alert Telescope (BAT) and the long-lived afterglow emission was subsequently observed by the GBM, LAT, Swift X-ray Telescope (XRT), and Swift UV Optical Telescope. The early-time observations reveal multiple emission components that evolve independently, with a delayed power-law component that exhibits significant spectral attenuation above 40 MeV in the first few seconds of the burst. This power-law component transitions to a harder spectrum that is consistent with the afterglow emission observed by the XRT at later times. This afterglow component is clearly identifiable in the GBM and BAT light curves as a slowly fading emission component on which the rest of the prompt emission is superimposed. As a result, we are able to observe the transition from internal-shock- to external-shock-dominated emission. We find that the temporal and spectral evolution of the broadband afterglow emission can be well modeled as synchrotron emission from a forward shock propagating into a wind-like circumstellar environment. We estimate the initial bulk Lorentz factor using the observed high-energy spectral cutoff. Considering the onset of the afterglow component, we constrain the deceleration radius at which this forward shock begins to radiate in order to estimate the maximum synchrotron energy as a function of time. We find that even in the LAT energy range, there exist high-energy photons that are in tension with the theoretical maximum energy that can be achieved through synchrotron emission from a shock. These violations of the maximum synchrotron energy are further compounded by the detection of very high-energy (VHE) emission above 300 GeV by MAGIC concurrent with our observations. We conclude that the observations of VHE photons from GRB 190114C necessitates either an additional emission mechanism at very high energies that is hidden in the synchrotron component in the LAT energy range, an acceleration mechanism that imparts energy to the particles at a rate that is faster than the electron synchrotron energy-loss rate, or revisions of the fundamental assumptions used in estimating the maximum photon energy attainable through the synchrotron process.
CRIS-Team Scopus Importer:2020-04-03

FERMI DETECTION DELAYED GeV EMISSION FROM THE SHORT GAMMA-RAY BURST 081024B - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Asano, K.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2010)
We report on the detailed analysis of the high-energy extended emission from the short gamma-ray burst (GRB) 081024B detected by the Fermi Gamma-ray Space Telescope. Historically, this represents the first clear detection of temporal extended emission from a short GRB. The light curve observed by the Fermi Gamma-ray Burst Monitor lasts approximately 0.8 s whereas the emission in the Fermi Large Area Telescope lasts for about 3 s. Evidence of longer lasting high-energy emission associated with long bursts has been already reported by previous experiments. Our observations, together with the earlier reported study of the bright short GRB 090510, indicate similarities in the high-energy emission of short and long GRBs and open the path to new interpretations.
CRIS-Team WoS Importer:2020-01-15

FERMI DETECTION OF THE PULSAR WIND NEBULA HESS J1640-465 - Slane, P.; Castro, D.; Funk, Stefan; Uchiyama, Y.; Lemiere, A.; Gelfand, J. D.; Lemoine-Goumard, M. (Astrophysical Journal, 2010)
We present observations of HESS J1640-465 with the Fermi-Large Area Telescope. The source is detected with high confidence as an emitter of high-energy gamma-rays. The spectrum lacks any evidence for the characteristic cutoff associated with emission from pulsars, indicating that the emission arises primarily from the pulsar wind nebula (PWN). Broadband modeling implies an evolved nebula with a low magnetic field resulting in a high gamma-ray to X-ray flux ratio. The Fermi emission exceeds predictions of the broadband model, and has a steeper spectrum, possibly resulting from a distinct excess of low energy electrons similar to what is inferred for both the Vela X and Crab PWNe.
CRIS-Team WoS Importer:2020-01-15

FERMI DISCOVERY OF GAMMA-RAY EMISSION FROM NGC 1275 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Asano, K.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; et al. (Astrophysical Journal, 2009)
We report the discovery of high-energy (E > 100 MeV) gamma-ray emission from NGC 1275, a giant elliptical galaxy lying at the center of the Perseus cluster of galaxies, based on observations made with the Large Area Telescope (LAT) of the Fermi Gamma-ray Space Telescope. The positional center of the gamma-ray source is only approximate to 3' away from the NGC 1275 nucleus, well within the 95% LAT error circle of approximate to 5'. The spatial distribution of gamma-ay photons is consistent with a point source. The average flux and power-law photon index measured with the LAT from 2008 August 4 to 2008 December 5 are F-gamma = (2.10 +/- 0.23) x 10(-7) ph (>100 MeV) cm(-2) s(-1) and Gamma = 2.17 +/- 0.05, respectively. The measurements are statistically consistent with constant flux during the four-month LAT observing period. Previous EGRET observations gave an upper limit of F-gamma < 3.72 x 10(-8) ph (>100 MeV) cm(-2) s(-1) to the gamma-ray flux from NGC 1275. This indicates that the source is variable on timescales of years to decades, and therefore restricts the fraction of emission that can be produced in extended regions of the galaxy cluster. Contemporaneous and historical radio observations are also reported. The broadband spectrum of NGC 1275 is modeled with a simple one-zone synchrotron/synchrotron self-Compton model and a model with a decelerating jet flow.
CRIS-Team WoS Importer:2020-01-15

Fermi Gamma-Ray Imaging of a Radio Galaxy - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Science, 2010)
The Fermi Gamma-ray Space Telescope has detected the gamma-ray glow emanating from the giant radio lobes of the radio galaxy Centaurus A. The resolved gamma-ray image shows the lobes clearly separated from the central active source. In contrast to all other active galaxies detected so far in high-energy gamma-rays, the lobe flux constitutes a considerable portion (greater than one-half) of the total source emission. The gamma-ray emission from the lobes is interpreted as inverse Compton-scattered relic radiation from the cosmic microwave background, with additional contribution at higher energies from the infrared-to-optical extragalactic background light. These measurements provide gamma-ray constraints on the magnetic field and particle energy content in radio galaxy lobes, as well as a promising method to probe the cosmic relic photon fields.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE CONSTRAINTS ON THE GAMMA-RAY OPACITY OF THE UNIVERSE - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Allafort, A.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2010)
The extragalactic background light (EBL) includes photons with wavelengths from ultraviolet to infrared, which are effective at attenuating gamma rays with energy above similar to 10 GeV during propagation from sources at cosmological distances. This results in a redshift- and energy-dependent attenuation of the gamma-ray flux of extragalactic sources such as blazars and gamma-ray bursts (GRBs). The Large Area Telescope on board Fermi detects a sample of gamma-ray blazars with redshift up to z similar to 3, and GRBs with redshift up to z similar to 4.3. Using photons above 10 GeV collected by Fermi over more than one year of observations for these sources, we investigate the effect of gamma-ray flux attenuation by the EBL. We place upper limits on the gamma-ray opacity of the universe at various energies and redshifts and compare this with predictions from well-known EBL models. We find that an EBL intensity in the optical-ultraviolet wavelengths as great as predicted by the "baseline" model of Stecker et al. can be ruled out with high confidence.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE DETECTION OF A BREAK IN THE GAMMA-RAY SPECTRUM OF THE SUPERNOVA REMNANT CASSIOPEIA A - Yuan, Yajie; Funk, Stefan; Johannesson, Guelauger; Lande, Joshua; Tibaldo, Luigi; Uchiyama, Yasunobu (Astrophysical Journal, 2013)
We report on observations of the supernova remnant Cassiopeia A in the energy range from 100 MeV to 100 GeV using 44 months of observations from the Large Area Telescope on board the Fermi Gamma-Ray Space Telescope. We perform a detailed spectral analysis of this source and report on a low-energy break in the spectrum at 1.72(-0.89)(+1.35) GeV. By comparing the results with models for the gamma-ray emission, we find that hadronic emission is preferred for the GeV energy range.
Keywords: acceleration of particles; gamma rays: general; ISM: supernova remnants; radiation mechanisms: non-thermal; supernovae: individual (Cassiopeia A)

FERMI LARGE AREA TELESCOPE DETECTION OF EXTENDED GAMMA-RAY EMISSION FROM THE RADIO GALAXY FORNAX A - Ackermann, M.; Ajello, Marco; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; Bonino, R.; Brandt, T. J.; et al. (Astrophysical Journal, 2016)
We report the Fermi Large Area Telescope detection of extended gamma-ray emission from the lobes of the radio galaxy Fornax. A using 6.1 years of Pass. 8 data. After Centaurus. A, this is now the second example of an extended gamma-ray source attributed to a radio galaxy. Both an extended flat disk morphology and a morphology following the extended radio lobes were preferred over a point-source description, and the core contribution was constrained to be < 14% of the total gamma-ray flux. A preferred alignment of the gamma-ray elongation with the radio lobes was demonstrated by rotating the radio lobes template. We found no significant evidence for variability on similar to 0.5 year timescales. Taken together, these results strongly suggest a lobe origin for the gamma-rays. With the extended nature of the > 100 MeV gamma-ray emission established, we model the source broadband emission considering currently available total lobe radio and millimeter flux measurements, as well as X-ray detections attributed to inverse Compton (IC) emission off the cosmic microwave background (CMB). Unlike the Centaurus. A case, we find that a leptonic model involving IC scattering of CMB and extragalactic background light (EBL) photons underpredicts the gamma-ray fluxes by factors of about similar to 2-3, depending on the EBL model adopted. An additional gamma-ray spectral component is thus required, and could be due to hadronic emission arising from proton-proton collisions of cosmic rays with thermal plasma within the radio lobes.
Keywords: galaxies: active; galaxies: individual (Fornax A); galaxies: jets; gamma rays: galaxies; radiation mechanisms: non-thermal

FERMI LARGE AREA TELESCOPE DETECTION OF PULSED gamma-RAYS FROM THE VELA-LIKE PULSARS PSR J1048-5832 AND PSR J2229+6114 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2009)
We report the detection of gamma-ray pulsations (>= 0.1GeV) from PSR J2229+ 6114 and PSR J1048-5832, the latter having been detected as a low-significance pulsar by EGRET. Data in the gamma-ray band were acquired by the Large Area Telescope (LAT) aboard the Fermi Gamma-ray Space Telescope, while the radio rotational ephemerides used to fold the gamma-ray light curves were obtained using the Green Bank Telescope, the Lovell telescope at Jodrell Bank, and the Parkes Telescope. The two young radio pulsars, located within the error circles of the previously unidentified EGRET sources 3EG J1048-5840 and 3EG J2227+6122, present spin-down characteristics similar to the Vela pulsar. PSR J1048-5832 shows two sharp peaks at phases 0.15 +/- 0.01 and 0.57 +/- 0.01 relative to the radio pulse confirming the EGRET light curve, while PSR J2229+ 6114 presents a very broad peak at phase 0.49 +/- 0.01. The gamma-ray spectra above 0.1 GeV of both pulsars are fit with power laws having exponential cutoffs near 3 GeV, leading to integral photon fluxes of (2.19 +/- 0.22 +/- 0.32) x 10(-7) cm(-2) s(-1) for PSR J1048-5832 and (3.77 +/- 0.22 +/- 0.44) x 10(-7) cm(-2) s(-1) for PSR J2229+6114. The first uncertainty is statistical and the second is systematic. PSR J1048-5832 is one of the two LAT sources whichwere entangled together as 3EG J1048-5840. These detections add to the growing number of young gamma-ray pulsars that make up the dominant population of GeV gamma-ray sources in the Galactic plane.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE DETECTION OF THE YOUNG SUPERNOVA REMNANT TYCHO - Giordano, F.; Naumann-Godo, M.; Ballet, J.; Bechtol, K.; Funk, Stefan; Lande, J.; Mazziotta, M. N.; Raino, S.; Tanaka, T.; Tibolla, O.; Uchiyama, Y. (Astrophysical Journal Letters, 2012)
After almost three years of data taking in sky-survey mode, the Fermi Large Area Telescope has detected gamma-ray emission toward Tycho's supernova remnant (SNR). The Tycho SNR is among the youngest remnants in the Galaxy, originating from a Type Ia Supernova in Lambda D 1572. The gamma-ray integral flux from 400 MeV up to 100 GeV has been measured to be (3.5 +/- 1.1(stat) +/- 0.7(syst))x 10(-9) cm(-2) s(-1) with a photon index of 2.3 +/- 0.2(stat) +/- 0.1(syst). A simple model consistent with TeV, X-ray, and radio data is sufficient to explain the observed emission as originating from pi(0) decays as a result of cosmic-ray acceleration and interaction with the ambient medium.
CRIS-Team WoS Importer:2020-01-15

FERMI/LARGE AREA TELESCOPE DISCOVERY OF GAMMA-RAY EMISSION FROM A RELATIVISTIC JET IN THE NARROW-LINE QUASAR PMN J0948+0022 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Battelino, M.; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
We report the discovery by the Large Area Telescope (LAT) onboard the Fermi Gamma-Ray Space Telescope of high-energy. gamma-ray emission from the peculiar quasar PMN J0948+0022 (z = 0.5846). The optical spectrum of this object exhibits rather narrow H beta (FWHM(H beta) similar to 1500 km s(-1)), weak forbidden lines, and is therefore classified as a narrow-line type I quasar. This class of objects is thought to have relatively small black hole mass and to accrete at a high Eddington ratio. The radio loudness and variability of the compact radio core indicate the presence of a relativistic jet. Quasi-simultaneous radio/optical/X-ray and gamma-ray observations are presented. Both radio and gamma-ray emissions (observed over five months) are strongly variable. The simultaneous optical and X-ray data from Swift show a blue continuum attributed to the accretion disk and a hard X-ray spectrum attributed to the jet. The resulting broadband spectral energy distribution (SED) and, in particular, the gamma-ray spectrum measured by Fermi are similar to those of more powerful Flat-Spectrum Radio Quasars (FSRQs). A comparison of the radio and gamma-ray characteristics of PMN J0948+0022 with the other blazars detected by LAT shows that this source has a relatively low radio and gamma-ray power with respect to other FSRQs. The physical parameters obtained from modeling the SED also fall at the low power end of the FSRQ parameter region discussed in Celotti & Ghisellini. We suggest that the similarity of the SED of PMN J0948+0022 to that of more massive and more powerful quasars can be understood in a scenario in which the SED properties depend on the Eddington ratio rather than on the absolute power.
CRIS-Team WoS Importer:2020-01-15

FERMI/LARGE AREA TELESCOPE DISCOVERY OF GAMMA-RAY EMISSION FROM THE FLAT-SPECTRUM RADIO QUASAR PKS 1454-354 - Abdo, A. A.; Ackermann, Markus; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2009)
We report the discovery by the Large Area Telescope (LAT) onboard the Fermi Gamma-Ray Space Telescope of high-energy gamma-ray (GeV) emission from the flat-spectrum radio quasar PKS 1454-354 (z = 1.424). On 2008 September 4, the source rose to a peak flux of (3.5 +/- 0.7) x 10(-6) ph cm(-2) s(-1) (E > 100 MeV) on a timescale of hours and then slowly dropped over the following 2 days. No significant spectral changes occurred during the flare. Fermi/LAT observations also showed that PKS 1454-354 is the most probable counterpart of the unidentified EGRET source 3EG J1500-3509. Multiwavelength measurements performed during the following days (7 September with Swift; 6-7 September with the ground-based optical telescope Automated Telescope for Optical Monitoring; 13 September with the Australia Telescope Compact Array) resulted in radio, optical, UV, and X-ray fluxes greater than archival data, confirming the activity of PKS 1454-354.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE DISCOVERY OF GeV GAMMA-RAY EMISSION FROM THE VICINITY OF SNR W44 - Uchiyama, Yasunobu; Funk, Stefan; Katagiri, Hideaki; Katsuta, Junichiro; Lemoine-Goumard, Marianne; Tajima, Hiroyasu; Tanaka, Takaaki; Torres, Diego F. (Astrophysical Journal Letters, 2012)
We report the detection of GeV gamma-ray emission from the molecular cloud complex that surrounds the supernova remnant (SNR) W44 using the Large Area Telescope on board Fermi. While the previously reported gamma-ray emission from SNR W44 is likely to arise from the dense radio-emitting filaments within the remnant, the gamma-ray emission that appears to come from the surrounding molecular cloud complex can be ascribed to the cosmic rays (CRs) that have escaped from W44. The non-detection of synchrotron radio emission associated with the molecular cloud complex suggests the decay of pi(0) mesons produced in hadronic collisions as the gamma-ray emission mechanism. The total kinetic energy channeled into the escaping CRs is estimated to be W-esc similar to (0.3-3) x 10(50) erg, in broad agreement with the conjecture that SNRs are the main sources of Galactic CRs.
CRIS-Team WoS Importer:2020-01-15

Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Ackermann, M.; Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; et al. (Astrophysical Journal Supplement Series, 2020)
We present the fourth Fermi Large Area Telescope catalog (4FGL) of gamma-ray sources. Based on the first eight years of science data from the Fermi Gamma-ray Space Telescope mission in the energy range from 50 MeV to 1 TeV, it is the deepest yet in this energy range. Relative to the 3FGL catalog, the 4FGL catalog has twice as much exposure as well as a number of analysis improvements, including an updated model for the Galactic diffuse gamma-ray emission, and two sets of light curves (one-year and two-month intervals). The 4FGL catalog includes 5064 sources above 4 sigma significance, for which we provide localization and spectral properties. Seventy-five sources are modeled explicitly as spatially extended, and overall, 358 sources are considered as identified based on angular extent, periodicity, or correlated variability observed at other wavelengths. For 1336 sources, we have not found plausible counterparts at other wavelengths. More than 3130 of the identified or associated sources are active galaxies of the blazar class, and 239 are pulsars.
CRIS-Team WoS Importer:2020-04-03

FERMI LARGE AREA TELESCOPE GAMMA-RAY DETECTION OF THE RADIO GALAXY M87 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Astrophysical Journal, 2009)
We report the Fermi Large Area Telescope (LAT) discovery of high-energy (MeV/GeV) gamma-ray emission positionally consistent with the center of the radio galaxy M87, at a source significance of over 10 sigma in 10 months of all-sky survey data. Following the detections of Cen A and Per A, this makes M87 the third radio galaxy seen with the LAT. The faint point-like gamma-ray source has a >100 MeV flux of 2.45 (+/-0.63) x 10(-8) photons cm(-2) s(-1) (photon index = 2.26 +/- 0.13) with no significant variability detected within the LAT observation. This flux is comparable with the previous EGRET upper limit (<2.18 x 10-8 photons cm(-2) s(-1), 2 sigma), thus there is no evidence for a significant MeV/GeV flare on decade timescales. Contemporaneous Chandra and Very Long Baseline Array data indicate low activity in the unresolved X-ray and radio core relative to previous observations, suggesting M87 is in a quiescent overall level over the first year of Fermi-LAT observations. The LAT gamma-ray spectrum is modeled as synchrotron self-Compton (SSC) emission from the electron population producing the radio-to-X-ray emission in the core. The resultant SSC spectrum extrapolates smoothly from the LAT band to the historical-minimum TeV emission. Alternative models for the core and possible contributions from the kiloparsec-scale jet in M87 are considered, and cannot be excluded.
CRIS-Team WoS Importer:2020-01-15

Fermi Large Area Telescope Measurements of the Diffuse Gamma-Ray Emission at Intermediate Galactic Latitudes - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Anderson, Brandon; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Physical Review Letters, 2009)
The diffuse galactic gamma-ray emission is produced by cosmic rays (CRs) interacting with the interstellar gas and radiation field. Measurements by the Energetic Gamma-Ray Experiment Telescope (EGRET) instrument on the Compton Gamma-Ray Observatory indicated excess gamma-ray emission greater than or similar to 1 GeV relative to diffuse galactic gamma-ray emission models consistent with directly measured CR spectra (the so-called "EGRET GeV excess"). The Large Area Telescope (LAT) instrument on the Fermi Gamma-Ray Space Telescope has measured the diffuse gamma-ray emission with improved sensitivity and resolution compared to EGRET. We report on LAT measurements for energies 100 MeV to 10 GeV and galactic latitudes 10 degrees <|b|< 20 degrees. The LAT spectrum for this region of the sky is well reproduced by a diffuse galactic gamma-ray emission model that is consistent with local CR spectra and inconsistent with the EGRET GeV excess.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE OBSERVATION OF SUPERNOVA REMNANT S147 - Katsuta, J.; Uchiyama, Y.; Tanaka, T.; Tajima, H.; Bechtol, K.; Funk, Stefan; Lande, J.; Ballet, J.; Hanabata, Y.; Lemoine-Goumard, M.; Takahashi, T. (Astrophysical Journal, 2012)
We present an analysis of gamma-ray data obtained with the Large Area Telescope on board the Fermi Gamma-ray Space Telescope in the region around supernova remnant (SNR) S147 (G180.0-1.7). A spatially extended gamma-ray source detected in an energy range of 0.2-10 GeV is found to coincide with SNR S147. We confirm its spatial extension at >5 sigma confidence level. The gamma-ray flux is (3.8 +/- 0.6) x 10(-8) photons cm(-2) s(-1), corresponding to a luminosity of 1.3 x 10(34) (d/1.3 kpc)(2) erg s(-1) in this energy range. The gamma-ray emission exhibits a possible spatial correlation with the prominent Ha filaments of SNR S147. There is no indication that the gamma-ray emission comes from the associated pulsar PSR J0538 + 2817. The gamma-ray spectrum integrated over the remnant is likely dominated by the decay of neutral pi mesons produced through the proton-proton collisions in the filaments. The reacceleration of the pre-existing cosmic rays and subsequent adiabatic compression in the filaments is sufficient to provide the energy density required of high-energy protons.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE OBSERVATIONS OF GAMMA-RAY PULSARS PSR J1057-5226, J1709-4429, AND J1952+3252 - Ardo, A. A.; Ajello, Marco; Antolini, E.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bonamente, E.; et al. (Astrophysical Journal, 2010)
The Fermi Large Area Telescope (LAT) data have confirmed the pulsed emission from all six high-confidence gamma-ray pulsars previously known from the EGRET observations. We report results obtained from the analysis of 13 months of LAT data for three of these pulsars (PSR J1057-5226, PSR J1709-4429, and PSR 11952+3252) each of which had some unique feature among the EGRET pulsars. The excellent sensitivity of LAT allows more detailed analysis of the evolution of the pulse profile with energy and also of the variation of the spectral shape with phase. We measure the cutoff energy of the pulsed emission from these pulsars for the first time and provide a more complete picture of the emission mechanism. The results confirm some, but not all, of the features seen in the EGRET data.
CRIS-Team WoS Importer:2020-01-15

Fermi Large Area Telescope observations of Local Group galaxies: detection of M31 and search for M33 - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Allafort, A.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Astronomy & Astrophysics, 2010)
Context. Cosmic rays (CRs) can be studied through the galaxy-wide gamma-ray emission that they generate when propagating in the interstellar medium. The comparison of the diffuse signals from different systems may inform us about the key parameters in CR acceleration and transport.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE OBSERVATIONS OF PSR J1836+5925 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Belfiore, Andrea; Bellazzini, R.; et al. (Astrophysical Journal, 2010)
The discovery of the gamma-ray pulsar PSR J1836+5925, powering the formerly unidentified EGRET source 3EG J1835+5918, was one of the early accomplishments of the Fermi Large Area Telescope (LAT). Sitting 25 degrees off the Galactic plane, PSR J1836+5925 is a 173 ms pulsar with a characteristic age of 1.8 million years, a spindown luminosity of 1.1 x 10(34) erg s(-1), and a large off-peak (OP) emission component, making it quite unusual among the known gamma-ray pulsar population. We present an analysis of one year of LAT data, including an updated timing solution, detailed spectral results, and a long-term light curve showing no indication of variability. No evidence for a surrounding pulsar wind nebula is seen and the spectral characteristics of the OP emission indicate it is likely magnetospheric. Analysis of recent XMM-Newton observations of the X-ray counterpart yields a detailed characterization of its spectrum, which, like Geminga, is consistent with that of a neutron star showing evidence for both magnetospheric and thermal emission.
CRIS-Team WoS Importer:2020-01-15

Fermi large area telescope observations of the cosmic-ray induced gamma-ray emission of the Earth's atmosphere - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Physical Review D, 2009)
We report on measurements of the cosmic-ray induced gamma-ray emission of Earth's atmosphere by the Large Area Telescope on board the Fermi Gamma-ray Space Telescope. The Large Area Telescope has observed the Earth during its commissioning phase and with a dedicated Earth limb following observation in September 2008. These measurements yielded similar to 6.4x10(6) photons with energies > 100 MeV and similar to 250 hours total live time for the highest quality data selection. This allows the study of the spatial and spectral distributions of these photons with unprecedented detail. The spectrum of the emission-often referred to as Earth albedo gamma-ray emission-has a power-law shape up to 500 GeV with spectral index Gamma=2.79 +/- 0.06.
CRIS-Team WoS Importer:2020-01-15

FERMI-LARGE AREA TELESCOPE OBSERVATIONS OF THE EXCEPTIONAL GAMMA-RAY OUTBURSTS OF 3C 273 IN 2009 SEPTEMBER - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, B.; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal Letters, 2010)
We present the light curves and spectral data of two exceptionally luminous gamma-ray outbursts observed by the Large Area Telescope experiment on board the Fermi Gamma-ray Space Telescope from 3C 273 in 2009 September. During these flares, having a duration of a few days, the source reached its highest gamma-ray flux ever measured. This allowed us to study, in some details, their spectral and temporal structures. The rise and the decay are asymmetric on timescales of 6 hr, and the spectral index was significantly harder during the flares than during the preceding 11 months. We also found that short, very intense flares put out the same time-integrated energy as long, less intense flares like that observed in 2009 August.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE OBSERVATIONS OF THE SUPERNOVA REMNANT W28 (G6.4-0.1) - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
We present detailed analysis of two gamma-ray sources, 1FGL J1801.3-2322c and 1FGL J1800.5-2359c, that have been found toward the supernova remnant (SNR) W28 with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope. 1FGL J1801.3-2322c is found to be an extended source within the boundary of SNR W28, and to extensively overlap with the TeV gamma-ray source HESS J1801-233, which is associated with a dense molecular cloud interacting with the SNR. The gamma-ray spectrum measured with the LAT from 0.2 to 100 GeV can be described by a broken power-law function with a break at similar to 1 GeV and photon indices of 2.09 +/- 0.08 (stat) +/- 0.28 (sys) below the break and 2.74 +/- 0.06 (stat) +/- 0.09 (sys) above the break. Given the clear association between HESS J1801-233 and the shocked molecular cloud and a smoothly connected spectrum in the GeV-TeV band, we consider the origin of the gamma-ray emission in both GeV and TeV ranges to be the interaction between particles accelerated in the SNR and the molecular cloud. The decay of neutral pions produced in interactions between accelerated hadrons and dense molecular gas provides a reasonable explanation for the broadband gamma-ray spectrum. 1FGL J1800.5-2359c, located outside the southern boundary of SNR W28, cannot be resolved. An upper limit on the size of the gamma-ray emission was estimated to be similar to 16' using events above similar to 2 GeV under the assumption of a circular shape with uniform surface brightness. It appears to coincide with the TeV source HESS J1800-240B, which is considered to be associated with a dense molecular cloud that contains the ultra compact H II region W28A2 (G5.89-0.39). We found no significant gamma-ray emission in the LAT energy band at the positions of TeV sources HESS J1800-230A and HESS J1800-230C. The LAT data for HESS J1800-230A combined with the TeV data points indicate a spectral break between 10 GeV and 100 GeV.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE OBSERVATIONS OF THE VELA-X PULSAR WIND NEBULA - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
We report on gamma-ray observations in the off-pulse window of the Vela pulsar PSR B0833-45 using 11 months of survey data from the Fermi Large Area Telescope (LAT). This pulsar is located in the 8 degrees diameter Vela supernova remnant, which contains several regions of non-thermal emission detected in the radio, X-ray, and gamma-ray bands. The gamma-ray emission detected by the LAT lies within one of these regions, the 2 degrees x 3 degrees area south of the pulsar known as Vela-X. The LAT flux is significantly spatially extended with a best-fit radius of 0.degrees 88 +/- 0.degrees 12 for an assumed radially symmetric uniform disk. The 200 MeV to 20 GeV LAT spectrum of this source is well described by a power law with a spectral index of 2.41 +/- 0.09 +/- 0.15 and integral flux above 100 MeV of (4.73 +/- 0.63 +/- 1.32) x 10(-7) cm(-2) s(-1). The first errors represent the statistical error on the fit parameters, while the second ones are the systematic uncertainties. Detailed morphological and spectral analyses give strong constraints on the energetics and magnetic field of the pulsar wind nebula system and favor a scenario with two distinct electron populations.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE OBSERVATIONS OF TWO GAMMA-RAY EMISSION COMPONENTS FROM THE QUIESCENT SUN - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2011)
We report the detection of high-energy gamma-rays from the quiescent Sun with the Large Area Telescope on board the Fermi Gamma-Ray Space Telescope (Fermi) during the first 18 months of the mission. These observations correspond to the recent period of low solar activity when the emission induced by cosmic rays (CRs) is brightest. For the first time, the high statistical significance of the observations allows clear separation of the two components: the point-like emission from the solar disk due to CR cascades in the solar atmosphere and extended emission from the inverse Compton (IC) scattering of CR electrons on solar photons in the heliosphere. The observed integral flux (>= 100 MeV) from the solar disk is (4.6 +/- 0.2inverted right perpendicularstatistical errorinverted left perpendicular(-0.08)(+1.0)inverted right perpendicularsystematic errorinverted left perpendicular) x 10(-7) cm(-2) s(-1), which is similar to 7 times higher than predicted by the "nominal" model of Seckel et al. In contrast, the observed integral flux (>= 100 MeV) of the extended emission from a region of 20 degrees radius centered on the Sun, but excluding the disk itself, (6.8 +/- 0.7[stat.](-0.4)(+0.5)[syst.]) x 10(-7) cm(-2) s(-1), along with the observed spectrum and the angular profile, is in good agreement with the theoretical predictions for the IC emission.
CRIS-Team WoS Importer:2020-01-15

Fermi Large Area Telescope Search for Photon Lines from 30 to 200 GeV and Dark Matter Implications - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; et al. (Physical Review Letters, 2010)
Dark matter (DM) particle annihilation or decay can produce monochromatic gamma rays readily distinguishable from astrophysical sources. gamma- ray line limits from 30 to 200 GeV obtained from 11 months of Fermi Large Area Space Telescope data from 20-300 GeV are presented using a selection based on requirements for a gamma-ray line analysis, and integrated over most of the sky. We obtain gamma-ray line flux upper limits in the range 0.6-4.5 x 10(-9) cm(-2) s(-1), and give corresponding DM annihilation cross-section and decay lifetime limits. Theoretical implications are briefly discussed.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE STUDY OF COSMIC RAYS AND THE INTERSTELLAR MEDIUM IN NEARBY MOLECULAR CLOUDS - Ackermann, Markus; Ajello, Marco; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2012)
We report an analysis of the interstellar gamma-ray emission from the Chamaeleon, R Coronae Australis (R CrA), and Cepheus and Polaris flare regions with the Fermi Large Area Telescope. They are among the nearest molecular cloud complexes, within similar to 300 pc from the solar system. The gamma-ray emission produced by interactions of cosmic rays (CRs) and interstellar gas in those molecular clouds is useful to study the CR densities and distributions of molecular gas close to the solar system. The obtained gamma-ray emissivities above 250 MeV are (5.9 +/- 0.1(stat-1.0sys)(+0.9)) x 10(-27) photons s(-1) sr(-1) H-atom(-1), (10.2 +/- 0.4(stat-1.7sys)(+1.2)) x 10(-27) photons s(-1) sr(-1) H-atom(-1), and (9.1 +/- 0.3(stat-0.6sys)(+1.5)) x 10(-27) photons s(-1) sr(-1) H-atom(-1) for the Chamaeleon, R CrA, and Cepheus and Polaris flare regions, respectively. Whereas the energy dependences of the emissivities agree well with that predicted from direct CR observations at the Earth, the measured emissivities from 250 MeV to 10 GeV indicate a variation of the CR density by similar to 20% in the neighborhood of the solar system, even if we consider systematic uncertainties. The molecular mass calibrating ratio, X-CO = N(H-2)/W-CO, is found to be (0.96 +/- 0.06(stat-0.12sys)(+0.15)) x 10(20) H-2-molecule cm(-2) (K km s(-1))(-1), (0.99 +/- 0.08(stat-0.10sys)(+0.18)) x 10(20) H-2-molecule cm(-2) (K km s(-1))(-1), and (0.63 +/- 0.02(stat-0.07sys)(+0.09)) x 10(20) H-2-molecule cm(-2) (K km s(-1))(-1) for the Chamaeleon, R CrA, and Cepheus and Polaris flare regions, respectively, suggesting a variation of X-CO in the vicinity of the solar system. From the obtained values of X-CO, the masses of molecular gas traced by W-CO in the Chamaeleon, R CrA, and Cepheus and Polaris flare regions are estimated to be similar to 5 x 10(3)M(circle dot), similar to 10(3)M(circle dot), and similar to 3.3 x 10(4)M(circle dot), respectively. A comparable amount of gas not traced well by standard Hi and CO surveys is found in the regions investigated.
CRIS-Team WoS Importer:2020-01-15

FERMI LARGE AREA TELESCOPE STUDY OF COSMIC-RAYS AND THE INTERSTELLAR MEDIUM IN NEARBY MOLECULAR CLOUDS (vol 755, 22, 2012) - Ackermann, M.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Berenji, B.; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2013)

FERMI LARGE AREA TELESCOPE THIRD SOURCE CATALOG - Acero, F.; Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Belfiore, A.; Bellazzini, R.; et al. (Astrophysical Journal Supplement Series, 2015)
We present the third Fermi Large Area Telescope (LAT) source catalog (3FGL) of sources in the 100 MeV-300 GeV range. Based on the first 4 yr of science data from the Fermi Gamma-ray Space Telescope mission, it is the deepest yet in this energy range. Relative to the Second Fermi LAT catalog, the 3FGL catalog incorporates twice as much data, as well as a number of analysis improvements, including improved calibrations at the event reconstruction level, an updated model for Galactic diffuse.-ray emission, a refined procedure for source detection, and improved methods for associating LAT sources with potential counterparts at other wavelengths. The 3FGL catalog includes 3033 sources above 4 sigma significance, with source location regions, spectral properties, and monthly light curves for each. Of these, 78 are flagged as potentially being due to imperfections in the model for Galactic diffuse emission. Twenty-five sources are modeled explicitly as spatially extended, and overall 238 sources are considered as identified based on angular extent or correlated variability (periodic or otherwise) observed at other wavelengths. For 1010 sources we have not found plausible counterparts at other wavelengths. More than 1100 of the identified or associated sources are active galaxies of the blazar class; several other classes of non-blazar active galaxies are also represented in the 3FGL. Pulsars represent the largest Galactic source class. From source counts of Galactic sources we estimate that the contribution of unresolved sources to the Galactic diffuse emission is similar to 3% at 1 GeV.
Keywords: catalogs; gamma-rays: general

FERMI LARGE AREA TELESCOPE VIEW OF THE CORE OF THE RADIO GALAXY CENTAURUS A - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2010)
We present gamma-ray observations with the Large Area Telescope (LAT) on board the Fermi Gamma-Ray Space Telescope of the nearby radio galaxy Centaurus A (Cen A). The previous EGRET detection is confirmed, and the localization is improved using data from the first 10 months of Fermi science operation. In previous work, we presented the detection of the lobes by the LAT; in this work, we concentrate on the gamma-ray core of Cen A. Flux levels as seen by the LAT are not significantly different from that found by EGRET, nor is the extremely soft LAT spectrum (Gamma = 2.67 +/- 0.10(stat) +/- 0.08(sys) where the photon flux is Phi alpha E-Gamma). The LAT core spectrum, extrapolated to higher energies, is marginally consistent with the non-simultaneous HESS spectrum of the source. The LAT observations are complemented by simultaneous observations from Suzaku, the Swift Burst Alert Telescope and X-ray Telescope, and radio observations with the Tracking Active Galactic Nuclei with Austral Milliarcsecond Interferometry program, along with a variety of non-simultaneous archival data from a variety of instruments and wavelengths to produce a spectral energy distribution (SED). We fit this broadband data set with a single-zone synchrotron/synchrotron self-Compton model, which describes the radio through GeV emission well, but fails to account for the non-simultaneous higher energy TeV emission observed by HESS from 2004 to 2008. The fit requires a low Doppler factor, in contrast to BL Lac objects which generally require larger values to fit their broadband SEDs. This indicates that the gamma-ray emission originates from a slower region than that from BL Lac objects, consistent with previous modeling results from Cen A. This slower region could be a slower moving layer around a fast spine, or a slower region farther out from the black hole in a decelerating flow. The fit parameters are also consistent with Cen A being able to accelerate ultra-high energy cosmic-rays, as hinted at by results from the Auger observatory.
CRIS-Team WoS Importer:2020-01-15

Fermi-LAT and Suzaku observations of the radio galaxy CentaurusB - Katsuta, J.; Tanaka, Y. T.; Stawarz, L.; O'Sullivan, S. P.; Cheung, C. C.; Kataoka, J.; Funk, Stefan; Yuasa, T.; Odaka, H.; Takahashi, T.; Svoboda, Jiri (Astronomy & Astrophysics, 2013)
Centaurus B is a nearby radio galaxy positioned in the southern hemisphere close to the Galactic plane. Here we present a detailed analysis of about 43 months of accumulated Fermi-LAT data of the gamma-ray counterpart of the source initially reported in the 2nd Fermi-LAT catalog, and of newly acquired Suzaku X-ray data. We confirm its detection at GeV photon energies and analyze the extension and variability of the gamma-ray source in the LAT dataset, in which it appears as a steady gamma-ray emitter. The X-ray core of Centaurus B is detected as a bright source of a continuum radiation. We do not detect, however, any diffuse X-ray emission from the known radio lobes, with the provided upper limit only marginally consistent with the previously claimed ASCA flux. Two scenarios that connect the X-ray and gamma-ray properties are considered. In the first one, we assume that the diffuse non-thermal X-ray emission component is not significantly below the derived Suzaku upper limit. In this case, modeling the inverse-Compton emission shows that the observed gamma-ray flux of the source may in principle be produced within the lobes. This association would imply that efficient in-situ acceleration of the radiating electrons is occurring and that the lobes are dominated by the pressure from the relativistic particles. In the second scenario, with the diffuse X-ray emission well below the Suzaku upper limits, the lobes in the system are instead dominated by the magnetic pressure. In this case, the observed gamma-ray flux is not likely to be produced within the lobes, but instead within the nuclear parts of the jet. By means of synchrotron self-Compton modeling, we show that this possibility could be consistent with the broad-band data collected for the unresolved core of Centaurus B, including the newly derived Suzaku spectrum.
CRIS-Team WoS Importer:2020-01-15

FERMI LAT DISCOVERY OF EXTENDED GAMMA-RAY EMISSION IN THE DIRECTION OF SUPERNOVA REMNANT W51C - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, B.; et al. (Astrophysical Journal Letters, 2009)
The discovery of bright gamma-ray emission coincident with supernova remnant (SNR) W51C is reported using the Large Area Telescope (LAT) onboard the Fermi Gamma-ray Space Telescope. W51C is a middle-aged remnant (similar to 10(4) yr) with intense radio synchrotron emission in its shell and known to be interacting with a molecular cloud. The gamma-ray emission is spatially extended, broadly consistent with the radio and X-ray extent of SNR W51C. The energy spectrum in the 0.2-50 GeV band exhibits steepening toward high energies. The luminosity is greater than 1 x 10(36) erg s(-1) given the distance constraint of D > 5.5 kpc, which makes this object one of the most luminous gamma-ray sources in our Galaxy. The observed gamma-rays can be explained reasonably by a combination of efficient acceleration of nuclear cosmic rays at supernova shocks and shock-cloud interactions. The decay of neutral pi mesons produced in hadronic collisions provides a plausible explanation for the gamma-ray emission. The product of the average gas density and the total energy content of the accelerated protons amounts to (n) over bar W-H(p) similar or equal to 5 x 10(51) (D/6 kpc)(2) erg cm(-3). Electron density constraints from the radio and X-ray bands render it difficult to explain the LAT signal as due to inverse Compton scattering. The Fermi LAT source coincident with SNR W51C sheds new light on the origin of Galactic cosmic rays.
CRIS-Team WoS Importer:2020-01-15

FERMI-LAT DISCOVERY OF GeV GAMMA-RAY EMISSION FROM THE YOUNG SUPERNOVA REMNANT CASSIOPEIA A - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal Letters, 2010)
We report on the first detection of GeV high-energy gamma-ray emission from a young supernova remnant (SNR) with the Large Area Telescope aboard the Fermi Gamma-ray Space Telescope. These observations reveal a source with no discernible spatial extension detected at a significance level of 12.2 sigma above 500 MeV a a location that is consistent with the position of the remnant of the supernova explosion that occurred around 1680 in the Cassiopeia constellation-Cassiopeia A (Cas A). The gamma-ray flux and spectral shape of the source are consistent with a scenario in which the gamma-ray emission originates from relativistic particles accelerated in the shell of this remnant. The total content of cosmic rays (electrons and protons) accelerated in Cas A can be estimated as W-CR similar or equal to (1-4) x 10(49) erg thanks to the well-known density in the remnant assuming that the observed gamma ray originates in the SNR shell(s). The magnetic field in the radio-emitting plasma can be robustly constrained as B >= 0.1 mG, providing new evidence of the magnetic field amplification at the forward shock and the strong field in the shocked ejecta.
CRIS-Team WoS Importer:2020-01-15

FERMI LAT OBSERVATION OF DIFFUSE GAMMA RAYS PRODUCED THROUGH INTERACTIONS BETWEEN LOCAL INTERSTELLAR MATTER AND HIGH-ENERGY COSMIC RAYS - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
Observations by the Large Area Telescope (LAT) on the Fermi mission of diffuse gamma-rays in a mid-latitude region in the third quadrant (Galactic longitude l from 200 degrees to 260 degrees and latitude vertical bar b vertical bar from 22 degrees to 60 degrees) are reported. The region contains no known large molecular cloud and most of the atomic hydrogen is within 1 kpc of the solar system. The contributions of gamma-ray point sources and inverse Compton scattering are estimated and subtracted. The residual gamma-ray intensity exhibits a linear correlation with the atomic gas column density in energy from 100 MeV to 10 GeV. The measured integrated gamma-ray emissivity is (1.63 +/- 0.05) x 10(-26) photons s(-1)sr(-1) H-atom(-1) and (0.66 +/- 0.02) x 10(-26) photons s(-1)sr(-1) H-atom(-1) above 100 MeV and above 300 MeV, respectively, with an additional systematic error of similar to 10%. The differential emissivity from 100 MeV to 10 GeV agrees with calculations based on cosmic ray spectra consistent with those directly measured, at the 10% level. The results obtained indicate that cosmic ray nuclei spectra within 1 kpc from the solar system in regions studied are close to the local interstellar spectra inferred from direct measurements at the Earth within similar to 10%.
CRIS-Team WoS Importer:2020-01-15

Fermi LAT observations of cosmic-ray electrons from 7 GeV to 1 TeV - Ackermann, Markus; Ajello, Marco; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellardi, F.; Bellazzini, R.; Belli, F.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2010)
We present the results of our analysis of cosmic-ray electrons using about 8 x 10(6) electron candidates detected in the first 12 months on-orbit by the Fermi Large Area Telescope. This work extends our previously published cosmic-ray electron spectrum down to 7 GeV, giving a spectral range of approximately 2.5 decades up to 1 TeV. We describe in detail the analysis and its validation using beam-test and on-orbit data. In addition, we describe the spectrum measured via a subset of events selected for the best energy resolution as a cross-check on the measurement using the full event sample. Our electron spectrum can be described with a power law proportional to E-3.08+/-0.05 with no prominent spectral features within systematic uncertainties. Within the limits of our uncertainties, we can accommodate a slight spectral hardening at around 100 GeV and a slight softening above 500 GeV.
CRIS-Team WoS Importer:2020-01-15

Fermi-LAT Observations of LIGO/Virgo Event GW170817 - Ajello, Marco; Allafort, A.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2018)
We present the Fermi Large Area Telescope (LAT) observations of the binary neutron star merger event GW170817 and the associated short gamma-ray burst (SGRB) GRB 170817A detected by the Fermi Gamma-ray Burst Monitor. The LAT was entering the South Atlantic Anomaly at the time of the LIGO/Virgo trigger (t(GW)) and therefore cannot place constraints on the existence of high-energy (E > 100 MeV) emission associated with the moment of binary coalescence. We focus instead on constraining high-energy emission on longer timescales. No candidate electromagnetic counterpart was detected by the LAT on timescales of minutes, hours, or days after the LIGO/Virgo detection. The resulting flux upper bound (at 95% C. L.) from the LAT is 4.5. x. 10(-10) erg cm(-2) s(-1) in the 0.1-1 GeV range covering a period from tGW. +. 1153 s to t(GW). +. 2027 s. At the distance of GRB 170817A, this flux upper bound corresponds to a luminosity upper bound of 9.7. x. 10(43) erg s(-1), which is five orders of magnitude less luminous than the only other LAT SGRB with known redshift, GRB 090510. We also discuss the prospects for LAT detection of electromagnetic counterparts to future gravitational-wave events from Advanced LIGO/Virgo in the context of GW170817/GRB 170817A.
Keywords: gamma-ray burst: general; gamma rays: general; gravitational waves

Fermi-LAT Observations of LIGO/Virgo Event GW170817 - Ajello, Marco; Allafort, A.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2018)
We present the Fermi Large Area Telescope (LAT) observations of the binary neutron star merger event GW170817 and the associated short gamma-ray burst (SGRB) GRB 170817A detected by the Fermi Gamma-ray Burst Monitor. The LAT was entering the South Atlantic Anomaly at the time of the LIGO/Virgo trigger (t(GW)) and therefore cannot place constraints on the existence of high-energy (E > 100 MeV) emission associated with the moment of binary coalescence. We focus instead on constraining high-energy emission on longer timescales. No candidate electromagnetic counterpart was detected by the LAT on timescales of minutes, hours, or days after the LIGO/Virgo detection. The resulting flux upper bound (at 95% C. L.) from the LAT is 4.5. x. 10(-10) erg cm(-2) s(-1) in the 0.1-1 GeV range covering a period from tGW. +. 1153 s to t(GW). +. 2027 s. At the distance of GRB 170817A, this flux upper bound corresponds to a luminosity upper bound of 9.7. x. 10(43) erg s(-1), which is five orders of magnitude less luminous than the only other LAT SGRB with known redshift, GRB 090510. We also discuss the prospects for LAT detection of electromagnetic counterparts to future gravitational-wave events from Advanced LIGO/Virgo in the context of GW170817/GRB 170817A.
Keywords: gamma-ray burst: general; gamma rays: general; gravitational waves

FERMI/LAT OBSERVATIONS OF LS 5039 - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal Letters, 2009)
The first results from observations of the high-mass X-ray binary LS 5039 using the Fermi Gamma-ray Space Telescope data between 2008 August and 2009 June are presented. Our results indicate variability that is consistent with the binary period, with the emission being modulated with a period of 3.903 +/- 0.005 days; the first detection of this modulation at GeV energies. The light curve is characterized by a broad peak around superior conjunction in agreement with inverse Compton scattering models. The spectrum is represented by a power law with an exponential cutoff, yielding an overall flux ( 100 MeV-300 GeV) of 4.9 +/- 0.5(stat) +/- 1.8(syst) x 10(-7) photon cm(-2) s(-1), with a cutoff at 2.1 +/- 0.3(stat) +/- 1.1(syst) GeV and photon index G = 1.9 +/- 0.1(stat) +/- 0.3(syst). The spectrum is observed to vary with orbital phase, specifically between inferior and superior conjunction. We suggest that the presence of a cutoff in the spectrum may be indicative of magnetospheric emission similar to the emission seen in many pulsars by Fermi.
CRIS-Team WoS Importer:2020-01-15

FERMI LAT OBSERVATIONS OF LS I+61 degrees 303: FIRST DETECTION OF AN ORBITAL MODULATION IN GeV GAMMA RAYS - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal Letters, 2009)
This Letter presents the first results from the observations of LS I + 61 degrees 303 using Large Area Telescope data from the Fermi Gamma-Ray Space Telescope between 2008 August and 2009 March. Our results indicate variability that is consistent with the binary period, with the emission being modulated at 26.6 +/- 0.5 days. This constitutes the first detection of orbital periodicity in high-energy gamma rays (20 MeV-100 GeV, HE). The light curve is characterized by a broad peak after periastron, as well as a smaller peak just before apastron. The spectrum is best represented by a power law with an exponential cutoff, yielding an overall flux above 100 MeV of 0.82 +/- 0.03(stat) +/- 0.07(syst) 10(-6) ph cm(-2) s(-1), with a cutoff at 6.3 +/- 1.1(stat) +/- 0.4(syst) GeV and photon index Gamma = 2.21 +/- 0.04(stat) +/- 0.06(syst). There is no significant spectral change with orbital phase. The phase of maximum emission, close to periastron, hints at inverse Compton scattering as the main radiation mechanism. However, previous very high-energy gamma ray (>100 GeV, VHE) observations by MAGIC and VERITAS show peak emission close to apastron. This and the energy cutoff seen with Fermi suggest that the link between HE and VHE gamma rays is nontrivial.
CRIS-Team WoS Importer:2020-01-15

FERMI-LAT OBSERVATIONS OF THE DIFFUSE gamma-RAY EMISSION: IMPLICATIONS FORCOSMIC RAYS AND THE INTERSTELLAR MEDIUM - Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2012)
The gamma-ray sky >100MeVis dominated by the diffuse emissions from interactions of cosmic rays with the interstellar gas and radiation fields of the Milky Way. Observations of these diffuse emissions provide a tool to study cosmic-ray origin and propagation, and the interstellar medium. We present measurements from the first 21 months of the Fermi Large Area Telescope (Fermi-LAT) mission and compare with models of the diffuse gamma-ray emission generated using the GALPROP code. The models are fitted to cosmic-ray data and incorporate astrophysical input for the distribution of cosmic-ray sources, interstellar gas, and radiation fields. To assess uncertainties associated with the astrophysical input, a grid of models is created by varying within observational limits the distribution of cosmic-ray sources, the size of the cosmic-ray confinement volume (halo), and the distribution of interstellar gas. An all-sky maximum-likelihood fit is used to determine the X-CO factor, the ratio between integrated CO-line intensity and H-2 column density, the fluxes and spectra of the gamma-ray point sources from the first Fermi-LAT catalog, and the intensity and spectrum of the isotropic background including residual cosmic rays that were misclassified as gamma-rays, all of which have some dependency on the assumed diffuse emission model. The models are compared on the basis of their maximum-likelihood ratios as well as spectra, longitude, and latitude profiles. We also provide residual maps for the data following subtraction of the diffuse emission models. The models are consistent with the data at high and intermediate latitudes but underpredict the data in the inner Galaxy for energies above a few GeV. Possible explanations for this discrepancy are discussed, including the contribution by undetected point-source populations and spectral variations of cosmic rays throughout the Galaxy. In the outer Galaxy, we find that the data prefer models with a flatter distribution of cosmic-ray sources, a larger cosmic-ray halo, or greater gas density than is usually assumed. Our results in the outer Galaxy are consistent with other Fermi-LAT studies of this region that used different analysis methods than employed in this paper.
CRIS-Team WoS Importer:2020-01-15

Fermi-LAT Observations of the Gamma-Ray Burst GRB 130427A - Ackermann, M.; Ajello, M.; Asano, K.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; et al. (Science, 2014)
The observations of the exceptionally bright gamma-ray burst (GRB) 130427A by the Large Area Telescope aboard the Fermi Gamma-ray Space Telescope provide constraints on the nature of these unique astrophysical sources. GRB 130427A had the largest fluence, highest-energy photon (95 GeV), longest gamma-ray duration (20 hours), and one of the largest isotropic energy releases ever observed from a GRB. Temporal and spectral analyses of GRB 130427A challenge the widely accepted model that the nonthermal high-energy emission in the afterglow phase of GRBs is synchrotron emission radiated by electrons accelerated at an external shock.

FERMI-LAT OBSERVATIONS OF THE GEMINGA PULSAR - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastier, D.; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bignami, G. F.; et al. (Astrophysical Journal, 2010)
We report on the Fermi-LAT observations of the Geminga pulsar, the second brightest non-variable GeV source in the gamma-ray sky and the first example of a radio-quiet gamma-ray pulsar. The observations cover one year, from the launch of the Fermi satellite through 2009 June 15. A data sample of over 60,000 photons enabled us to build a timing solution based solely on gamma-rays. Timing analysis shows two prominent peaks, separated by Delta phi = 0.497 +/- 0.004 in phase, which narrow with increasing energy. Pulsed gamma-rays are observed beyond 18 GeV, precluding emission below 2.7 stellar radii because of magnetic absorption. The phase-averaged spectrum was fitted with a power law with exponential cutoff of spectral index Gamma = (1.30 +/- 0.01 +/- 0.04), cutoff energy E-0 = (2.46 +/- 0.04 +/- 0.17) GeV, and an integral photon flux above 0.1 GeV of (4.14 +/- 0.02 +/- 0.32) x 10(-6) cm(-2) s(-1). The first uncertainties are statistical and the second ones are systematic. The phase-resolved spectroscopy shows a clear evolution of the spectral parameters, with the spectral index reaching a minimum value just before the leading peak and the cutoff energy having maxima around the peaks. The phase-resolved spectroscopy reveals that pulsar emission is present at all rotational phases. The spectral shape, broad pulse profile, and maximum photon energy favor the outer magnetospheric emission scenarios.
CRIS-Team WoS Importer:2020-01-15

FERMI-LAT OBSERVATIONS OF THE LIGO EVENT GW150914 - Ackermann, M.; Ajello, Marco; Albert, A.; Anderson, B.; Arimoto, M.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; et al. (Astrophysical Journal Letters, 2016)
The Fermi Large Area Telescope (LAT) has an instantaneous field of view (FoV) covering similar to 1/5 of the sky and it completes a survey of the entire sky in high-energy gamma-rays every 3 hr. It enables searches for transient phenomena over timescales from milliseconds to years. Among these phenomena could be electromagnetic counterparts to gravitational wave (GW) sources. In this paper, we present a detailed study of the LAT observations relevant to Laser Interferometer Gravitational-wave Observatory (LIGO) event GW150914, which is the first direct detection of gravitational waves and has been interpreted as being due to the coalescence of two stellar-mass black holes. The localization region for GW150914 was outside the LAT FoV at the time of the GW signal. However, as part of routine survey observations, the LAT observed the entire LIGO localization region within similar to 70 minutes of the trigger and thus enabled a comprehensive search for a.-ray counterpart to GW150914. The study of the LAT data presented here did not find any potential counterparts to GW150914, but it did provide limits on the presence of a transient counterpart above 100 MeV on timescales of hours to days over the entire GW150914 localization region.
Keywords: gamma-ray burst: general; gamma-rays: general; gravitational waves; methods: observational

Fermi LAT search for dark matter in gamma-ray lines and the inclusive photon spectrum - Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Barbiellini, G.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Physical Review D, 2012)
Dark matter particle annihilation or decay can produce monochromatic gamma-ray lines and contribute to the diffuse gamma-ray background. Flux upper limits are presented for gamma-ray spectral lines from 7 to 200 GeV and for the diffuse gamma-ray background from 4.8 GeV to 264 GeV obtained from two years of Fermi Large Area Telescope data integrated over most of the sky. We give cross-section upper limits and decay lifetime lower limits for dark matter models that produce gamma-ray lines or contribute to the diffuse spectrum, including models proposed as explanations of the PAMELA and Fermi cosmic-ray data.
CRIS-Team WoS Importer:2020-01-15

FERMI-LAT SEARCH FOR PULSAR WIND NEBULAE AROUND GAMMA-RAY PULSARS - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2011)
The high sensitivity of the Fermi-LAT (Large Area Telescope) offers the first opportunity to study faint and extended GeV sources such as pulsar wind nebulae (PWNe). After one year of observation the LAT detected and identified three PWNe: the Crab Nebula, Vela-X, and the PWN inside MSH 15-52. In the meantime, the list of LAT detected pulsars increased steadily. These pulsars are characterized by high energy loss rates ((E) over dot) from similar to 3 x 10(33) erg s(-1) to 5 x 10(38) erg s(-1) and are therefore likely to power a PWN. This paper summarizes the search for PWNe in the off-pulse windows of 54 LAT-detected pulsars using 16 months of survey observations. Ten sources show significant emission, seven of these likely being of magnetospheric origin. The detection of significant emission in the off-pulse interval offers new constraints on the gamma-ray emitting regions in pulsar magnetospheres. The three other sources with significant emission are the Crab Nebula, Vela-X, and a new PWN candidate associated with the LAT pulsar PSR J1023-5746, coincident with the TeV source HESS J1023-575. We further explore the association between the HESS and the Fermi source by modeling its spectral energy distribution. Flux upper limits derived for the 44 remaining sources are used to provide new constraints on famous PWNe that have been detected at keV and/or TeV energies.
CRIS-Team WoS Importer:2020-01-15

FERMI LAT STACKING ANALYSIS OF SWIFT LOCALIZED GRBs - Ackermann, M.; Ajello, M.; Anderson, B.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bhat, P. N.; Bissaldi, Elisabetta; Bonino, R.; et al. (Astrophysical Journal, 2016)
We perform a comprehensive stacking analysis of data collected by the Fermi. Large Area Telescope (LAT) of gamma-ray bursts (GRBs) localized by the Swift. spacecraft, which were not detected by the LAT but which fell within the instrument's field of view at the time of trigger. We examine a total of 79 GRBs by comparing the observed counts over a range of time intervals to that expected from designated background orbits, as well as by using a joint likelihood technique to model the expected distribution of stacked counts. We find strong evidence for subthreshold emission at MeV to GeV energies using both techniques. This observed excess is detected during intervals that include and exceed the durations typically characterizing the prompt emission observed at keV energies and lasts at least 2700 s after the co-aligned burst trigger. By utilizing a novel cumulative likelihood analysis, we find that although a burst's prompt gamma-ray and afterglow X-ray flux both correlate with the strength of the subthreshold emission, the X-ray afterglow flux measured by Swift's X-ray Telescope at 11 hr post trigger correlates far more significantly. Overall, the extended nature of the subthreshold emission and its connection to the burst's afterglow brightness lend. further support to the external forward shock origin of the late-time emission detected by the LAT. These results suggest that the extended high-energy emission observed by the LAT may be a relatively common feature but remains undetected in a majority of bursts owing. to instrumental threshold effects.
Keywords: gamma-ray burst: general; gamma rays: general; methods: data analysis; X-rays: bursts

FERMI-LAT STUDY OF GAMMA-RAY EMISSION IN THE DIRECTION OF SUPERNOVA REMNANT W49B - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2010)
We present an analysis of the gamma-ray data obtained with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope in the direction of SNR W49B (G43.3-0.2). A bright unresolved gamma-ray source detected at a significance of 38 sigma is found to coincide with SNR W49B. The energy spectrum in the 0.2-200 GeV range gradually steepens toward high energies. The luminosity is estimated to be 1.5 x 10(36) (D/8 kpc)(2) erg s(-1) in this energy range. There is no indication that the gamma-ray emission comes from a pulsar. Assuming that the supernova remnant (SNR) shell is the site of gamma-ray production, the observed spectrum can be explained either by the decay of neutral pi mesons produced through the proton-proton collisions or by electron bremsstrahlung. The calculated energy density of relativistic particles responsible for the LAT flux is estimated to be remarkably large, U-e,U-p > 10(4) eV cm(-3), for either gamma-ray production mechanism.
CRIS-Team WoS Importer:2020-01-15

FERMI OBSERVATIONS OF CASSIOPEIA AND CEPHEUS: DIFFUSE GAMMA-RAY EMISSION IN THE OUTER GALAXY - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; et al. (Astrophysical Journal, 2010)
We present the analysis of the interstellar gamma-ray emission measured by the Fermi Large Area Telescope toward a region in the second Galactic quadrant at 100 degrees <= l <= 145 degrees and -15 degrees <= b <= +30 degrees. This region encompasses the prominent Gould Belt clouds of Cassiopeia, Cepheus, and the Polaris flare, as well as atomic and molecular complexes at larger distances, like that associated with NGC 7538 in the Perseus arm. The good kinematic separation in velocity between the local, Perseus, and outer arms, and the presence of massive complexes in each of them, make this region well suited to probe cosmic rays (CRs) and the interstellar medium beyond the solar circle. The gamma-ray emissivity spectrum of the gas in the Gould Belt is consistent with expectations based on the locally measured CR spectra. The gamma-ray emissivity decreases from the Gould Belt to the Perseus arm, but the measured gradient is flatter than expectations for CR sources peaking in the inner Galaxy as suggested by pulsars. The X-CO = N(H-2)/W-CO conversion factor is found to increase from (0.87 +/- 0.05) x 10(20) cm(-2) (K km s(-1))(-1) in the Gould Belt to (1.9 +/- 0.2) x 10(20) cm(-2) (K km s(-1))(-1) in the Perseus arm. We derive masses for the molecular clouds under study. Dark gas, not properly traced by radio and microwave surveys, is detected in the Gould Belt through a correlated excess of dust and gamma-ray emission: its mass amounts to similar to 50% of the CO-traced mass.
CRIS-Team WoS Importer:2020-01-15

FERMI OBSERVATIONS OF gamma-RAY EMISSION FROM THE MOON - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwoo, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2012)
We report on the detection of high-energy gamma-ray emission from the Moon during the first 24 months of observations by the Fermi Large Area Telescope (LAT). This emission comes from particle cascades produced by cosmic-ray (CR) nuclei and electrons interacting with the lunar surface. The differential spectrum of the Moon is soft and can be described as a log-parabolic function with an effective cutoff at 2-3 GeV, while the average integral flux measured with the LAT from the beginning of observations in 2008 August to the end of 2010 August is F(> 100 MeV) = (1.04 +/- 0.01 [statistical error] +/- 0.1 [systematic error]) x 10(-6) cm(-2) s(-1). This flux is about a factor 2-3 higher than that observed between 1991 and 1994 by the EGRET experiment on board the Compton Gamma Ray Observatory, F(> 100 MeV) approximate to 5 x 10(-7) cm-2 s-1, when solar activity was relatively high. The higher gamma-ray flux measured by Fermi is consistent with the deep solar minimum conditions during the first 24 months of the mission, which reduced effects of heliospheric modulation, and thus increased the heliospheric flux of Galactic CRs. A detailed comparison of the light curve with McMurdo Neutron Monitor rates suggests a correlation of the trends. The Moon and the Sun are so far the only known bright emitters of gamma-rays with fast celestial motion. Their paths across the sky are projected onto the Galactic center and high Galactic latitudes as well as onto other areas crowded with high-energy gamma-ray sources. Analysis of the lunar and solar emission may thus be important for studies of weak and transient sources near the ecliptic.
CRIS-Team WoS Importer:2020-01-15

FERMI OBSERVATIONS OF TeV-SELECTED ACTIVE GALACTIC NUCLEI - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
We report on observations of TeV-selected active galactic nuclei (AGNs) made during the first 5.5 months of observations with the Large Area Telescope (LAT) on-board the Fermi Gamma-ray Space Telescope (Fermi). In total, 96 AGNs were selected for study, each being either (1) a source detected at TeV energies (28 sources) or (2) an object that has been studied with TeV instruments and for which an upper limit has been reported (68 objects). The Fermi observations show clear detections of 38 of these TeV-selected objects, of which 21 are joint GeV-TeV sources, and 29 were not in the third EGRET catalog. For each of the 38 Fermi-detected sources, spectra and light curves are presented. Most can be described with a power law of spectral index harder than 2.0, with a spectral break generally required to accommodate the TeV measurements. Based on an extrapolation of the Fermi spectrum, we identify sources, not previously detected at TeV energies, which are promising targets for TeV instruments. Evidence for systematic evolution of the gamma-ray spectrum with redshift is presented and discussed in the context of interaction with the extragalactic background light.
CRIS-Team WoS Importer:2020-01-15

First Fermi-LAT Solar Flare Catalog - Ajello, M.; Baldini, L.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; Bruel, P.; Buson, S.; Cameron, R. A.; Caputo, R.; et al. (Astrophysical Journal Supplement Series, 2021)
We present the first Fermi-Large Area Telescope (LAT) solar flare catalog covering the 24th solar cycle. This catalog contains 45 Fermi-LAT solar flares (FLSFs) with emission in the gamma-ray energy band (30 MeV-10 GeV) detected with a significance of >= 5 sigma over the years 2010-2018. A subsample containing 37 of these flares exhibits delayed emission beyond the prompt-impulsive hard X-ray phase, with 21 flares showing delayed emission lasting more than two hours. No prompt-impulsive emission is detected in four of these flares. We also present in this catalog observations of GeV emission from three flares originating from active regions located behind the limb of the visible solar disk. We report the lightcurves, spectra, best proton index, and localization (when possible) for all FLSFs. The gamma-ray spectra are consistent with the decay of pions produced by >300 MeV protons. This work contains the largest sample of high-energy gamma-ray flares ever reported and provides a unique opportunity to perform population studies on the different phases of the flare and thus allowing a new window in solar physics to be opened.
CRIS-Team WoS Importer:2021-02-12

First ground-based measurement of sub-20 GeV to 100 GeV gamma-Rays from the Vela pulsar with HESS II - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Aims. We report on the measurement and investigation of pulsed high-energy y-ray emission from the Vela pulsar, PSR B0833-45, based on observations with the largest telescope of H.E.S.S., CT5, in monoscopic mode, and on data obtained with the Fermi-LAT.
CRIS-Team WoS Importer:2020-01-15
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-Thermal

First intensity interferometry measurements with the H.E.S.S. telescopes - Zmija, Andreas; Vogel, Naomi; Wohlleben, Frederik; Anton, Gisela; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2024)
Intensity interferometry for astrophysical observations has gained increasing interest in the last decade. The method of correlating photon fluxes at different telescopes for high resolution astronomy without access to the phase of the incoming light is insensitive to atmospheric turbulence and does not require high-precision optical path control. The necessary large collection areas can be provided by Imaging Atmospheric Cherenkov Telescopes. Implementation of intensity interferometers to existing telescope systems such as VERITAS and MAGIC has proven to be successful for high-resolution imaging of stars. In 2022 April we equipped two telescopes of the H.E.S.S. array in Namibia with an intensity interferometry setup to measure southern sky stars and star systems during the bright moon period. We mounted an external optical system to the lid of the telescope cameras, which splits the incoming light and feeds it into two photomultipliers in order to measure the zero-baseline correlation within one telescope in addition to the cross-correlation between the telescopes. The optical elements are motorized, which enables live correction of tracking inaccuracies of the telescopes. During the campaign we measured the spatial correlation curves and thereby the angular diameters of λ Sco (Shaula) and σ Sgr (Nunki), while we also performed systematic studies of our interferometer using the multiple star system of α Cru (Acrux).
CRIS-Team Scopus Importer:2024-01-26
Keywords: instrumentation: high angular resolution; instrumentation: interferometers; methods: observational; stars: imaging; techniques: interferometric; telescopes

First limits on the very-high energy gamma-ray afterglow emission of a fast radio burst: H.E.S.S. Observations of FRB 150418 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Aims. Following the detection of the fast radio burst FRB150418 by the SUPERB project at the Parkes radio telescope, we aim to search for very-high energy gamma-ray afterglow emission.Methods. Follow-up observations in the very-high energy gamma-ray domain were obtained with the H.E.S.S. imaging atmospheric Cherenkov telescope system within 14.5 h of the radio burst.Results. The obtained 1.4 h of gamma-ray observations are presented and discussed. At the 99% C.L. we obtained an integral upper limit on the gamma-ray flux of Phi(gamma)(E > 350 GeV) < 1.33 x 10(-8) m(-2) s(-1). Differential flux upper limits as function of the photon energy were derived and used to constrain the intrinsic high-energy afterglow emission of FRB 150418.Conclusions. No hints for high-energy afterglow emission of FRB 150418 were found. Taking absorption on the extragalactic background light into account and assuming a distance of z = 0 : 492 based on radio and optical counterpart studies and consistent with the FRB dispersion, we constrain the gamma-ray luminosity at 1 TeV to L < 5 : 1 x 10(47) erg/s at 99% C.L.
Keywords: Astroparticle physics; Gamma rays: general

FlashCam: A fully digital camera for the Cherenkov telescope array medium-sized telescopes - Pühlhofer, G.; Barcelo, M.; Bauer, C.; Bi, B.; Catalano, Jacqueline; Diebold, S.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
FlashCam is an innovative camera designed for the focal plane instrumentation of Cherenkov telescopes. The concept of the FlashCam trigger and readout system is based on the continuous digitization and digital processing of the photo detector signals on FPGAs, and on a high performance, Ethernet-based front-end readout. Because of the modular design, the electronics that have been developed can serve either photomultiplier tubes or silicon-based photon detectors. In the framework of the CTA (Cherenkov telescope array) project, the FlashCam team has developed a PMT-based camera that is suitable for the medium-sized telescopes. With over 100 Cherenkov telescopes, the CTA observatory will run the most sensitive ground-based telescope systems for TeV gamma-ray astronomy when the two arrays in the Northern and Southern Hemisphere (with three different telescope sizes) will go into operation in the upcoming years.
CRIS-Team Scopus Importer:2019-12-31
Keywords: Cherenkov Telescope Array; electronics; gamma-rays; Imaging Atmospheric Cherenkov Telescopes

Focal Plane Detectors for the Advanced Gamma-Ray Imaging System (AGIS) - Otte, A. N.; Byrum, K.; Drake, G.; Falcone, A.; Funk, Stefan; Horan, D.; Mukherjee, R.; Smith, A.; Tajima, H.; Wagner, R. G.; Williams, D. A. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

Front-end electronics of the Compact High Energy Camera - Leach, S. A.; Lapington, J. S.; Ross, D.; Thornhill, J.; Duffy, C.; Funk, Stefan; Zink, Adrian; Jankowsky, David; White, R.; Zorn, J.; Tibaldo, L.; Varner, G.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
The Compact High Energy Camera is a focal plane camera designed for two mirror Schwarzschild–Couder design imaging air Cherenkov telescopes such as the SST-2M variants on the Cherenkov Telescope Array. It utilises a 2048-pixel array of silicon photomultipliers arranged in thirty-two 8 x 8 pixel 2 tiles. Each detector tile is instrumented with a front-end electronics module designed to provide single photon counting with sub-nanosecond timing, full-waveform digitisation and event triggering capabilities based around TARGET ASICs. Performance results including triggering, digitiser noise, signal crosstalk, linearity and dynamic range from initial laboratory tests have been collated and are presented.
CRIS-Team Scopus Importer:2019-05-07
Keywords: CHEC; CTA; Front-end electronics; Full-waveform readout; Readout; Silicon photomultipliers; SST-2M; TARGET

Future GLAST observations of SNRs and PWNe - Funk, Stefan (First GLAST Symposium, 2007)
CRIS-Team WoS Importer:2020-01-15

Gammapy: A Python package for gamma-ray astronomy - Donath, Axel; Terrier, Régis; Remy, Quentin; Sinha, Atreyee; Nigro, Cosimo; Pintore, Fabio; Khélifi, Bruno; Olivera-Nieto, Laura; Ruiz, Jose Enrique; Brügge, Kai; Linhoff, Maximilian; Contreras, Jose Luis; et al. (Astronomy & Astrophysics, 2023)
Context. Traditionally, TeV-γ-ray astronomy has been conducted by experiments employing proprietary data and analysis software. However, the next generation of γ-ray instruments, such as the Cherenkov Telescope Array Observatory (CTAO), will be operated as open observatories. Alongside the data, they will also make the associated software tools available to a wider community. This necessity prompted the development of open, high-level, astronomical software customized for high-energy astrophysics. Aims. In this article, we present Gammapy, an open-source Python package for the analysis of astronomical γ-ray data, and illustrate the functionalities of its first long-term-support release, version 1.0. Built on the modern Python scientific ecosystem, Gammapy provides a uniform platform for reducing and modeling data from different γ-ray instruments for many analysis scenarios. Gammapy complies with several well-established data conventions in high-energy astrophysics, providing serialized data products that are interoperable with other software packages. Methods. Starting from event lists and instrument response functions, Gammapy provides functionalities to reduce these data by binning them in energy and sky coordinates. Several techniques for background estimation are implemented in the package to handle the residual hadronic background affecting γ-ray instruments. After the data are binned, the flux and morphology of one or more γ-ray sources can be estimated using Poisson maximum likelihood fitting and assuming a variety of spectral, temporal, and spatial models. Estimation of flux points, likelihood profiles, and light curves is also supported. Results. After describing the structure of the package, we show, using publicly available gamma-ray data, the capabilities of Gammapy in multiple traditional and novel γ-ray analysis scenarios, such as spectral and spectro-morphological modeling and estimations of a spectral energy distribution and a light curve. Its flexibility and its power are displayed in a final multi-instrument example, where datasets from different instruments, at different stages of data reduction, are simultaneously fitted with an astrophysical flux model.
CRIS-Team Scopus Importer:2023-11-17
Keywords: Astroparticle physics; Gamma rays: general; Methods: data analysis; Methods: statistical

GAMMA-RAY ACTIVITY IN THE CRAB NEBULA: THE EXCEPTIONAL FLARE OF 2011 APRIL - Buehler, Rolf; Scargle, J. D.; Blandford, R. D.; Baldini, Luca; Baring, M. G.; Belfiore, Andrea; Charles, E.; Chiang, J.; D'Ammando, F.; Dermer, C. D.; Funk, Stefan; Grove, J. E.; et al. (Astrophysical Journal, 2012)
The Large Area Telescope on board the Fermi satellite observed a gamma-ray flare in the Crab Nebula lasting for approximately nine days in April of 2011. The source, which at optical wavelengths has a size of approximate to 11 lt-yr across, doubled its gamma-ray flux within eight hours. The peak photon flux was (186 +/- 6) x 10(-7) cm(-2) s(-1) above 100 MeV, which corresponds to a 30-fold increase compared to the average value. During the flare, a new component emerged in the spectral energy distribution, which peaked at an energy of (375 +/- 26) MeV at flare maximum. The observations imply that the emission region was likely relativistically beamed toward us and that variations in its motion are responsible for the observed spectral variability.
CRIS-Team WoS Importer:2020-01-15

Gamma-ray blazar spectra with H.E.S.S. II mono analysis: The case of PKS 2155-304 and PG 1553+113 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Astronomy & Astrophysics, 2017)
Context. The addition of a 28 m Cherenkov telescope (CT5) to the H.E.S.S. array extended the experiment's sensitivity to lower energies. The lowest energy threshold is obtained using monoscopic analysis of data taken with CT5, providing access to gamma-ray energies below 100 GeV for small zenith angle observations. Such an extension of the instrument's energy range is particularly beneficial for studies of active galactic nuclei with soft spectra, as expected for those at a redshift ≥0.5. The high-frequency peaked BL Lac objects PKS 2155-304 (z = 0:116) and PG 1553+113 (0:43 < z < 0:58) are among the brightest objects in the gamma-ray sky, both showing clear signatures of gamma-ray absorption at E > 100 GeV interpreted as being due to interactions with the extragalactic background light (EBL). Aims. The aims of this work are twofold: to demonstrate the monoscopic analysis of CT5 data with a low energy threshold, and to obtain accurate measurements of the spectral energy distributions (SED) of PKS 2155-304 and PG 1553+113 near their SED peaks at energies 100 GeV. Methods. Multiple observational campaigns of PKS 2155-304 and PG 1553+113 were conducted during 2013 and 2014 using the full H.E.S.S. II instrument (CT1'5). A monoscopic analysis of the data taken with the new CT5 telescope was developed along with an investigation into the systematic uncertainties on the spectral parameters which are derived from this analysis. Results. Using the data from CT5, the energy spectra of PKS 2155-304 and PG 1553+113 were reconstructed down to conservative threshold energies of 80 GeV for PKS 2155-304, which transits near zenith, and 110 GeV for the more northern PG 1553+113. The measured spectra, well fitted in both cases by a log-parabola spectral model (with a 5.0φ statistical preference for non-zero curvature for PKS 2155-304 and 4.5φ for PG 1553+113), were found consistent with spectra derived from contemporaneous Fermi-LAT data, indicating a sharp break in the observed spectra of both sources at E 100 GeV. When corrected for EBL absorption, the intrinsic H.E.S.S. II mono and Fermi-LAT spectrum of PKS 2155-304 was found to show significant curvature. For PG 1553+113, however, no significant detection of curvature in the intrinsic spectrum could be found within statistical and systematic uncertainties.
Keywords: BL Lacertae objects: individual: PG 1553+113; BL Lacertae objects: individual: PKS 2155-304; Galaxies: active; Gamma rays: galaxies

Gamma-Ray Blazars within the First 2 Billion Years - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal Letters, 2017)
The detection of high-redshift (z > 3) blazars enables the study of the evolution of the most luminous relativistic jets over cosmic time. More importantly, high-redshift blazars tend to host massive black holes and can be used to constrain the space density of heavy black holes in the early universe. Here, we report the first detection with the Fermi-Large Area Telescope of five gamma-ray-emitting blazars beyond z. =. 3.1, more distant than any blazars previously detected in.-rays gamma Among these five objects, NVSS J151002+570243 is now the most distant known gamma-ray-emitting blazar at z =. 4.31. These objects have steeply falling gamma-ray spectral energy distributions (SEDs), and. those that have been observed in X-rays have a very hard X-ray spectrum, both typical of powerful blazars. Their Compton dominance ( ratio of the inverse Compton to synchrotron peak luminosities) is also very large (>20). All of these properties place these objects among the most extreme members of the blazar population. Their optical spectra and the modeling of their optical-UV SEDs confirm that these objects harbor massive black holes (MBH similar to 10(8-10) M circle dot 8 10). We find that, at z approximate to 4, the space density of >10(9)M circle dot black holes hosted in radio-loud and radio-quiet active galactic nuclei are similar, implying that radio-loudness may play a key role in rapid black hole growth in the early universe.
CRIS-Team WoS Importer:2020-01-15

GAMMA-RAY EMISSION FROM CRUSHED CLOUDS IN SUPERNOVA REMNANTS - Uchiyama, Yasunobu; Blandford, Roger D.; Funk, Stefan; Tajima, Hiroyasu; Tanaka, Takaaki (Astrophysical Journal Letters, 2010)
It is shown that the radio and gamma-ray emission observed from newly found "GeV-bright" supernova remnants (SNRs) can be explained by a model in which a shocked cloud and shock-accelerated cosmic rays (CRs) frozen in it are simultaneously compressed by the supernova blast wave as a result of formation of a radiative cloud shock. Simple reacceleration of pre-existing CRs is generally sufficient to power the observed gamma-ray emission through the decays of pi(0)-mesons produced in hadronic interactions between high-energy protons (nuclei) and gas in the compressed-cloud layer. This model provides a natural account of the observed synchrotron radiation in SNRs W51C, W44, and IC 443 with flat radio spectral index, which can be ascribed to a combination of secondary and reaccelerated electrons and positrons.
CRIS-Team WoS Importer:2020-01-15

Gamma-Ray Emission from the Shell of Supernova Remnant W44 Revealed by the Fermi LAT - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Science, 2010)
Recent observations of supernova remnants (SNRs) hint that they accelerate cosmic rays to energies close to similar to 10(15) electron volts. However, the nature of the particles that produce the emission remains ambiguous. We report observations of SNR W44 with the Fermi Large Area Telescope at energies between 2 x 10(8) electron volts and 3 x 10(11) electron volts. The detection of a source with a morphology corresponding to the SNR shell implies that the emission is produced by particles accelerated there. The gamma-ray spectrum is well modeled with emission from protons and nuclei. Its steepening above similar to 10(9) electron volts provides a probe with which to study how particle acceleration responds to environmental effects such as shock propagation in dense clouds and how accelerated particles are released into interstellar space.
CRIS-Team WoS Importer:2020-01-15

Gamma-Ray Flares from the Crab Nebula - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Science, 2011)
A young and energetic pulsar powers the well-known Crab Nebula. Here, we describe two separate gamma-ray (photon energy greater than 100 mega-electron volts) flares from this source detected by the Large Area Telescope on board the Fermi Gamma-ray Space Telescope. The first flare occurred in February 2009 and lasted approximately 16 days. The second flare was detected in September 2010 and lasted approximately 4 days. During these outbursts, the gamma-ray flux from the nebula increased by factors of four and six, respectively. The brevity of the flares implies that the gamma rays were emitted via synchrotron radiation from peta-electron-volt (10(15) electron volts) electrons in a region smaller than 1.4 x 10(-2) parsecs. These are the highest-energy particles that can be associated with a discrete astronomical source, and they pose challenges to particle acceleration theory.
CRIS-Team WoS Importer:2020-01-15

GAMMA-RAY LIGHT CURVES AND VARIABILITY OF BRIGHT FERMI-DETECTED BLAZARS - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Antolini, E.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
This paper presents light curves as well as the first systematic characterization of variability of the 106 objects in the high-confidence Fermi Large Area Telescope Bright AGN Sample (LBAS). Weekly light curves of this sample, obtained during the first 11 months of the Fermi survey (2008 August 4-2009 July 4), are tested for variability and their properties are quantified through autocorrelation function and structure function analysis. For the brightest sources, 3 or 4 day binned light curves are extracted in order to determine power density spectra (PDSs) and to fit the temporal structure of major flares. More than 50% of the sources are found to be variable with high significance, where high states do not exceed 1/4 of the total observation range. Variation amplitudes are larger for flat spectrum radio quasars and low/intermediate synchrotron frequency peaked BL Lac objects. Autocorrelation timescales derived from weekly light curves vary from four to a dozen of weeks. Variable sources of the sample have weekly and 3-4 day bin light curves that can be described by 1/f(alpha) PDS, and show two kinds of gamma-ray variability: (1) rather constant baseline with sporadic flaring activity characterized by flatter PDS slopes resembling flickering and red noise with occasional intermittence and (2)-measured for a few blazars showing strong activity-complex and structured temporal profiles characterized by long-term memory and steeper PDS slopes, reflecting a random walk underlying mechanism. The average slope of the PDS of the brightest 22 FSRQs and of the 6 brightest BL Lacs is 1.5 and 1.7, respectively. The study of temporal profiles of well-resolved flares observed in the 10 brightest LBAS sources shows that they generally have symmetric profiles and that their total duration vary between 10 and 100 days. Results presented here can assist in source class recognition for unidentified sources and can serve as reference for more detailed analysis of the brightest gamma-ray blazars.
CRIS-Team WoS Importer:2020-01-15

GAMMA-RAY OBSERVATIONS OF THE SUPERNOVA REMNANT RX J0852.0-4622 WITH THE FERMI LARGE AREA TELESCOPE - Tanaka, T.; Allafort, A.; Ballet, J.; Funk, Stefan; Giordano, Francesco; Hewitt, J.; Lemoine-Goumard, M.; Tajima, H.; Tibolla, O.; Uchiyama, Y. (Astrophysical Journal Letters, 2011)
We report on gamma-ray observations of the supernova remnant (SNR) RX J0852.0-4622 with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope. In the Fermi-LAT data, we find a spatially extended source at the location of the SNR. The extension is consistent with the SNR size seen in other wavelengths such as X-rays and TeV gamma rays, leading to the identification of the gamma-ray source with the SNR. The spectrum is well described as a power law with a photon index of Gamma = 1.85 +/- 0.06 (stat)(-0.19)(+0.18) (sys), which smoothly connects to the H. E. S. S. spectrum in the TeV energy band. We discuss the gamma-ray emission mechanism based on multiwavelength data. The broadband data can be fit well by a model in which the gamma rays are of hadronic origin. We also consider a scenario with inverse Compton scattering of electrons as the emission mechanism of the gamma rays. Although the leptonic model predicts a harder spectrum in the Fermi-LAT energy range, the model can fit the data considering the statistical and systematic errors.
CRIS-Team WoS Importer:2020-01-15

Gamma Rays from Fast Black-hole Winds - Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; Bonino, R.; Bruel, P.; et al. (Astrophysical Journal, 2021)
Massive black holes at the centers of galaxies can launch powerful wide-angle winds that, if sustained over time, can unbind the gas from the stellar bulges of galaxies. These winds may be responsible for the observed scaling relation between the masses of the central black holes and the velocity dispersion of stars in galactic bulges. Propagating through the galaxy, the wind should interact with the interstellar medium creating a strong shock, similar to those observed in supernovae explosions, which is able to accelerate charged particles to high energies. In this work we use data from the Fermi Large Area Telescope to search for the gamma-ray emission from galaxies with an ultrafast outflow (UFO): a fast (v similar to 0.1 c), highly ionized outflow, detected in absorption at hard X-rays in several nearby active galactic nuclei (AGN). Adopting a sensitive stacking analysis we are able to detect the average gamma-ray emission from these galaxies and exclude that it is due to processes other than UFOs. Moreover, our analysis shows that the gamma-ray luminosity scales with the AGN bolometric luminosity and that these outflows transfer similar to 0.04% of their mechanical power to gamma-rays. Interpreting the observed gamma-ray emission as produced by cosmic rays (CRs) accelerated at the shock front, we find that the gamma-ray emission may attest to the onset of the wind-host interaction and that these outflows can energize charged particles up to the transition region between galactic and extragalactic CRs.
CRIS-Team WoS Importer:2021-11-26

GeV GAMMA-RAY FLUX UPPER LIMITS FROM CLUSTERS OF GALAXIES - Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Blasi, Pasquale; Bloom, E. D.; et al. (Astrophysical Journal Letters, 2010)
The detection of diffuse radio emission associated with clusters of galaxies indicates populations of relativistic leptons infusing the intracluster medium (ICM). Those electrons and positrons are either injected into and accelerated directly in the ICM, or produced as secondary pairs by cosmic-ray ions scattering on ambient protons. Radiation mechanisms involving the energetic leptons together with the decay of neutral pions produced by hadronic interactions have the potential to produce abundant GeV photons. Here, we report on the search for GeV emission from clusters of galaxies using data collected by the Large Area Telescope on the Fermi Gamma-ray Space Telescope from 2008 August to 2010 February. Thirty-three galaxy clusters have been selected according to their proximity and high mass, X-ray flux and temperature, and indications of non-thermal activity for this study. We report upper limits on the photon flux in the range 0.2-100 GeV toward a sample of observed clusters (typical values (1-5) x 10(-9) photon cm(-2) s(-1)) considering both point-like and spatially resolved models for the high-energy emission and discuss how these results constrain the characteristics of energetic leptons and hadrons, and magnetic fields in the ICM. The volume-averaged relativistic-hadron-to-thermal energy density ratio is found to be <5%-10% in several clusters.
CRIS-Team WoS Importer:2020-01-15

GeV gamma-Rays and the Origin of Cosmic Rays - Funk, Stefan (CENTENARY SYMPOSIUM 2012: DISCOVERY OF COSMIC RAYS, 2013)
CRIS-Team WoS Importer:2020-01-15

GeV OBSERVATIONS OF STAR-FORMING GALAXIES WITH THE FERMI LARGE AREA TELESCOPE - Ackermann, Markus; Ajello, Marco; Allafort, A.; Baldini, Luca; Ballet, J.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2012)
Recent detections of the starburst galaxies M82 and NGC 253 by gamma-ray telescopes suggest that galaxies rapidly forming massive stars are more luminous at gamma-ray energies compared to their quiescent relatives. Building upon those results, we examine a sample of 69 dwarf, spiral, and luminous and ultraluminous infrared galaxies at photon energies 0.1-100 GeV using 3 years of data collected by the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope (Fermi). Measured fluxes from significantly detected sources and flux upper limits for the remaining galaxies are used to explore the physics of cosmic rays in galaxies. We find further evidence for quasi-linear scaling relations between gamma-ray luminosity and both radio continuum luminosity and total infrared luminosity which apply both to quiescent galaxies of the Local Group and low-redshift starburst galaxies (conservative P-values less than or similar to 0.05 accounting for statistical and systematic uncertainties). The normalizations of these scaling relations correspond to luminosity ratios of log(L0.1-100GeV/L-1.4GHz) = 1.7 +/- 0.1((statistical)) +/- 0.2((dispersion)) and log(L0.1-100GeV/L8-1000 (mu m)) = -4.3 +/- 0.1((statistical)) +/- 0.2((dispersion)) for a galaxy with a star formation rate of 1 M-circle dot yr(-1), assuming a Chabrier initial mass function. Using the relationship between infrared luminosity and gamma-ray luminosity, the collective intensity of unresolved star-forming galaxies at redshifts 0 < z < 2.5 above 0.1 GeV is estimated to be 0.4-2.4 x 10(-6) ph cm(-2) s(-1) sr(-1) (4%-23% of the intensity of the isotropic diffuse component measured with the LAT). We anticipate that similar to 10 galaxies could be detected by their cosmic-ray-induced gamma-ray emission during a 10 year Fermi mission.
CRIS-Team WoS Importer:2020-01-15

Giant gamma-ray bubbles in the Milky Way - Franckowiak, Anna; Funk, Stefan (Physics Today, 2014)

GLAST and ground-based gamma-ray astronomy - Funk, Stefan; et al. (First GLAST Symposium, 2007)
CRIS-Team WoS Importer:2020-01-15

Ground- and Space-Based Gamma-Ray Astronomy - Funk, Stefan (Annual Review of Nuclear and Particle Science, 2015)
Keywords: Cosmic rays; Dark matter; Fermi-LAT; Galactic center; Imaging atmospheric Cherenkov telescopes; γ-ray astronomy

HESS and Fermi-LAT observations of PSR B1259-63/LS 2883 during its 2014 and 2017 periastron passages - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. PSR B1259-63/LS 2883 is a gamma-ray binary system consisting of a pulsar in an eccentric orbit around a bright Oe stellar-type companion star that features a dense circumstellar disc. The bright broad-band emission observed at phases close to periastron offers a unique opportunity to study particle acceleration and radiation processes in binary systems. Observations at gamma-ray energies constrain these processes through variability and spectral characterisation studies.
CRIS-Team WoS Importer:2020-01-31
Keywords: Pulsars: general; Radiation mechanisms: non-thermal; Shock waves; γ-rays: general; Binaries: general; Astroparticle physics

HESS and Suzaku observations of the Vela X pulsar wind nebula - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Berge, D.; Bernloehr, K.; et al. (Astronomy & Astrophysics, 2019)
Context. Pulsar wind nebulae (PWNe) represent the most prominent population of Galactic very-high-energy gamma-ray sources and are thought to be an efficient source of leptonic cosmic rays. Vela X is a nearby middle-aged PWN, which shows bright X-ray and TeV gamma-ray emission towards an elongated structure called the cocoon.
CRIS-Team WoS Importer:2019-07-23
Keywords: Gamma rays: stars; Pulsars: individual: PSR B0833-45; Radiation mechanisms: non-thermal; Stars: winds; outflows; Acceleration of particles

HESS detection of very high-energy gamma-ray emission from the quasar PKS 0736+017 - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, M.; Martins, V. Barbosa; Barnard, M.; et al. (Astronomy & Astrophysics, 2020)
Context. Flat-spectrum radio-quasars (FSRQs) are rarely detected at very high energies (E& x2004;>=& x2004;100 GeV) due to their low-frequency-peaked spectral energy distributions. At present, only six FSRQs are known to emit very high-energy (VHE) photons, representing only 7% of the VHE extragalactic catalog, which is largely dominated by high-frequency-peaked BL Lacertae objects. Aims. Following the detection of MeV-GeV gamma-ray flaring activity from the FSRQ PKS 0736+017 (z& x2004;=& x2004;0.189) with Fermi-LAT, the H.E.S.S. array of Cherenkov telescopes triggered target-of-opportunity (ToO) observations on February 18, 2015, with the goal of studying the gamma-ray emission in the VHE band. Methods. H.E.S.S. ToO observations were carried out during the nights of February 18, 19, 21, and 24, 2015. Together with Fermi-LAT, the multi-wavelength coverage of the flare includes Swift observations in soft X-ray and optical-UV bands, and optical monitoring (photometry and spectro-polarimetry) by the Steward Observatory, and the ATOM, the KAIT, and the ASAS-SN telescopes. Results. VHE emission from PKS 0736+017 was detected with H.E.S.S. only during the night of February 19, 2015. Fermi-LAT data indicate the presence of a gamma-ray flare, peaking at the time of the H.E.S.S. detection, with a flux doubling timescale of around six hours. The gamma-ray flare was accompanied by at least a 1 mag brightening of the non-thermal optical continuum. No simultaneous observations at longer wavelengths are available for the night of the H.E.S.S. detection. The gamma-ray observations with H.E.S.S. and Fermi-LAT are used to put constraints on the location of the gamma-ray emitting region during the flare: it is constrained to be just outside the radius of the broad-line region r(BLR) with a bulk Lorentz factor Gamma& x2004;similar or equal to& x2004;20, or at the level of the radius of the dusty torus r(torus) with Gamma& x2004;similar or equal to& x2004;60. Conclusions. PKS 0736+017 is the seventh FSRQ known to emit VHE photons, and at z& x2004;=& x2004;0.189 is the nearest so far. The location of the gamma-ray emitting region during the flare can be tightly constrained thanks to opacity, variability, and collimation arguments.
CRIS-Team WoS Importer:2020-02-18
Keywords: Astroparticle physics; Gamma rays: general; Quasars: individual: PKS 0736+017; Relativistic processes

HESS discovery of very high energy gamma-ray emission from PKS 0625-354 - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguner, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Monthly Notices of the Royal Astronomical Society, 2018)
PKS 0625-354 (z = 0.055) was observed with the four High Energy Stereoscopic System (H.E.S.S.) telescopes in 2012 during 5.5 h. The source was detected above an energy threshold of 200 GeV at a significance level of 6.1 sigma. No significant variability is found in these observations. The source is well described with a power-law spectrum with photon index Gamma = 2.84 +/- 0.50(stat) +/- 0.10(syst) and normalization (at E-0 = 1.0 TeV) N-0(E-0)=(0.58 +/- 0.22(stat) +/- 0.12(syst)) x 10(-12) TeV-1 cm(-2) s(-1). Multiwavelength data collected with Fermi-LAT, Swift-XRT, Swift-UVOT, ATOM and WISE are also analysed. Significant variability is observed only in the Fermi-LAT gamma-ray and Swift-XRT X-ray energy bands. Having a good multiwavelength coverage from radio to very high energy, we performed a broad-band modelling from two types of emission scenarios. The results from a one zone lepto-hadronic and a multizone leptonic models are compared and discussed. On the grounds of energetics, our analysis favours a leptonic multizone model. Models associated to the X-ray variability constraint support previous results, suggesting a BL Lac nature of PKS 0625-354 with, however, a large-scale jet structure typical of a radio galaxy.
Keywords: radiation mechanisms: non-thermal; galaxies: active; galaxies: individual: PKS 0625-354; galaxies: jets; gamma-rays: galaxies

HESS Follow-up Observations of Binary Black Hole Coalescence Events during the Second and Third Gravitational-wave Observing Runs of Advanced LIGO and Advanced Virgo - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Ashkar, H.; Backes, M.; Baghmanyan,; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernlohr, K.; et al. (Astrophysical Journal, 2021)
We report on the observations of four well-localized binary black hole (BBH) mergers by the High Energy Stereoscopic System (H.E.S.S.) during the second and third observing runs of Advanced LIGO and Advanced Virgo, O2 and O3. H.E.S.S. can observe 20 deg(2) of the sky at a time and follows up gravitational-wave (GW) events by "tiling" localization regions to maximize the covered localization probability. During O2 and O3, H.E.S.S. observed large portions of the localization regions, between 35% and 75%, for four BBH mergers (GW170814, GW190512_180714, GW190728_064510, and S200224ca). For these four GW events, we find no significant signal from a pointlike source in any of the observations, and we set upper limits on the very high energy (>100 GeV) gamma-ray emission. The 1-10 TeV isotropic luminosity of these GW events is below 10(45) erg s(-1) at the times of the H.E.S.S. observations, around the level of the low-luminosity GRB 190829A. Assuming no changes are made to how follow-up observations are conducted, H.E.S.S. can expect to observe over 60 GW events per year in the fourth GW observing run, O4, of which eight would be observable with minimal latency.
CRIS-Team WoS Importer:2021-12-24

HESS J0632+057: A NEW GAMMA-RAY BINARY? - Hinton, J. A.; Skilton, J. L.; Funk, Stefan; Brucker, Julia; Aharonian, F. A.; Dubus, Guillaume; Fiasson, A.; Gallant, Y.; Hofmann, W.; Marcowith, A.; Reimer, Olaf (Astrophysical Journal Letters, 2009)
The High Energy Stereoscopic System (HESS) survey of the Galactic plane has established the existence of a substantial number (similar to 40) of Galactic TeV gamma-ray sources, a large fraction of which remain unidentified. HESS J0632+057 is one of a small fraction of these objects, which is point-like in nature (< 2' rms), and is one of only two point-like sources that remain unidentified. Follow-up observations of this object with XMM-Newton have revealed an X-ray source coincident with the TeV source and with the massive star MWC 148, of the spectral type B0pe. This source exhibits a hard spectrum, consistent with an absorbed power law with Gamma = 1.26 +/- 0.04, and shows significant variability on hour timescales. We discuss this spatial coincidence and the implied spectral energy distribution of this object and argue that it is likely a new gamma-ray binary system with a close resemblance to the three known members of this class and, in particular, to LS I+61 303. Further, X-ray, radio, and optical observations of this system are needed to firmly establish HESS J0632+057 as a new member of this rare class of Galactic objects.
CRIS-Team WoS Importer:2020-01-15

HESS J1741-302: a hidden accelerator in the Galactic plane - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
The H.E.S.S. Collaboration has discovered a new very high energy (VHE, E > 0.1 TeV) gamma-ray source, HESS J1741-302, located in the Galactic plane. Despite several attempts to constrain its nature, no plausible counterpart has been found so far at X-ray and MeV/GeV gamma-ray energies, and the source remains unidentified. An analysis of 145-h of observations of HESS J1741-302 at VHEs has revealed a steady and relatively weak TeV source (similar to 1% of the Crab Nebula flux), with a spectral index of Gamma = 2.3 +/- 0.2(stat) +/- 0.2(sys), extending to energies up to 10 TeV without any clear signature of a cut-off. In a hadronic scenario, such a spectrum implies an object with particle acceleration up to energies of several hundred TeV. Contrary to most H.E.S.S. unidentified sources, the angular size of HESS J1741-302 is compatible with the H.E.S.S. point spread function at VHEs, with an extension constrained to be below 0.068 degrees at a 99% confidence level. The gamma-ray emission detected by H.E.S.S. can be explained both within a hadronic scenario, due to collisions of protons with energies of hundreds of TeV with dense molecular clouds, and in a leptonic scenario, as a relic pulsar wind nebula, possibly powered by the middle-aged (20 kyr) pulsar PSR B1737-30. A binary scenario, related to the compact radio source 1LC 358.266+0.038 found to be spatially coincident with the best fit position of HESS J1741-302, is also envisaged.
Keywords: gamma rays: ISM; gamma rays: general; cosmic rays; ISM: clouds

HESS J1825-137: A pulsar wind nebula associated with PSR B1823-13? - Funk, Stefan; et al. (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

H.E.S.S. Limits on Linelike Dark Matter Signatures in the 100 GeV to 2 TeV Energy Range Close to the Galactic Center - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; et al. (Physical Review Letters, 2016)
A search for dark matter linelike signals iss performed in the vicinity of the Galactic Center by the H.E.S.S. experiment on observational data taken in 2014. An unbinned likelihood analysis iss developed to improve the sensitivity to linelike signals. The upgraded analysis along with newer data extend the energy coverage of the previous measurement down to 100 GeV. The 18 h of data collected with the H.E.S.S. array allow one to rule out at 95% C.L. the presence of a 130 GeV line (at l=-1.5°, b=0° and for a dark matter profile centered at this location) previously reported in Fermi-LAT data. This new analysis overlaps significantly in energy with previous Fermi-LAT and H.E.S.S. results. No significant excess associated with dark matter annihilations was found in the energy range of 100 GeV to 2 TeV and upper limits on the gamma-ray flux and the velocity weighted annihilation cross section are derived adopting an Einasto dark matter halo profile. Expected limits for present and future large statistics H.E.S.S. observations are also given.

HESS observations of PKS 2155-304 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The high-frequency peaked BL Lac PKS 2155-304 at redshift z=0.117 has been detected with high significance (similar to45sigma) at energies greater than 160 GeV, using the H.E.S.S. stereoscopic array of imaging air-Cherenkov telescopes in Namibia. A strong signal is found in each of the data sets corresponding to the dark periods of July and October, 2002, and June-September, 2003. The observed flux of VHE gamma rays shows variability on time scales of months, days, and hours. The monthly-averaged integral flux above 300 GeV varies between 10% and 60% of the flux observed from the Crab Nebula. Energy spectra are measured for these individual periods of data taking and are characterized by a steep power law with a time-averaged photon index of Gamma=3.32+/-0.06. An improved chi(2) per degree of freedom is found when either a power law with an exponential cutoff energy or a broken power law are fit to the time-averaged energy spectrum. However, the significance of the improvement is marginal (similar to2sigma). The suggested presence of features in the energy spectrum may be intrinsic to the emission from the blazar, or an indication of absorption of TeV gamma rays by the extragalactic infrared background light.
CRIS-Team WoS Importer:2020-01-15

HESS observations of RX J1713.7-3946 with improved angular and spectral resolution: Evidence for gamma-ray emission extending beyond the X-ray emitting shell - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, E. O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
Supernova remnants exhibit shock fronts (shells) that can accelerate charged particles up to very high energies. In the past decade, measurements of a handful of shell-type supernova remnants in very high-energy gamma rays have provided unique insights into the acceleration process. Among those objects, RX J1713.7-3946 (also known as G347.3-0.5) has the largest surface brightness, allowing us in the past to perform the most comprehensive study of morphology and spatially resolved spectra of any such very high-energy gamma-ray source. Here we present extensive new H.E.S.S. measurements of RX J1713.7-3946, almost doubling the observation time compared to our previous publication. Combined with new improved analysis tools, the previous sensitivity is more than doubled. The H.E.S.S. angular resolution of 0.048 degrees (0.036 degrees above 2 TeV) is unprecedented in gamma-ray astronomy and probes physical scales of 0.8 (0.6) parsec at the remnant's location. The new H. E. S. S. image of RX J1713.7-3946 allows us to reveal clear morphological di ff erences between X-rays and gamma rays. In particular, for the outer edge of the brightest shell region, we find the first ever indication for particles in the process of leaving the acceleration shock region. By studying the broadband energy spectrum, we furthermore extract properties of the parent particle populations, providing new input to the discussion of the leptonic or hadronic nature of the gamma-ray emission mechanism.
CRIS-Team WoS Importer:2020-01-15
Keywords: ISM: Supernova remnants; cosmic rays; gamma rays: General; Acceleration of particles; astroparticle physic

HESS observations of the flaring gravitationally lensed galaxy PKS 1830-211 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
PKS 1830-211 is a known macrolensed quasar located at a redshift of z = 2.5. Its highenergy gamma-ray emission has been detected with the Fermi-Large Area Telescope (LAT) instrument and evidence for lensing was obtained by several authors from its high-energy data. Observations of PKS 1830-211 were taken with the High Energy Stereoscopic System (H.E.S.S.) array of Imaging Atmospheric Cherenkov Telescopes in 2014 August, following a flare alert by the Fermi-LAT Collaboration. The H.E.S.S observations were aimed at detecting a gamma-ray flare delayed by 20-27 d from the alert flare, as expected from observations at other wavelengths. More than 12 h of good-quality data were taken with an analysis threshold of similar to 67 GeV. The significance of a potential signal is computed as a function of the date and the average significance over the whole period. Data are compared to simultaneous observations by Fermi-LAT. No photon excess or significant signal is detected. An upper limit on PKS 1830-211 flux above 67 GeV is computed and compared to the extrapolation of the Fermi-LAT flare spectrum.
CRIS-Team WoS Importer:2019-07-26
Keywords: gamma-rays: galaxies; gravitational lensing: strong; diffuse radiation

High-energy emission from a magnetar giant flare in the Sculptor galaxy - Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bonino, R.; et al. (Nature Astronomy, 2021)
Magnetars are the most highly magnetized neutron stars in the cosmos (with magnetic field 10(13)-10(15) G). Giant flares from magnetars are rare, short-duration (about 0.1 s) bursts of hard X-rays and soft gamma rays(1,2). Owing to the limited sensitivity and energy coverage of previous telescopes, no magnetar giant flare has been detected at gigaelectronvolt (GeV) energies. Here, we report the discovery of GeV emission from a magnetar giant flare on 15 April 2020 (refs. (3,4) and A. J. Castro-Tirado et al., manuscript in preparation). The Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope detected GeV gamma rays from 19 s until 284 s after the initial detection of a signal in the megaelectronvolt (MeV) band. Our analysis shows that these gamma rays are spatially associated with the nearby (3.5 megaparsecs) Sculptor galaxy and are unlikely to originate from a cosmological gamma-ray burst. Thus, we infer that the gamma rays originated with the magnetar giant flare in Sculptor. We suggest that the GeV signal is generated by an ultra-relativistic outflow that first radiates the prompt MeV-band photons, and then deposits its energy far from the stellar magnetosphere. After a propagation delay, the outflow interacts with environmental gas and produces shock waves that accelerate electrons to very high energies; these electrons then emit GeV gamma rays as optically thin synchrotron radiation. This observation implies that a relativistic outflow is associated with the magnetar giant flare, and suggests the possibility that magnetars can power some short gamma-ray bursts.
CRIS-Team WoS Importer:2021-01-29

HIGH-ENERGY GAMMA-RAY EMISSION FROM SOLAR FLARES: SUMMARY OF FERMI LARGE AREA TELESCOPE DETECTIONS AND ANALYSIS OF TWO M-CLASS FLARES - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Bonamente, E.; Bottacini, E.; et al. (Astrophysical Journal, 2014)
We present the detections of 18 solar flares detected in high-energy gamma-rays (above 100 MeV) with the Fermi Large Area Telescope (LAT) during its first 4 yr of operation. This work suggests that particle acceleration up to very high energies in solar flares is more common than previously thought, occurring even in modest flares, and for longer durations. Interestingly, all these flares are associated with fairly fast coronal mass ejections (CMEs). We then describe the detailed temporal, spatial, and spectral characteristics of the first two long-lasting events: the 2011 March 7 flare, a moderate (M3.7) impulsive flare followed by slowly varying gamma-ray emission over 13 hr, and the 2011 June 7 M2.5 flare, which was followed by gamma-ray emission lasting for 2 hr. We compare the Fermi LAT data with X-ray and proton data measurements from GOES and RHESSI. We argue that the gamma-rays are more likely produced through pion decay than electron bremsstrahlung, and we find that the energy spectrum of the proton distribution softens during the extended emission of the 2011 March 7 flare. This would disfavor a trapping scenario for particles accelerated during the impulsive phase of the flare and point to a continuous acceleration process at play for the duration of the flares. CME shocks are known for accelerating the solar energetic particles (SEPs) observed in situ on similar timescales, but it might be challenging to explain the production of gamma-rays at the surface of the Sun while the CME is halfway to the Earth. A stochastic turbulence acceleration process occurring in the solar corona is another likely scenario. Detailed comparison of characteristics of SEPs and gamma-ray-emitting particles for several flares will be helpful to distinguish between these two possibilities.
Keywords: Sun: flares; Sun: X-rays; gamma rays

High-energy particle acceleration in the shell of a supernova remnant - Funk, Stefan; et al. (Nature, 2004)
A significant fraction of the energy density of the interstellar medium is in the form of high-energy charged particles ( cosmic rays)(1). The origin of these particles remains uncertain. Although it is generally accepted that the only sources capable of supplying the energy required to accelerate the bulk of Galactic cosmic rays are supernova explosions, and even though the mechanism of particle acceleration in expanding supernova remnant (SNR) shocks is thought to be well understood theoretically(2,3), unequivocal evidence for the production of high-energy particles in supernova shells has proven remarkably hard to find. Here we report on observations of the SNR RX J1713.7 - 3946 ( G347.3 - 0.5), which was discovered by ROSAT(4) in the X-ray spectrum and later claimed as a source of high-energy gamma-rays(5,6) of TeV energies (1 TeV = 10(12) eV). We present a TeV gamma-ray image of the SNR: the spatially resolved remnant has a shell morphology similar to that seen in X-rays, which demonstrates that very-high-energy particles are accelerated there. The energy spectrum indicates efficient acceleration of charged particles to energies beyond 100 TeV, consistent with current ideas of particle acceleration in young SNR shocks.
CRIS-Team WoS Importer:2020-01-15

Hitomi (ASTRO-H) X-ray Astronomy Satellite - Takahashi, Tadayuki; Kokubun, Motohide; Mitsuda, Kazuhisa; Kelley, Richard L.; Ohashi, Takaya; Aharonian, Felix; Akamatsu, Hiroki; Akimoto, Fumie; Allen, Steven W.; Anabuki, Naohisa; Angelini, Lorella; Arnaud, Keith; et al. (Journal of Astronomical Telescopes, Instruments, and Systems, 2018)
The Hitomi (ASTRO-H) mission is the sixth Japanese x-ray astronomy satellite developed by a large international collaboration, including Japan, USA, Canada, and Europe. The mission aimed to provide the highest energy resolution ever achieved at E > 2 keV, using a microcalorimeter instrument, and to cover a wide energy range spanning four decades in energy from soft x-rays to gamma rays. After a successful launch on February 17, 2016, the spacecraft lost its function on March 26, 2016, but the commissioning phase for about a month provided valuable information on the onboard instruments and the spacecraft system, including astrophysical results obtained from first light observations. The paper describes the Hitomi (ASTRO-H) mission, its capabilities, the initial operation, and the instruments/spacecraft performances confirmed during the commissioning operations for about a month. (C) The Authors. Published by SPIE under a Creative Commons Attribution 3.0 Unported License.
CRIS-Team WoS Importer:2020-01-15

Inauguration and First Light of the GCT-M Prototype for the Cherenkov Telescope Array - Watson, J. J.; De Franco, A.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, D.; Boisson, C.; Bousquet, J. -J.; Brown, A. M.; Bryan, M.; et al. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2017)
CRIS-Team WoS Importer:2020-01-15

Incremental Fermi Large Area Telescope Fourth Source Catalog - Abdollahi, S.; Acero, F.; Baldini, L.; Ballet, J.; Bastieri, D.; Bellazzini, R.; Berenji, B.; Berretta, A.; Bissaldi, E.; Blandford, R. D.; Bloom, E.; Bonino, R.; et al. (Astrophysical Journal Supplement Series, 2022)
We present an incremental version (4FGL-DR3, for Data Release 3) of the fourth Fermi Large Area Telescope (LAT) catalog of gamma-ray sources. Based on the first 12 years of science data in the energy range from 50 MeV to 1 TeV, it contains 6658 sources. The analysis improves on that used for the 4FGL catalog over eight years of data: more sources are fit with curved spectra, we introduce a more robust spectral parameterization for pulsars, and we extend the spectral points to 1 TeV. The spectral parameters, spectral energy distributions, and associations are updated for all sources. Light curves are rebuilt for all sources with 1 yr intervals (not 2 month intervals). Among the 5064 original 4FGL sources, 16 were deleted, 112 are formally below the detection threshold over 12 yr (but are kept in the list), while 74 are newly associated, 10 have an improved association, and seven associations were withdrawn. Pulsars are split explicitly between young and millisecond pulsars. Pulsars and binaries newly detected in LAT sources, as well as more than 100 newly classified blazars, are reported. We add three extended sources and 1607 new point sources, mostly just above the detection threshold, among which eight are considered identified, and 699 have a plausible counterpart at other wavelengths. We discuss the degree-scale residuals to the global sky model and clusters of soft unassociated point sources close to the Galactic plane, which are possibly related to limitations of the interstellar emission model and missing extended sources.
CRIS-Team WoS Importer:2022-07-15

Indirect detection of dark matter with gamma rays - Funk, Stefan (Proceedings of the National Academy of Sciences of the United States of America, 2015)
The details of what constitutes the majority of the mass that makes up dark matter in the Universe remains one of the prime puzzles of cosmology and particle physics today-80 y after the first observational indications. Today, it is widely accepted that dark matter exists and that it is very likely composed of elementary particles, which are weakly interacting and massive [weakly interacting massive particles (WIMPs)]. As important as dark matter is in our understanding of cosmology, the detection of these particles has thus far been elusive. Their primary properties such as mass and interaction cross sections are still unknown. Indirect detection searches for the products of WIMP annihilation or decay. This is generally done through observations of.-ray photons or cosmic rays. Instruments such as the Fermi large-area telescope, high-energy stereoscopic system, major atmospheric gamma-ray imaging Cherenkov, and very energetic radiation imaging telescope array, combined with the future Cherenkov telescope array, will provide important complementarity to other search techniques. Given the expected sensitivities of all search techniques, we are at a stage where the WIMP scenario is facing stringent tests, and it can be expected that WIMPs will be either be detected or the scenario will be so severely constrained that it will have to be rethought. In this sense, we are on the threshold of discovery. In this article, I will give a general overview of the current status and future expectations for indirect searches of dark matter (WIMP) particles.
CRIS-Team WoS Importer:2020-01-15

Inferred Cosmic-Ray Spectrum from Fermi Large Area Telescope gamma-Ray Observations of Earth's Limb - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; et al. (Physical Review Letters, 2014)
Recent accurate measurements of cosmic-ray (CR) species by ATIC-2, CREAM, and PAMELA reveal an unexpected hardening in the proton and He spectra above a few hundred GeV, a gradual softening of the spectra just below a few hundred GeV, and a harder spectrum of He compared to that of protons. These newly discovered features may offer a clue to the origin of high-energy CRs. We use the Fermi Large Area Telescope observations of the gamma-ray emission from Earth's limb for an indirect measurement of the local spectrum of CR protons in the energy range similar to 90 GeV-6 TeV (derived from a photon energy range 15 GeV-1 TeV). Our analysis shows that single power law and broken power law spectra fit the data equally well and yield a proton spectrum with index 2.68 +/- 0.04 and 2.61 +/- 0.08 above similar to 200 GeV, respectively.

In-flight measurement of the absolute energy scale of the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Allafort, A.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; et al. (Astroparticle Physics, 2012)
The Large Area Telescope (LAT) on-board the Fermi Gamma-ray Space Telescope is a pair-conversion telescope designed to survey the gamma-ray sky from 20 MeV to several hundreds of GeV. In this energy band there are no astronomical sources with sufficiently well known and sharp spectral features to allow an absolute calibration of the LAT energy scale. However, the geomagnetic cutoff in the cosmic ray electron-plus-positron (CRE) spectrum in low Earth orbit does provide such a spectral feature. The energy and spectral shape of this cutoff can be calculated with the aid of a numerical code tracing charged particles in the Earth's magnetic field. By comparing the cutoff value with that measured by the LAT in different geomagnetic positions, we have obtained several calibration points between similar to 6 and similar to 13 GeV with an estimated uncertainty of similar to 2%. An energy calibration with such high accuracy reduces the systematic uncertainty in LAT measurements of, for example, the spectral cutoff in the emission from gamma ray pulsars. (C) 2011 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

INSIGHTS INTO THE HIGH-ENERGY gamma-RAY EMISSION OF MARKARIAN 501 FROM EXTENSIVE MULTIFREQUENCY OBSERVATIONS IN THE FERMI ERA - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2011)
We report on the gamma-ray activity of the blazar Mrk 501 during the first 480 days of Fermi operation. We find that the average Large Area Telescope (LAT) gamma-ray spectrum of Mrk 501 can be well described by a single power-law function with a photon index of 1.78 +/- 0.03. While we observe relatively mild flux variations with the Fermi-LAT (within less than a factor of two), we detect remarkable spectral variability where the hardest observed spectral index within the LAT energy range is 1.52 +/- 0.14, and the softest one is 2.51 +/- 0.20. These unexpected spectral changes do not correlate with the measured flux variations above 0.3 GeV. In this paper, we also present the first results from the 4.5 month long multifrequency campaign (2009 March 15-August 1) on Mrk 501, which included the Very Long Baseline Array (VLBA), Swift, RXTE, MAGIC, and VERITAS, the F-GAMMA, GASP-WEBT, and other collaborations and instruments which provided excellent temporal and energy coverage of the source throughout the entire campaign. The extensive radio to TeV data set from this campaign provides us with the most detailed spectral energy distribution yet collected for this source during its relatively low activity. The average spectral energy distribution of Mrk 501 is well described by the standard one-zone synchrotron self-Compton (SSC) model. In the framework of this model, we find that the dominant emission region is characterized by a size less than or similar to 0.1 pc (comparable within a factor of few to the size of the partially resolved VLBA core at 15-43 GHz), and that the total jet power (similar or equal to 10(44) erg s(-1)) constitutes only a small fraction (similar to 10(-3)) of the Eddington luminosity. The energy distribution of the freshly accelerated radiating electrons required to fit the time-averaged data has a broken power-law form in the energy range 0.3 GeV-10 TeV, with spectral indices 2.2 and 2.7 below and above the break energy of 20 GeV. We argue that such a form is consistent with a scenario in which the bulk of the energy dissipation within the dominant emission zone of Mrk 501 is due to relativistic, proton-mediated shocks. We find that the ultrarelativistic electrons and mildly relativistic protons within the blazar zone, if comparable in number, are in approximate energy equipartition, with their energy dominating the jet magnetic field energy by about two orders of magnitude.
CRIS-Team WoS Importer:2020-01-15

Introducing the CTA concept - Acharya, B. S.; Actis, M.; Aghajani, T.; Agnetta, G.; Aguilar, J.; Aharonian, F.; Ajello, M.; Akhperjanian, A.; Alcubierre, M.; Aleksic, J.; Alfaro, R.; Aliu, E.; et al. (Astroparticle Physics, 2013)
The Cherenkov Telescope Array (CTA) is a new observatory for very high-energy (VHE) gamma rays. CTA has ambitions science goals, for which it is necessary to achieve full-sky coverage, to improve the sensitivity by about an order of magnitude, to span about four decades of energy, from a few tens of GeV to above 100 TeV with enhanced angular and energy resolutions over existing VHE gamma-ray observatories. An international collaboration has formed with more than 1000 members from 27 countries in Europe, Asia, Africa and North and South America. In 2010 the CTA Consortium completed a Design Study and started a three-year Preparatory Phase which leads to production readiness of CTA in 2014. In this paper we introduce the science goals and the concept of CTA, and provide an overview of the project. © 2013 Elsevier B.V. All rights reserved.
Keywords: Air showers; Cherenkov Telescopes; TeV gamma-ray astronomy

Investigating the Nature of Late-time High-energy GRB Emission through Joint Fermi/Swift Observations - Ajello, Marco; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; Bruel, P.; Buehler, R.; et al. (Astrophysical Journal, 2018)
We use joint observations by the Swift X-ray Telescope (XRT) and the Fermi Large Area Telescope (LAT) of gamma-ray burst (GRB) afterglows to investigate the nature of the long-lived high-energy emission observed by Fermi LAT. Joint broadband spectral modeling of XRT and LAT data reveals that LAT nondetections of bright X-ray afterglows are consistent with a cooling break in the inferred electron synchrotron spectrum below the LAT and/or XRT energy ranges. Such a break is sufficient to suppress the high-energy emission so as to be below the LAT detection threshold. By contrast, LAT-detected bursts are best fit by a synchrotron spectrum with a cooling break that lies either between or above the XRT and LAT energy ranges. We speculate that the primary difference between GRBs with LAT afterglow detections and the nondetected population may be in the type of circumstellar environment in which these bursts occur, with late-time LAT detections preferentially selecting GRBs that occur in low wind-like circumburst density profiles. Furthermore, we find no evidence of high-energy emission in the LAT-detected population significantly in excess of the flux expected from the electron synchrotron spectrum fit to the observed X-ray emission. The lack of excess emission at high energies could be due to a shocked external medium in which the energy density in the magnetic field is stronger than or comparable to that of the relativistic electrons behind the shock, precluding the production of a dominant synchrotron self-Compton (SSC) component in the LAT energy range. Alternatively, the peak of the SSC emission could be beyond the 0.1-100 GeV energy range considered for this analysis.
Keywords: gamma-ray burst: general

Investigating the Nature of Late-time High-energy GRB Emission through Joint Fermi/Swift Observations - Ajello, Marco; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; Bruel, P.; Buehler, R.; et al. (Astrophysical Journal, 2018)
We use joint observations by the Swift X-ray Telescope (XRT) and the Fermi Large Area Telescope (LAT) of gamma-ray burst (GRB) afterglows to investigate the nature of the long-lived high-energy emission observed by Fermi LAT. Joint broadband spectral modeling of XRT and LAT data reveals that LAT nondetections of bright X-ray afterglows are consistent with a cooling break in the inferred electron synchrotron spectrum below the LAT and/or XRT energy ranges. Such a break is sufficient to suppress the high-energy emission so as to be below the LAT detection threshold. By contrast, LAT-detected bursts are best fit by a synchrotron spectrum with a cooling break that lies either between or above the XRT and LAT energy ranges. We speculate that the primary difference between GRBs with LAT afterglow detections and the nondetected population may be in the type of circumstellar environment in which these bursts occur, with late-time LAT detections preferentially selecting GRBs that occur in low wind-like circumburst density profiles. Furthermore, we find no evidence of high-energy emission in the LAT-detected population significantly in excess of the flux expected from the electron synchrotron spectrum fit to the observed X-ray emission. The lack of excess emission at high energies could be due to a shocked external medium in which the energy density in the magnetic field is stronger than or comparable to that of the relativistic electrons behind the shock, precluding the production of a dominant synchrotron self-Compton (SSC) component in the LAT energy range. Alternatively, the peak of the SSC emission could be beyond the 0.1-100 GeV energy range considered for this analysis.
Keywords: gamma-ray burst: general

LAT perspectives in detection of high energy cosmic ray electrons - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

LED as laboratory test source for astronomical intensity interferometry - Zmija, Andreas; Deiml, Peter; Malyshev, Dmitry; Zink, Adrian; Anton, Gisela; Michel, Thilo; Funk, Stefan (Optics Express, 2020)
The challenge of astronomical intensity interferometry is to detect the small photon-bunching signals of distant sources with a broad optical bandwidth. We have built a Hanbury Brown-Twiss-like laboratory intensity interferometer with a focus on a relatively broad bandwidth (1 nm FWHM optical filter) and high photon rates (up to 10 MHz) per channel compared to typical (non-astronomical) intensity interferometry applications. As a light source we use a green LED to simulate starlight. The LED has proven to be a compact high-power source of stochastic light with a special advantage of a small emission area, which favours spatial coherence. Using single-photon correlations, we detect a bunching signal in the second-order correlation function with a coherence time of <1 ps and an amplitude of <4 · 10−4 and describe signal and background quantitatively for a 40 hours measurement. In this paper we show our setup, present the correlation measurements and compare them to theoretical expectations.
CRIS-Team Scopus Importer:2020-02-21

Limits on dark matter annihilation signals from the Fermi LAT 4-year measurement of the isotropic gamma-ray background - Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bregeon, J.; et al. (Journal of Cosmology and Astroparticle Physics, 2015)
We search for evidence of dark matter (DM) annihilation in the isotropic gamma-ray background (IGRB) measured with 50 months of Fermi Large Area Telescope (LAT) observations. An improved theoretical description of the cosmological DM annihilation signal, based on two complementary techniques and assuming generic weakly interacting massive particle (WIMP) properties, renders more precise predictions compared to previous work. More specifically, we estimate the cosmologically-induced gamma-ray intensity to have an uncertainty of a factor similar to 20 in canonical setups. We consistently include both the Galactic and extragalactic signals under the same theoretical framework, and study the impact of the former on the IGRB spectrum derivation. We find no evidence for a DM signal and we set limits on the DM-induced isotropic gamma-ray signal. Our limits are competitive for DM particle masses up to tens of TeV and, indeed, are the strongest limits derived from Fermi LAT data at TeV energies. This is possible thanks to the new Fermi LAT IGRB measurement, which now extends up to an energy of 820 GeV. We quantify uncertainties in detail and show the potential this type of search offers for testing the WIMP paradigm with a complementary and truly cosmological probe of DM particle signals.
CRIS-Team WoS Importer:2020-01-15

Locating the TeV-excess from the galactic centre region - Funk, Stefan; et al. (High Energy Gamma-Ray Astronomy, 2005)
CRIS-Team WoS Importer:2020-01-15

MAGIC and Fermi-LAT gamma-ray results on unassociated HAWC sources - Ahnen, M. L.; Ansoldi, S.; Antonelli, L. A.; Arcaro, C.; Baack, D.; Babic, A.; Banerjee, Biswajit; Bangale, P.; Barres De Almeida, U.; Barrio, J. A.; Becerra Gonzalez, J.; Bednarek, W.; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
The HAWC Collaboration released the 2HWC catalogue of TeV sources, in which 19 show no association with any known high-energy (HE; E ≳ 10 GeV) or very-high-energy (VHE; E ≳ 300 GeV) sources. This catalogue motivated follow-up studies by both the Major Atmospheric Gamma-ray Imaging Cherenkov (MAGIC) and Fermi-LAT (Large Area Telescope) observatories with the aim of investigating gamma-ray emission over a broad energy band. In this paper, we report the results from the first joint work between High Altitude Water Cherenkov (HAWC), MAGIC, and Fermi-LAT on three unassociated HAWC sources: 2HWC J2006+341, 2HWC J1907+084∗, and 2HWC J1852+013∗. Although no significant detection was found in the HE and VHE regimes, this investigation shows that a minimum 1° extension (at 95 per cent confidence level) and harder spectrum in the GeV than the one extrapolated from HAWC results are required in the case of 2HWC J1852+013∗, whilst a simply minimum extension of 0.16° (at 95 per cent confidence level) can already explain the scenario proposed by HAWC for the remaining sources. Moreover, the hypothesis that these sources are pulsar wind nebulae is also investigated in detail.
CRIS-Team Scopus Importer:2019-09-24
Keywords: astroparticle physics; gamma rays: general; pulsars: general

Maximum likelihood reconstruction for grating-based X-ray microscopy - Wolf, Andreas; Schuster, Max; Ludwig, Veronika; Anton, Gisela; Funk, Stefan (Optics Express, 2020)
The combination of grating-based phase-contrast imaging with X-ray microscopy can result in a complicated image formation. Generally, transverse shifts of the interference fringes are nonlinearly dependent on phase differences of the measured wave front. We present an iterative reconstruction scheme based on a regularized maximum likelihood cost function that fully takes this dependency into account. The scheme is validated by numerical simulations. It is particularly advantageous at low photon numbers and when the premises for deconvolution-based reconstructions are not met. Our reconstruction scheme hence enables a broader applicability of X-ray grating interferometry in imaging and wave front sensing.
CRIS-Team Scopus Importer:2020-05-22

Measurement of Separate Cosmic-Ray Electron and Positron Spectra with the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Allafort, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; Bloom, E. D.; et al. (Physical Review Letters, 2012)
We measured separate cosmic-ray electron and positron spectra with the Fermi Large Area Telescope. Because the instrument does not have an onboard magnet, we distinguish the two species by exploiting Earth's shadow, which is offset in opposite directions for opposite charges due to Earth's magnetic field. We estimate and subtract the cosmic-ray proton background using two different methods that produce consistent results. We report the electron-only spectrum, the positron-only spectrum, and the positron fraction between 20 and 200 GeV. We confirm that the fraction rises with energy in the 20-100 GeV range. The three new spectral points between 100 and 200 GeVare consistent with a fraction that is continuing to rise with energy.
CRIS-Team WoS Importer:2020-01-15

Measurement of the Cosmic Ray e(+)+e(-) Spectrum from 20 GeV to 1 TeV with the Fermi Large Area Telescope - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Battelino, M.; Baughman, B. M.; Bechtol, K.; et al. (Physical Review Letters, 2009)
Designed as a high-sensitivity gamma-ray observatory, the Fermi Large Area Telescope is also an electron detector with a large acceptance exceeding 2 m(2) sr at 300 GeV. Building on the gamma-ray analysis, we have developed an efficient electron detection strategy which provides sufficient background rejection for measurement of the steeply falling electron spectrum up to 1 TeV. Our high precision data show that the electron spectrum falls with energy as E-3.0 and does not exhibit prominent spectral features. Interpretations in terms of a conventional diffusive model as well as a potential local extra component are briefly discussed.
CRIS-Team WoS Importer:2020-01-15

Measurement of the EBL spectral energy distribution using the VHE gamma-ray spectra of HESS blazars - Abdalla, H.; Abramowski, A.; Aharonian, F.; Ait Benkhali, F.; Akhperjanian, A. G.; Andersson, T.; Angüner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; et al. (Astronomy & Astrophysics, 2017)
Very high-energy gamma rays (VHE, E greater than or similar to 100 GeV) propagating over cosmological distances can interact with the low-energy photons of the extragalactic background light (EBL) and produce electron-positron pairs. The transparency of the Universe to VHE gamma rays is then directly related to the spectral energy distribution (SED) of the EBL. The observation of features in the VHE energy spectra of extragalactic sources allows the EBL to be measured, which otherwise is very difficult. An EBL model-independent measurement of the EBL SED with the H.E.S.S. array of Cherenkov telescopes is presented. It was obtained by extracting the EBL absorption signal from the reanalysis of high-quality spectra of blazars. From H.E.S.S. data alone the EBL signature is detected at a significance of 9.5 sigma, and the intensity of the EBL obtained in different spectral bands is presented together with the associated gamma-ray horizon.
CRIS-Team WoS Importer:2020-01-15
Keywords: Infrared: diffuse background; Cosmic background radiation; Gamma rays: galaxies; BL Lacertae objects: general

Measurement of the high-energy gamma-ray emission from the Moon with the Fermi Large Area Telescope - Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bonino, R.; Bottacini, E.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2016)
We have measured the gamma-ray emission spectrum of the Moon using the data collected by the Large Area Telescope onboard the Fermi satellite during its first seven years of operation, in the energy range from 30 MeV up to a few GeV. We have also studied the time evolution of the flux, finding a correlation with the solar activity. We have developed a full Monte Carlo simulation describing the interactions of cosmic rays with the lunar surface. The results of the present analysis can be explained in the framework of this model, where the production of gamma rays is due to the interactions of cosmic-ray proton and helium nuclei with the surface of the Moon. Finally, we have used our simulation to derive the cosmic-ray proton and helium spectra near Earth from the Moon gamma-ray data.

Measuring the Cosmic-Ray Acceleration Efficiency of a Supernova Remnant - Helder, E. A.; Vink, Jacco; Bassa, C. G.; Bamba, A.; Bleeker, J. A. M.; Funk, Stefan; Ghavamian, P.; Van Der Heyden, K. J.; Verbunt, F.; Yamazaki, R. (Science, 2009)
Cosmic rays are the most energetic particles arriving at Earth. Although most of them are thought to be accelerated by supernova remnants, the details of the acceleration process and its efficiency are not well determined. Here we show that the pressure induced by cosmic rays exceeds the thermal pressure behind the northeast shock of the supernova remnant RCW 86, where the x-ray emission is dominated by synchrotron radiation from ultrarelativistic electrons. We determined the cosmic-ray content from the thermal Doppler broadening measured with optical spectroscopy, combined with a proper-motion study in x-rays. The measured postshock proton temperature, in combination with the shock velocity, does not agree with standard shock heating, implying that >50% of the postshock pressure is produced by cosmic rays.
CRIS-Team WoS Importer:2020-01-15

MINUTE-TIMESCALE > 100 MeV gamma-RAY VARIABILITY DURING THE GIANT OUTBURST OF QUASAR 3C 279 OBSERVED BY FERMI-LAT IN 2015 JUNE - Uchiyama, Y.; Sikora, M.; Nalewajko, K.; Ohsugi, T.; Maldera, S.; Negro, M.; La Mura, G.; Mirabal, N.; Anantua, R.; Yuan, Y.; Cavazzuti, E.; Bonino, R.; et al. (Astrophysical Journal Letters, 2016)
On 2015 June 16, Fermi- LAT observed a giant outburst from the flat spectrum radio quasar 3C 279 with a peak >100 MeV flux of similar to 3.6 x 10(-5) photons cm(-2) s(-1), averaged over orbital period intervals. It is historically the highest gamma-ray flux observed from the source, including past EGRET observations, with the gamma-ray isotropic luminosity reaching similar to 10(49) erg s(-1). During the outburst, the Fermi spacecraft, which has an orbital period of 95.4 minutes, was operated in a special pointing mode to optimize the exposure for 3C 279. For the first time, significant flux variability at sub-orbital timescales was found in blazar observations by Fermi- LAT. The source flux variability was resolved down to 2-minute binned timescales, with flux doubling times of less than 5 minutes. The observed minute-scale variability suggests a very compact emission region at hundreds of Schwarzschild radii from the central engine in conical jet models. A minimum bulk jet Lorentz factor (Gamma) of 35 is necessary to avoid both internal gamma-ray absorption and super-Eddington jet power. In the standard external radiation Comptonization scenario, G should be at least 50 to avoid overproducing the synchrotron self-Compton component. However, this predicts extremely low magnetization (similar to 5 x 10(-4)). Equipartition requires Gamma as high as 120, unless the emitting region is a small fraction of the dissipation region. Alternatively, we consider. rays originating as synchrotron radiation of gamma e similar to 1.6 x 10(6) electrons, in a magnetic field B similar to 1.3 kG, accelerated by strong electric fields E similar to B in the process of magnetoluminescence. At such short distance scales, one cannot immediately exclude the production of gamma-rays in hadronic processes.
Keywords: galaxies: active; galaxies: jets; gamma rays: galaxies; quasars: individual (3C 279); radiation mechanisms: non-thermal

Monte Carlo design studies for the Cherenkov Telescope Array - Bernloehr, K.; Barnacka, A.; Becherini, Y.; Blanch Bigas, O.; Carmona, E.; Colin, P.; Decerprit, G.; Di Pierro, Federico; Dubois, F.; Farnier, C.; Funk, Stefan; Hermann, G.; et al. (Astroparticle Physics, 2013)
The Cherenkov Telescopes Array (CTA) is planned as the future instrument for very-high-energy (VHE) gamma-ray astronomy with a wide energy range of four orders of magnitude and an improvement in sensitivity compared to current instruments of about an order of magnitude. Monte Carlo simulations are a crucial tool in the design of CTA. The ultimate goal of these simulations is to find the most cost-effective solution for given physics goals and thus sensitivity goals or to find, for a given cost, the solution best suited for different types of targets with CTA. Apart from uncertain component cost estimates, the main problem in this procedure is the dependence on a huge number of configuration parameters, both in specifications of individual telescope types and in the array layout. This is addressed by simulation of a huge array intended as a superset of many different realistic array layouts, and also by simulation of array subsets for different telescope parameters. Different analysis methods - in use with current installations and extended (or developed specifically) for CTA - are applied to the simulated data sets for deriving the expected sensitivity of CTA. In this paper we describe the current status of this iterative approach to optimize the CTA design and layout. (C) 2012 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Monte Carlo studies for the optimisation of the Cherenkov Telescope Array layout - Acharyya, A.; Agudo, I.; Angüner, E. O.; Alfaro, R.; Alfaro, J.; Alispach, C.; Aloisio, R.; Alves Batista, R.; Amans, J. P.; Amati, L.; Amato, E.; Ambrosi, G.; et al. (Astroparticle Physics, 2019)
The Cherenkov Telescope Array (CTA) is the major next-generation observatory for ground-based very-high-energy gamma-ray astronomy. It will improve the sensitivity of current ground-based instruments by a factor of five to twenty, depending on the energy, greatly improving both their angular and energy resolutions over four decades in energy (from 20 GeV to 300 TeV). This achievement will be possible by using tens of imaging Cherenkov telescopes of three successive sizes. They will be arranged into two arrays, one per hemisphere, located on the La Palma island (Spain) and in Paranal (Chile). We present here the optimised and final telescope arrays for both CTA sites, as well as their foreseen performance, resulting from the analysis of three different large-scale Monte Carlo productions.
CRIS-Team Scopus Importer:2019-05-02
Keywords: Cherenkov telescopes; Cosmic rays; Gamma rays; IACT technique; Monte Carlo simulations

Monte Carlo studies of medium-size telescope designs for the Cherenkov Telescope Array - Wood, M.; Jogler, T.; Dumm, J.; Funk, Stefan; Funk, Stefan (Astroparticle Physics, 2016)
We present studies for optimizing the next generation of ground-based imaging atmospheric Cherenkov telescopes (IACTs). Results focus on mid-sized telescopes (MSTs) for CTA, detecting very high energy gamma rays in the energy range from a few hundred GeV to a few tens of TeV. We describe a novel, flexible detector Monte Carlo package, FAST (FAst Simulation for imaging air cherenkov Telescopes), that we use to simulate different array and telescope designs. The simulation is somewhat simplified to allow for efficient exploration over a large telescope design parameter space. We investigate a wide range of telescope performance parameters including optical resolution, camera pixel size, and light collection area. In order to ensure a comparison of the arrays at their maximum sensitivity, we analyze the simulations with the most sensitive techniques used in the field, such as maximum likelihood template reconstruction and boosted decision trees for background rejection. Choosing telescope design parameters representative of the proposed Davies-Cotton (DC) and Schwarzchild-Couder (SC) MST designs, we compare the performance of the arrays by examining the gamma-ray angular resolution and differential point-source sensitivity. We-further investigate the array performance under a wide range of conditions, determining the impact of the number of telescopes, telescope separation, night sky background, and geomagnetic field. We find a 30-40% improvement in the gamma-ray angular resolution at all energies when comparing arrays with an equal number of SC and DC telescopes, significantly enhancing point-source sensitivity in the MST energy range. We attribute the increase in point-source sensitivity to the improved optical point-spread function and smaller pixel size of the SC telescope design. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Monte Carlo simulations; Cherenkov telescopes; IACT technique; Gamma rays; Cosmic rays

Monte-Carlo studies of the angular resolution of a future Cherenkov gamma-ray telescope - Funk, Stefan; Hinton, J. A. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

Morphological and spectral studies of the shell-type SNRs RX J1713.7-3946 and RX J0852.0-4622 with HESS - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

Multi-messenger Observations of a Binary Neutron Star Merger - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, Paolo; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; Afrough, M.; et al. (Astrophysical Journal Letters, 2017)
On 2017 August 17 a binary neutron star coalescence candidate (later designated GW170817) with merger time 12:41:04 UTC was observed through gravitational waves by the Advanced LIGO and Advanced Virgo detectors. The Fermi Gamma-ray Burst Monitor independently detected a gamma-ray burst (GRB 170817A) with a time delay of similar to 1.7 s with respect to the merger time. From the gravitational-wave signal, the source was initially localized to a sky region of 31 deg(2) at a luminosity distance of 40(-8)(+8) Mpc and with component masses consistent with neutron stars. The component masses were later measured to be in the range 0.86 to 2.26 M-circle dot. An extensive observing campaign was launched across the electromagnetic spectrum leading to the discovery of a bright optical transient (SSS17a, now with the IAU identification of AT 2017gfo) in NGC 4993 (at similar to 40 Mpc) less than 11 hours after the merger by the One-Meter, Two Hemisphere (1M2H) team using the 1 m Swope Telescope. The optical transient was independently detected by multiple teams within an hour. Subsequent observations targeted the object and its environment. Early ultraviolet observations revealed a blue transient that faded within 48 hours. Optical and infrared observations showed a redward evolution over similar to 10 days. Following early non-detections, X-ray and radio emission were discovered at the transient's position similar to 9 and similar to 16 days, respectively, after the merger. Both the X-ray and radio emission likely arise from a physical process that is distinct from the one that generates the UV/optical/near-infrared emission. No ultra-high-energy gamma-rays and no neutrino candidates consistent with the source were found in follow-up searches. These observations support the hypothesis that GW170817 was produced by the merger of two neutron stars in NGC4993 followed by a short gamma-ray burst (GRB 170817A) and a kilonova/macronova powered by the radioactive decay of r-process nuclei synthesized in the ejecta.
Keywords: gravitational waves; stars: neutron

Multi-wavelength observations of PKS 2155-304 with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The High Energy Stereoscopic System (HESS) has observed the high-frequency peaked BL Lac object PKS 2155- 304 in 2003 between October 19 and November 26 in Very High Energy (VHE) gamma-rays (E >= 160 GeV for these observations). Observations were carried out simultaneously with the Proportional Counter Array (PCA) on board the Rossi X-ray Timing Explorer satellite ( RXTE), the Robotic Optical Transient Search Experiment (ROTSE) and the Nancay decimetric radiotelescope (NRT). Intra-night variability is seen in the VHE band, the source being detected with a high significance on each night it was observed. Variability is also found in the X-ray and optical bands on kilosecond timescales, along with flux-dependent spectral changes in the X-rays. A transient X-ray event with a 1500 s timescale is detected, making this the fastest X-ray flare seen in this object. No correlation can be established between the X-ray and the gamma-ray fluxes, or any of the other wavebands, over the small range of observed variability. The average HESS spectrum shows a very soft power law shape with a photon index of 3.37 +/- 0.07(stat) +/- 0.10(sys). The energy outputs in the 2 - 10 keV and in the VHE gamma-ray range are found to be similar, with the X-rays and the optical fluxes at a level comparable to some of the lowest historical measurements, indicating that PKS 2155- 304 was in a low or quiescent state during the observations. Both a leptonic and a hadronic model are used to derive source parameters from these observations. These parameters are found to be sensitive to the model of Extragalactic Background Light (EBL) that attenuates the VHE signal at this source's redshift (z = 0.117).
CRIS-Team WoS Importer:2020-01-15

Multi-wavelength selection and identification of gamma-ray blazar candidates - Paggi, Alessandro; D'Abrusco, Raffaele; Massaro, F.; Landoni, Marco; Milisavljevic, D.; Masetti, N.; Ricci, F.; Jimenez-Bailon, E.; Chavushyan, Vahram; Giroletti, M.; Smith, H. A.; Margutti, R.; et al. (EXTRAGALACTIC JETS FROM EVERY ANGLE, 2015)
CRIS-Team WoS Importer:2020-01-15

Noise reduction for single-shot grating-based phase-contrast imaging at an x-ray backlighter - Schreiner, Stephan; Akstaller, Bernhard; Dietrich, Lisa; Meyer, Pascal; Neumayer, Paul; Schuster, Max; Wolf, Andreas; Zielbauer, Bernhard; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2021)
X-ray backlighters allow the capture of sharp images of fast dynamic processes due to extremely short exposure times. Moiré imaging enables simultaneously measuring the absorption and differential phase-contrast (DPC) of these processes. Acquiring images with one single shot limits the X-ray photon flux, which can result in noisy images. Increasing the photon statistics by repeating the experiment to gain the same image is not possible if the investigated processes are dynamic and chaotic. Furthermore, to reconstruct the DPC and transmission image, an additional measurement captured in absence of the object is required. For these reference measurements, shot-to-shot fluctuations in X-ray spectra and a source position complicate the averaging of several reference images for noise reduction. Here, two approaches of processing multiple reference images in combination with one single object image are evaluated regarding the image quality. We found that with only five reference images, the contrast-to-noise ratio can be improved by approximately 13% in the DPC image. This promises improvements for short-exposure single-shot acquisitions of rapid processes, such as laser-produced plasma shock-waves in high-energy density experiments at backlighter X-ray sources such as the PHELIX high-power laser facility.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Grating-based phase-contrast; Image processing; Image quality improvement; Single-shot X-ray phase-contrast imaging; X-ray back-lighter; X-ray generators and sources

Novel technique for monitoring the performance of the LAT instrument on board the GLAST satellite - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

OBSERVATION OF SUPERNOVA REMNANT IC 443 WITH THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
We report observation of the supernova remnant (SNR) IC 443 (G189.1+3.0) with the Fermi Gamma-ray Space Telescope Large Area Telescope (LAT) in the energy band between 200 MeV and 50 GeV. IC 443 is a shell-type SNR with mixed morphology located off the outer Galactic plane where high-energy emission has been detected in the X-ray, GeV and TeV gamma-ray bands. Past observations suggest IC 443 has been interacting with surrounding interstellar matter. Proximity between dense shocked molecular clouds and GeV-TeV gamma-ray emission regions detected by EGRET, MAGIC, and VERITAS suggests an interpretation that cosmic-ray (CR) particles are accelerated by the SNR. With the high gamma-ray statistics and broad energy coverage provided by the LAT, we accurately characterize the gamma-ray emission produced by the CRs accelerated at IC 443. The emission region is extended in the energy band with theta(68) = 0 degrees.27 +/- 0 degrees.01(stat) +/- 0 degrees.03(sys) for an assumed two-dimensional Gaussian profile and overlaps almost completely with the extended source region of VERITAS. Its centroid is displaced significantly from the known pulsar wind nebula (PWN) which suggests the PWN is not the major contributor in the present energy band. The observed spectrum changes its power-law slope continuously and continues smoothly to the MAGIC and VERITAS data points. The combined gamma-ray spectrum (200 MeV < E < 2 TeV) is reproduced well by decays of neutral pions produced by a broken power-law proton spectrum with a break around 70 GeV.
CRIS-Team WoS Importer:2020-01-15

Observation of the microquasar LS 5039 with HESS - Funk, Stefan; et al. (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

Observations of M31 and M33 with the Fermi Large Area Telescope: A Galactic Center Excess in Andromeda? - Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal, 2017)
The Fermi Large Area Telescope (LAT) has opened the way for comparative studies of cosmic rays (CRs) and high-energy objects in the Milky Way (MW) and in other, external, star-forming galaxies. Using 2 yr of observations with the Fermi LAT, Local Group galaxy M31 was detected as a marginally extended gamma-ray source, while only an upper limit has been derived for the other nearby galaxy M33. We revisited the gamma-ray emission in the direction of M31 and M33 using more than 7 yr of LAT Pass 8 data in the energy range 0.1-100 GeV, presenting detailed morphological and spectral analyses. M33 remains undetected, and we computed an upper limit of 2.0 x 10(-12) erg cm(-2) s(-1) on the 0.1-100 GeV energy flux (95% confidence level). This revised upper limit remains consistent with the observed correlation between gamma-ray luminosity and star formation rate tracers and implies an average CR density in M33 that is at most half of that of the MW. M31 is detected with a significance of nearly 10 sigma. Its spectrum is consistent with a power law with photon index Gamma = 2.4 +/- 0.1(stat) (vertical bar) (syst) and a 0.1-100 GeV energy flux of (5.6 +/- 0.6(stat vertical bar syst)) x 10(-12) erg cm(-1) s(-1). M31 is detected to be extended with a 4 sigma significance. The spatial distribution of the emission is consistent with a uniform-brightness disk with a radius of 0 degrees.4 and no offset from the center of the galaxy, but nonuniform intensity distributions cannot be excluded. The flux from M31 appears confined to the inner regions of the galaxy and does not fill the disk of the galaxy or extend far from it. The gamma-ray signal is not correlated with regions rich in gas or star formation activity, which suggests that the emission is not interstellar in origin, unless the energetic particles radiating in gamma rays do not originate in recent star formation. Alternative and nonexclusive interpretations are that the emission results from a population of millisecond pulsars dispersed in the bulge and disk of M31 by disrupted globular clusters or from the decay or annihilation of dark matter particles, similar to what has been proposed to account for the so-called Galactic center excess found in Fermi-LAT observations of the MW.
CRIS-Team WoS Importer:2020-01-15

Observations of Mkn 421 in 2004 with HESS at large zenith angles - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Mkn 421 was observed during a high flux state for nine nights in April and May 2004 with the fully operational High Energy Stereoscopic System (HESS) in Namibia. The observations were carried out at zenith angles of 60 degrees- 65 degrees, which result in an average energy threshold of 1.5 TeV and a collection area reaching 2 km(2) at 10 TeV. Roughly 7000 photons from Mkn 421 were accumulated with an average gamma-ray rate of 8 photons/min. The overall significance of the detection exceeds 100 standard deviations. The light-curve of integrated fluxes above 2 TeV shows changes of the diurnal flux up to a factor of 4.3. For nights of high flux, intra-night variability is detected with a decay time of less than 1 h. The time averaged energy spectrum is curved and is well described by a power-law with a photon index Gamma = 2.1 +/- 0.1(stat) +/- 0.3(sys) and an exponential cutoff at E-c = 3.1(+ 0.5 - 0.4)(stat) +/- 0.9(sys) TeV and an average integral flux above 2 TeV of 3 Crab flux units. Significant variations of the spectral shape are detected with a spectral hardening as the flux increases. Contemporaneous multi-wavelength observations at lower energies (X-rays and gamma-rays above approximate to 300 GeV) indicate smaller relative variability amplitudes than seen above 2 TeV during high flux state observed in April 2004.
CRIS-Team WoS Importer:2020-01-15

Observations of selected AGN with HESS - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
A sample of selected active galactic nuclei (AGN) was observed in 2003 and 2004 with the High Energy Stereoscopic System (HESS), an array of imaging atmospheric-Cherenkov telescopes in Namibia. The redshifts of these candidate very-high-energy (VHE, > 100 GeV) gamma-ray emitters range from z = 0.00183 to z = 0.333. Significant detections were already reported for some of these objects, such as PKS 2155-304 and Markarian 421. Marginal evidence (3.1 sigma) for a signal is found from large-zenith-angle observations of Markarian 501, corresponding to an integral flux of I(> 1.65 TeV) = (1.5 +/- 0.6(stat)+/- 0.3(syst)) x 10(-12) cm(-2) s(-1) or similar to 15% of the Crab Nebula flux. Integral flux upper limits for 19 other AGN, based on exposures of similar to 1 to similar to 8 h live time, and with average energy thresholds between 160 GeV and 610 GeV, range from 0.4% to 5.1% of the Crab Nebula flux. All the upper limits are the most constraining ever reported for these objects.
CRIS-Team WoS Importer:2020-01-15

Observations of SNR RX J1713.7-3946 with HESS - Funk, Stefan; et al. (High Energy Gamma-Ray Astronomy, 2005)
CRIS-Team WoS Importer:2020-01-15

Observations of the Galactic Centre region in very high energy gamma-rays with HESS - Funk, Stefan; et al. (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

OBSERVATIONS OF THE YOUNG SUPERNOVA REMNANT RX J1713.7-3946 WITH THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Allafort, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2011)
We present observations of the young supernova remnant (SNR) RX J1713.7-3946 with the Fermi Large Area Telescope (LAT). We clearly detect a source positionally coincident with the SNR. The source is extended with a best-fit extension of 0 degrees.55 +/- 0 degrees.04 matching the size of the non-thermal X-ray and TeV gamma-ray emission from the remnant. The positional coincidence and the matching extended emission allow us to identify the LAT source with SNR RX J1713.7-3946. The spectrum of the source can be described by a very hard power law with a photon index of Gamma = 1.5 +/- 0.1 that coincides in normalization with the steeper H. E. S. S.-detected gamma-ray spectrum at higher energies. The broadband gamma-ray emission is consistent with a leptonic origin as the dominant mechanism for the gamma-ray emission.
CRIS-Team WoS Importer:2020-01-15

ON THE NATURE OF THE GAMMA-RAY SOURCE 2FGL J1823.8+4312: THE DISCOVERY OF A NEW CLASS OF EXTRAGALACTIC X-RAY SOURCES - Massaro, Francesco; Paggi, Alessandro; D'Abrusco, Raffaele; Tosti, Gino; Grindlay, J. E.; Smith, Howard A.; Digel, S. W.; Funk, Stefan (Astrophysical Journal Letters, 2012)
One of the unsolved mysteries of gamma-ray astronomy concerns the nature of unidentified gamma-ray sources. Recently, using the Second Fermi LAT source catalog (2FGL) and the Wide-field Infrared Survey Explorer (WISE) archive, we discovered that the WISE counterparts of gamma-ray blazars, a class of active galactic nuclei, delineate a region (the WISE Gamma-ray Strip) in three-dimensional infrared color space well separated from the locus of other astronomical objects. Based on this result, we built an association procedure to recognize if there are WISE blazar candidates within the positional uncertainty region of the unidentified gamma-ray sources. Here we report on our analysis of 2FGL J1823.8+4312, a gamma-ray active galactic nucleus of uncertain type associated with the X-ray source 1RXS J182418.7+430954 according to the 2FGL, to verify whether it is a blazar. Applying our association method we found two sources with IR colors typical of gamma-ray blazars, located within the 99.9% confidence region of 2FGL J1823.8+4312: WISE J182352.33+431452.5 and WISE J182409.25+431404.7. We then searched in the Chandra, NVSS, and SDSS archival observations for their counterparts. We discovered that WISE J182352.33+431452.5, our preferred gamma-ray blazar candidate according to our WISE association procedure, is detected in the optical and in the X-rays but not in the radio, making it extremely unusual if it is a blazar. Given its enigmatic spectral energy distribution, we considered the possibility that it is a "radio-faint blazar" or the prototype of a new class of extragalactic sources; our conclusion is independent of whether WISE J182352.33+431452.5 is the actual counterpart of 2FGL J1823.8+4312.
CRIS-Team WoS Importer:2020-01-15

Operating performance of the gamma-ray Cherenkov telescope: An end-to-end Schwarzschild-Couder telescope prototype for the Cherenkov Telescope Array - Dournaux, J. L.; De Franco, A.; Laporte, P.; White, R.; Greenshaw, T.; Sol, H.; Abchiche, A.; Allan, D.; Amans, J. P.; Armstrong, T. P.; Balzer, A.; Berge, D.; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2017)
The Cherenkov Telescope Array (CTA) consortium aims to build the next-generation ground-based very-high-energy gamma-ray observatory. The array will feature different sizes of telescopes allowing it to cover a wide gamma-ray energy band from about 20. GeV to above 100. TeV. The highest energies, above 5. TeV, will be covered by a large number of Small-Sized Telescopes (SSTs) with a field-of-view of around 9°. The Gamma-ray Cherenkov Telescope (GCT), based on Schwarzschild-Couder dual-mirror optics, is one of the three proposed SST designs. The GCT is described in this contribution and the first images of Cherenkov showers obtained using the telescope and its camera are presented. These were obtained in November 2015 in Meudon, France.
Keywords: Cherenkov detector; Cherenkov telescopes; CTA; GCT; IACT; Schwarzschild-Couder telescope

Optical intensity interferometry lab tests in preparation of stellar diameter measurements at IACTs at GHz photon rates - Zmija, Andreas; Vogel, Naomi; Anton, Gisela; Malyshev, Dmitry; Michel, Thilo; Zink, Adrian; Funk, Stefan (Monthly Notices of the Royal Astronomical Society, 2022)
Astronomical intensity interferometry enables quantitative measurements of the source geometry by measuring the photon fluxes in individual telescopes and correlating them, rather than correlating the electromagnetic waves' amplitudes. This simplifies the realization of large telescope baselines and high angular resolutions. Imaging Atmospheric Cherenkov Telescopes (IACTs), intended to detect the optical emission of γ-ray-induced air showers, are excellent candidates to perform intensity correlations in the optical at reasonable signal-to-noise ratios. The detected coherence time is on the scale of (10-12)-(10-15) s-depending on the optical bandwidth of the measurement-which challenges the detection system to work in a stable and accurate way. We developed an intensity interferometry set-up applicable to IACTs, which measures the photocurrents from photomultipliers and correlates them offline, and as such is designed to handle the very large photon rates provided by the telescopes. We present measurements in the lab simulating starlight using a xenon lamp and measured at different degrees of temporal and spatial coherence. Necessary calibration procedures are described with the goal of understanding the measurements quantitatively. Measured coherence times between 5 femtoseconds (corresponding signal-to-background ratio 5 × 10-7) and 110 femtoseconds (signal-to-background ratio 10-5) are in good agreement with expectations, and so are the noise levels in the correlations, reaching down to 6 × 10-8, after measurements between 30 min and 1 h.
CRIS-Team Scopus Importer:2021-12-24
Keywords: instrumentation: detectors; instrumentation: interferometers; stars: imaging; techniques: interferometric

OPTICAL SPECTROSCOPIC OBSERVATIONS OF BLAZARS AND gamma-RAY BLAZAR CANDIDATES IN THE SLOAN DIGITAL SKY SURVEY DATA RELEASE NINE - Massaro, F.; Masetti, N.; D'Abrusco, R.; Paggi, A.; Funk, Stefan (Astronomical Journal, 2014)
We present an analysis of the optical spectra available in the Sloan Digital Sky Survey data release nine (SDSS DR9) for the blazars listed in the ROMA-BZCAT and for the gamma-ray blazar candidates selected according to their IR colors. First, we adopt a statistical approach based on Monte Carlo simulations to find the optical counterparts of the blazars listed in the ROMA-BZCAT catalog. Then, we crossmatched the SDSS spectroscopic catalog with our selected samples of blazars and gamma-ray blazar candidates, searching for those with optical spectra available to classify our blazar-like sources and, whenever possible, to confirm their redshifts. Our main objectives are to determine the classification of uncertain blazars listed in the ROMA-BZCAT and to discover new gamma-ray blazars. For the ROMA-BZCAT sources, we investigated a sample of 84 blazars, confirming the classification for 20 of them and obtaining 18 new redshift estimates. For the gamma-ray blazars, indicated as potential counterparts of unassociated Fermi sources or with uncertain nature, we established the blazar-like nature of 8 out of the 27 sources analyzed and confirmed 14 classifications.
Keywords: galaxies: active; quasars: general; methods: statistical; radiation mechanisms: non-thermal; surveys

OPTICAL SPECTROSCOPIC OBSERVATIONS OF gamma-RAY BLAZAR CANDIDATES. I. PRELIMINARY RESULTS - Paggi, A.; Milisavljevic, D.; Masetti, N.; Jimenez-Bailon, E.; Chavushyan, V.; D'Abrusco, R.; Massaro, F.; Giroletti, M.; Smith, H. A.; Margutti, R.; Tosti, G.; Martinez-Galarza, J. R.; et al. (Astronomical Journal, 2014)
A significant fraction (similar to 30%) of the gamma-ray sources listed in the second Fermi/LAT (2FGL) catalog is still of unknown origin, being not yet associated with counterparts at lower energies. Using the available information at lower energies and optical spectroscopy on the selected counterparts of these gamma-ray objects, we can pinpoint their exact nature. Here, we present a pilot project pointing to assess the effectiveness of the several classification methods developed to select gamma-ray blazar candidates. To this end, we report optical spectroscopic observations of a sample of five gamma-ray blazar candidates selected on the basis of their infrared Wide-field Infrared Survey Explorer (WISE) colors or of their low-frequency radio properties. Blazars come in two main classes, BL Lac objects and FSRQs, showing similar optical spectra except for the stronger emission lines of the latter. For three of our sources, the almost featureless optical spectra obtained confirm their BL Lac nature, while for the source WISEJ022051.24+250927.6 we observe emission lines with equivalent width EW similar to 31 angstrom, identifying it as a FSRQ with z = 0.48. The source WISEJ064459.38+603131.7, although not featuring a clear radio counterpart, shows a blazar-like spectrum with weak emission lines with EW similar to 7 angstrom, yielding a redshift estimate of z = 0.36. In addition, we report optical spectroscopic observations of four WISE sources associated with known gamma-ray blazars without a firm classification or redshift estimate. For the latter sources, we confirm a BL Lac classification, with a tentative redshift estimate for the source WISEJ100800.81+062121.2 of z = 0.65.
Keywords: BL Lacertae objects: general; galaxies: active; radiation mechanisms: non-thermal

Particle transport within the pulsar wind nebula HESS J1825-137 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2019)
Context. We present a detailed view of the pulsar wind nebula (PWN) HESS J1825-137. We aim to constrain the mechanisms dominating the particle transport within the nebula, accounting for its anomalously large size and spectral characteristics. Aims. The nebula was studied using a deep exposure from over 12 years of H.E.S.S. I operation, together with data from H.E.S.S. II that improve the low-energy sensitivity. Enhanced energy-dependent morphological and spatially resolved spectral analyses probe the very high energy (VHE, E > 0.1 TeV) γ-ray properties of the nebula. Methods. The nebula emission is revealed to extend out to 1.5° from the pulsar, ∼1.5 times farther than previously seen, making HESS J1825-137, with an intrinsic diameter of ∼100 pc, potentially the largest γ-ray PWN currently known. Characterising the strongly energy-dependent morphology of the nebula enables us to constrain the particle transport mechanisms. A dependence of the nebula extent with energy of RE α with α = -0.29 ± 0.04 stat ± 0.05 sys disfavours a pure diffusion scenario for particle transport within the nebula. The total γ-ray flux of the nebula above 1 TeV is found to be (1.12 ± 0.03 stat ± 0.25 sys ) × 10 -11 cm -2 s -1 , corresponding to ∼64% of the flux of the Crab nebula. Results. HESS J1825-137 is a PWN with clearly energy-dependent morphology at VHE γ-ray energies. This source is used as a laboratory to investigate particle transport within intermediate-age PWNe. Based on deep observations of this highly spatially extended PWN, we produce a spectral map of the region that provides insights into the spectral variation within the nebula.
CRIS-Team Scopus Importer:2019-05-02
Keywords: gamma rays: general; acceleration of particles; convection; diffusion; pulsars: general

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Performance verification of the FlashCam prototype camera for the Cherenkov Telescope Array - Werner, F.; Bauer, C.; Bernhard, S.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; Garrecht, F.; et al. (ELSEVIER SCIENCE BV, 2017)
The Cherenkov Telescope Array (CTA) is a future gamma-ray observatory that is planned to significantly improve upon the sensitivity and precision of the current generation of Cherenkov telescopes. The observatory will consist of several dozens of telescopes with different sizes and equipped with different types of cameras. Of these, the FlashCam camera system is the first to implement a fully digital signal processing chain which allows for a traceable, configurable trigger scheme and flexible signal reconstruction. As of autumn 2016, a prototype FlashCam camera for the medium-sized telescopes of CTA nears completion. First results of the ongoing system tests demonstrate that the signal chain and the readout system surpass CTA requirements. The stability of the system is shown using long-term temperature cycling.
Keywords: Gamma-ray astronomy; Cherenkov camera; Performance verification; Temperature stability; CTA; MST; FlashCam

Periodic Emission from the Gamma-Ray Binary 1FGL J1018.6-5856 - Ackermann, Markus; Ajello, Marco; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Belfiore, Andrea; Bellazzini, R.; Berenji, B.; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Science, 2012)
Gamma-ray binaries are stellar systems containing a neutron star or black hole, with gamma-ray emission produced by an interaction between the components. These systems are rare, even though binary evolution models predict dozens in our Galaxy. A search for gamma-ray binaries with the Fermi Large Area Telescope (LAT) shows that 1FGL J1018.6-5856 exhibits intensity and spectral modulation with a 16.6-day period. We identified a variable x-ray counterpart, which shows a sharp maximum coinciding with maximum gamma-ray emission, as well as an O6V((f)) star optical counterpart and a radio counterpart that is also apparently modulated on the orbital period. 1FGL J1018.6-5856 is thus a gamma-ray binary, and its detection suggests the presence of other fainter binaries in the Galaxy.
CRIS-Team WoS Importer:2020-01-15

PKS 1502+106: A NEW AND DISTANT GAMMA-RAY BLAZAR IN OUTBURST DISCOVERED BY THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2010)
The Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope discovered a rapid (similar to 5 days duration), high-energy (E > 100 MeV) gamma-ray outburst from a source identified with the blazar PKS 1502+106 (OR 103, S3 1502+10, z = 1.839) starting on 2008 August 5 (similar to 23 UTC, MJD 54683.95), and followed by bright and variable flux over the next few months. Results on the gamma-ray localization and identification, as well as spectral and temporal behavior during the first months of the Fermi all-sky survey, are reported here in conjunction with a multiwaveband characterization as a result of one of the first Fermi multifrequency campaigns. The campaign included a Swift ToO (followed up by a 16 day observation on August 7-22, MJD 54685-54700), VLBA (within the MOJAVE program), Owens Valley Radio Observatory (OVRO) 40 m, Effelsberg-100 m, Metsahovi-14 m, RATAN-600, and Kanata-Hiroshima radio/optical observations. Results from the analysis of archival observations by INTEGRAL, XMM-Newton, and Spitzer space telescopes are reported for a more complete picture of this new gamma-ray blazar. PKS 1502+106 is a sub-GeV peaked, powerful flat spectrum radio quasar (luminosity at E > 100 MeV, L-gamma, is about 1.1 x 10(49) erg s(-1), and black hole mass likely close to 10(9) M-circle dot), exhibiting marked gamma-ray bolometric dominance, in particular during the asymmetric outburst (L-gamma/L-opt similar to 100, and 5 day averaged flux F-E > 100MeV = 2.91 +/- 1.4 x 10(-6) ph cm(-2) s(-1)), which was characterized by a factor greater than 3 of flux increase in less than 12 hr. The outburst was observed simultaneously from optical to X-ray bands (F0.3-10keV = 2.18(-0.12)(+0.15) x 10(-12) erg cm(-2) s(-1), and hard photon index similar to 1.5, similar to past values) with a flux increase of less than 1 order of magnitude with respect to past observations, and was likely controlled by Comptonization of external-jet photons produced in the broad-line region (BLR) in the gamma-ray band. No evidence of a possible blue bump signature was observed in the optical-UV continuum spectrum, while some hints for a possible 4 day time lag with respect to the gamma-ray flare were found. Nonetheless, the properties of PKS 1502+106 and the strict optical/UV, X-, and gamma-ray cross-correlations suggest the contribution of the synchrotron self-Compton (SSC), in-jet, process should dominate from radio to X- rays. This mechanism may also be responsible for the consistent gamma-ray variability observed by the LAT on longer timescales, after the ignition of activity at these energies provided by the BLR-dissipated outburst. Modulations and subsequent minor, rapid flare events were detected, with a general fluctuation mode between pink-noise and a random-walk. The averaged gamma-ray spectrum showed a deviation from a simple power law, and can be described by a log-parabola curved model peaking around 0.4-0.5 GeV. The maximum energy of photons detected from the source in the first four months of LAT observations was 15.8 GeV, with no significant consequences on extragalactic background light predictions. A possible radio counterpart of the gamma-ray outburst can be assumed only if a delay of more than three months is considered on the basis of opacity effects at cm and longer wavelengths.
CRIS-Team WoS Importer:2020-01-15

Population study of Galactic supernova remnants at very high gamma-ray energies with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Shell-type supernova remnants (SNRs) are considered prime candidates for the acceleration of Galactic cosmic rays (CRs) up to the knee of the CR spectrum at E approximate to 3 x 10(15) eV. Our MilkyWay galaxy hosts more than 350 SNRs discovered at radio wavelengths and at high energies, of which 220 fall into the H.E.S.S. Galactic Plane Survey (HGPS) region. Of those, only 50 SNRs are coincident with a H.E.S.S source and in 8 cases the very high-energy (VHE) emission is firmly identified as an SNR. The H.E.S.S. GPS provides us with a legacy for SNR population study in VHE gamma-rays and we use this rich data set to extract VHE flux upper limits from all undetected SNRs. Overall, the derived flux upper limits are not in contradiction with the canonical CR paradigm. Assuming this paradigm holds true, we can constrain typical ambient density values around shell-type SNRs to n <= 7 cm(-3) and electron-to-proton energy fractions above 10 TeV to epsilon(ep) <= 5 x 10(-3). Furthermore, comparisons of VHE with radio luminosities in non-interacting SNRs reveal a behaviour that is in agreement with the theory of magnetic field amplification at shell-type SNRs.
Keywords: gamma rays: general; ISM: supernova remnants

Precision measurement of optical pulsation using a Cherenkov telescope - Funk, Stefan; et al. (Astroparticle Physics, 2006)
During 2003, a camera designed to measure the optical pulsations of pulsars was installed on a telescope of the H.E.S.S. array. The array is designed for gamma-ray astronomy in the similar to 100 GeV-100 TeV energy regime. The aims of this exercise were two-fold: to prove the pulsar timing capabilities of H.E.S.S. on all relevant time-scales, and to explore the possibility of performing sensitive optical pulsar measurements using the similar to 100m(2) mirror of a Cherenkov telescope. Measurements of the Crab pulsar with this instrument demonstrate an order of magnitude sensitivity improvement over previous attempts using Cherenkov telescopes. Here we describe the design and performance of the system and discuss design considerations for future instruments of this type. (c) 2006 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Preliminary results of the LAT calibration unit beam tests - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

Prospects for Cherenkov Telescope Array Observations of the Young Supernova Remnant RX J1713.73946 - Acero, F.; Aloisio, R.; Amans, J.; Amato, E.; Antonelli, L. A.; Aramo, C.; Armstrong, T.; Arqueros, F.; Asano, K.; Ashley, M.; Backes, M.; Balazs, C.; et al. (Astrophysical Journal, 2017)
Keywords: cosmic rays; gamma rays: ISM; ISM: individual objects: RX J1713.7 dash3946; G347.3 dash0.5

PSR J1907+0602: A RADIO-FAINT GAMMA-RAY PULSAR POWERING A BRIGHT TeV PULSAR WIND NEBULA - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2010)
We present multiwavelength studies of the 106.6 ms gamma-ray pulsar PSR J1907+06 near the TeV source MGRO J1908+06. Timing observations with Fermi result in a precise position determination for the pulsar of R.A. = 19(h)07(m)54.(s)7(2), decl. = +06 degrees 02'16(2)'' placing the pulsar firmly within the TeV source extent, suggesting the TeV source is the pulsar wind nebula of PSR J1907+0602. Pulsed gamma-ray emission is clearly visible at energies from 100 MeV to above 10 GeV. The phase-averaged power-law index in the energy range E > 0.1 GeV is Gamma = 1.76 +/- 0.05 with an exponential cutoff energy E-c = 3.6 +/- 0.5 GeV. We present the energy-dependent gamma-ray pulsed light curve as well as limits on off-pulse emission associated with the TeV source. We also report the detection of very faint (flux density of similar or equal to 3.4 mu Jy) radio pulsations with the Arecibo telescope at 1.5 GHz having a dispersion measure DM = 82.1 +/- 1.1 cm(-3) pc. This indicates a distance of 3.2 +/- 0.6 kpc and a pseudo-luminosity of L-1400 similar or equal to 0.035 mJy kpc(2). A Chandra ACIS observation revealed an absorbed, possibly extended, compact (less than or similar to 4 '') X-ray source with significant nonthermal emission at R.A. = 19(h)07(m)54.(s)76, decl. = + 06 degrees 02'14.'' 6 with a flux of 2.3(-1.4)(+0.6) x 10(-14) erg cm(-2) s(-1). From archival ASCA observations, we place upper limits on any arcminute scale 2-10 keV X-ray emission of similar to 1 x 10(-13) erg cm(-2) s(-1). The implied distance to the pulsar is compatible with that of the supernova remnant G40.5-0.5, located on the far side of the TeV nebula from PSR J1907+0602, and the S74 molecular cloud on the nearer side which we discuss as potential birth sites.
CRIS-Team WoS Importer:2020-01-15

PULSED GAMMA-RAYS FROM PSR J2021+3651 WITH THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Battelino, M.; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
We report the detection of pulsed gamma-rays from the young, spin-powered radio pulsar PSR J2021+3651 using data acquired with the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope (formerly GLAST). The light curve consists of two narrow peaks of similar amplitude separated by 0.468 +/- 0.002 in phase. The first peak lags the maximum of the 2 GHz radio pulse by 0.162 +/- 0.004 +/- 0.01 in phase. The integral gamma-ray photon flux above 100 MeV is (56 +/- 3 +/- 11) x 10(-8) cm(-2) s(-1). The photon spectrum is well described by an exponentially cut-off power law of the form dF/dE = kE(-Gamma)e((-E/Ec)), where the energy E is expressed in GeV. The photon index is Gamma = 1.5 +/- 0.1 +/- 0.1 and the exponential cut-off is E-c = 2.4 +/- 0.3 +/- 0.5 GeV. The first uncertainty is statistical and the second is systematic. The integral photon flux of the bridge is approximately 10% of the pulsed emission, and the upper limit on off-pulse gamma-ray emission from a putative pulsar wind nebula is < 10% of the pulsed emission at the 95% confidence level. Radio polarization measurements yield a rotation measure of RM = 524 +/- 4 rad m(-2) but a poorly constrained magnetic geometry. Re-analysis of Chandra X-ray Observatory data enhanced the significance of the weak X-ray pulsations, and the first peak is roughly phase aligned with the first gamma-ray peak. We discuss the emission region and beaming geometry based on the shape and spectrum of the gamma-ray light curve combined with radio and X-ray measurements, and the implications for the pulsar distance. Gamma-ray emission from the polar cap region seems unlikely for this pulsar.
CRIS-Team WoS Importer:2020-01-15

PULSED GAMMA RAYS FROM THE MILLISECOND PULSAR J0030+0451 WITH THE FERMI LARGE AREA TELESCOPE - Abdo, A. A.; Ackermann, Markus; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Battelino, M.; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2009)
We report the discovery of gamma-ray pulsations from the nearby isolated millisecond pulsar (MSP) PSR J0030+0451 with the Large Area Telescope on the Fermi Gamma-ray Space Telescope (formerly GLAST). This discovery makes PSR J0030+0451 the second MSP to be detected in gamma rays after PSR J0218+4232, observed by the EGRET instrument on the Compton Gamma-Ray Observatory. The spin-down power (E) over dot = 3.5 x 10(33) erg s(-1) is an order of magnitude lower than the empirical lower bound of previously known gamma-ray pulsars. The emission profile is characterized by two narrow peaks, 0.07 +/- 0.01 and 0.08 +/- 0.02 wide, respectively, separated by 0.44 +/- 0.02 in phase. The first gamma-ray peak falls 0.15 +/- 0.01 after the main radio peak. The pulse shape is similar to that of the "normal" gamma-ray pulsars. An exponentially cutoff power-law fit of the emission spectrum leads to an integral photon flux above 100 MeV of (6.76 +/- 1.05 +/- 1.35) x 10(-8) cm(-2) s(-1) with cutoff energy (1.7 +/- 0.4 +/- 0.5) GeV. Based on its parallax distance of (300 +/- 90) pc, we obtain a gamma-ray efficiency L-gamma/E similar or equal to 15% for the conversion of spin-down energy rate into gamma-ray radiation, assuming isotropic emission.
CRIS-Team WoS Importer:2020-01-15

Quantum gravity phenomenology at the dawn of the multi-messenger era—A review - Addazi, A.; Alvarez-Muniz, J.; Alves Batista, R.; Amelino-Camelia, G.; Antonelli, V.; Arzano, M.; Asorey, M.; Atteia, J. L.; Bahamonde, S.; Bajardi, F.; Ballesteros, A.; Baret, B.; et al. (Progress in Particle and Nuclear Physics, 2022)
The exploration of the universe has recently entered a new era thanks to the multi-messenger paradigm, characterized by a continuous increase in the quantity and quality of experimental data that is obtained by the detection of the various cosmic messengers (photons, neutrinos, cosmic rays and gravitational waves) from numerous origins. They give us information about their sources in the universe and the properties of the intergalactic medium. Moreover, multi-messenger astronomy opens up the possibility to search for phenomenological signatures of quantum gravity. On the one hand, the most energetic events allow us to test our physical theories at energy regimes which are not directly accessible in accelerators; on the other hand, tiny effects in the propagation of very high energy particles could be amplified by cosmological distances. After decades of merely theoretical investigations, the possibility of obtaining phenomenological indications of Planck-scale effects is a revolutionary step in the quest for a quantum theory of gravity, but it requires cooperation between different communities of physicists (both theoretical and experimental). This review, prepared within the COST Action CA18108 “Quantum gravity phenomenology in the multi-messenger approach”, is aimed at promoting this cooperation by giving a state-of-the art account of the interdisciplinary expertise that is needed in the effective search of quantum gravity footprints in the production, propagation and detection of cosmic messengers.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Cosmic neutrinos; Gamma-ray astronomy; Gravitational waves; Lorentz invariance violation and deformation; Ultra-high-energy cosmic rays

RADIO AND gamma-RAY CONSTRAINTS ON THE EMISSION GEOMETRY AND BIRTHPLACE OF PSR J2043+2740 - Noutsos, A.; Abdo, A. A.; Ackermann, Markus; Ajello, M.; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bonamente, E.; et al. (Astrophysical Journal, 2011)
We report on the first year of Fermi gamma-ray observations of pulsed high-energy emission from the old PSR J2043 + 2740. The study of the gamma-ray efficiency of such old pulsars gives us an insight into the evolution of pulsars' ability to emit in gamma rays as they age. The gamma-ray light curve of this pulsar above 0.1 GeV is clearly defined by two sharp peaks, 0.353 +/- 0.035 periods apart. We have combined the gamma-ray profile characteristics of PSR J2043 + 2740 with the geometrical properties of the pulsar's radio emission, derived from radio-polarization data, and constrained the pulsar-beam geometry in the framework of a two-pole caustic (TPC) and an outer gap (OG) model. The ranges of magnetic inclination and viewing angle were determined to be alpha, zeta similar to 52 degrees-57 degrees, 61 degrees-68 degrees for the TPC model, and alpha, zeta similar to 62 degrees-73 degrees, 74 degrees-81 degrees and alpha, zeta similar to 72 degrees-83 degrees, 60 degrees-75 degrees for the OG model. Based on this geometry, we assess possible birth locations for this pulsar and derive a likely proper motion, sufficiently high to be measurable with VLBI. At a characteristic age of 1.2 Myr, PSR J2043 + 2740 is the third oldest of all discovered, non-recycled, gamma-ray pulsars: it is twice as old as the next oldest, PSR J0357 + 32, and younger only than the recently discovered PSR J1836 + 5925 and PSR J2055 + 25, both of which are at least five and ten times less energetic, respectively.
CRIS-Team WoS Importer:2020-01-15

Radio and X-ray Observations of the Possible New Gamma-ray binary HESS J0632+057 - Skilton, J. L.; Hinton, J. A.; Brucker, Julia; Pandey-Pommier, M.; Cheung, C. C.; Aharonian, F. A.; Dubus, G.; Fiasson, A.; Funk, Stefan; Gallant, Y.; Marcowith, A.; Reimer, Olaf (HIGH ENERGY PHENOMENA IN MASSIVE STARS, 2010)
CRIS-Team WoS Importer:2020-01-15

Readout electronics testing during mass production of FlashCam cameras for the Cherenkov Telescope Array - Diebold, S.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Capasso, M.; Eisenkolb, F.; Eschbach, Stefan; Florin, D.; Foehr, C.; Funk, Stefan; Gadola, A.; et al. (OPTICS FOR EUV, X-RAY, AND GAMMA-RAY ASTRONOMY VIII, 2017)
CRIS-Team WoS Importer:2020-01-15

Resolving the Crab pulsar wind nebula at teraelectronvolt energies - Abdalla, H.; Aharonian, F.; Ait Benkhali, F.; Angüner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Backes, M.; Barnard, M.; Becherini, Y.; Becker Tjus, J.; Berge, D.; et al. (Nature Astronomy, 2019)
The Crab nebula is one of the most-studied cosmic particle accelerators, shining brightly across the entire electromagnetic spectrum up to very-high-energy gamma rays1,2. It is known from observations in the radio to gamma-ray part of the spectrum that the nebula is powered by a pulsar, which converts most of its rotational energy losses into a highly relativistic outflow. This outflow powers a pulsar wind nebula, a region of up to ten light-years across, filled with relativistic electrons and positrons. These particles emit synchrotron photons in the ambient magnetic field and produce very-high-energy gamma rays by Compton up-scattering of ambient low-energy photons. Although the synchrotron morphology of the nebula is well established, it has not been known from which region the very-high-energy gamma rays are emitted3–8. Here we report that the Crab nebula has an angular extension at gamma-ray energies of 52 arcseconds (assuming a Gaussian source width), much larger than at X-ray energies. This result closes a gap in the multi-wavelength coverage of the nebula, revealing the emission region of the highest-energy gamma rays. These gamma rays enable us to probe a previously inaccessible electron and positron energy range. We find that simulations of the electromagnetic emission reproduce our measurement, providing a non-trivial test of our understanding of particle acceleration in the Crab nebula.
CRIS-Team Scopus Importer:2019-11-15

Resolving the extragalactic γ-ray background above 50 GeV with the fermi large area telescope - Reposeur, T.; Di Mauro, M.; Zimmer, S.; Negro, M.; La Mura, G.; Sanchez-Conde, M.; Britto, R. J.; Cavazzuti, E.; Bonino, R.; Iafrate, G.; Moskalenko, I. V.; Orlando, E.; et al. (Physical Review Letters, 2016)
The Fermi Large Area Telescope (LAT) Collaboration has recently released a catalog of 360 sources detected above 50 GeV (2FHL). This catalog was obtained using 80 months of data re-processed with Pass 8, the newest event-level analysis, which significantly improves the acceptance and angular resolution of the instrument. Most of the 2FHL sources at high Galactic latitude are blazars. Using detailed Monte Carlo simulations, we measure, for the first time, the source count distribution, dN= dS, of extragalactic.-ray sources at E > 50 GeV and find that it is compatible with a Euclidean distribution down to the lowest measured source flux in the 2FHL (8 x 10(-12) ph cm(-2) s(-1)). We employ a one-point photon fluctuation analysis to constrain the behavior of dN= dS below the source detection threshold. Overall, the source count distribution is constrained over three decades in flux and found compatible with a broken power law with a break flux, Sb, in the range [8 x 10-12; 1.5 x 10-11] ph cm(-2) s(-1) and power-law indices below and above the break of a 2. [1.60; 1.75] and a 1 +/- 2.49 +/- 0.12, respectively. Integration of dN= dS shows that point sources account for at least 86_16 -14 % of the total extragalactic gamma-ray background. The simple form of the derived source count distribution is consistent with a single population (i. e., blazars) dominating the source counts to the minimum flux explored by this analysis. We estimate the density of sources detectable in blind surveys that will be performed in the coming years by the Cherenkov Telescope Array.

Results from the HESS Galactic plane survey - Funk, Stefan (Proceedings of the 29th International Cosmic Ray Conference, Vol 4: OG 2.1, 2.2 & 2.3, 2005)
CRIS-Team WoS Importer:2020-01-15

REVEALING W51C AS A COSMIC RAY SOURCE USING FERMI-LAT DATA - Jogler, T.; Funk, Stefan (Astrophysical Journal, 2016)
Supernova remnants (SNRs) are commonly believed to be the primary sources of Galactic cosmic rays. Despite intensive study of the non-thermal emission of many SNRs the identification of the accelerated particle type relies heavily on assumptions of ambient-medium parameters that are only loosely constrained. Compelling evidence of hadronic acceleration can be provided by detecting a strong roll-off in the secondary γ-ray spectrum below the production threshold energy of about 135 MeV, the so called "pion bump." Here we use five years of Fermi-Large Area Telescope data to study the spectrum above 60 MeV of the middle-aged SNR W51C. A clear break in the power-law γ-ray spectrum at is detected with significance and we show that this break is most likely associated with the energy production threshold of mesons. A high-energy break in the γ-ray spectrum at about 2.7 GeV is found with significance. The spectral index at energies beyond this second break is and closely matches the spectral index derived by the MAGIC Collaboration above 75 GeV. Therefore our analysis provides strong evidence to explain the γ-ray spectrum of W51C by a single particle population of protons with a momentum spectrum best described by a broken power law with break momentum W51C is the third middle-aged SNR that displays compelling evidence for cosmic-ray acceleration and thus strengthens the case of SNRs as the main source of Galactic cosmic rays.
Keywords: astroparticle physics; gamma-rays: general; ISM: supernova remnants

Revealing x-ray and gamma ray temporal and spectral similarities in the GRB 190829A afterglow - Taylor, Andrew M.; Aharonian, Felix; Romoli, Carlo; Khangulyan, Dmitry; Ruiz-Velasco, Edna; Schüssler, Fabian; Zhu, Sylvia J.; Büchele, Matthias; Eichhorn, Florian; Funk, Stefan; Glawion, Dorit; Jankowsky, David; et al. (Science, 2021)
Gamma-ray bursts (GRBs), which are bright flashes of gamma rays from extragalactic sources followed by fading afterglow emission, are associated with stellar core collapse events. We report the detection of very-high-energy (VHE) gamma rays from the afterglow of GRB 190829A, between 4 and 56 hours after the trigger, using the High Energy Stereoscopic System (H.E.S.S.). The low luminosity and redshift of GRB 190829A reduce both internal and external absorption, allowing determination of its intrinsic energy spectrum. Between energies of 0.18 and 3.3 tera-electron volts, this spectrum is described by a power law with photon index of 2.07 ± 0.09, similar to the x-ray spectrum. The x-ray and VHE gamma-ray light curves also show similar decay profiles. These similar characteristics in the x-ray and gamma-ray bands challenge GRB afterglow emission scenarios.
CRIS-Team Scopus Importer:2021-06-18

Science with e-ASTROGAM A space mission for MeV-GeV gamma-ray astrophysics - Funk, Stefan; et al. (Journal of High Energy Astrophysics, 2018)
e-ASTROGAM ('enhanced ASTROGAM') is a breakthrough Observatory space mission, with a detector composed by a Silicon tracker, a calorimeter, and an anticoincidence system, dedicated to the study of the non-thermal Universe in the photon energy range from 0.3 MeV to 3 GeV - the lower energy limit can be pushed to energies as low as 150 keV for the tracker, and to 30 keV for calorimetric detection. The mission is based on an advanced space-proven detector technology, with unprecedented sensitivity, angular and energy resolution, combined with polarimetric capability. Thanks to its performance in the MeV-GeV domain, substantially improving its predecessors, e-ASTROGAM will open a new window on the non-thermal Universe, making pioneering observations of the most powerful Galactic and extragalactic sources, elucidating the nature of their relativistic outflows and their effects on the surroundings. With a line sensitivity in the MeV energy range one to two orders of magnitude better than previous generation instruments, e-ASTROGAM will determine the origin of key isotopes fundamental for the understanding of supernova explosion and the chemical evolution of our Galaxy. The mission will provide unique data of significant interest to a broad astronomical community, complementary to powerful observatories such as LIGO-Virgo-GEO600-KAGRA, SKA, ALMA, E-ELT, TMT, LSST, JWST, Athena, CTA, IceCube, KM3NeT, and LISA. (C) 2018 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Searches for cosmic-ray electron anisotropies with the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Bloom, E. D.; Bonamente, E.; et al. (Physical Review D, 2010)
The Large Area Telescope on board the Fermi satellite (Fermi LAT) detected more than 1.6 x 10(6) cosmic-ray electrons/positrons with energies above 60 GeV during its first year of operation. The arrival directions of these events were searched for anisotropies of angular scale extending from similar to 10 degrees up to 90 degrees, and of minimum energy extending from 60 GeV up to 480 GeV. Two independent techniques were used to search for anisotropies, both resulting in null results. Upper limits on the degree of the anisotropy were set that depended on the analyzed energy range and on the anisotropy's angular scale. The upper limits for a dipole anisotropy ranged from similar to 0.5% to similar to 10%.
CRIS-Team WoS Importer:2020-01-15

Searches for gamma-ray lines and 'pure WIMP' spectra from Dark Matter annihilations in dwarf galaxies with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Journal of Cosmology and Astroparticle Physics, 2018)
Dwarf spheroidal galaxies are among the most promising targets for detecting signals of Dark Matter (DM) annihilations. The H.E.S.S. experiment has observed five of these systems for a total of about 130 hours. The data are re-analyzed here, and, in the absence of any detected signals, are interpreted in terms of limits on the DM annihilation cross section. Two scenarios are considered: i) DM annihilation into mono-energetic gamma-rays and ii) DM in the form of pure WIMP multiplets that, annihilating into all electroweak bosons, produce a distinctive gamma-ray spectral shape with a high-energy peak at the DM mass and a lower-energy continuum. For case i), upper limits at 95% confidence level of about less than or similar to 3 x 10(-25) cm(3) s(-1) are obtained in the mass range of 400 GeV to 1TeV. For case ii), the full spectral shape of the models is used and several excluded regions are identified, but the thermal masses of the candidates are not robustly ruled out.
CRIS-Team WoS Importer:2020-01-15

Search for Cosmic-Ray Electron and Positron Anisotropies with Seven Years of Fermi Large Area Telescope Data - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Physical Review Letters, 2017)
The Large Area Telescope on board the Fermi Gamma-ray Space Telescope has collected the largest ever sample of high-energy cosmic-ray electron and positron events since the beginning of its operation. Potential anisotropies in the arrival directions of cosmic-ray electrons or positrons could be a signature of the presence of nearby sources. We use almost seven years of data with energies above 42 GeV processed with the Pass 8 reconstruction. The present data sample can probe dipole anisotropies down to a level of 10(-3). We take into account systematic effects that could mimic true anisotropies at this level. We present a detailed study of the event selection optimization of the cosmic-ray electrons and positrons to be used for anisotropy searches. Since no significant anisotropies have been detected on any angular scale, we present upper limits on the dipole anisotropy. The present constraints are among the strongest to date probing the presence of nearby young and middle-aged sources.
CRIS-Team WoS Importer:2020-01-15

SEARCH FOR COSMIC-RAY-INDUCED GAMMA-RAY EMISSION IN GALAXY CLUSTERS - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bloom, E. D.; et al. (Astrophysical Journal, 2014)
Current theories predict relativistic hadronic particle populations in clusters of galaxies in addition to the already observed relativistic leptons. In these scenarios hadronic interactions give rise to neutral pions which decay into gamma rays that are potentially observable with the Large Area Telescope (LAT) on board the Fermi space telescope. We present a joint likelihood analysis searching for spatially extended gamma-ray emission at the locations of 50 galaxy clusters in four years of Fermi-LAT data under the assumption of the universal cosmic-ray (CR) model proposed by Pinzke & Pfrommer. We find an excess at a significance of 2.7 sigma, which upon closer inspection, however, is correlated to individual excess emission toward three galaxy clusters: A400, A1367, and A3112. We discuss these cases in detail and conservatively attribute the emission to unmodeled background systems (for example, radio galaxies within the clusters). Through the combined analysis of 50 clusters, we exclude hadronic injection efficiencies in simple hadronic models above 21% and establish limits on the CR to thermal pressure ratio within the virial radius, R-200, to be below 1.25%-1.4% depending on the morphological classification. In addition, we derive new limits on the gamma-ray flux from individual clusters in our sample.
Keywords: galaxies: clusters: intracluster medium; gamma rays: galaxies: clusters

Search for Dark Matter Annihilation Signals from Unidentified Fermi-LAT Objects with HESS - Abdalla, H.; Spencer, Samuel; Aharonian, Felix; Ait Benkhali, F.; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Barbosa-Martins, V.; et al. (Astrophysical Journal, 2021)
Cosmological N-body simulations show that Milky Way-sized galaxies harbor a population of unmerged dark matter (DM) subhalos. These subhalos could shine in gamma-rays and eventually be detected in gamma-ray surveys as unidentified sources. We performed a thorough selection among unidentified Fermi-Large Area Telescope Objects (UFOs) to identify them as possible tera-electron-volt-scale DM subhalo candidates. We search for very-high-energy (E greater than or similar to 100 GeV) gamma-ray emissions using H.E.S.S. observations toward four selected UFOs. Since no significant very-high-energy gamma-ray emission is detected in any data set of the four observed UFOs or in the combined UFO data set, strong constraints are derived on the product of the velocity-weighted annihilation cross section sigma v by the J factor for the DM models. The 95% confidence level observed upper limits derived from combined H.E.S.S. observations reach sigma vJ values of 3.7 x 10(-5) and 8.1 x 10(-6) GeV(2 )cm(-2 )s(-1) in the W (+) W (-) and tau (+) tau (-) channels, respectively, for a 1 TeV DM mass. Focusing on thermal weakly interacting massive particles, the H.E.S.S. constraints restrict the J factors to lie in the range 6.1 x 10(19)-2.0 x 10(21) GeV(2 )cm(-5) and the masses to lie between 0.2 and 6 TeV in the W (+) W (-) channel. For the tau (+) tau (-) channel, the J factors lie in the range 7.0 x 10(19)-7.1 x 10(20) GeV(2 )cm(-5) and the masses lie between 0.2 and 0.5 TeV. Assuming model-dependent predictions from cosmological N-body simulations on the J-factor distribution for Milky Way-sized galaxies, the DM models with masses >0.3 TeV for the UFO emissions can be ruled out at high confidence level.
CRIS-Team WoS Importer:2021-09-10

Search for Dark Matter Annihilation Signals in the H.E.S.S. Inner Galaxy Survey - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Angüner, E. O.; Armand, C.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; et al. (Physical Review Letters, 2022)
The central region of the Milky Way is one of the foremost locations to look for dark matter (DM) signatures. We report the first results on a search for DM particle annihilation signals using new observations from an unprecedented γ-ray survey of the Galactic Center (GC) region, i.e., the Inner Galaxy Survey, at very high energies (?100 GeV) performed with the H.E.S.S. array of five ground-based Cherenkov telescopes. No significant γ-ray excess is found in the search region of the 2014-2020 dataset and a profile likelihood ratio analysis is carried out to set exclusion limits on the annihilation cross section ?σv?
CRIS-Team Scopus Importer:2022-09-30

Search for Dark Matter Annihilations towards the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Anguener, E.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2016)
The inner region of the Milky Way halo harbors a large amount of dark matter (DM). Given its proximity, it is one of the most promising targets to look for DM. We report on a search for the annihilations of DM particles using gamma-ray observations towards the inner 300 pc of the Milky Way, with the H.E.S.S. array of ground-based Cherenkov telescopes. The analysis is based on a 2D maximum likelihood method using Galactic Center (GC) data accumulated by H.E.S.S. over the last 10 years (2004-2014), and does not show any significant gamma-ray signal above background. Assuming Einasto and Navarro-Frenk-White DM density profiles at the GC, we derive upper limits on the annihilation cross section <sigma nu="">. These constraints are the strongest obtained so far in the TeV DM mass range and improve upon previous limits by a factor 5. For the Einasto profile, the constraints reach <sigma nu=""> values of 6 x 10(-26) cm(3) s(-1) in the W+W- channel for a DM particle mass of 1.5 TeV, and 2 x 10(-26) cm(3) s(-1) in the tau(+)tau(-) channel for a 1 TeV mass. For the first time, ground-based gamma-ray observations have reached sufficient sensitivity to probe <sigma nu=""> values expected from the thermal relic density for TeV DM particles.</sigma></sigma></sigma>

SEARCH FOR DARK MATTER SATELLITES USING FERMI-LAT - Ackermann, Markus; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; Bonamente, E.; Borgland, A. W.; et al. (Astrophysical Journal, 2012)
Numerical simulations based on the ACDM model of cosmology predict a large number of as yet unobserved Galactic dark matter satellites. We report the results of a Large Area Telescope (LAT) search for these satellites via the gamma-ray emission expected from the annihilation of weakly interacting massive particle (WIMP) dark matter. Some dark matter satellites are expected to have hard gamma-ray spectra, finite angular extents, and a lack of counterparts at other wavelengths. We sought to identify LAT sources with these characteristics, focusing on gamma-ray spectra consistent with WIMP annihilation through the b (b) over bar channel. We found no viable dark matter satellite candidates using one year of data, and we present a framework for interpreting this result in the context of numerical simulations to constrain the velocity-averaged annihilation cross section for a conventional 100 GeV WIMP annihilating through the b (b) over bar channel.
CRIS-Team WoS Importer:2020-01-15

SEARCH FOR EARLY GAMMA-RAY PRODUCTION IN SUPERNOVAE LOCATED IN A DENSE CIRCUMSTELLAR MEDIUM WITH THE FERMI LAT - Ackermann, M.; Arcavi, I.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Astrophysical Journal, 2015)
Supernovae (SNe) exploding in a dense circumstellar medium (CSM) are hypothesized to accelerate cosmic rays in collisionless shocks and emit GeV gamma-rays and TeV neutrinos on a timescale of several months. We perform the first systematic search for gamma-ray emission in Fermi Large Area Telescope data in the energy range from 100 MeV to 300 GeV from the ensemble of 147 SNe Type IIn exploding in a dense CSM. We search for a gamma-ray excess at each SNe location in a one-year time window. In order to enhance a possible weak signal, we simultaneously study the closest and optically brightest sources of our sample in a joint-likelihood analysis in three different time windows (1 year, 6 months, and 3 months). For the most promising source of the sample, SN 2010jl (PTF 10aaxf), we repeat the analysis with an extended time window lasting 4.5 years. We do not find a significant excess in gamma-rays for any individual source nor for the combined sources and provide model-independent flux upper limits for both cases. In addition, we derive limits on the gamma-ray luminosity and the ratio of gamma-ray-to-optical luminosity ratio as a function of the index of the proton injection spectrum assuming a generic gamma-ray production model. Furthermore, we present detailed flux predictions based on multi-wavelength observations and the corresponding flux upper limit at a 95% confidence level (CL) for the source SN 2010jl (PTF 10aaxf).
Keywords: cosmic rays; gamma rays: general; methods: data analysis; supernovae: general

SEARCH FOR EXTENDED GAMMA-RAY EMISSION FROM THE VIRGO GALAXY CLUSTER WITH FERMI-LAT - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2015)
Galaxy clusters are one of the prime sites to search for dark matter (DM) annihilation signals. Depending on the substructure of the DM halo of a galaxy cluster and the cross sections for DM annihilation channels, these signals might be detectable by the latest generation of gamma-ray telescopes. Here we use three years of Fermi-Large Area Telescope data, which are the most suitable for searching for very extended emission in the vicinity of the nearby Virgo galaxy cluster. Our analysis reveals statistically significant extended emission which can be well characterized by a uniformly emitting disk profile with a radius of 3 degrees that moreover is offset from the cluster center. We demonstrate that the significance of this extended emission strongly depends on the adopted interstellar emission model (IEM) and is most likely an artifact of our incomplete description of the IEM in this region. We also search for and find new point source candidates in the region. We then derive conservative upper limits on the velocity-averaged DM pair annihilation cross section from Virgo. We take into account the potential gamma-ray flux enhancement due to DM sub-halos and its complex morphology as a merging cluster. For DM annihilating into b (b) over bar, assuming a conservative sub-halo model setup, we find limits that are between 1 and 1.5 orders of magnitude above the expectation from the thermal cross section for m(DM) <= 100 GeV. In a more optimistic scenario, we exclude similar to 3 x 10(-26)cm(3)s(-1) for m(DM)less than or similar to 40 GeV for the same channel. Finally, we derive upper limits on the gamma-ray-flux produced by hadronic cosmic-ray interactions in the inter cluster medium. We find that the volume-averaged cosmic-ray-to-thermal pressure ratio is less than similar to 6%.
CRIS-Team WoS Importer:2020-01-15

Search for Extended Sources in the Galactic Plane Using Six Years of Fermi-Large Area Telescope Pass 8 Data above 10GeV - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; Brandt, T. J.; et al. (Astrophysical Journal, 2017)
The spatial extension of gamma-ray source is an essential ingredient to determine its spectral properties, as well as its potential multiwavelength counterpart. The capability to spatially resolve gamma-ray sources is greatly improved by the newly delivered Fermi-Large Area Telescope (LAT) Pass 8 event-level analysis, which provides a greater acceptance and an improved point-spread function, two crucial factors for the detection of extended sources. Here, we present a complete search for extended sources located within 7 degrees from the Galactic plane, using 6 yr of Fermi-LAT data above 10 GeV. We find 46 extended sources and provide their morphological and spectral characteristics. This constitutes the first catalog of hard Fermi-LAT extended sources, named the Fermi Galactic Extended Source Catalog, which allows a thorough study of the properties of the Galactic plane in the sub-TeV domain.
CRIS-Team WoS Importer:2020-01-15

SEARCH FOR GAMMA-RAY EMISSION FROM DES DWARF SPHEROIDAL GALAXY CANDIDATES WITH FERMI-LAT DATA - Drlica-Wagner, A.; Albert, A.; Bechtol, K.; Wood, M.; Strigari, L.; Sanchez-Conde, M.; Baldini, L.; Essig, R.; Cohen-Tanugi, J.; Anderson, B.; Bellazzini, R.; Bloom, E. D.; et al. (Astrophysical Journal Letters, 2015)
Due to their proximity, high dark-matter (DM) content, and apparent absence of non-thermal processes, Milky Way dwarf spheroidal satellite galaxies (dSphs) are excellent targets for the indirect detection of DM. Recently, eight new dSph candidates were discovered using the first year of data from the Dark Energy Survey (DES). We searched for gamma-ray emission coincident with the positions of these new objects in six years of Fermi Large Area Telescope data. We found no significant excesses of gamma-ray emission. Under the assumption that the DES candidates are dSphs with DM halo properties similar to the known dSphs, we computed individual and combined limits on the velocity-averaged DM annihilation cross section for these new targets. If the estimated DM content of these dSph candidates is confirmed, they will constrain the annihilation cross section to lie below the thermal relic cross section for DM particles with masses less than or similar to 20 GeV annihilating via the b (b) over bar or pi(+)pi(-) channels.
Keywords: dark matter; galaxies: dwarf; gamma rays: galaxies; Local Group

Search for Gamma-Ray Emission from Local Primordial Black Holes with the Fermi Large Area Telescope - Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2018)
Black holes with masses below approximately 10(15) g are expected to emit gamma-rays with energies above a few tens of MeV, which can be detected by the Fermi Large Area Telescope (LAT). Although black holes with these masses cannot be formed as a result of stellar evolution, they may have formed in the early universe and are therefore called primordial black holes (PBHs). Previous searches for PBHs have focused on either short-timescale bursts or the contribution of PBHs to the isotropic gamma-ray emission. We show that, in cases of individual PBHs, the Fermi-LAT is most sensitive to PBHs with temperatures above approximately 16 GeV and masses 6 x 10(11) g, which it can detect out to a distance of about 0.03 pc. These PBHs have a remaining lifetime of months to years at the start of the Fermi mission. They would appear as potentially moving point sources with gamma-ray emission that become spectrally harder and brighter with time until the PBH completely evaporates. In this paper, we develop a new algorithm to detect the proper motion of gamma-ray point sources, and apply it to 318 unassociated point sources at a high galactic latitude in the third Fermi-LAT source catalog. None of the unassociated point sources with spectra consistent with PBH evaporation show significant proper motion. Using the nondetection of PBH candidates, we derive a 99% confidence limit on the PBH evaporation rate in the vicinity of Earth, <(rho)over dot>(PBH) < 7.2 x 10(3) pc(-3) yr(-1). This limit is similar to the limits obtained with ground-based gamma-ray observatories.
Keywords: astroparticle physics; black hole physics; methods: data analysis

Search for Gamma-Ray Emission from Local Primordial Black Holes with the Fermi Large Area Telescope - Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Berenji, B.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal, 2018)
Black holes with masses below approximately 10(15) g are expected to emit gamma-rays with energies above a few tens of MeV, which can be detected by the Fermi Large Area Telescope (LAT). Although black holes with these masses cannot be formed as a result of stellar evolution, they may have formed in the early universe and are therefore called primordial black holes (PBHs). Previous searches for PBHs have focused on either short-timescale bursts or the contribution of PBHs to the isotropic gamma-ray emission. We show that, in cases of individual PBHs, the Fermi-LAT is most sensitive to PBHs with temperatures above approximately 16 GeV and masses 6 x 10(11) g, which it can detect out to a distance of about 0.03 pc. These PBHs have a remaining lifetime of months to years at the start of the Fermi mission. They would appear as potentially moving point sources with gamma-ray emission that become spectrally harder and brighter with time until the PBH completely evaporates. In this paper, we develop a new algorithm to detect the proper motion of gamma-ray point sources, and apply it to 318 unassociated point sources at a high galactic latitude in the third Fermi-LAT source catalog. None of the unassociated point sources with spectra consistent with PBH evaporation show significant proper motion. Using the nondetection of PBH candidates, we derive a 99% confidence limit on the PBH evaporation rate in the vicinity of Earth, <(rho)over dot>(PBH) < 7.2 x 10(3) pc(-3) yr(-1). This limit is similar to the limits obtained with ground-based gamma-ray observatories.
Keywords: astroparticle physics; black hole physics; methods: data analysis

SEARCH for GAMMA-RAY EMISSION from the COMA CLUSTER with SIX YEARS of FERMI-LAT DATA - Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; et al. (Astrophysical Journal, 2016)
We present results from γ-ray observations of the Coma cluster incorporating six years of Fermi-LAT data and the newly released "Pass 8" event-level analysis. Our analysis of the region reveals low-significance residual structures within the virial radius of the cluster that are too faint for a detailed investigation with the current data. Using a likelihood approach that is free of assumptions on the spectral shape we derive upper limits on the γ-ray flux that is expected from energetic particle interactions in the cluster. We also consider a benchmark spatial and spectral template motivated by models in which the observed radio halo is mostly emission by secondary electrons. In this case, the median expected and observed upper limits for the flux above 100 are 1.7 times;10 ph cm s and 5.2 times;10 ph cm s respectively (the latter corresponds to residual emission at the level of 1.8σ). These bounds are comparable to or higher than predicted levels of hadronic gamma-ray emission in cosmic-ray (CR) models with or without reacceleration of secondary electrons, although direct comparisons are sensitive to assumptions regarding the origin and propagation mode of CRs and magnetic field properties. The minimal expected γ-ray flux from radio and star-forming galaxies within the Coma cluster is roughly an order of magnitude below the median sensitivity of our analysis.
Keywords: galaxies: clusters: individual (Coma); gamma rays: galaxies: cluster

Search for gamma-Ray Line Signals from Dark Matter Annihilations in the Inner Galactic Halo from 10 Years of Observations with HESS - Abdallah, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, M.; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Physical Review Letters, 2018)
Spectral lines are among the most powerful signatures for dark matter (DM) annihilation searches in very-high-energy gamma rays. The central region of the Milky Way halo is one of the most promising targets given its large amount of DM and proximity to Earth. We report on a search for a monoenergetic spectral line from self-annihilations of DM particles in the energy range from 300 GeV to 70 TeV using a two-dimensional maximum likelihood method taking advantage of both the spectral and spatial features of the signal versus background. The analysis makes use of Galactic center observations accumulated over ten years (2004-2014) with the H.E.S.S. array of ground-based Cherenkov telescopes. No significant gamma-ray excess above the background is found. We derive upper limits on the annihilation cross section (sigma v) for monoenergetic DM lines at the level of 4 x 10(-28) cm(3) s(-1) at 1 TeV, assuming an Einasto DM profile for the Milky Way halo. For a DM mass of 1 TeV, they improve over the previous ones by a factor of 6. The present constraints are the strongest obtained so far for DM particles in the mass range 300 GeV-70 TeV. Ground-based gamma-ray observations have reached sufficient sensitivity to explore relevant velocity-averaged cross sections for DM annihilation into two gamma-ray photons at the level expected from the thermal relic density for TeV DM particles.

Search for gamma-ray spectral lines with the Fermi Large Area Telescope and dark matter implications - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonamente, E.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2013)
Weakly interacting massive particles (WIMPs) are a theoretical class of particles that are excellent dark matter candidates. WIMP annihilation or decay may produce essentially monochromatic gamma rays detectable by the Fermi Large Area Telescope (LAT) against the astrophysical gamma-ray emission of the Galaxy. We have searched for spectral lines in the energy range 5-300 GeV using 3.7 years of data, reprocessed with updated instrument calibrations and an improved energy dispersion model compared to the previous Fermi-LAT Collaboration line searches. We searched in five regions selected to optimize sensitivity to different theoretically motivated dark matter density distributions. We did not find any globally significant lines in our a priori search regions and present 95% confidence limits for annihilation cross sections of self-conjugate WIMPs and decay lifetimes. Our most significant fit occurred at 133 GeV in our smallest search region and had a local significance of 3.3 standard deviations, which translates to a global significance of 1.5 standard deviations. We discuss potential systematic effects in this search, and examine the feature at 133 GeV in detail. We find that the use both of reprocessed data and of additional

SEARCH FOR SPATIALLY EXTENDED FERMI LARGE AREA TELESCOPE SOURCES USING TWO YEARS OF DATA - Lande, J.; Ackermann, Markus; Allafort, A.; Ballet, J.; Bechtol, K.; Burnett, T. H.; Cohen-Tanugi, Johann; Drlica-Wagner, A.; Funk, Stefan; Giordano, F.; Grondin, M. -H.; Kerr, Matthew; et al. (Astrophysical Journal, 2012)
Spatial extension is an important characteristic for correctly associating. gamma-ray-emitting sources with their counterparts at other wavelengths and for obtaining an unbiased model of their spectra. We present a new method for quantifying the spatial extension of sources detected by the Large Area Telescope (LAT), the primary science instrument on the Fermi Gamma-ray Space Telescope (Fermi). We perform a series of Monte Carlo simulations to validate this tool and calculate the LAT threshold for detecting the spatial extension of sources. We then test all sources in the second Fermi-LAT catalog for extension. We report the detection of seven new spatially extended sources.
CRIS-Team WoS Importer:2020-01-15

Search for Spectral Irregularities due to Photon-Axionlike-Particle Oscillations with the Fermi Large Area Telescope - Ajello, M.; Albert, A.; Anderson, B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, R.; Bottacini, E.; et al. (Physical Review Letters, 2016)
We report on the search for spectral irregularities induced by oscillations between photons and axionlike-particles (ALPs) in the gamma-ray spectrum of NGC 1275, the central galaxy of the Perseus cluster. Using 6 years of Fermi Large Area Telescope data, we find no evidence for ALPs and exclude couplings above 5 x 10(-12) GeV-1 for ALP masses 0.5 less than or similar to m(a) less than or similar to 5 neV at 95% confidence. The limits are competitive with the sensitivity of planned laboratory experiments, and, together with other bounds, strongly constrain the possibility that ALPs can reduce the gamma-ray opacity of the Universe.

Search for TeV emission from the region around PSR B1706-44 with the HESS experiment - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The region around PSR B1706 - 44 has been observed with the HESS imaging atmospheric Cherenkov telescopes in 2003. No evidence for gamma-ray emission in the TeV range was found at the pulsar position or at the radio arc which corresponds to the supernova remnant G343.1 - 2.3. The 99% confidence level flux upper limit at the pulsar position is F-ul( E > 350 GeV) = 1.4 x 10(-12) s(-1) cm(-2) assuming a power law (dN/dE proportional to E-Gamma) with photon index of Gamma = 2.5 and F-ul( E > 500 GeV) = 1.3 x 10(-12) s(-1) cm(-2) without an assumption on the spectral shape. The reported upper limits correspond to 8% of the flux from an earlier detection by the CANGAROO experiment.
CRIS-Team WoS Importer:2020-01-15

Searching for Dark Matter Annihilation from Milky Way Dwarf Spheroidal Galaxies with Six Years of Fermi Large Area Telescope Data - Ackermann, Markus; Albert, A.; Anderson, B.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Physical Review Letters, 2015)
The dwarf spheroidal satellite galaxies (dSphs) of the Milky Way are some of the most dark matter (DM) dominated objects known. We report on gamma-ray observations of Milky Way dSphs based on six years of Fermi Large Area Telescope data processed with the new PASS8 event-level analysis. None of the dSphs are significantly detected in gamma rays, and we present upper limits on the DM annihilation cross section from a combined analysis of 15 dSphs. These constraints are among the strongest and most robust to date and lie below the canonical thermal relic cross section for DM of mass less than or similar to 100 GeV annihilating via quark and tau-lepton channels.
CRIS-Team WoS Importer:2020-01-15

Searching for TeV Gamma-Ray Emission from SGR 1935+2154 during Its 2020 X-Ray and Radio Bursting Phase - Abdalla, H.; Aharonian, F.; Mitchell, Alison; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
Magnetar hyperflares are the most plausible explanation for fast radio bursts (FRBs)-enigmatic powerful radio pulses with durations of several milliseconds and high brightness temperatures. The first observational evidence for this scenario was obtained in 2020 April when an FRB was detected from the direction of the Galactic magnetar and soft gamma-ray repeater SGR 1935+2154. The FRB was preceded by two gamma-ray outburst alerts by the BAT instrument aboard the Swift satellite, which triggered follow-up observations by the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observed SGR 1935+2154 for 2 hr on 2020 April 28. The observations are coincident with X-ray bursts from the magnetar detected by INTEGRAL and Fermi-GBM, thus providing the first very high energy gamma-ray observations of a magnetar in a flaring state. High-quality data acquired during these follow-up observations allow us to perform a search for short-time transients. No significant signal at energies E > 0.6 TeV is found, and upper limits on the persistent and transient emission are derived. We here present the analysis of these observations and discuss the obtained results and prospects of the H.E.S.S. follow-up program for soft gamma-ray repeaters.
CRIS-Team WoS Importer:2021-10-08

SEARCHING THE GAMMA-RAY SKY FOR COUNTERPARTS TO GRAVITATIONAL WAVE SOURCES: FERMI GAMMA-RAY BURST MONITOR. AND LARGE AREA TELESCOPE OBSERVATIONS OF LVT151012 AND GW151226 - Racusin, J. L.; Burns, E.; Goldstein, A.; Connaughton, V.; Wilson-Hodge, C. A.; Jenke, P.; Blackburn, L.; Briggs, M. S.; Broida, J.; Camp, J.; Christensen, Nelson; Hui, C. M.; et al. (Astrophysical Journal, 2017)
We present the Fermi Gamma-ray Burst Monitor (GBM) and Large Area Telescope (LAT) observations of the LIGO binary black hole merger event GW151226 and candidate LVT151012. At the time of the LIGO triggers on LVT151012 and GW151226, GBM was observing 68% and 83% of the localization regions, and LAT was observing 47% and 32%, respectively. No candidate electromagnetic counterparts were detected by either the GBM or LAT. We present a detailed analysis of the GBM and LAT data over a range of timescales from seconds to years, using automated pipelines and new techniques for characterizing the flux upper bounds across large areas of the sky. Due to the partial GBM and LAT coverage of the large LIGO localization regions at the trigger times for both events, differences in source distances and masses, as well as the uncertain degree to which emission from these sources could be beamed, these non-detections cannot be used to constrain the variety of theoretical models recently applied to explain the candidate GBM counterpart to GW150914.
CRIS-Team WoS Importer:2020-01-15

SECOND CATALOG OF ACTIVE GALACTIC NUCLEI DETECTED BY THE FERMI LARGE AREA TELESCOPE (vol 743, 171, 2011) - Ackermann, M.; Ajello, M.; Allafort, A.; Antolini, E.; Atwood, W. B.; Axelsson, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2015)

Serendipitous discovery of the unidentified extended TeV gamma-ray source HESS J1303-631 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
The serendipitous discovery of an unidentified extended TeV gamma-ray source close to the galactic plane named HESSJ1303-631 at a significance of 21 standard deviations is reported. The observations were performed between February and June 2004 with the HESS stereoscopic system of Cherenkov telescopes in Namibia. HESS J1303-631 was discovered roughly 0.6 degrees north of the binary system PSRB1259-63/SS2883, the target object of the initial observation campaign which was also detected at TeV energies in the same field of view. HESS J1303-631 is extended with a width of an assumed intrinsic Gaussian emission profile of sigma = (0.16 +/- 0.02)degrees. and the integral flux above 380 GeV is compatible with constant emission over the entire observational period of (17 +/- 3)% of the Crab Nebula flux. The measured energy spectrum can be described by a power-law dN/dE similar to E-Gamma with a photon index of G = 2.44 +/- 0.05(stat) +/- 0.2(syst). Up to now, no counterpart at other wavelengths is identified. Various possible TeV production scenarios are discussed.
CRIS-Team WoS Importer:2020-01-15

Setup for meV-resolution inelastic X-ray scattering measurements and X-ray diffraction at the Matter in Extreme Conditions endstation at the Linac Coherent Light Source - Mcbride, E. E.; White, T. G.; Descamps, A.; Fletcher, L. B.; Appel, K.; Condamine, F. P.; Curry, C. B.; Dallari, Francesco; Funk, Stefan; Galtier, E.; Gauthier, Maxence; Goede, S.; et al. (Review of Scientific Instruments, 2018)
We describe a setup for performing inelastic X-ray scattering and X-ray diffraction measurements at the Matter in Extreme Conditions (MEC) endstation of the Linac Coherent Light Source. This technique is capable of performing high-, meV-resolution measurements of dynamic ion features in both crystalline and non-crystalline materials. A four-bounce silicon (533) monochromator was used in conjunction with three silicon (533) diced crystal analyzers to provide an energy resolution of similar to 50 meV over a range of similar to 500 meV in single shot measurements. In addition to the instrument resolution function, we demonstrate the measurement of longitudinal acoustic phonon modes in polycrystalline diamond. Furthermore, this setup may be combined with the high intensity laser drivers available at MEC to create warm dense matter and subsequently measure ion acoustic modes. Published by AIP Publishing.
CRIS-Team WoS Importer:2020-01-15

Simulation studies of the high-energy component of a future imaging Cherenkov telescope array - Funk, Stefan; Hinton, J. A. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

Single-exposure X-ray phase imaging microscopy with a grating interferometer - Wolf, Andreas; Akstaller, Bernhard; Cipiccia, Silvia; Flenner, Silja; Hagemann, Johannes; Ludwig, Veronika; Meyer, Pascal; Schropp, Andreas; Schuster, Max; Seifert, Maria; Weule, Mareike; Michel, Thilo; et al. (Journal of Synchrotron Radiation, 2022)
The advent of hard X-ray free-electron lasers enables nanoscopic X-ray imaging with sub-picosecond temporal resolution. X-ray grating interferometry offers a phase-sensitive full-field imaging technique where the phase retrieval can be carried out from a single exposure alone. Thus, the method is attractive for imaging applications at X-ray free-electron lasers where intrinsic pulse-to-pulse fluctuations pose a major challenge. In this work, the single-exposure phase imaging capabilities of grating interferometry are characterized by an implementation at the I13-1 beamline of Diamond Light Source (Oxfordshire, UK). For comparison purposes, propagation-based phase contrast imaging was also performed at the same instrument. The characterization is carried out in terms of the quantitativeness and the contrast-to-noise ratio of the phase reconstructions as well as via the achievable spatial resolution. By using a statistical image reconstruction scheme, previous limitations of grating interferometry regarding the spatial resolution can be mitigated as well as the experimental applicability of the technique.
CRIS-Team Scopus Importer:2022-05-27
Keywords: grating interferometry; phase contrast X-ray imaging; phase retrieval; X-ray microscopy

Single-shot grating-based phase-contrast imaging of a micrometer sample at a laser-driven x-ray backlighter source - Akstaller, Bernhard; Schreiner, Stephan; Hofmann, Fabian; Meyer, P.; Neumayer, P.; Schuster, Max; Wolf, Andreas; Zielbauer, B.; Ludwig, Veronika; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Instrumentation, 2021)
A single-shot x-ray phase-contrast imaging technique with short exposure time allows to capture sharp images of fast dynamic processes despite low absorption contrast. We demonstrate the capabilities of a robust single-shot grating-based phase-contrast imaging setup at the Petawatt High-Energy Laser for Heavy Ion EXperiments (PHELIX) at the GSI Helmholtzzentrum für Schwerionenforschung GmbH. A static test sample was imaged at 47-fold magnification using a laser-driven high-energy x-ray backlighter source. The retrieved transmission and phase-contrast images yield reproducible results. The reconstructed differential phase-images are quantitatively explained. In addition to the phase-images, propagation signatures are found in the data and used for result verification. The obtained results demonstrate the capabilities of the grating setup which can be used to image microscopic dynamic processes in high-energy density plasma experiments at PHELIX or similar high-power laser facilities.
CRIS-Team Scopus Importer:2021-07-16
Keywords: Inspection with x-rays; Plasma diagnostics - interferometry; spectroscopy and imaging; X-ray radiography and digital radiography (DR)

Solution to the Cosmic Ray Anisotropy Problem - Mertsch, Philipp; Funk, Stefan (Physical Review Letters, 2015)
In the standard diffusive picture for transport of cosmic rays (CRs), a gradient in the CR density induces a typically small, dipolar anisotropy in their arrival directions. This is being widely advertised as a tool for finding nearby sources. However, the predicted dipole amplitude at TeV and PeV energies exceeds the measured one by almost 2 orders of magnitude. Here, we critically examine the validity of this prediction, which is based on averaging over an ensemble of turbulent magnetic fields. We focus on (1) the deviations of the dipole in a particular random realization from the ensemble average, and (2) the possibility of a misalignment between the regular magnetic field and the CR gradient. We find that if the field direction and the gradient direction are close to similar to 90 degrees, the dipole amplitude is considerably suppressed and can be reconciled with observations, which sheds light on a long-standing problem. Furthermore, we show that the dipole direction in general does not coincide with the gradient direction, thus hampering the search for nearby sources.

SPECTRAL PROPERTIES OF BRIGHT FERMI-DETECTED BLAZARS IN THE GAMMA-RAY BAND - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2010)
The gamma-ray energy spectra of bright blazars of the LAT Bright AGN Sample LBAS) are investigated using Fermi-LAT data. Spectral properties hardness, curvature, and variability) established using a data set accumulated over 6 months of operation are presented and discussed for different blazar classes and subclasses: flat spectrum radio quasars (FSRQs), low-synchrotron peaked BLLacs (LSP-BLLacs), intermediate-synchrotron peaked BLLacs (ISP-BLLacs), and high-synchrotron peaked BLLacs (HSP-BLLacs). The distribution of photon index G, obtained from a power-law fit above 100 MeV) is found to correlate strongly with blazar subclass. The change in spectral index from that averaged over the 6 months observing period is < 0.2-0.3 when the flux varies by about an order of magnitude, with a tendency toward harder spectra when the flux is brighter for FSRQs and LSP-BLLacs. A strong departure from a single power-law spectrum appears to be a common feature for FSRQs. This feature is also present for some high-luminosity LSP-BLLacs, and a small number of ISP-BLLacs. It is absent in all LBAS HSP-BLLacs. For 3C 454.3 and AO 0235+164, the two brightest FSRQ source and LSP-BLLac source, respectively, a broken power law (BPL) gives the most acceptable of power law, BPL, and curved forms. The consequences of these findings are discussed.
CRIS-Team WoS Importer:2020-01-15

Spectrum of the Isotropic Diffuse Gamma-Ray Emission Derived from First-Year Fermi Large Area Telescope Data - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Physical Review Letters, 2010)
We report on the first Fermi Large Area Telescope (LAT) measurements of the so-called "extra-galactic" diffuse gamma-ray emission (EGB). This component of the diffuse gamma-ray emission is generally considered to have an isotropic or nearly isotropic distribution on the sky with diverse contributions discussed in the literature. The derivation of the EGB is based on detailed modeling of the bright foreground diffuse Galactic gamma-ray emission, the detected LAT sources, and the solar gamma-ray emission. We find the spectrum of the EGB is consistent with a power law with a differential spectral index gamma = 2.41 +/- 0.05 and intensity I(>100 MeV) = (1.03 +/- 0.17) x 10(-5) cm(-2) s(-1) sr(-1), where the error is systematics dominated. Our EGB spectrum is featureless, less intense, and softer than that derived from EGRET data.
CRIS-Team WoS Importer:2020-01-15

Status of identification of VHE gamma-ray sources - Funk, Stefan (Astrophysics and Space Science, 2007)
With the recent advances made by Cherenkov telescopes such as H.E.S.S. the field of very high-energy (VHE) gamma-ray astronomy has recently entered a new era in which for the first time populations of Galactic sources such as e.g. Pulsar wind nebulae (PWNe) or Supernova remnants (SNRs) can be studied. However, while some of the new sources can be associated by positional coincidence as well as by consistent multi-wavelength data to a known counterpart at other wavelengths, most of the sources remain not finally identified. In the following, the population of Galactic H.E.S.S. sources will be used to demonstrate the status of the identifications, to classify them into categories according to this status and to point out outstanding problems.
CRIS-Team WoS Importer:2020-01-15

SUPPLEMENT: "LOCALIZATION AND BROADBAND FOLLOW-UP OF THE GRAVITATIONAL-WAVE TRANSIENT GW150914" (2016, ApJL, 826, L13) - Abbott, B. P.; Abbott, R.; Abbott, T. D.; Abernathy, M. R.; Acernese, F.; Ackley, K.; Adams, C.; Adams, T.; Addesso, P.; Adhikari, R. X.; Adya, V. B.; Affeldt, C.; et al. (Astrophysical Journal Supplement Series, 2016)
This Supplement provides supporting material for Abbott et al. (2016a). We briefly summarize past electromagnetic (EM) follow-up efforts as well as the organization and policy of the current EM follow-up program. We compare the four probability sky maps produced for the gravitational-wave transient GW150914, and provide additional details of the EM follow-up observations that were performed in the different bands.
Keywords: gravitational waves; methods: observational

Surveys with the Cherenkov Telescope Array - Dubus, Guillaume; Contreras, J. L.; Funk, Stefan; Gallant, Y.; Hassan, Tarek; Hinton, J.; Inoue, Yoshiyuki; Knoedlseder, J.; Martin, P.; Mirabal, Nestor; De Naurois, M.; Renaud, M. (Astroparticle Physics, 2013)
Surveys open up unbiased discovery space and generate legacy datasets of long-lasting value. One of the goals of imaging arrays of Cherenkov telescopes like CTA is to survey areas of the sky for faint very high energy gamma-ray (VHE) sources, especially sources that would not have drawn attention were it not for their VHE emission (e.g. the Galactic "dark accelerators"). More than half the currently known VHE sources are to be found in the Galactic Plane. Using standard techniques, CTA can carry out a survey of the region vertical bar l vertical bar <= 60 degrees, vertical bar b vertical bar <= 2 degrees in 250 h (1/4th the available time per year at one location) down to a uniform sensitivity of 3 mCrab (a "Galactic Plane survey"). CTA could also survey 1/4th of the sky down to a sensitivity of 20 mCrab in 370 h of observing time (an "all-sky survey"), which complements well the surveys by the Fermi/LAT at lower energies and extended air shower arrays at higher energies. Observations in (non-standard) divergent pointing mode may shorten the "all-sky survey" time to about 100 h with no loss in survey sensitivity. We present the scientific rationale for these surveys, their place in the multi-wavelength context, their possible impact and their feasibility. We find that the Galactic Plane survey has the potential to detect hundreds of sources. Implementing such a survey should be a major goal of CTA. Additionally, about a dozen blazars, or counterparts to Fermi/LAT sources, are expected to be detected by the all-sky survey, whose prime motivation is the search for extragalactic "dark accelerators". (C) 2012 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

Suzaku hard X-ray observations of HESS J1813-178 - Reimer, Olaf; Funk, Stefan; Hinton, J. A.; Tanaka, T.; Ebisawa, K.; Anada, T. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

Suzaku Observation of the Unidentified Very High Energy Gamma-Ray Source HESS J1702-420 - Fujinaga, Takahisa; Bamba, Aya; Dotani, Tadayasu; Ozaki, Masanobu; Puehlhofer, Gerd; Wagner, Stefan; Reimer, Olaf; Funk, Stefan; Hinton, Jim (Publications of the Astronomical Society of Japan, 2011)
A deep X-ray observation of the unidentified very high energy (VHE) gamma-ray source HESS J1702-420, for the first time, was carried out by Suzaku. No bright sources were detected in the XIS field of view (FOV), except for two faint point-like sources. The two sources, however, are considered not to be related to HESS J1702-420, because their fluxes in the 2-10 keV band (similar to 10(-14) erg s(-1) cm(-2)) are similar to 3 orders of magnitude smaller than the VHF gamma-ray flux in the 1-10 TeV band (F-TeV = 3.1 x 10(-11) erg s(-1) cm(-2)). We compared the energy spectrum of diffuse emission, extracted from the entire XIS FOV with those from nearby observations. If we consider the systematic error of background subtraction, no significant diffuse emission was detected with an upper limit of F-X < 2.7 x 10(-12) erg s(-1) cm(-2) in the 2-10 keV band for an assumed power-law spectrum of Gamma = 2.1 and a source size same as that in the VHE band. The upper limit of the X-ray flux is twelve-times as small as the VHE gamma-ray flux. The large flux ratio (F-TeV/F-X) indicates that HESS J1702-420 is another example of a "dark" particle accelerator. If we use a simple one-zone leptonic model, in which VHE gamma-rays are produced through inverse Compton scattering of the cosmic microwave background and interstellar far-infrared emission, and the X-rays via the synchrotron mechanism, an upper limit of the magnetic field (1.7 mu AG) is obtained from the flux ratio. Because the magnetic field is weaker than the typical value in the galactic plane (3-10 mu G), the simple one-zone model may not work for HESS J1702-420 and a significant fraction of the VHE gamma-rays may originate from protons.
CRIS-Team WoS Importer:2020-01-15

SWIFT AND FERMI OBSERVATIONS OF THE EARLY AFTERGLOW OF THE SHORT GAMMA-RAY BURST 090510 - De Pasquale, M.; Schady, Patricia; Kuin, N. P. M.; Page, M. J.; Curran, P. A.; Zane, Silvia; Oates, S. R.; Holland, S. T.; Breeveld, A. A.; Hoversten, E. A.; Chincarini, G.; Grupe, D.; et al. (Astrophysical Journal Letters, 2010)
We present the observations of GRB090510 performed by the Fermi Gamma-Ray Space Telescope and the Swift observatory. This is a bright, short burst that shows an extended emission detected in the GeV range. Furthermore, its optical emission initially rises, a feature so far observed only in long bursts, while the X-ray flux shows an initial shallow decrease, followed by a steeper decay. This exceptional behavior enables us to investigate the physical properties of the gamma-ray burst outflow, poorly known in short bursts. We discuss internal and external shock models for the broadband energy emission of this object.
CRIS-Team WoS Importer:2020-01-15

TARGET 5: A new multi-channel digitizer with triggering capabilities for gamma-ray atmospheric Cherenkov telescopes - Albert, A.; Funk, Stefan; Katagiri, Hideaki; Kawashima, T.; Murphy, M.; Okumura, Akira; Quagliani, R.; Sapozhnikov, L.; Shigenaka, A.; Tajima, H.; Tibaldo, Luigi; Vandenbroucke, J.; et al. (Astroparticle Physics, 2017)
TARGET 5 is a new application-specific integrated circuit (ASIC) of the TARGET family, designed for the readout of signals from photosensors in the cameras of imaging atmospheric Cherenkov telescopes (IACTs) for ground-based gamma-ray astronomy. TARGET 5 combines sampling and digitization on 16 signal channels with the formation of trigger signals based on the analog sum of groups of four channels. We describe the ASIC architecture and performance. TARGET 5 improves over the performance of the first-generation TARGET ASIC, achieving: tunable sampling frequency from <0.4 GSa/s to >1 GSa/s; a dynamic range on the data path of 1.2 V with effective dynamic range of 11 bits and DC noise of similar to 0.6 mV; 3-dB bandwidth of 500 MHz; crosstalk between adjacent channels <1.3%; charge resolution improving from 40% to <4% between 3 photoelectrons (p.e.) and >100 p.e. (assuming 4 mV per p.e.); and minimum stable trigger threshold of 20 mV (5 p.e.) with trigger noise of 5 mV (1.2 p.e.), which is mostly limited by interference between trigger and sampling operations. TARGET 5 is the first ASIC of the TARGET family used in an IACT prototype, providing one development path for readout electronics in the forthcoming Cherenkov Telescope Array (CTA). (C) 2017 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

TARGET: A Digitizing And Trigger ASIC For The Cherenkov Telescope Array - Funk, Stefan; Jankowsky, David; Katagiri, Hideaki; Kraus, Michael; Okumura, Akira; Schoorlemmer, Harm; Shigenaka, A.; Tajima, H.; Tibaldo, Luigi; Varner, G.; Zink, Adrian; Zorn, Justus (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2017)
CRIS-Team WoS Importer:2020-01-15

TARGET: A multi-channel digitizer chip for very-high-energy gamma-ray telescopes - Bechtol, K.; Funk, Stefan; Okumura, Akira; Ruckman, L. L.; Simons, A.; Tajima, H.; Vandenbroucke, J.; Varner, G. S. (Astroparticle Physics, 2012)
The next-generation very-high-energy (VHE) gamma-ray observatory, the Cherenkov Telescope Array, will feature dozens of imaging atmospheric Cherenkov telescopes (IACTs), each with thousands of pixels of photo-sensors. To be affordable and reliable, reading out such an array of up to a million channels requires event recording technology that is highly integrated and modular, with a low cost per channel. We present the design and performance of a chip targeted to this application: the TeV Array Readout with GSa/s sampling and Event Trigger (TARGET). This application-specific integrated circuit (ASIC) has 16 parallel input channels, a 4096-sample buffer for each channel, adjustable input termination, self-trigger functionality, and tight window-selected readout. We report the performance of the first-generation version of this chip (TARGET 1) in terms of sampling frequency, power consumption, dynamic range, current-mode gain, analog bandwidth, and cross talk. The large number of channels per chip allows a low cost per channel (10 to 20 including front-end and back-end electronics but not including photosensors) to be achieved with a TARGET-based IACT readout system. In addition to basic performance parameters of the TARGET 1 chip, we present a camera module prototype as well as a second-generation chip (TARGET 2), both of which have now been produced. (C) 2012 Elsevier B.V-. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

TeV Emission of Galactic Plane Sources with HAWC and HESS - Abdalla, H.; Mitchell, Alison; Aharonian, Felix; Spencer, Samuel; Benkhali, F. Ait; Anguner, E. O.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan,; et al. (Astrophysical Journal, 2021)
The High Altitude Water Cherenkov (HAWC) observatory and the High Energy Stereoscopic System (H.E.S.S.) are two leading instruments in the ground-based very-high-energy gamma-ray domain. HAWC employs the water Cherenkov detection (WCD) technique, while H.E.S.S. is an array of Imaging Atmospheric Cherenkov Telescopes (IACTs). The two facilities therefore differ in multiple aspects, including their observation strategy, the size of their field of view, and their angular resolution, leading to different analysis approaches. Until now, it has been unclear if the results of observations by both types of instruments are consistent: several of the recently discovered HAWC sources have been followed up by IACTs, resulting in a confirmed detection only in a minority of cases. With this paper, we go further and try to resolve the tensions between previous results by performing a new analysis of the H.E.S.S. Galactic plane survey data, applying an analysis technique comparable between H.E.S.S. and HAWC. Events above 1 TeV are selected for both data sets, the point-spread function of H.E.S.S. is broadened to approach that of HAWC, and a similar background estimation method is used. This is the first detailed comparison of the Galactic plane observed by both instruments. H.E.S.S. can confirm the gamma-ray emission of four HAWC sources among seven previously undetected by IACTs, while the three others have measured fluxes below the sensitivity of the H.E.S.S. data set. Remaining differences in the overall gamma-ray flux can be explained by the systematic uncertainties. Therefore, we confirm a consistent view of the gamma-ray sky between WCD and IACT techniques.
CRIS-Team WoS Importer:2021-08-20

TeV Gamma-Ray Observations of the Binary Neutron Star Merger GW170817 with HESS - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astrophysical Journal Letters, 2017)
We search for high-energy gamma-ray emission from the binary neutron star merger GW170817 with the H.E.S.S. Imaging Air Cherenkov Telescopes. The observations presented here have been obtained starting only 5.3 hr after GW170817. The H.E.S.S. target selection identified regions of high probability to find a counterpart of the gravitational-wave event. The first of these regions contained the counterpart SSS17a that has been identified in the optical range several hours after our observations. We can therefore present the first data obtained by a ground-based pointing instrument on this object. A subsequent monitoring campaign with the H.E.S.S. telescopes extended over several days, covering timescales from 0.22 to 5.2 days and energy ranges between 270 GeV to 8.55 TeV. No significant gamma-ray emission has been found. The derived upper limits on the very-high-energy gamma-ray flux for the first time constrain non-thermal, high-energy emission following the merger of a confirmed binary neutron star system.
CRIS-Team WoS Importer:2020-01-15

The 2014 TeV γ-Ray Flare of Mrk 501 Seen with H.E.S.S.: Temporal and Spectral Constraints on Lorentz Invariance Violation - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Astrophysical Journal, 2019)
The blazar Mrk 501 (z = 0.034) was observed at very-high-energy (VHE, E ≳ 100 GeV) gamma-ray wavelengths during a bright flare on the night of 2014 June 23-24 (MJD 56832) with the H.E.S.S. phase-II array of Cherenkov telescopes. Data taken that night by H.E.S.S. at large zenith angle reveal an exceptional number of gamma-ray photons at multi-TeV energies, with rapid flux variability and an energy coverage extending significantly up to 20 TeV. This data set is used to constrain Lorentz invariance violation (LIV) using two independent channels: a temporal approach considers the possibility of an energy dependence in the arrival time of gamma-rays, whereas a spectral approach considers the possibility of modifications to the interaction of VHE gamma-rays with extragalactic background light (EBL) photons. The non-detection of energy-dependent time delays and the non-observation of deviations between the measured spectrum and that of a supposed power-law intrinsic spectrum with standard EBL attenuation are used independently to derive strong constraints on the energy scale of LIV (E QG ) in the subluminal scenario for linear and quadratic perturbations in the dispersion relation of photons. For the case of linear perturbations, the 95% confidence level limits obtained are E QG,1 > 3.6 ×10 17 GeV using the temporal approach and E QG,1 > 2.6 ×10 19 GeV using the spectral approach. For the case of quadratic perturbations, the limits obtained are E QG,2 > 8.5 ×10 10 GeV using the temporal approach and E QG,2 > 7.8 ×10 11 GeV using the spectral approach.
CRIS-Team Scopus Importer:2019-05-14
Keywords: astroparticle physics; BL Lacertae objects: individual (Mrk 501); gamma rays: galaxies

The Advanced Gamma-ray Imaging System (AGIS) - Science Highlights - Buckley, J.; Coppi, P.; Digel, S.; Funk, Stefan; Krawczynski, H.; Krennrich, F.; Pohl, Martin; Romani, R.; Vassiliev, V. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

The Advanced Gamma-ray Imaging System (AGIS) - Simulation Studies - Maier, G.; Buckley, J.; Bugaev, V.; Fegan, S.; Funk, Stefan; Konopelko, A.; Vassiliev, V. V. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2009)
CRIS-Team WoS Importer:2020-01-15

The Advanced Particle-astrophysics Telescope (APT) Project Status - Buckley, James H.; Alnussirat, S.; Altomare, C.; Bose, R. G.; Braun, D.; Buhler, J. D.; Burns, E.; Chamberlain, R. D.; Chen, W.; Cherry, M. L.; Di Venere, L.; Dumonthier, J.; et al. (Proceedings of Science, 2022)
We describe the development of a future gamma-ray/cosmic-ray mission called the Advanced Particle-astrophysics Telescope (APT). The instrument will combine a pair tracker and Compton telescope in a single monolithic design. By using scintillating fibers for the tracker and wavelength-shifting fibers to readout CsI detectors, the instrument will achieve an order of magnitude improvement in sensitivity compared with Fermi but with fewer readout channels, and lower complexity. By incorporating multiple Compton imaging over a very large effective area, the instrument will also achieve orders of magnitude improvement in MeV sensitivity compared with other proposed instruments. The mission would have a broad impact on astroparticle physics, but the primary science drivers for the mission include: (1) probing WIMP dark matter across the entire natural mass range and annihilation cross section for a thermal WIMP, (2) providing a nearly all-sky instantaneous FoV, with prompt sub-degree localization and polarization measurements for gamma-ray transients such as neutron-star mergers and (3) making measurements of rare utraheavy cosmic ray nuclei to distinguish between n-star merger and SNae r-process synthesis of the heavy elements. We will describe ongoing work including a series of accelerator beam tests, a piggy-back Antactic flight (APTlite) and the recently funded long-duration balloon mission: the Antarctic Demonstrator for APT (ADAPT).
CRIS-Team Scopus Importer:2022-12-23

The Advanced Particle-astrophysics Telescope: Simulation of the Instrument Performance for Gamma-Ray Detection - Alnussirat, S.; Altomare, C.; Bose, R. G.; Braun, D.; Buckley, James H.; Buhler, J. D.; Burns, E.; Chamberlain, R. D.; Chen, Wenlei; Cherry, M. L.; Di Venere, L.; Dumonthier, J.; et al. (Proceedings of Science, 2022)
We present simulations of the instrument performance of the Advanced Particle-astrophysics Telescope (APT), a mission concept of a γ-ray and cosmic-ray observatory in a sun-Earth Lagrange orbit. The key components of the APT detector include a multiple-layer tracker composed of scintillating fibers and an imaging calorimeter composed of thin layers of CsI:Na scintillators. The design is aimed at maximizing effective area and field of view for γ-ray and cosmic-ray measurements, subject to constraints on instrument cost and total payload mass. We simulate a detector design based on 3-meter scintillating fibers and develop reconstruction algorithms for γ-rays from a few hundreds of keV up to a few TeV energies. At the photon energy above 30 MeV, pair-production/shower reconstruction is applied; the results show that APT could provide an order of magnitude improvement in effective area and sensitivity for γ-ray detection compared with the Fermi Large Area Telescope (LAT). A multiple-Compton-scattering reconstruction at photon energies below 10 MeV achieves sensitive detection of faint γ-ray bursts (GRBs) and other γ-ray transients down to ∼ 0.01 MeV/cm2 with degree-level to sub-degree-level localization accuracy. The Compton analysis also provides a measurement of polarization where the minimum detectable degree of polarization for ∼ 1 MeV/cm2 GRBs is below 20%. In addition to the APT simulations, we present the simulated performance of the Antarctic Demonstrator for APT, a 0.5m-square cross section balloon experiment that includes all of the key elements of the full APT detector.
CRIS-Team Scopus Importer:2022-12-23

The ASTRO-H Mission - Takahashi, Tadayuki; Mitsuda, Kazuhisa; Kelley, Richard; Aharonian, Felix; Akimoto, Fumie; Allen, Steve; Anabuki, Naohisa; Angelini, Lorella; Arnaud, Keith; Awaki, Hisamitsu; Bamba, Aya; Bando, Nobutaka; et al. (SPACE TELESCOPES AND INSTRUMENTATION 2010: ULTRAVIOLET TO GAMMA RAY, 2010)
CRIS-Team WoS Importer:2020-01-15

The ASTRO-H X-ray Astronomy Satellite - Takahashi, Tadayuki; Mitsuda, Kazuhisa; Kelley, Richard; Aharonian, Felix; Akamatsu, Hiroki; Akimoto, Fumie; Allen, Steve; Anabuki, Naohisa; Angelini, Lorella; Arnaud, Keith; Asai, Makoto; Audard, Marc; et al. (International Society for Optical Engineering; 1999, 2014)
The joint JAXA/NASA ASTRO-H mission is the sixth in a series of highly successful X-ray missions developed by the Institute of Space and Astronautical Science (ISAS), with a planned launch in 2015. The ASTRO-H mission is equipped with a suite of sensitive instruments with the highest energy resolution ever achieved at E > 3 keV and a wide energy range spanning four decades in energy from soft X-rays to gamma-rays. The simultaneous broad band pass, coupled with the high spectral resolution of Delta E <= 7 eV of the micro-calorimeter, will enable a wide variety of important science themes to be pursued. ASTRO-H is expected to provide breakthrough results in scientific areas as diverse as the large-scale structure of the Universe and its evolution, the behavior of matter in the gravitational strong field regime, the physical conditions in sites of cosmic-ray acceleration, and the distribution of dark matter in galaxy clusters at different redshifts.
Keywords: X-ray; Hard X-ray; Gamma-ray; X-ray Astronomy; Gamma-ray Astronomy; micro-calorimeter

The central trigger system of the HESS telescope array - Funk, Stefan; et al. (High Energy Gamma-Ray Astronomy, 2005)
CRIS-Team WoS Importer:2020-01-15

THE DISCOVERY OF gamma-RAY EMISSION FROM THE BLAZAR RGB J0710+591 - Acciari, V. A.; Aliu, E.; Arlen, T.; Aune, T.; Bautista, M.; Beilicke, M.; Benbow, W.; Boettcher, M.; Boltuch, D.; Bradbury, S. M.; Buckley, J. H.; Bugaev, V.; et al. (Astrophysical Journal Letters, 2010)
The high-frequency-peaked BL Lacertae object RGB J0710+591 was observed in the very high-energy (VHE; E > 100 GeV) wave band by the VERITAS array of atmospheric Cherenkov telescopes. The observations, taken between 2008 December and 2009 March and totaling 22.1 hr, yield the discovery of VHE gamma rays from the source. RGB J0710+591 is detected at a statistical significance of 5.5 standard deviations (5.5 sigma) above the background, corresponding to an integral flux of (3.9 +/- 0.8) x 10(-12) cm(-2) s(-1) (3% of the Crab Nebula's flux) above 300 GeV. The observed spectrum can be fit by a power law from 0.31 to 4.6 TeV with a photon spectral index of 2.69 +/- 0.26(stat) +/- 0.20(sys). These data are complemented by contemporaneous multiwavelength data from the Fermi Large Area Telescope, the Swift X-ray Telescope, the Swift Ultra-Violet and Optical Telescope, and the Michigan-Dartmouth-MIT observatory. Modeling the broadband spectral energy distribution (SED) with an equilibrium synchrotron self-Compton model yields a good statistical fit to the data. The addition of an external-Compton component to the model does not improve the fit nor brings the system closer to equipartition. The combined Fermi and VERITAS data constrain the properties of the high-energy emission component of the source over 4 orders of magnitude and give measurements of the rising and falling sections of the SED.
CRIS-Team WoS Importer:2020-01-15

The e-ASTROGAM gamma-ray space observatory for the multimessenger astronomy of the 2030s - Tatischeff, V.; De Angelis, A.; Tavani, M.; Grenier, I.; Oberlack, U.; Hanlon, L.; Walter, R.; Argan, Andrea; Von Ballmoos, Peter; Bulgarelli, Andrea; Donnarumma, I.; Hernanz, M.; et al. (SPACE TELESCOPES AND INSTRUMENTATION 2018: ULTRAVIOLET TO GAMMA RAY, 2018)
CRIS-Team WoS Importer:2020-01-15

The e-ASTROGAM mission Exploring the extreme Universe with gamma rays in the MeV - GeV range - De Angelis, Alessandro; Tatischeff, V.; Tavani, M.; Oberlack, U.; Grenier, I.; Hanloni, L.; Walter, R.; Argan, A.; Von Ballmoos, P.; Bulgarelli, Andrea; Donnarumma, Immacolata; Hernanz, Margarita; et al. (Experimental Astronomy, 2017)
e-ASTROGAM ('enhanced ASTROGAM') is a breakthrough Observatory space mission, with a detector composed by a Silicon tracker, a calorimeter, and an anticoincidence system, dedicated to the study of the non-thermal Universe in the photon energy range from 0.3 MeV to 3 GeV - the lower energy limit can be pushed to energies as low as 150 keV, albeit with rapidly degrading angular resolution, for the tracker, and to 30 keV for calorimetric detection. The mission is based on an advanced space-proven detector technology, with unprecedented sensitivity, angular and energy resolution, combined with polarimetric capability. Thanks to its performance in the MeV-GeV domain, substantially improving its predecessors, e-ASTROGAM will open a new window on the non-thermal Universe, making pioneering observations of the most powerful Galactic and extragalactic sources, elucidating the nature of their relativistic outflows and their effects on the surroundings. With a line sensitivity in the MeV energy range one to two orders of magnitude better than previous generation instruments, e-ASTROGAM will determine the origin of key isotopes fundamental for the understanding of supernova explosion and the chemical evolution of our Galaxy. The mission will provide unique data of significant interest to a broad astronomical community, complementary to powerful observatories such as LIGO-Virgo-GEO600-KAGRA, SKA, ALMA, E-ELT, TMT, LSST, JWST, Athena, CTA, IceCube, KM3NeT, and the promise of eLISA.
Keywords: High-Energy Gamma-Ray Astronomy; High-Energy Astrophysics; Nuclear Astrophysics; Compton and Pair Creation Telescope; Gamma-Ray Bursts; Active Galactic Nuclei; Jets; Outflows; Multiwavelength Observations of the Universe; Counterparts of gravitational waves; Fermi; Dark Matter; Nucleosynthesis; Early Universe; Supernovae; Cosmic Rays; Cosmic Antimatter

The e-ASTROGAM mission Exploring the extreme Universe with gamma rays in the MeV - GeV range - De Angelis, Alessandro; Tatischeff, V.; Tavani, M.; Oberlack, U.; Grenier, I.; Hanloni, L.; Walter, R.; Argan, A.; Von Ballmoos, P.; Bulgarelli, Andrea; Donnarumma, Immacolata; Hernanz, Margarita; et al. (Experimental Astronomy, 2017)
e-ASTROGAM ('enhanced ASTROGAM') is a breakthrough Observatory space mission, with a detector composed by a Silicon tracker, a calorimeter, and an anticoincidence system, dedicated to the study of the non-thermal Universe in the photon energy range from 0.3 MeV to 3 GeV - the lower energy limit can be pushed to energies as low as 150 keV, albeit with rapidly degrading angular resolution, for the tracker, and to 30 keV for calorimetric detection. The mission is based on an advanced space-proven detector technology, with unprecedented sensitivity, angular and energy resolution, combined with polarimetric capability. Thanks to its performance in the MeV-GeV domain, substantially improving its predecessors, e-ASTROGAM will open a new window on the non-thermal Universe, making pioneering observations of the most powerful Galactic and extragalactic sources, elucidating the nature of their relativistic outflows and their effects on the surroundings. With a line sensitivity in the MeV energy range one to two orders of magnitude better than previous generation instruments, e-ASTROGAM will determine the origin of key isotopes fundamental for the understanding of supernova explosion and the chemical evolution of our Galaxy. The mission will provide unique data of significant interest to a broad astronomical community, complementary to powerful observatories such as LIGO-Virgo-GEO600-KAGRA, SKA, ALMA, E-ELT, TMT, LSST, JWST, Athena, CTA, IceCube, KM3NeT, and the promise of eLISA.
Keywords: High-Energy Gamma-Ray Astronomy; High-Energy Astrophysics; Nuclear Astrophysics; Compton and Pair Creation Telescope; Gamma-Ray Bursts; Active Galactic Nuclei; Jets; Outflows; Multiwavelength Observations of the Universe; Counterparts of gravitational waves; Fermi; Dark Matter; Nucleosynthesis; Early Universe; Supernovae; Cosmic Rays; Cosmic Antimatter

THE FERMI ALL-SKY VARIABILITY ANALYSIS: A LIST OF FLARING GAMMA-RAY SOURCES AND THE SEARCH FOR TRANSIENTS IN OUR GALAXY - Ackermann, M.; Ajello, M.; Albert, A.; Allafort, A.; Antolini, E.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Blandford, R. D.; et al. (Astrophysical Journal, 2013)
In this paper, we present the Fermi All-sky Variability Analysis (FAVA), a tool to systematically study the variability of the gamma-ray sky measured by the Large Area Telescope on board the Fermi Gamma-ray Space Telescope. For each direction on the sky, FAVA compares the number of gamma-rays observed in a given time window to the number of gamma-rays expected for the average emission detected from that direction. This method is used in weekly time intervals to derive a list of 215 flaring gamma-ray sources. We proceed to discuss the 27 sources found at Galactic latitudes smaller than 10 degrees and show that, despite their low latitudes, most of them are likely of extragalactic origin.
Keywords: binaries: general; BL Lacertae objects: general; catalogs; galaxies: active; stars: flare; surveys

The Fermi Galactic Center GeV Excess and Implications for Dark Matter - Ackermann, Markus; Ajello, Marco; Albert, A.; Atwood, W. B.; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; et al. (Astrophysical Journal, 2017)
The region around the Galactic Center (GC) is now well established to be brighter at energies of a few GeV than what is expected from conventional models of diffuse gamma-ray emission and catalogs of known gamma-ray sources. We study the GeV excess using 6.5 yr of data from the Fermi Large Area Telescope. We characterize the uncertainty of the GC excess spectrum and morphology due to uncertainties in cosmic-ray source distributions and propagation, uncertainties in the distribution of interstellar gas in the Milky Way, and uncertainties due to a potential contribution from the Fermi bubbles. We also evaluate uncertainties in the excess properties due to resolved point sources of gamma rays. The GC is of particular interest, as it would be expected to have the brightest signal from annihilation of weakly interacting massive dark matter (DM) particles. However, control regions along the Galactic plane, where a DM signal is not expected, show excesses of similar amplitude relative to the local background. Based on the magnitude of the systematic uncertainties, we conservatively report upper limits for the annihilation cross-section as a function of particle mass and annihilation channel.
CRIS-Team WoS Importer:2020-01-15

The Fermi Gamma-Ray Space Telescope Discovers the Pulsar in the Young Galactic Supernova Remnant CTA 1 - Abdo, A. A.; Ackermann, Markus; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Science, 2008)
Energetic young pulsars and expanding blast waves [ supernova remnants (SNRs)] are the most visible remains after massive stars, ending their lives, explode in core-collapse supernovae. The Fermi Gamma- Ray Space Telescope has unveiled a radio quiet pulsar located near the center of the compact synchrotron nebula inside the supernova remnant CTA 1. The pulsar, discovered through its gamma- ray pulsations, has a period of 316.86 milliseconds and a period derivative of 3.614 x 10(-13) seconds per second. Its characteristic age of 10(4) years is comparable to that estimated for the SNR. We speculate that most unidentified Galactic gamma- ray sources associated with star- forming regions and SNRs are such young pulsars.
CRIS-Team WoS Importer:2020-01-15

THE FERMI LARGE AREA TELESCOPE ON ORBIT: EVENT CLASSIFICATION, INSTRUMENT RESPONSE FUNCTIONS, AND CALIBRATION - Ackermann, Markus; Ajello, Marco; Albert, A.; Allafort, A.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal Supplement Series, 2012)
The Fermi Large Area Telescope (Fermi-LAT, hereafter LAT), the primary instrument on the Fermi Gamma-ray Space Telescope (Fermi) mission, is an imaging, wide field-of-view, high-energy gamma-ray telescope, covering the energy range from 20 MeV to more than 300 GeV. During the first years of the mission, the LAT team has gained considerable insight into the in-flight performance of the instrument. Accordingly, we have updated the analysis used to reduce LAT data for public release as well as the instrument response functions (IRFs), the description of the instrument performance provided for data analysis. In this paper, we describe the effects that motivated these updates. Furthermore, we discuss how we originally derived IRFs from Monte Carlo simulations and later corrected those IRFs for discrepancies observed between flight and simulated data. We also give details of the validations performed using flight data and quantify the residual uncertainties in the IRFs. Finally, we describe techniques the LAT team has developed to propagate those uncertainties into estimates of the systematic errors on common measurements such as fluxes and spectra of astrophysical sources.
CRIS-Team WoS Importer:2020-01-15

THE FERMI-LAT HIGH-LATITUDE SURVEY: SOURCE COUNT DISTRIBUTIONS AND THE ORIGIN OF THE EXTRAGALACTIC DIFFUSE BACKGROUND - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Antolini, E.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; et al. (Astrophysical Journal, 2010)
This is the first of a series of papers aimed at characterizing the populations detected in the high-latitude sky of the Fermi-LAT survey. In this work, we focus on the intrinsic spectral and flux properties of the source sample. We show that when selection effects are properly taken into account, Fermi sources are on average steeper than previously found (e.g., in the bright source list) with an average photon index of 2.40 +/- 0.02 over the entire 0.1-100 GeV energy band. We confirm that flat spectrum radio quasars have steeper spectra than BL Lacertae objects with an average index of 2.48 +/- 0.02 versus 2.18 +/- 0.02. Using several methods, we build the deepest source count distribution at GeV energies, deriving that the intrinsic source (i.e., blazar) surface density at F-100 >= 10(-9) ph cm(2) s(-1) is 0.12(-0.02)(+0.03) deg(-2). The integration of the source count distribution yields that point sources contribute 16(+/- 1.8)% (+/- 7% systematic uncertainty) of the GeV isotropic diffuse background. At the fluxes currently reached by LAT, we can rule out the hypothesis that pointlike sources (i.e., blazars) produce a larger fraction of the diffuse emission.
CRIS-Team WoS Importer:2020-01-15

The first catalog of Fermi-LAT sources below 100 MeV - Principe, Giacomo; Malyshev, Dmitry; Ballet, J.; Funk, Stefan (Astronomy & Astrophysics, 2018)
We present the first Fermi Large Area Telescope (LAT) low energy catalog (1FLE) of sources detected in the energy range 30-100 MeV. The imaging Compton telescope (COMPTEL) onboard NASA's Compton Gamma-Ray Observatory detected sources below 30 MeV, while catalogs of point sources released by the Fermi-LAT and EGRET collaborations use energies above 100 MeV. Because the Fermi-LAT detects gamma rays with energies as low as 20 MeV, we create a list of sources detected in the energy range between 30 and 100 MeV, which closes a gap of point source analysis between the COMPTEL catalog and the Fermi-LAT catalogs. One of the main challenges in the analysis of point sources is the construction of the background diffuse emission model. In our analysis, we use a background-independent method to search for point-like sources based on a wavelet transform implemented in the PGWave code. The 1FLE contains 198 sources detected above 3 sigma significance with eight years and nine months of the Fermi-LAT data. For 187 sources in the 1FLE catalog we have found an association in the Fermi-LAT 3FGL catalog: 148 are extragalactic, 22 are Galactic, and 17 are unclassified in the 3FGL. The ratio of the number of flat spectrum radio quasars (FSRQ) to BL Lacertae (BL Lacs) in 1FLE is three to one, which can be compared with an approximately 1:1 ratio for the 3FGL or a 1:6 ratio for 3FHL. The higher ratio of the FSRQs in the 1FLE is expected due to generally softer spectra of FSRQs relative to BL Lacs. Most BL Lacs in 1FLE are of low-synchrotron peaked blazar type (18 out of 31), which have softer spectra and higher redshifts than BL Lacs on average. Correspondingly, we find that the average redshift of the BL Lacs in 1FLE is higher than in 3FGL or 3FHL. There are 11 sources that do not have associations in the 3FGL. Most of the unassociated sources either come from regions of bright diffuse emission or have several known 3FGL sources in the vicinity, which can lead to source confusion. The remaining unassociated sources have significance less than 4 sigma.
CRIS-Team WoS Importer:2020-01-15

The first Cherenkov Telescope Array Science Symposium - Funk, Stefan; Hinton, J. A. (Nature Astronomy, 2019)
Held in Bologna, Italy, in May 2019, the conference served to engage a wide community in the planning for this first open observatory in very-high-energy gamma rays, expected to start full operation in 2025.
CRIS-Team Scopus Importer:2019-07-16

THE FIRST FERMI-LAT CATALOG OF SOURCES ABOVE 10 GeV - Ackermann, M.; Ajello, M.; Allafort, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bechtol, K.; Belfiore, A.; Bellazzini, R.; Bernieri, E.; et al. (Astrophysical Journal Supplement Series, 2013)
We present a catalog of gamma-ray sources at energies above 10 GeV based on data from the Large Area Telescope (LAT) accumulated during the first 3 yr of the Fermi Gamma-ray Space Telescope mission. The first Fermi catalog of > 10 GeV sources (1FHL) has 514 sources. For each source we present location, spectrum, a measure of variability, and associations with cataloged sources at other wavelengths. We found that 449 (87%) could be associated with known sources, of which 393 (76% of the 1FHL sources) are active galactic nuclei. Of the 27 sources associated with known pulsars, we find 20 (12) to have significant pulsations in the range > 10 GeV (> 25 GeV). In this work we also report that, at energies above 10 GeV, unresolved sources account for 27% +/- 8% of the isotropic. gamma-ray background, while the unresolved Galactic population contributes only at the few percent level to the Galactic diffuse background. We also highlight the subset of the 1FHL sources that are best candidates for detection at energies above 50-100 GeV with current and future ground-based gamma-ray observatories.
Keywords: catalogs; gamma rays: general

THE FIRST FERMI LAT SUPERNOVA REMNANT CATALOG - Acero, F.; Ackermann, M.; Ajello, M.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; et al. (Astrophysical Journal Supplement Series, 2016)
To uniformly determine the properties of supernova remnants (SNRs) at high energies, we have developed the first systematic survey at energies from 1 to 100 GeV using data from the Fermi Large Area Telescope (LAT). Based on the spatial overlap of sources detected at GeV energies with SNRs known from radio surveys, we classify 30 sources as likely GeV SNRs. We also report 14 marginal associations and 245 flux upper limits. A mock catalog in which the positions of known remnants are scrambled in Galactic longitude allows us to determine an upper limit of 22% on the number of GeV candidates falsely identified as SNRs. We have also developed a method to estimate spectral and spatial systematic errors arising from the diffuse interstellar emission model, a key component of all Galactic Fermi LAT analyses. By studying remnants uniformly in aggregate, we measure the GeV properties common to these objects and provide a crucial context for the detailed modeling of individual SNRs. Combining our GeV results with multiwavelength (MW) data, including radio, X-ray, and TeV, we demonstrate the need for improvements to previously sufficient, simple models describing the GeV and radio emission from these objects. We model the GeV and MW emission from SNRs in aggregate to constrain their maximal contribution to observed Galactic cosmic rays.
Keywords: acceleration of particles; catalogs; cosmic rays; gamma-rays: ISM; ISM: supernova remnants; radiation mechanisms: nonthermal

THE FIRST FERMI MULTIFREQUENCY CAMPAIGN ON BL LACERTAE: CHARACTERIZING THE LOW-ACTIVITY STATE OF THE EPONYMOUS BLAZAR - Abdo, A. A.; Ackermann, Markus; Ajello, Marco; Antolini, E.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Berenji, Bijan; Blandford, R. D.; et al. (Astrophysical Journal, 2011)
We report on observations of BL Lacertae during the first 18 months of Fermi LAT science operations and present results from a 48 day multifrequency coordinated campaign from 2008 August 19 to 2008 October 7. The radio to gamma-ray behavior of BL Lac is unveiled during a low-activity state thanks to the coordinated observations of radio-band (Metsahovi and VLBA), near-IR/optical (Tuorla, Steward, OAGH, and MDM), and X-ray (RXTE and Swift) observatories. No variability was resolved in gamma rays during the campaign, and the brightness level was 15 times lower than the level of the 1997 EGRET outburst. Moderate and uncorrelated variability has been detected in UV and X-rays. The X-ray spectrum is found to be concave, indicating the transition region between the low- and high-energy components of the spectral energy distribution (SED). VLBA observation detected a synchrotron spectrum self-absorption turnover in the innermost part of the radio jet appearing to be elongated and inhomogeneous, and constrained the average magnetic field there to be less than 3 G. Over the following months, BL Lac appeared variable in gamma rays, showing flares (in 2009 April and 2010 January). There is no evidence for the correlation of gamma rays with the optical flux monitored from the ground in 18 months. The SED may be described by a single-zone or a two-zone synchrotron self-Compton (SSC) model, but a hybrid SSC plus external radiation Compton model seems to be preferred based on the observed variability and the fact that it provides a fit closest to equipartition.
CRIS-Team WoS Importer:2020-01-15

The Fourth Catalog of Active Galactic Nuclei Detected by the Fermi Large Area Telescope - Ajello, M.; Angioni, R.; Axelsson, M.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Becerra Gonzalez, J.; Bellazzini, R.; Bissaldi, E.; Bloom, E. D.; Bonino, R.; Bottacini, E.; et al. (Astrophysical Journal, 2020)
The fourth catalog of active galactic nuclei (AGNs) detected by the Fermi Gamma-ray Space Telescope Large Area Telescope (4LAC) between 2008 August 4 and 2016 August 2 contains . It includes 85% more sources than the previous 3LAC catalog based on 4 yr of data. AGNs represent at least 79% of the high-latitude sources in the fourth Fermi-Large Area Telescope Source Catalog (4FGL), which covers the energy range from 50 MeV to 1 TeV. In addition, gamma-ray AGNs are found at low Galactic latitudes. Most of the 4LAC AGNs are blazars (98%), while the remainder are other types of AGNs. The blazar population consists of 24% Flat Spectrum Radio Quasars (FSRQs), 38% BL Lac-type objects, and 38% blazar candidates of unknown types (BCUs). On average, FSRQs display softer spectra and stronger variability in the gamma-ray band than BL Lacs do, confirming previous findings. All AGNs detected by ground-based atmospheric Cerenkov telescopes are also found in the 4LAC.
CRIS-Team WoS Importer:2020-04-17

The Fourth Catalog of Active Galactic Nuclei Detected by the Fermi Large Area Telescope: Data Release 3 - Ajello, M.; Baldini, L.; Ballet, J.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Berretta, A.; Bissaldi, E.; Bonino, R.; Brill, A.; Bruel, P.; Buson, S.; et al. (Astrophysical Journal Supplement Series, 2022)
An incremental version of the fourth catalog of active galactic nuclei (AGNs) detected by the Fermi Large Area Telescope is presented. This version (4LAC-DR3) derives from the third data release of the 4FGL catalog based on 12 yr of E > 50 MeV gamma-ray data, where the spectral parameters, spectral energy distributions (SEDs), yearly light curves, and associations have been updated for all sources. The new reported AGNs include 587 blazar candidates and four radio galaxies. We describe the properties of the new sample and outline changes affecting the previously published one. We also introduce two new parameters in this release, namely the peak energy of the SED high-energy component and the corresponding flux. These parameters allow an assessment of the Compton dominance, the ratio of the inverse-Compton to the synchrotron-peak luminosities, without relying on X-ray data.
CRIS-Team WoS Importer:2023-01-20

The Gamma-ray Cherenkov Telescope, an end-to end Schwarzschild-Couder telescope prototype proposed for the Cherenkov Telescope Array - Dournaux, J. L.; Abchiche, A.; Allan, D.; Amans, J. P.; Armstrong, T. P.; Balzer, A.; Berge, D.; Boisson, C.; Bousquet, J. -J.; Brown, A. M.; Bryan, M.; Buchholtz, G.; et al. (GROUND-BASED AND AIRBORNE INSTRUMENTATION FOR ASTRONOMY VI, 2016)
CRIS-Team WoS Importer:2020-01-15

The Gamma-ray Cherenkov Telescope for the Cherenkov Telescope Array - Tibaldo, Luigi; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Bergey, D.; Boisson, C.; Bousquet, J. -J.; Brown, A. M.; Bryan, M.; Buchholtz, G.; et al. (HIGH ENERGY GAMMA-RAY ASTRONOMY, 2017)
CRIS-Team WoS Importer:2020-01-15

The gamma-ray spectrum of the core of Centaurus A as observed with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Armand, C.; Arrieta, M.; Backes, Michael; Balzer, A.; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
Centaurus A (Cen A) is the nearest radio galaxy discovered as a very-high-energy (VHE; 100 GeV-100 TeV) gamma-ray source by the High Energy Stereoscopic System (H.E.S.S.). It is a faint VHE gamma-ray emitter, though its VHE flux exceeds both the extrapolation from early Fermi-LAT observations as well as expectations from a (misaligned) single-zone synchrotron-self Compton (SSC) description. The latter satisfactorily reproduces the emission from Cen A at lower energies up to a few GeV. New observations with H.E.S.S., comparable in exposure time to those previously reported, were performed and eight years of Fermi-LAT data were accumulated to clarify the spectral characteristics of the gamma-ray emission from the core of Cen A. The results allow us for the first time to achieve the goal of constructing a representative, contemporaneous gamma-ray core spectrum of Cen A over almost five orders of magnitude in energy. Advanced analysis methods, including the template fitting method, allow detection in the VHE range of the core with a statistical significance of 12 sigma on the basis of 213 hours of total exposure time. The spectrum in the energy range of 250 GeV-6 TeV is compatible with a power-law function with a photon index Gamma = 2.52 +/- 0.13(stat) +/- 0.20(sys). An updated Fermi-LAT analysis provides evidence for spectral hardening by Delta Gamma similar or equal to 0.4 +/- 0.1 at gamma-ray energies above 2.8(-0.6)(+1.0) GeV at a level of 4.0 sigma. The fact that the spectrum hardens at GeV energies and extends into the VHE regime disfavour a single-zone SSC interpretation for the overall spectral energy distribution (SED) of the core and is suggestive of a new gamma-ray emitting component connecting the high-energy emission above the break energy to the one observed at VHE energies. The absence of significant variability at both GeV and TeV energies does not yet allow disentanglement of the physical nature of this component, though a jet-related origin is possible and a simple two-zone SED model fit is provided to this end.
CRIS-Team WoS Importer:2020-01-15
Keywords: Radiation mechanisms: non-thermal; Gamma rays: galaxies

The GCT camera for the Cherenkov Telescope Array - Lapington, J. S.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, David; Boisson, C.; Bousquet, J. -J.; Bose, R.; Brown, A. M.; Bryan, M.; et al. (ELSEVIER SCIENCE BV, 2017)
The Gamma Cherenkov Telescope (GCT) is one of the designs proposed for the Small Sized Telescope (SST) section of the Cherenkov Telescope Array (CTA). The GCT uses dual-mirror optics, resulting in a compact telescope with good image quality and a large field of view with a smaller, more economical, camera than is achievable with conventional single mirror solutions. The photon counting GCT camera is designed to record the flashes of atmospheric Cherenkov light from gamma and cosmic ray initiated cascades, which last only a few tens of nanoseconds.The GCT optics require that the camera detectors follow a convex surface with a radius of curvature of 1 m and a diameter of similar to 35 cm, which is approximated by tiling the focal plane with 32 modules. The first camera prototype is equipped with multi-anode photomultipliers, each comprising an 8x8 array of 6x6 mm(2) pixels to provide the required angular scale, adding up to 2048 pixels in total. Detector signals are shaped, amplified and digitised by electronics based on custom ASICs that provide digitisation at 1 GSample/s. The camera is self-triggering, retaining images where the focal plane light distribution matches predefined spatial and temporal criteria. The electronics are housed in the liquid-cooled, sealed camera enclosure. LED flashers at the corners of the focal plane provide a calibration source via reflection from the secondary mirror.The first GCT camera prototype underwent preliminary laboratory tests last year. In November 2015, the camera was installed on a prototype GCT telescope (SST-GATE) in Paris and was used to successfully record the first Cherenkov light of any CTA prototype, and the first Cherenkov light seen with such a dual-mirror optical system. A second full-camera prototype based on Silicon Photomultipliers is under construction. Up to 35 GCTs are envisaged for CTA.
Keywords: GCT; Cherenkov Telescope Array; Schwarzschild-Couder; Imaging air Cherenkov telescope; Photon-counting; Camera

The GCT camera for the Cherenkov Telescope Array - Lapington, J. S.; Abchiche, A.; Allan, D.; Amans, J. -P.; Armstrong, T. P.; Balzer, A.; Berge, David; Boisson, C.; Bousquet, J. -J.; Bose, R.; Brown, A. M.; Bryan, M.; et al. (ELSEVIER SCIENCE BV, 2017)
The Gamma Cherenkov Telescope (GCT) is one of the designs proposed for the Small Sized Telescope (SST) section of the Cherenkov Telescope Array (CTA). The GCT uses dual-mirror optics, resulting in a compact telescope with good image quality and a large field of view with a smaller, more economical, camera than is achievable with conventional single mirror solutions. The photon counting GCT camera is designed to record the flashes of atmospheric Cherenkov light from gamma and cosmic ray initiated cascades, which last only a few tens of nanoseconds.The GCT optics require that the camera detectors follow a convex surface with a radius of curvature of 1 m and a diameter of similar to 35 cm, which is approximated by tiling the focal plane with 32 modules. The first camera prototype is equipped with multi-anode photomultipliers, each comprising an 8x8 array of 6x6 mm(2) pixels to provide the required angular scale, adding up to 2048 pixels in total. Detector signals are shaped, amplified and digitised by electronics based on custom ASICs that provide digitisation at 1 GSample/s. The camera is self-triggering, retaining images where the focal plane light distribution matches predefined spatial and temporal criteria. The electronics are housed in the liquid-cooled, sealed camera enclosure. LED flashers at the corners of the focal plane provide a calibration source via reflection from the secondary mirror.The first GCT camera prototype underwent preliminary laboratory tests last year. In November 2015, the camera was installed on a prototype GCT telescope (SST-GATE) in Paris and was used to successfully record the first Cherenkov light of any CTA prototype, and the first Cherenkov light seen with such a dual-mirror optical system. A second full-camera prototype based on Silicon Photomultipliers is under construction. Up to 35 GCTs are envisaged for CTA.
Keywords: GCT; Cherenkov Telescope Array; Schwarzschild-Couder; Imaging air Cherenkov telescope; Photon-counting; Camera

The GeV-TeV connection in galactic gamma-ray sources - Funk, Stefan; Reimer, Olaf; Torres, D. F.; Hinton, J. A. (Astrophysical Journal, 2008)
Recent observations with atmospheric Cerenkov telescope systems such as H. E. S. S. and MAGIC have revealed a large number of new sources of very high energy (VHE) gamma-rays from 100 GeV to 100 TeV, mostly concentrated along the Galactic plane. At lower energies (100MeVto 10 GeV) the satellite-based instrument EGRET revealed a population of sources clustering along the Galactic plane. Given their adjacent energy bands, a systematic correlation study between the two source catalogs seems appropriate. Here, the populations of Galactic sources in both energy domains are characterized on observational as well as on phenomenological grounds. Surprisingly few common sources are found in terms of positional coincidence and spectral consistency. These common sources and their potential counterparts and emission mechanisms are discussed in detail. In cases of detection in only one energy band, for the first time consistent upper limits in the other energy band have been derived. The EGRET upper limits are rather unconstraining due to the sensitivity mismatch to current VHE instruments. The VHE upper limits put strong constraints on simple power-law extrapolation of several of the EGRET spectra and thus strongly suggest cutoffs in the unexplored energy range from 10 to 100 GeV. Physical reasons for the existence of cutoffs and for differences in the source population at GeV and TeV energies are discussed. Finally, predictions are derived for common GeV-TeV sources for the upcoming GLAST mission, bridging for the first time the energy gap between current GeV and TeV instruments.
CRIS-Team WoS Importer:2020-01-15

The HESS Galactic plane survey - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; Becherini, Y.; et al. (Astronomy & Astrophysics, 2018)
We present the results of the most comprehensive survey of the Galactic plane in very high-energy (VHE) gamma-rays, including a public release of Galactic sky maps, a catalog of VHE sources, and the discovery of 16 new sources of VHE gamma-rays. The High Energy Spectroscopic System (H.E.S.S.) Galactic plane survey (HGPS) was a decade-long observation program carried out by the H.E.S.S. I array of Cherenkov telescopes in Namibia from 2004 to 2013. The observations amount to nearly 2700 h of quality-selected data, covering the Galactic plane at longitudes from l = 250 degrees to 65 degrees and latitudes vertical bar b vertical bar <= 3 degrees. In addition to the unprecedented spatial coverage, the HGPS also features a relatively high angular resolution (0.08 degrees approximate to 5 arcmin mean point spread function 68% containment radius), sensitivity (less than or similar to 1.5% Crab flux for point-like sources), and energy range (0.2-100 TeV). We constructed a catalog of VHE gamma-ray sources from the HGPS data set with a systematic procedure for both source detection and characterization of morphology and spectrum. We present this likelihood-based method in detail, including the introduction of a model component to account for unresolved, large-scale emission along the Galactic plane. In total, the resulting HGPS catalog contains 78 VHE sources, of which 14 are not reanalyzed here, for example, due to their complex morphology, namely shell-like sources and the Galactic center region. Where possible, we provide a firm identification of the VHE source or plausible associations with sources in other astronomical catalogs. We also studied the characteristics of the VHE sources with source parameter distributions. 16 new sources were previously unknown or unpublished, and we individually discuss their identifications or possible associations. We firmly identified 31 sources as pulsar wind nebulae (PWNe), supernova remnants (SNRs), composite SNRs, or gamma-ray binaries. Among the 47 sources not yet identified, most of them (36) have possible associations with cataloged objects, notably PWNe and energetic pulsars that could power VHE PWNe.
Keywords: gamma rays: general; surveys; Galaxy: general

The HESS survey of the inner galaxy in very high energy gamma rays - Funk, Stefan; et al. (Astrophysical Journal, 2006)
We report on a survey of the inner part of the Galactic plane in very high energy gamma rays with the H. E. S. S. Cerenkov telescope system. The Galactic plane between +/- 30 degrees in longitude and 3 +/-degrees in latitude relative to the Galactic center was observed in 500 pointings for a total of 230 hr, reaching an average flux sensitivity of 2% of the Crab Nebula at energies above 200 GeV. Fourteen previously unknown sources were detected at a significance level greater than 4 sigma after accounting for all trials involved in the search. Initial results on the eight most significant of these sources were already reported elsewhere (Aharonian and coworkers). Here we present detailed spectral and morphological information for all the new sources, along with a discussion on possible counterparts in other wavelength bands. The distribution in Galactic latitude of the detected sources appears to be consistent with a scale height in the Galactic disk for the parent population smaller than 100 pc, consistent with expectations for supernova remnants and/or pulsar wind nebulae.
CRIS-Team WoS Importer:2020-01-15

The Imprint of the Extragalactic Background Light in the Gamma-Ray Spectra of Blazars - Ackermann, Markus; Ajello, Marco; Allafort, A.; Schady, Patricia; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Blandford, R. D.; Bloom, E. D.; Borgland, A. W.; et al. (Science, 2012)
The light emitted by stars and accreting compact objects through the history of the universe is encoded in the intensity of the extragalactic background light (EBL). Knowledge of the EBL is important to understand the nature of star formation and galaxy evolution, but direct measurements of the EBL are limited by galactic and other foreground emissions. Here, we report an absorption feature seen in the combined spectra of a sample of gamma-ray blazars out to a redshift of z similar to 1.6. This feature is caused by attenuation of gamma rays by the EBL at optical to ultraviolet frequencies and allowed us to measure the EBL flux density in this frequency band.
CRIS-Team WoS Importer:2020-01-15

THE LOW-FREQUENCY RADIO CATALOG OF FLAT-SPECTRUM SOURCES - Massaro, F.; Giroletti, M.; D'Abrusco, R.; Masetti, N.; Paggi, A.; Cowperthwaite, Philip S.; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2014)
A well known property of the gamma-ray sources detected by Cos-B in the 1970s, by the Compton Gamma-Ray Observatory in the 1990s, and recently by the Fermi observations is the presence of radio counterparts, particularly for those associated with extragalactic objects. This observational evidence is the basis of the radio-gamma-ray connection established for the class of active galactic nuclei known as blazars. In particular, the main spectral property of the radio counterparts associated with gamma-ray blazars is that they show a flat spectrum in the GHz frequency range. Our recent analysis dedicated to search blazar-like candidates as potential counterparts for the unidentified gamma-ray sources allowed us to extend the radio-gamma-ray connection in the MHz regime. We also showed that blazars below 1 GHz maintain flat radio spectra. Thus, on the basis of these new results, we assembled a low-frequency radio catalog of flat-spectrum sources built by combining the radio observations of the Westerbork Northern Sky Survey and of the Westerbork in the southern hemisphere catalog with those of the NRAO Very Large Array Sky survey (NVSS). This could be used in the future to search for new, unknown blazar-like counterparts of gamma-ray sources. First, we found NVSS counterparts of Westerbork Synthesis Radio Telescope radio sources, and then we selected flat-spectrum radio sources according to a new spectral criterion, specifically defined for radio observations performed below 1 GHz. We also described the main properties of the catalog listing 28,358 radio sources and their logN-logS distributions. Finally, a comparison with the Green Bank 6 cm radio source catalog was performed to investigate the spectral shape of the low-frequency flat-spectrum radio sources at higher frequencies.
Keywords: galaxies: active; quasars: general; radiation mechanisms: non-thermal; surveys

The magnetic bootstrap - Funk, Stefan; et al. (FIRST GLAST SYMPOSIUM, 2007)
CRIS-Team WoS Importer:2020-01-15

The radio counterpart of the likely TeV binary HESS J0632+057 - Skilton, J. L.; Pandey-Pommier, M.; Hinton, J. A.; Cheung, C. C.; Aharonian, F. A.; Brucker, Julia; Dubus, Guillaume; Fiasson, A.; Funk, Stefan; Gallant, Y.; Marcowith, A.; Reimer, Olaf (Monthly Notices of the Royal Astronomical Society, 2009)
The few known gamma-ray binary systems are all associated with variable radio and X-ray emission. The TeV source HESS J0632+057, apparently associated with the Be star MWC 148, is plausibly I new member of this class. Following the identification of a variable X-ray counterpart to the TeV source we conducted Giant Metrewave Radio Telescope (GMRT) and Very Large Array (VLA) observations in 2008 June-September to search for the radio counterpart of this object. A point-like radio source at the position of the star is detected in both 1280-MHz GMRT and 5-GHz VLA observations, with an average spectral index, alpha, of similar to 0.6. In the VLA data there is significant flux variability oil similar to month time-scales around the mean flux density of approximate to 0.3 mJy. These radio properties (and the overall spectral energy distribution) are consistent with an interpretation of HESS J0632+057 as a lower power analogue of the established gamma-ray binary systems.
CRIS-Team WoS Importer:2020-01-15

The Search for Spatial Extension in High-latitude Sources Detected by the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal Supplement Series, 2018)
We present a search for spatial extension in high-latitude (vertical bar b vertical bar > 5 degrees) sources in recent Fermi point source catalogs. The result is the Fermi High-Latitude Extended Sources Catalog, which provides source extensions (or upper limits thereof) and likelihood profiles for a suite of tested source morphologies. We find 24. extended sources, 19 of which were not previously characterized as extended. These include sources that are potentially associated with supernova remnants and star-forming regions. We also found extended.-ray emission in the vicinity of the Cen. A radio lobes and-at GeV energies for the first time-spatially coincident with the radio emission of the SNR CTA 1, as well as from the Crab Nebula. We also searched for halos around active galactic nuclei, which are predicted from electromagnetic cascades induced by the e(+)e(-) pairs that are deflected in intergalactic magnetic fields. These pairs are produced when gamma-rays interact with background radiation fields. We do not find evidence for extension in individual sources or in stacked source samples. This enables us to place limits on the flux of the extended source components, which are then used to constrain the intergalactic magnetic field to be stronger than 3 x 10(-16) G for a coherence length lambda greater than or similar to 10 kpc, even when conservative assumptions on the source duty cycle are made. This improves previous limits by several orders of magnitude.
Keywords: BL Lacertae objects: general; catalogs; gamma rays: general; ISM: H II Regions; ISM: supernova remnants

The Search for Spatial Extension in High-latitude Sources Detected by the Fermi Large Area Telescope - Ackermann, Markus; Ajello, Marco; Baldini, Luca; Ballet, Jean; Barbiellini, G.; Bastieri, Denis; Bellazzini, R.; Bissaldi, Elisabetta; Blandford, R. D.; Bloom, E. D.; Bonino, Raffaella; Bottacini, E.; et al. (Astrophysical Journal Supplement Series, 2018)
We present a search for spatial extension in high-latitude (vertical bar b vertical bar > 5 degrees) sources in recent Fermi point source catalogs. The result is the Fermi High-Latitude Extended Sources Catalog, which provides source extensions (or upper limits thereof) and likelihood profiles for a suite of tested source morphologies. We find 24. extended sources, 19 of which were not previously characterized as extended. These include sources that are potentially associated with supernova remnants and star-forming regions. We also found extended.-ray emission in the vicinity of the Cen. A radio lobes and-at GeV energies for the first time-spatially coincident with the radio emission of the SNR CTA 1, as well as from the Crab Nebula. We also searched for halos around active galactic nuclei, which are predicted from electromagnetic cascades induced by the e(+)e(-) pairs that are deflected in intergalactic magnetic fields. These pairs are produced when gamma-rays interact with background radiation fields. We do not find evidence for extension in individual sources or in stacked source samples. This enables us to place limits on the flux of the extended source components, which are then used to constrain the intergalactic magnetic field to be stronger than 3 x 10(-16) G for a coherence length lambda greater than or similar to 10 kpc, even when conservative assumptions on the source duty cycle are made. This improves previous limits by several orders of magnitude.
Keywords: BL Lacertae objects: general; catalogs; gamma rays: general; ISM: H II Regions; ISM: supernova remnants

THE SECOND CATALOG OF ACTIVE GALACTIC NUCLEI DETECTED BY THE FERMI LARGE AREA TELESCOPE - Ackermann, Markus; Ajello, Marco; Allafort, A.; Antolini, E.; Atwood, W. B.; Axelsson, Magnus; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; et al. (Astrophysical Journal, 2011)
The second catalog of active galactic nuclei (AGNs) detected by the Fermi Large Area Telescope (LAT) in two years of scientific operation is presented. The second LAT AGN catalog (2LAC) includes 1017 gamma-ray sources located at high Galactic latitudes (vertical bar b vertical bar > 10 degrees) that are detected with a test statistic (TS) greater than 25 and associated statistically with AGNs. However, some of these are affected by analysis issues and some are associated with multiple AGNs. Consequently, we define a Clean Sample which includes 886 AGNs, comprising 395 BL Lacertae objects (BL Lac objects), 310 flat-spectrum radio quasars (FSRQs), 157 candidate blazars of unknown type (i.e., with broadband blazar characteristics but with no optical spectral measurement yet), 8 misaligned AGNs, 4 narrow-line Seyfert 1 (NLS1s), 10 AGNs of other types, and 2 starburst galaxies. Where possible, the blazars have been further classified based on their spectral energy distributions (SEDs) as archival radio, optical, and X-ray data permit. While almost all FSRQs have a synchrotron-peak frequency < 10(14) Hz, about half of the BL Lac objects have a synchrotron-peak frequency > 10(15) Hz. The 2LAC represents a significant improvement relative to the first LAT AGN catalog (1LAC), with 52% more associated sources. The full characterization of the newly detected sources will require more broadband data. Various properties, such as gamma-ray fluxes and photon power-law spectral indices, redshifts, gamma-ray luminosities, variability, and archival radio luminosities and their correlations are presented and discussed for the different blazar classes. The general trends observed in 1LAC are confirmed.
CRIS-Team WoS Importer:2020-01-15

The Second Catalog of Flaring Gamma-Ray Sources from the Fermi All-sky Variability Analysis - Abdollahi, S.; Ackermann, Markus; Ajello, Marco; Albert, A.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Gonzalez, J. Becerra; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; et al. (Astrophysical Journal, 2017)
We present the second catalog of flaring gamma-ray sources (2FAV) detected with the Fermi All-sky Variability Analysis (FAVA), a tool that blindly searches for transients over the entire sky observed by the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope. With respect to the first FAVA catalog, this catalog benefits from a larger data set, the latest LAT data release (Pass 8), as well as from an improved analysis that includes likelihood techniques for a more precise localization of the transients. Applying this analysis to the first 7.4 years of Fermi observations, and in two separate energy bands 0.1-0.8 GeV and 0.8-300 GeV, a total of 4547 flares were detected with significance greater than 6s (before trials), on the timescale of one week. Through spatial clustering of these flares, 518 variable gamma-ray sources were identified. Based on positional coincidence, likely counterparts have been found for 441 sources, mostly among the blazar class of active galactic nuclei. For 77 2FAV sources, no likely gamma-ray counterpart has been found. For each source in the catalog, we provide the time, location, and spectrum of each flaring episode. Studying the spectra of the flares, we observe a harder-when-brighter behavior for flares associated with blazars, with the exception of BL Lac flares detected in the low-energy band. The photon indexes of the flares are never significantly smaller than 1.5. For a leptonic model, and under the assumption of isotropy, this limit suggests that the spectrum of freshly accelerated electrons is never harder than p similar to 2.
Keywords: astroparticle physics; catalogs; galaxies: active; gamma rays: general; techniques: photometric

THE SECOND FERMI LARGE AREA TELESCOPE CATALOG OF GAMMA-RAY PULSARS - Abdo, A. A.; Ajello, M.; Allafort, A.; Baldini, L.; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, D.; Belfiore, A.; Bellazzini, R.; Bhattacharyya, B.; Bissaldi, E.; et al. (Astrophysical Journal Supplement Series, 2013)
This catalog summarizes 117 high-confidence >= 0.1 GeV gamma-ray pulsar detections using three years of data acquired by the Large Area Telescope (LAT) on the Fermi satellite. Half are neutron stars discovered using LAT data through periodicity searches in gamma-ray and radio data around LAT unassociated source positions. The 117 pulsars are evenly divided into three groups: millisecond pulsars, young radio-loud pulsars, and young radio-quiet pulsars. We characterize the pulse profiles and energy spectra and derive luminosities when distance information exists. Spectral analysis of the off-peak phase intervals indicates probable pulsar wind nebula emission for four pulsars, and off-peak magnetospheric emission for several young and millisecond pulsars. We compare the gamma-ray properties with those in the radio, optical, and X-ray bands. We provide flux limits for pulsars with no observed gamma-ray emission, highlighting a small number of gamma-faint, radio-loud pulsars. The large, varied gamma-ray pulsar sample constrains emission models. Fermi's selection biases complement those of radio surveys, enhancing comparisons with predicted population distributions.
Keywords: catalogs; pulsars: general; stars: neutron

THE SPECTRUM AND MORPHOLOGY OF THE FERMI BUBBLES - Ackermann, M.; Albert, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; Bottacini, E.; et al. (Astrophysical Journal, 2014)
The Fermi bubbles are two large structures in the gamma-ray sky extending to 55 degrees above and below the Galactic center. We analyze 50 months of Fermi Large Area Telescope data between 100MeV and 500 GeV above 10 degrees in Galactic latitude to derive the spectrum and morphology of the Fermi bubbles. We thoroughly explore the systematic uncertainties that arise when modeling the Galactic diffuse emission through two separate approaches. The gamma-ray spectrum is well described by either a log parabola or a power law with an exponential cutoff. We exclude a simple power law with more than 7 sigma significance. The power law with an exponential cutoff has an index of 1.9 +/- 0.2 and a cutoff energy of 110 +/- 50 GeV. We find that the gamma-ray luminosity of the bubbles is 4.4(-0.9)(+2.4) x 10(37) erg s(-1). We confirm a significant enhancement of gamma-ray emission in the southeastern part of the bubbles, but we do not find significant evidence for a jet. No significant variation of the spectrum across the bubbles is detected. The width of the boundary of the bubbles is estimated to be 3.4(-2.6)(+3.7) deg. Both inverse Compton (IC) models and hadronic models including IC emission from secondary leptons fit the gamma-ray data well. In the IC scenario, synchrotron emission from the same population of electrons can also explain the WMAP and Planck microwave haze with a magnetic field between 5 and 20 mu G.
Keywords: astroparticle physics; cosmic rays; Galaxy: general; Galaxy: halo; gamma rays: diffuse background; methods: data analysis

THE SPECTRUM OF ISOTROPIC DIFFUSE GAMMA-RAY EMISSION BETWEEN 100 MeV AND 820 GeV - Ackermann, M.; Ajello, M.; Albert, A.; Atwood, W. B.; Baldini, L.; Ballet, J.; Barbiellini, G.; Bastieri, Denis; Bechtol, K.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; et al. (Astrophysical Journal, 2015)
The gamma-ray sky can be decomposed into individually detected sources, diffuse emission attributed to the interactions of Galactic cosmic rays with gas and radiation fields, and a residual all-sky emission component commonly called the isotropic diffuse gamma-ray background (IGRB). The IGRB comprises all extragalactic emissions too faint or too diffuse to be resolved in a given survey, as well as any residual Galactic foregrounds that are approximately isotropic. The first IGRB measurement with the Large Area Telescope (LAT) on board the Fermi Gamma-ray Space Telescope (Fermi) used 10 months of sky-survey data and considered an energy range between 200 MeV and 100 GeV. Improvements in event selection and characterization of cosmic-ray backgrounds, better understanding of the diffuse Galactic emission (DGE), and a longer data accumulation of 50 months allow for a refinement and extension of the IGRB measurement with the LAT, now covering the energy range from 100 MeV to 820 GeV. The IGRB spectrum shows a significant high-energy cutoff feature and can be well described over nearly four decades in energy by a power law with exponential cutoff having a spectral index of 2.32 +/- 0.02 and a break energy of (279 +/- 52) GeV using our baseline DGE model. The total intensity attributed to the IGRB is (7.2 +/- 0.6) x 10(-6) cm(-2) s(-1) sr(-1) above 100 MeV, with an additional +15%/-30% systematic uncertainty due to the Galactic diffuse foregrounds.
Keywords: diffuse radiation; gamma rays: diffuse background

The starburst galaxy NGC 253 revisited by H.E.S.S. and Fermi-LAT - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, Michael; Barnard, Monica; Becherini, Y.; Tjus, J. Becker; et al. (Astronomy & Astrophysics, 2018)
Context. NGC 253 is one of only two starburst galaxies found to emit gamma-rays from hundreds of MeV to multi-TeV energies. Accurate measurements of the very-high-energy (VHE; E> 100 GeV) and high-energy (HE; E > 60 MeV) spectra are crucial to study the underlying particle accelerators, probe the dominant emission mechanism(s) and to study cosmic-ray interaction and transport.
CRIS-Team WoS Importer:2020-01-15
Keywords: Astroparticle physics; Galaxies: starburst; Gamma rays: galaxies

The supernova remnant W49B as seen with HESS and Fermi-LAT - Abdalla, H.; Abramowski, A.; Aharonian, F.; Benkhali, F. Ait; Akhperjanian, A. G.; Andersson, T.; Anguener, O.; Arrieta, M.; Aubert, P.; Backes, Michael; Balzer, A.; Barnard, Monica; et al. (Astronomy & Astrophysics, 2018)
The supernova remnant (SNR) W49B originated from a core-collapse supernova that occurred between one and four thousand years ago, and subsequently evolved into a mixed-morphology remnant, which is interacting with molecular clouds (MC). Gamma-ray observations of SNR-MC associations are a powerful tool to constrain the origin of Galactic cosmic rays, as they can probe the acceleration of hadrons through their interaction with the surrounding medium and subsequent emission of non-thermal photons. We report the detection of a gamma-ray source coincident with W49B at very high energies (VHE; E > 100 GeV) with the H.E.S.S. Cherenkov telescopes together with a study of the source with five years of Fermi-LAT high-energy gamma-ray (0.06-300 GeV) data. The smoothly connected, combined source spectrum, measured from 60 MeV to multi-TeV energies, shows two significant spectral breaks at 304 +/- 20 MeV and 8.4(-2.5)(+2.5) GeV; the latter is constrained by the joint fit from the two instruments. The detected spectral features are similar to those observed in several other SNR-MC associations and are found to be indicative of gamma-ray emission produced through neutral-pion decay.
Keywords: gamma rays: general; ISM: supernova remnants; ISM: clouds

The trigger system of the HESS telescope array - Funk, Stefan; et al. (Astroparticle Physics, 2004)
H.E.S.S. - The High Energy Stereoscopic System - is a new system of large atmospheric Cherenkov telescopes for GeV/TeV gamma-ray astronomy. This paper describes the trigger system of H.E.S.S. with emphasis on the multi-telescope array level trigger. The system trigger requires the simultaneous detection of air-showers by several telescopes at the hardware level. This requirement allows a suppression of background events which in turn leads to a lower system energy threshold for the detection of gamma-rays. The implementation of the H.E.S.S. trigger system is presented along with data taken to characterise its performance. (C) 2004 Elsevier B.V. All rights reserved.
CRIS-Team WoS Importer:2020-01-15

THE VELA PULSAR: RESULTS FROM THE FIRST YEAR OF FERMI LAT OBSERVATIONS - Abdo, A. A.; Ackermann, Markus; Ajello, M.; Allafort, A.; Atwood, W. B.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Baring, M. G.; Bastieri, Denis; Baughman, B. M.; Bechtol, K.; et al. (Astrophysical Journal, 2010)
We report on analysis of timing and spectroscopy of the Vela pulsar using 11 months of observations with the Large Area Telescope (LAT) on the Fermi Gamma-ray Space Telescope. The intrinsic brightness of Vela at GeV energies combined with the angular resolution and sensitivity of the LAT allows us to make the most detailed study to date of the energy-dependent light curves and phase-resolved spectra, using a LAT-derived timing model. The light curve consists of two peaks (P1 and P2) connected by bridge emission containing a third peak (P3). We have confirmed the strong decrease of the P1/P2 ratio with increasing energy seen with EGRET and previous Fermi LAT data, and observe that P1 disappears above 20 GeV. The increase with energy of the mean phase of the P3 component can be followed with much greater detail, showing that P3 and P2 are present up to the highest energies of pulsation. We find significant pulsed emission at phases outside the main profile, indicating that magnetospheric emission exists over 80% of the pulsar period. With increased high-energy counts the phase-averaged spectrum is seen to depart from a power law with simple exponential cutoff, and is better fit with a more gradual cutoff. The spectra in fixed-count phase bins are well fit with power laws with exponential cutoffs, revealing a strong and complex phase dependence of the cutoff energy, especially in the peaks. By combining these results with predictions of the outer magnetosphere models that map emission characteristics to phase, it will be possible to probe the particle acceleration and the structure of the pulsar magnetosphere with unprecedented detail.
CRIS-Team WoS Importer:2020-01-15

Three-dimensional imaging of xylem at cell wall level through near field nano holotomography - Koddenberg, Tim; Greving, Imke; Hagemann, Johannes; Flenner, Silja; Krause, Andreas; Laipple, Daniel; Klein, Kim C.; Schmitt, Uwe; Schuster, Max; Wolf, Andreas; Seifert, Maria; Ludwig, Veronika; et al. (Scientific Reports, 2021)
Detailed imaging of the three-dimensionally complex architecture of xylary plants is important for studying biological and mechanical functions of woody plants. Apart from common two-dimensional microscopy, X-ray micro-computed tomography has been established as a three-dimensional (3D) imaging method for studying the hydraulic function of wooden plants. However, this X-ray imaging method can barely reach the resolution needed to see the minute structures (e.g. pit membrane). To complement the xylem structure with 3D views at the nanoscale level, X-ray near-field nano-holotomography (NFH) was applied to analyze the wood species Pinus sylvestris and Fagus sylvatica. The demanded small specimens required focused ion beam (FIB) application. The FIB milling, however, influenced the image quality through gallium implantation on the cell-wall surfaces. The measurements indicated that NFH is appropriate for imaging wood at nanometric resolution. With a 26 nm voxel pitch, the structure of the cell-wall surface in Pinus sylvestris could be visualized in genuine detail. In wood of Fagus sylvatica, the structure of a pit pair, including the pit membrane, between two neighboring fibrous cells could be traced tomographically.
CRIS-Team Scopus Importer:2021-03-19

Time-resolved hadronic particle acceleration in the recurrent nova RS Ophiuchi - Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Ashkar, H.; Backes, M.; Baghmanyan, V.; Martins, V. Barbosa; Batzofin, R.; Becherini, Y.; Berge, D.; Bernloehr, K.; Bi, B.; et al. (Science, 2022)
Recurrent novae are repeating thermonuclear explosions in the outer layers of white dwarfs, due to the accretion of fresh material from a binary companion. The shock generated when ejected material slams into the companion star's wind can accelerate particles. We report very-high-energy [VHE: greater than or similar to 100 giga-electron volts] gamma rays from the recurrent nova RS Ophiuchi, up to 1 month after its 2021 outburst, observed using the High Energy Stereoscopic System (H.E.S.S.). The temporal profile of VHE emission is similar to that of lower-energy giga-electron volt emission, indicating a common origin, with a 2-day delay in peak flux. These observations constrain models of time-dependent particle energization, favoring a hadronic emission scenario over the leptonic alternative. Shocks in dense winds provide favorable environments for efficient acceleration of cosmic rays to very high energies.
CRIS-Team WoS Importer:2022-06-03

Towards a 3D likelihood analysis in very-high-energy γ-ray astronomy: The case of H.E.S.S. - Mohrmann, Lars; Nakashima, Kaori; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; van Eldik, Christopher; Ohm, Stefan (Proceedings of Science, 2019)
The estimation of the residual background due to cosmic ray-induced air showers represents a key element of every analysis of Imaging Atmospheric Cherenkov Telescope (IACT) data. In the past, most techniques have relied on a measurement of the background in supposedly source-free regions within the observed field of view. However, this approach is problematic in regions with many (potentially overlapping) γ-ray sources or large-scale diffuse γ-ray emission, like e.g. the Galactic Plane. For these cases, a template-based 3D likelihood analysis might be superior. In this approach, a spectro-morphological model template, consisting of one or multiple source components and a background component, is fit to the data, resulting in a complete spectral and spatial description of the field of view. In this contribution, we present our efforts to establish a 3D likelihood analysis for data taken with the H.E.S.S. system of IACTs, using the open-source analysis packages ctools and Gammapy. In particular, we focus on the development of a template model for the cosmic ray-induced background - a major challenge in such an approach - from archival H.E.S.S. data. We characterise the obtained model and demonstrate its application using publicly available H.E.S.S. data. The validation of this analysis approach on experimental data also constitutes an important step towards the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team Scopus Importer:2021-04-20

Trigger performance verification of the FlashCam prototype camera - Sailer, S.; Werner, F.; Hermann, G.; Barcelo, M.; Bauer, C.; Bernhard, S.; Biegger, M.; Canelli, F.; Capasso, M.; Diebold, S.; Eisenkolb, F.; Eschbach, Stefan; et al. (Nuclear Instruments and Methods in Physics Research Section A: Accelerators, Spectrometers, Detectors and Associated Equipment, 2019)
FlashCam is a camera proposed for the medium-sized telescopes of the Cherenkov Telescope Array (CTA). We compare camera trigger rates obtained from measurements with the camera prototype in the laboratory and Monte Carlo simulations, when scanning the parameter space of the fully-digital trigger logic and the intensity of a continuous light source mimicking the night sky background (NSB) during on-site operation. The comparisons of the measured data results to the Monte Carlo simulations are used to verify the FlashCam trigger logic and the expected trigger performance.
CRIS-Team Scopus Importer:2019-06-25
Keywords: CTA; DAQ; Data management; FlashCam; Front end; Trigger

Unresolved Gamma-Ray Sky through its Angular Power Spectrum - Ackermann, M.; Ajello, M.; Baldini, Luca; Ballet, J.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bonino, Raffaella; Bottacini, E.; Bregeon, J.; et al. (Physical Review Letters, 2018)
The gamma-ray sky has been observed with unprecedented accuracy in the last decade by the Fermi-large area telescope (LAT), allowing us to resolve and understand the high-energy Universe. The nature of the remaining unresolved emission [unresolved gamma-ray background (UGRB)] below the LAT source detection threshold can be uncovered by characterizing the amplitude and angular scale of the UGRB fluctuation field. This Letter presents a measurement of the UGRB autocorrelation angular power spectrum based on eight years of Fermi-LAT Pass 8 data products. The analysis is designed to be robust against contamination from resolved sources and noise systematics. The sensitivity to subthreshold sources is greatly enhanced with respect to previous measurements. We find evidence (with similar to 3.7 sigma significance) that the scenario in which two classes of sources contribute to the UGRB signal is favored over a single class. A double power law with exponential cutoff can explain the anisotropy energy spectrum well, with photon indices of the two populations being 2.55 +/- 0.23 and 1.86 +/- 0.15.
CRIS-Team WoS Importer:2020-01-15

UNVEILING THE NATURE OF THE UNIDENTIFIED GAMMA-RAY SOURCES. III. GAMMA-RAY BLAZAR-LIKE COUNTERPARTS AT LOW RADIO FREQUENCIES - Massaro, Francesco; D'Abrusco, Raffaele; Giroletti, Marcello; Paggi, Alessandro; Masetti, Nicola; Tosti, G.; Nori, M.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
About one-third of the gamma-ray sources listed in the second Fermi Large Area Telescope catalog (2FGL) have no firmly established counterpart at lower energies and so are classified as unidentified gamma-ray sources (UGSs). Here, we propose a new approach to find candidate counterparts for the UGSs based on the 325 MHz radio survey performed with the Westerbork Synthesis Radio Telescope in the northern hemisphere. First, we investigate the low-frequency radio properties of blazars, the largest known population of gamma-ray sources; then we search for sources with similar radio properties combining the information derived from theWesterbork Northern Sky Survey (WENSS) with those of the NRAO Very Large Array Sky Survey. We present a list of candidate counterparts for 32 UGSs with at least one counterpart in the WENSS. We also performed an extensive research in the literature to look for infrared and optical counterparts of the gamma-ray blazar candidates selected using the low-frequency radio observations to confirm their nature. On the basis of our multifrequency research, we identify 23 new gamma-ray blazar candidates out of the 32 UGSs investigated. Comparison with previous results on the UGSs is also presented. Finally, we speculate on the advantages of using low-frequency radio observations to associate UGSs and to search for gamma-ray pulsar candidates.
CRIS-Team WoS Importer:2020-01-15

UNVEILING THE NATURE OF THE UNIDENTIFIED GAMMA-RAY SOURCES. IV. THE SWIFT CATALOG OF POTENTIAL X-RAY COUNTERPARTS - Paggi, Alessandro; Massaro, Francesco; D'Abrusco, Raffaele; Smith, H. A.; Masetti, Nicola; Giroletti, Marcello; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
A significant fraction (similar to 30%) of the high-energy. gamma-ray sources listed in the second Fermi Large Area Telescope (LAT) catalog are still of unknown origin, having not yet been associated with counterparts at lower energies. To investigate the nature of these enigmatic sources, we present an extensive search of X-ray sources lying in the positional uncertainty region of a selected sample of these unidentified gamma-ray sources (UGSs) that makes use of all available observations performed by the Swift X-ray Telescope before 2013 March 31, available for 205 UGSs. To detect the fainter sources, we merged all the observations covering the Fermi LAT positional uncertainty region at a 95% level of confidence of each UGS. This yields a catalog of 357 X-ray sources, finding candidate X-ray counterparts for similar to 70% of the selected sample. In particular, 25% of the UGSs feature a single X-ray source within their positional uncertainty region, while 45% have multiple X-ray sources. For each X-ray source, we also looked in the corresponding Swift UVOT merged images for optical and ultraviolet counterparts, also performing source photometry. We found ultraviolet-optical correspondences for similar to 70% of the X-ray sources. We searched several major radio, infrared, optical, and ultraviolet surveys for possible counterparts within the positional error of the sources in the X-ray catalog to obtain additional information on their nature. Applying the kernel density estimation technique to infrared colors of Wide-Field Infrared Survey Explorer counterparts of our X-ray sources we select six gamma-ray blazar candidates. In addition, comparing our results with previous analyses, we select 11 additional gamma-ray blazar candidates.
CRIS-Team WoS Importer:2020-01-15

UNVEILING THE NATURE OF THE UNIDENTIFIED GAMMA-RAY SOURCES. V. ANALYSIS OF THE RADIO CANDIDATES WITH THE KERNEL DENSITY ESTIMATION - Massaro, Francesco; D'Abrusco, Raffaele; Paggi, Alessandro; Masetti, Nicola; Giroletti, Marcello; Tosti, G.; Smith, Howard A.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
Nearly one-third of the gamma-ray sources detected by Fermi are still unidentified, despite significant recent progress in this area. However, all of the gamma-ray extragalactic sources associated in the second Fermi-LAT catalog have a radio counterpart. Motivated by this observational evidence, we investigate all the radio sources of the major radio surveys that lie within the positional uncertainty region of the unidentified gamma-ray sources (UGSs) at a 95% level of confidence. First, we search for their infrared counterparts in the all-sky survey performed by the Wide-field Infrared Survey Explorer (WISE) and then we analyze their IR colors in comparison with those of the known gamma-ray blazars. We propose a new approach, on the basis of a two-dimensional kernel density estimation technique in the single [3.4] - [4.6] - [12] mu m WISE color-color plot, replacing the constraint imposed in our previous investigations on the detection at 22 mu m of each potential IR counterpart of the UGSs with associated radio emission. The main goal of this analysis is to find distant gamma-ray blazar candidates that, being too faint at 22 mu m, are not detected by WISE and thus are not selected by our purely IR-based methods. We find 55 UGSs that likely correspond to radio sources with blazar-like IR signatures. An additional 11 UGSs that have blazar-like IR colors have been found within the sample of sources found with deep recent Australia Telescope Compact Array observations.
CRIS-Team WoS Importer:2020-01-15

UNVEILING THE NATURE OF UNIDENTIFIED GAMMA-RAY SOURCES. II. RADIO, INFRARED, AND OPTICAL COUNTERPARTS OF THE GAMMA-RAY BLAZAR CANDIDATES - Massaro, Francesco; D'Abrusco, Raffaele; Paggi, Alessandro; Masetti, Nicola; Giroletti, Marcello; Tosti, G.; Smith, Howard A.; Funk, Stefan (Astrophysical Journal Supplement Series, 2013)
A significant fraction (similar to 30%) of the high-energy gamma-ray sources listed in the second Fermi Large Area Telescope catalog (2FGL) are still of unknown origin, being not yet associated with counterparts at low energies. We recently developed a new association method to identify if there is a. gamma-ray blazar candidate within the positional uncertainty region of a generic 2FGL source. This method is entirely based on the discovery that blazars have distinct infrared colors with respect to other extragalactic sources found, thanks to the Wide-field Infrared Survey Explorer (WISE) all-sky observations. Several improvements have also been performed to increase the efficiency of our method in recognizing. gamma-ray blazar candidates. In this paper we applied our method to two different samples, the first constituted by unidentified. gamma-ray sources (UGSs), and the second by active galaxies of uncertain type, both listed in the 2FGL. We present a catalog of IR counterparts for similar to 20% of the UGSs investigated. Then, we also compare our results for the associated sources with those present in the literature. In addition, we illustrate the extensive archival research carried out to identify the radio, infrared, optical, and X-ray counterparts of the WISEselected,. gamma-ray blazar candidates. Finally, we discuss the future developments of our method based on ground-based follow-up observations.
CRIS-Team WoS Importer:2020-01-15

UNVEILING THE NATURE OF UNIDENTIFIED gamma-RAY SOURCES. VI. gamma-RAY BLAZAR CANDIDATES IN THE WISH SURVEY AND THEIR RADIO PROPERTIES - Nori, M.; Giroletti, M.; Massaro, F.; D'Abrusco, R.; Paggi, A.; Tosti, G.; Funk, Stefan (Astrophysical Journal Supplement Series, 2014)
According to the Fermi Large Area Telescope Second Source Catalog (2FGL), about one-third of the gamma-ray sources listed have no assigned counterparts at lower energies. Many statistical methods have been developed to find proper counterparts for these sources. We explore the sky area covered at low radio frequency by the Westerbork in the Southern Hemisphere (WISH) survey to search for blazar-like associations among the unidentified gamma-ray sources (UGSs) listed in the 2FGL. Searching the WISH and NRAO Very Large Array Sky Survey radio surveys within the positional uncertainty regions of the 2FGL UGSs, we select as gamma-ray blazar candidates the radio sources characterized by flat radio spectra between 352 MHz and 1400 MHz. We propose new gamma-ray blazar associations for eight UGSs and we also discuss their spectral properties at low radio frequencies. We compare the radio flux density distribution of the low radio frequency gamma-ray blazar candidates with that of gamma-ray blazars associated with other methods. We find significant differences between these distributions. Finally, we discuss the results of this association method and its possible applicability to other regions of the sky and future radio surveys.
Keywords: BL Lacertae objects: general; galaxies: active; radiation mechanisms: non-thermal

Updated search for spectral lines from Galactic dark matter interactions with pass 8 data from the Fermi Large Area Telescope - Ackermann, M.; Ajello, M.; Albert, A.; Anderson, B.; Atwood, W. B.; Baldini, L.; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bissaldi, E.; Blandford, R. D.; Bloom, E. D.; et al. (Physical Review D - Particles, Fields, Gravitation and Cosmology, 2015)
Dark matter in the Milky Way may annihilate directly into. rays, producing a monoenergetic spectral line. Therefore, detecting such a signature would be strong evidence for dark matter annihilation or decay. We search for spectral lines in the Fermi Large Area Telescope observations of the Milky Way halo in the energy range 200 MeV-500 GeV using analysis methods from our most recent line searches. The main improvements relative to previous works are our use of 5.8 years of data reprocessed with the Pass 8 event-level analysis and the additional data resulting from the modified observing strategy designed to increase exposure of the Galactic center region. We search in five sky regions selected to optimize sensitivity to different theoretically motivated dark matter scenarios and find no significant detections. In addition to presenting the results from our search for lines, we also investigate the previously reported tentative detection of a line at 133 GeV using the new Pass 8 data.

Upper limits on very-high-energy gamma-ray emission from core-collapse supernovae observed with HESS - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguener, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Ashkar, H.; Backes, Michael; Martins, V. Barbosa; Barnard, M.; Becherini, Y.; et al. (Astronomy & Astrophysics, 2019)
Young core-collapse supernovae with dense-wind progenitors may be able to accelerate cosmic-ray hadrons beyond the knee of the cosmic-ray spectrum, and this may result in measurable gamma-ray emission. We searched for gamma-ray emission from ten super- novae observed with the High Energy Stereoscopic System (H.E.S.S.) within a year of the supernova event. Nine supernovae were observed serendipitously in the H.E.S.S. data collected between December 2003 and December 2014, with exposure times ranging from 1.4 to 53 h. In addition we observed SN 2016adj as a target of opportunity in February 2016 for 13 h. No significant gamma-ray emission has been detected for any of the objects, and upper limits on the >1 TeV gamma-ray flux of the order of similar to 10(-13) cm(-)(2)s(-1) are established, corresponding to upper limits on the luminosities in the range similar to 2 x 10(39) to similar to 1 x 10(42) erg s(-1). These values are used to place model-dependent constraints on the mass-loss rates of the progenitor stars, implying upper limits between similar to 2 x 10(-5) and similar to 2 x 10(-3) M-circle dot yr(-1) under reasonable assumptions on the particle acceleration parameters.
CRIS-Team WoS Importer:2019-06-28

Upper limits to the SN1006 multi-TeV gamma-ray flux from HESS observations - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Observations of the shell-type supernova remnant SN1006 have been carried out with the HESS system of Cherenkov telescopes during 2003 (18.2 h with two operating telescopes) and 2004 (6.3 h with all four telescopes). No evidence for TeV gamma-ray emission from any compact or extended region associated with the remnant is seen and resulting upper limits at the 99.9% confidence level are up to a factor 10 lower than previously-published fluxes from CANGAROO. For SN1006 at its current epoch of evolution we define limits for a number of important global parameters. Upper limits on the gamma-ray luminosity (for E = 0.26 to 10 TeV, distance d = 2 kpc) of L-gamma < 1.7 x 10(33) erg s(-1), and the total energy in corresponding accelerated protons, W-p < 1.6 x 10(50) erg are estimated ( for proton energies E-p similar to 1.5 to 60 TeV and assuming the lowest value n = 0.05 cm(-3) of the ambient target density discussed in literature). Extending this estimate to cover the range of proton energies observed in the cosmic ray spectrum up to the knee (we take here E-p similar to 1 GeV to 3 PeV, assuming a differential particle index -2) gives W-P < 6.3 x 10(50) erg. A lower limit on the post-shock magnetic field of B > 25 G results when considering the synchrotron/inverse-Compton framework for the observed X-ray flux and gamma-ray upper limits.
CRIS-Team WoS Importer:2020-01-15

Validation of open-source science tools and background model construction in gamma-ray astronomy - Mohrmann, Lars; Specovius, Andreas; Tiziani, Domenico; Funk, Stefan; Malyshev, Dmitry; Nakashima, Kaori; van Eldik, Christopher (Astronomy & Astrophysics, 2019)
In classical analyses of gamma-ray data from imaging atmospheric Cherenkov telescopes (IACTs), such as the High Energy Stereoscopic System (H.E.S.S.), aperture photometry, or photon counting, is applied in a (typically circular) region of interest (RoI) encompassing the source. A key element in the analysis is to estimate the amount of background in the RoI due to residual cosmic ray-induced air showers in the data. Various standard background estimation techniques have been developed in the last decades, most of them rely on a measurement of the background from source-free regions within the observed field of view. However, in particular in the Galactic plane, source analysis and background estimation are hampered by the large number of, sometimes overlapping, gamma-ray sources and large-scale di ffuse gamma-ray emission. For complicated fields of view, a three-dimensional (3D) likelihood analysis shows the potential to be superior to classical analysis. In this analysis technique, a spectromorphological model, consisting of one or multiple source components and a background component, is fitted to the data, resulting in a complete spectral and spatial description of the field of view. For the application to IACT data, the major challenge of such an approach is the construction of a robust background model. In this work, we apply the 3D likelihood analysis to various test data recently made public by the H.E.S.S. collaboration, using the open analysis frameworks ctools and Gammapy. First, we show that, when using these tools in a classical analysis approach and comparing to the proprietary H.E.S.S. analysis framework, virtually identical high-level analysis results, such as field-of-view maps and spectra, are obtained. We then describe the construction of a generic background model from data of H.E.S.S. observations, and demonstrate that a 3D likelihood analysis using this background model yields high-level analysis results that are highly compatible with those obtained from the classical analyses. This validation of the 3D likelihood analysis approach on experimental data is an important step towards using this method for IACT data analysis, and in particular for the analysis of data from the upcoming Cherenkov Telescope Array (CTA).
CRIS-Team WoS Importer:2020-01-17

VERITAS and Fermi-LAT Observations of TeV Gamma-Ray Sources Discovered by HAWC in the 2HWC Catalog - Abeysekara, A. U.; Archer, A.; Benbow, W.; Bird, Ralph; Brose, R.; Buchovecky, M.; Buckley, J. H.; Bugaev, V.; Chromey, A. J.; Connolly, M. P.; Cui, W.; Daniel, M. K.; et al. (Astrophysical Journal, 2018)
The High Altitude Water Cherenkov (HAWC) collaboration recently published their 2HWC catalog, listing 39 very high energy (VHE; >100 GeV) gamma-ray sources based on 507 days of observation. Among these, 19 sources are not associated with previously known teraelectronvolt (TeV) gamma-ray sources. We have studied 14 of these sources without known counterparts with VERITAS and Fermi-LAT. VERITAS detected weak gamma-ray emission in the 1 TeV-30 TeV band in the region of DA 495, a pulsar wind nebula coinciding with 2HWC J1953+294, confirming the discovery of the source by HAWC. We did not find any counterpart for the selected 14 new HAWC sources from our analysis of Fermi-LAT data for energies higher than 10 GeV. During the search, we detected gigaelectronvolt (GeV) gamma-ray emission coincident with a known TeV pulsar wind nebula, SNR G54.1+0.3 (VER J1930+188), and a 2HWC source, 2HWC J1930+188. The fluxes for isolated, steady sources in the 2HWC catalog are generally in good agreement with those measured by imaging atmospheric Cherenkov telescopes. However, the VERITAS fluxes for SNR G54.1+0.3, DA 495, and TeV J2032+4130 are lower than those measured by HAWC, and several new HAWC sources are not detected by VERITAS. This is likely due to a change in spectral shape, source extension, or the influence of diffuse emission in the source region.
Keywords: gamma rays: general

VERITAS and Fermi-LAT Observations of TeV Gamma-Ray Sources Discovered by HAWC in the 2HWC Catalog - Abeysekara, A. U.; Archer, A.; Benbow, W.; Bird, Ralph; Brose, R.; Buchovecky, M.; Buckley, J. H.; Bugaev, V.; Chromey, A. J.; Connolly, M. P.; Cui, W.; Daniel, M. K.; et al. (Astrophysical Journal, 2018)
The High Altitude Water Cherenkov (HAWC) collaboration recently published their 2HWC catalog, listing 39 very high energy (VHE; >100 GeV) gamma-ray sources based on 507 days of observation. Among these, 19 sources are not associated with previously known teraelectronvolt (TeV) gamma-ray sources. We have studied 14 of these sources without known counterparts with VERITAS and Fermi-LAT. VERITAS detected weak gamma-ray emission in the 1 TeV-30 TeV band in the region of DA 495, a pulsar wind nebula coinciding with 2HWC J1953+294, confirming the discovery of the source by HAWC. We did not find any counterpart for the selected 14 new HAWC sources from our analysis of Fermi-LAT data for energies higher than 10 GeV. During the search, we detected gigaelectronvolt (GeV) gamma-ray emission coincident with a known TeV pulsar wind nebula, SNR G54.1+0.3 (VER J1930+188), and a 2HWC source, 2HWC J1930+188. The fluxes for isolated, steady sources in the 2HWC catalog are generally in good agreement with those measured by imaging atmospheric Cherenkov telescopes. However, the VERITAS fluxes for SNR G54.1+0.3, DA 495, and TeV J2032+4130 are lower than those measured by HAWC, and several new HAWC sources are not detected by VERITAS. This is likely due to a change in spectral shape, source extension, or the influence of diffuse emission in the source region.
Keywords: gamma rays: general

Very high energy gamma-ray emission from two blazars of unknown redshift and upper limits on their distance - Abdalla, H.; Adam, R.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Armstrong, T.; Ashkar, H.; Backes, M.; Baghmanyan, V.; et al. (Monthly Notices of the Royal Astronomical Society, 2020)
We report on the detection of very high energy (VHE; E > 100 GeV) gamma-ray emission from the BL Lac objects KUV 00311-1938 and PKS 1440-389 with the High Energy Stereoscopic System (H.E.S.S.). H.E.S.S. observations were accompanied or preceded by multiwavelength observations with Fermi/LAT, XRT and UVOT onboard the Swift satellite, and ATOM. Based on an extrapolation of the Fermi/LAT spectrum towards the VHE gamma-ray regime, we deduce a 95 per cent confidence level upper limit on the unknown redshift of KUV 00311-1938 of z < 0.98 and of PKS 1440-389 of z < 0.53. When combined with previous spectroscopy results, the redshift of KUV 00311-1938 is constrained to 0.51 <= z < 0.98 and of PKS 1440-389 to 0.14 (sic) z < 0.53.
CRIS-Team WoS Importer:2020-06-26

Very high energy gamma rays from the composite SNR G0.9+0.1 - Funk, Stefan; et al. (Astronomy & Astrophysics, 2005)
Very high energy (> 100 GeV) gamma-ray emission has been detected for the first time from the composite supernova remnant G0.9+ 0.1 using the HESS instrument. The source is detected with a significance of approximate to 13sigma, and a photon flux above 200 GeV of ( 5.7 +/- 0.7(stat) +/- 1.2(sys)) x 10(-12) cm(-2) s(-1), making it one of the weakest sources ever detected at TeV energies. The photon spectrum is compatible with a power law ( dN/dE proportional to E-Gamma) with photon index Gamma = 2.40 +/- 0.11(stat) +/- 0.20(sys). The gamma-ray emission appears to originate in the plerionic core of the remnant, rather than the shell, and can be plausibly explained as inverse Compton scattering of relativistic electrons.
CRIS-Team WoS Importer:2020-01-15

Very high energy gamma rays from the direction of Sagittarius A - Funk, Stefan; et al. (Astronomy & Astrophysics, 2004)
We report the detection of a point-like source of very high energy (VHE) gamma-rays coincident within 1' of Sgr A* obtained with the HESS array of Cherenkov telescopes. The gamma-rays exhibit a power-law energy spectrum with a spectral index of -2.2+/-0.09+/-0.15 and a flux above the 165 GeV threshold of (1.82+/-0.22)x10(-7) m(-2) s(-1). The measured flux and spectrum differ substantially from recent results reported in particular by the CANGAROO collaboration.
CRIS-Team WoS Importer:2020-01-15

VHE gamma-ray discovery and multiwavelength study of the blazar 1ES 2322-409 - Abdalla, H.; Aharonian, F.; Benkhali, F. Ait; Anguner, E. O.; Arakawa, M.; Arcaro, C.; Armand, C.; Arrieta, M.; Backes, M.; Barnard, M.; Becherini, Y.; Tjus, J. Becker; et al. (Monthly Notices of the Royal Astronomical Society, 2019)
A hotspot at a position compatible with the BL. Lac object 1ES 2322-409 was serendipitously detected with H.E.S.S. during observations performed in 2004 and 2006 on the blazar PKS 2316-423. Additional data on 1ES 2322-409 were taken in 2011 and 2012, leading to a total live-time of 22.3 h. Point-like very-high-energy (VHE; E > 100 GeV) gamma-ray emission is detected from a source centred on the IFS 2322-409 position, with an excess of 116.7 events at a significance of 6.0 sigma. The average VHE gamma-ray spectrum is well described with a power law with a photon index Gamma = 3.40 +/- 0.66(stat) +/- 0.20(sys) and an integral flux Phi(E > 200 GeV) = (3.11 +/- 0.71(stat) 0.62(sys)) x 10(-2)cm(-2)s(-1), which corresponds to 1.1 per cent of the Crab nebula flux above 200 GeV. Multiwavelength data obtained with Fermi LAT, Swift XRT and UVOT, RXTE PCA, ATOM, and additional data from WISE, GROND, and Catalina are also used to characterize the broad-band non-thermal emission of lES 2322-409. The multiwavelength behaviour indicates day-scale variability. Swift UVOT and XRT data show strong variability at longer scales. A spectral energy distribution (SED) is built from contemporaneous observations obtained around a high state identified in Swift data. A modelling of the SED is performed with a stationary homogeneous one-zone synchrotronself-Compton leptonic model. The redshift of the source being unknown, two plausible values were tested for the modelling. A systematic scan of the model parameters space is performed, resulting in a well-constrained combination of values providing a good description of the broad-band behaviour of 1ES 2322-409.
CRIS-Team WoS Importer:2019-04-09
Keywords: BL Lacertae objects: individual: 1ES 2322-409; galaxies: active; gamma-rays: galaxies; Radiation mechanisms: non-thermal

VHE,gamma-ray emitting pulsar wind nebulae discovered by HESS - Funk, Stefan; et al. (40 YEARS OF PULSARS: MILLISECOND PULSARS, MAGNETARS AND MORE, 2007)
CRIS-Team WoS Importer:2020-01-15

VHE Gamma-ray supernova remnants - Funk, Stefan (Advances in Space Research, 2008)
Increasing observational evidence gathered especially in X-rays and gamma-rays during the course of the last few years support the notion that Supernova remnants (SNRs) are Galactic particle accelerators up to energies close to the "knee" in the energy spectrum of Cosmic rays. This review summarises the current status of gamma-ray observations of SNRs. Shell-type as well as plerionic type SNRs are addressed and prospect for observations of these two source classes with the upcoming GLAST satellite in the energy regime above 100 MeV are given. (C) 2007 Published by Elsevier Ltd on behalf of COSPAR.
CRIS-Team WoS Importer:2020-01-15

XMM-Newton observations of HESS J1813-178 reveal a composite Supernova remnant - Funk, Stefan; et al. (Astronomy & Astrophysics, 2007)
Aims. We present X-ray and (CO)-C-12(J = 1-0) observations of the very-high-energy (VHE) gamma-ray source HESS J1813-178 with the aim of understanding the origin of the gamma-ray emission.
CRIS-Team WoS Importer:2020-01-15

XMM-Newton observations reveal the x-ray counterpart of the very high energy gamma-ray source hess J1640-465 - Funk, Stefan; et al. (Astrophysical Journal, 2007)
We present X-ray observations of the as of yet unidentified very high energy (VHE) gamma-ray source HESS J1640-465 with the aim of establishing a counterpart of this source in the keV energy range, and identifying the mechanism responsible for the VHE emission. The 21.8 ks XMM-Newton observation of HESS J1640-465 in 2005 September represents a significant improvement in sensitivity and angular resolution over previous ASCA studies in this region. These new data show a hard-spectrum X-ray-emitting object at the centroid of the H. E. S. S. source, within the shell of the radio supernova remnant (SNR) G338.3-0.0. This object is consistent with the position and flux previously measured by both ASCA and Swift XRT, but is now shown to be significantly extended. We argue that this object is very likely the counterpart to HESS J1640-465, and that both objects may represent the pulsar wind nebula of an as of yet undiscovered pulsar associated with G338.3-0.0.
CRIS-Team WoS Importer:2020-01-15

X-ray Dark-Field Imaging for Improved Contrast in Historical Handwritten Literature - Akstaller, Bernhard; Schreiner, Stephan; Dietrich, Lisa; Rauch, Constantin; Schuster, Max; Ludwig, Veronika; Hofmann-Randall, Christina; Michel, Thilo; Anton, Gisela; Funk, Stefan (Journal of Imaging, 2022)
If ancient documents are too fragile to be opened, X-ray imaging can be used to recover the content non-destructively. As an extension to conventional attenuation imaging, dark-field imaging provides access to microscopic structural object information, which can be especially advantageous for materials with weak attenuation contrast, such as certain metal-free inks in paper. With cotton paper and different self-made inks based on authentic recipes, we produced test samples for attenuation and dark-field imaging at a metal-jet X-ray source. The resulting images show letters written in metal-free ink that were recovered via grating-based dark-field imaging. Without the need for synchrotron-like beam quality, these results set the ground for a mobile dark-field imaging setup that could be brought to a library for document scanning, avoiding long transport routes for valuable historic documents.
CRIS-Team Scopus Importer:2022-10-07
Keywords: cultural heritage; grating-based phase-contrast imaging; X-ray dark-field imaging

X-ray observations of unidentified HESS gamma-ray sources - Funk, Stefan (First GLAST Symposium, 2007)
CRIS-Team WoS Importer:2020-01-15